Abstract: Automatic Dementia Screening and Scoring by Applying Deep Learning on Clock-drawing Tests - Chen, Shuqing; Stromer, Daniel; Alnasser Alabdalrahim, Harb; Schwab, Stefan; Weih, Markus; Maier, Andreas (Informatik aktuell, 2021)
CRIS-Team Scopus Importer:2021-04-09

Acute care and secondary prevention of stroke with newly detected versus known atrial fibrillation - Wang, Ruihao; Macha, Kosmas; Haupenthal, David; Gaßmann, Luise; Siedler, Gabriela; Stoll, Svenja; Fröhlich, Kilian; Köhn, Julia; Schwab, Stefan; Kallmünzer, Bernd (European Journal of Neurology, 2022)
Background and purpose: Atrial fibrillation (AF) in stroke patients can be classified as either “known AF” (KAF), defined as AF confirmed before stroke onset, or “AF detected after stroke” (AFDAS), defined as AF diagnosed after stroke onset. While KAF is considered primarily cardiogenic, AFDAS includes patients with stroke-triggered neurogenic arrhythmias. This study aimed to investigate the clinical course of stroke, functional outcomes and the value of oral anticoagulation (OAC) for secondary prevention according to AF subtype. Methods: Acute ischemic stroke patients were consecutively enrolled and AF was classified as AFDAS or KAF. Stroke severity was assessed using the National Institutes of Health Stroke Scale (NIHSS) and 3-month functional outcomes were measured on the modified Rankin scale. Inverse probability weighting was applied to adjust for baseline confounders in patients with AFDAS and KAF. Multivariate logistic regression models were calculated to investigate the value of OAC for secondary prevention. Results: A total of 822 stroke patients with AF were included, of whom 234 patients (28.5%) had AFDAS. AFDAS patients had a lower prevalence of coronary artery disease, heart failure, and sustained AF, but higher rates of large vessel occlusion compared to KAF patients. NIHSS scores were lower in patients on pre-stroke anticoagulation. OAC for secondary prevention was associated with favorable 3-month functional outcome (odds ratio 7.60, 95% confidence interval 3.42–16.88) independently of AF subtype. The rate of stroke recurrence did not differ significantly. Conclusions: Clinical characteristics suggest that AFDAS might comprise a distinct pathophysiological and clinical entity among stroke patients with AF. The benefit of anticoagulation for secondary prevention was not affected by AF subtype.
CRIS-Team Scopus Importer:2022-04-22
Keywords: acute ischemic stroke; atrial fibrillation detected after stroke; known atrial fibrillation; modified Rankin scale; oral anticoagulation; stroke recurrence

Acute ischemic stroke and transient ischemic attack: an update on recent practically relevant clinical trials - Staykov, Dimitre; Schwab, Stefan (Neurohospitalist, 2014)
EVALuna2:22365

Acute right insular ischaemic lesions and poststroke left ventricular dysfunction - Winder, Klemens; Villegas Millar, Carolina; Siedler, Gabriela; Knott, Michael; Dörfler, Arnd; Engel, Anna; Achenbach, Stephan; Hilz, Max-Josef; Kallmünzer, Bernd; Schwab, Stefan; Seifert, Frank; Fröhlich, Kilian (Stroke and Vascular Neurology, 2023)
IntroductionMyocardial injury related to acute ischaemic stroke is common even without primary cardiac disease. We intended to determine associations between values of left ventricular ejection fraction (LVEF) and ischaemic stroke lesion sites. MethodsOf a local database, patients with acute first-ever ischaemic stroke confirmed by brain imaging but without pre-existing heart disease were included. The cardiac morphology and LVEF were obtained from transthoracic or transesophageal echocardiography, and impaired LVEF was categorised as mild (35%-50%), moderate (34%-25%) and severe (<25%). Patient age, stroke severity, ischaemic lesion volume, prevalence of troponin I increase (>0.1 ng/mL), atrial fibrillation and cardiac wall motion abnormalities were assessed and compared between patients with and without impaired LVEF after stroke (significance: p<0.05). A multivariate voxelwise lesion analysis correlated LVEF after stroke with sites of ischaemic lesions. ResultsOf 1209 patients who had a stroke, 231 (mean age 66.3 +/- 14.0 years) met the inclusion criteria; 40 patients (17.3%) had an impaired LVEF after stroke. Patients with impaired LVEF had higher infarct volumes (53.8 mL vs 30.0 mL, p=0.042), a higher prevalence of troponin increase (17.5% vs 4.2%, p=0.006), cardiac wall motion abnormalities (42.5% vs 5.2%, p<0.001) and atrial fibrillation (60.0% vs 26.2%, p<0.001) than patients with LVEF of >50%. The multivariate voxelwise lesion analysis yielded associations between decreased LVEF and damaged voxels in the insula, amygdala and operculum of the right hemisphere. ConclusionOur imaging analysis unveils a prominent role of the right hemispheric central autonomic network, especially of the insular cortex, in the brain-heart axis. Our results support preliminary evidence that acute ischaemic stroke in distinct brain regions of the central autonomic network may directly impair cardiac function and thus further supports the concept of a distinct stroke-heart syndrome.
CRIS-Team WoS Importer:2023-02-24

Acute Stroke With Large Vessel Occlusion and Minor Clinical Deficits: Prognostic Factors and Therapeutic Implications - Volbers, Bastian; Gröger, Rebecca; Engelhorn, Tobias; Marsch, Armin; Macha, Kosmas; Schwab, Stefan; Dörfler, Arnd; Lang, Stefan; Kallmünzer, Bernd (Frontiers in Neurology, 2021)
Background and Purpose: The optimal acute management of patients with large vessel occlusion (LVO) and minor clinical deficits on admission [National Institutes of Health Stroke Scale (NIHSS) <= 4] remains to be elucidated. The aim of the present study was to investigate the prognostic factors and therapeutic management of those patients.
CRIS-Team WoS Importer:2021-11-19

Adherence to oral anticoagulation in secondary stroke prevention - the first year of direct oral anticoagulants - Sauer, Rolf; Sauer, Eva-Maria; Bobinger, Tobias; Blinzler, Christian; Huttner, Hagen; Schwab, Stefan; Köhrmann, Martin (Journal of Stroke and Cerebrovascular Diseases, 2015)
Patients with ischemic stroke caused by atrial fibrillation (AF) have a high risk of recurrence without adequate secondary prevention with oral anticoagulation (OAC). We investigated adherence to OAC in the first year after introduction of direct oral anticoagulants.In 284 appropriate patients, the rate of anticoagulation (AC) at discharge, adherence at 90 days and 1 year, changes between substances, and predictors for adherence to AC were analyzed. Functional outcome was assessed using the modified Rankin Scale score.AC was initiated in 70.3% of survivors before discharge. In these patients, only 8.6% and 9.9% discontinued AC after 90 days and 1 year, respectively. In 22.1%, AC was recommended but not started before discharge. Only 53.2% of them received AC at 90 days, increasing to 67.5% at 1 year. A total of 7.6% of patients were deemed unsuitable for AC, none of them subsequently received AC. Overall, 85.4% of patients suitable for AC were treated at 1-year follow-up. No independent predictors for withholding AC were identified. Switching of medication occurred in only a minority of patients within the first year.AC is feasible in more than 90% patients with acute ischemic stroke and AF. When initiated during the acute hospital stay, AC is discontinued in only a minority of patients. However, if AC is recommended but not started during initial hospitalization the rate of AC treatment at 90 days and 1 year is much lower. Therefore, AC should be initiated within the acute hospital stay whenever possible.
EVALuna2:22269

Afterdischarges elicited by cortical electric stimulation in humans: When do they occur and what do they mean? - Gollwitzer, Stephanie; Hopfengaertner, Ruediger; Roessler, Karl; Müller, Tamara; Olmes, David Gerhard; Lang, Johannes; Koehn, Julia; Onugoren, Muejgan Dogan; Heyne, Jana; Schwab, Stefan; Hamer, Hajo (Epilepsy and Behavior, 2018)
INTRODUCTION: Afterdischarges (ADs) are a common and unwanted byproduct of direct cortical stimulation during invasive electroencephalography (EEG) recordings. Brief pulse stimulation (BPS) can sometimes terminate ADs. This study investigated AD characteristics and their relevance for emergence of stimulation seizures. In addition, AD response to BPS was analyzed. MATERIAL AND METHODS: Invasive EEG recordings including mapping with direct cortical stimulation in patients with refractory epilepsy at the Erlangen Epilepsy Center were retrospectively reviewed. Afterdischarge defined as stimulation-induced rhythmic epileptiform discharges of more than a two-second duration were analyzed regarding incidence, localization, duration, propagation pattern, morphology, and seizure emergence. In addition, the influence of AD characteristics and stimulation settings on BPS success rate was studied. RESULTS: A number of 4261 stimulation trials in 20 patients were investigated. Afterdischarge occurred in 518 trials (14.2%) and lasted 12.4 s (standard deviation [SD]: 8.6 s) on average. We elicited ADs in the seizure onset zone (SOZ) (n = 64; 19.4%), the irritative zone (n = 105, 20.0%), and outside the irritative area (n = 222, 12.5%). Rhythmic spikes (30.5%) and spike-wave complexes (30.3%) represented predominant morphologies. Afterdischarge morphology in the SOZ and hippocampus differed from other areas with polyspikes and sequential spikes being the most common types there (p = 0.0005; p < 0.0001 respectively). Hippocampal ADs were particularly frequent (n = 50, 38.2%) and long-lasting (mean: 16.6, SD: 8.3 s). Brief pulse stimulation was applied in 18.1% of the AD trials (n = 94) and was successful in 37.4% (n = 40). Success rates were highest when BPS was delivered within 9.5 s (p = 0.0048) and in ADs of spike-wave morphology (p = 0.0004). Fifteen clinical seizures emerged from ADs (3.55%), mostly evolving from sequential spikes. Afterdischarges in patients with stimulation seizures appeared more widespread (p < 0.0001) and lasted longer (mean duration 7.0 s) than in those without (mean duration 21.0 s, p = 0.0054). CONCLUSION: Afterdischarges appear in the epileptogenic and nonepileptogenic cortex. Duration and propagation patterns can help to quantify the risk of stimulation seizures, with sequential spikes being most susceptible to seizure elucidation. The hippocampus is highly sensitive to AD release. Brief pulse stimulation is a safe and efficacious way to terminate ADs, especially when delivered quickly after AD onset.
EVALuna2:34938

Age of epilepsy onset as modulating factor for naming deficit after epilepsy surgery: a voxel-based lesion-symptom mapping study - Reindl, Caroline; Walther, Katrin; Allgäuer, Anna-Lena; Lang, Johannes; Welte, Tamara; Stritzelberger, Jenny; Gollwitzer, Stephanie; Schwarz, Michael; Trollmann, Regina; Madzar, Dominik; Knott, Michael; Dörfler, Arnd; et al. (Scientific Reports, 2023)
Age at onset of epilepsy is an important predictor of deterioration in naming ability following epilepsy surgery. In 141 patients with left hemispheric epilepsy and language dominance who received epilepsy surgery at the Epilepsy Centre Erlangen, naming of objects (Boston naming test, BNT) was assessed preoperatively and 6 months postoperatively. Surgical lesions were plotted on postoperative MRI and normalized for statistical analysis using voxel-based lesion-symptom mapping (VBLSM). The correlation between lesion and presence of postoperative naming deterioration was examined varying the considered age range of epilepsy onsets. The VBLSM analysis showed that volumes of cortex areas in the left temporal lobe, which were associated with postoperative decline of naming, increased with each year of later epilepsy onset. In patients with later onset, an increasing left posterior temporobasal area was significantly associated with a postoperative deficit when included in the resection. For late epilepsy onset, the temporomesial expansion also included the left hippocampus. The results underline that early onset of epilepsy is a good prognostic factor for unchanged postoperative naming ability following epilepsy surgery. For later age of epilepsy onset, the extent of the area at risk of postoperative naming deficit at 6 months after surgery included an increasing left temporobasal area which finally also comprised the hippocampus.
CRIS-Team Scopus Importer:2023-09-08

Alpha power decrease in quantitative EEG detects development of cerebral infarction after subarachnoid hemorrhage early - Müller, Tamara; Gollwitzer, Stephanie; Hopfengartner, Ruediger; Rampp, Stefan; Lang, Johannes; Stritzelberger, Jenny; Madzar, Dominik; Reindl, Caroline; Sprügel, Maximilian; Onugoren, Muejgan Dogan; Mühlen, Iris; Kuramatsu, Joji; et al. (Clinical Neurophysiology, 2021)
Objective: In subarachnoid hemorrhage (SAH), transcranial Doppler/color-coded-duplex sonography (TCD/TCCS) is used to detect delayed cerebral ischemia (DCI). In previous studies, quantitative electroencephalography (qEEG) also predicted imminent DCI. This study aimed to compare and analyse the ability of qEEG and TCD/TCCS to early identify patients who will develop later manifest cerebral infarction. Methods: We analysed cohorts of two previous qEEG studies. Continuous six-channel-EEG with artefact rejection and a detrending procedure was applied. Alpha power decline of ≥ 40% for ≥ 5 hours compared to a 6-hour-baseline was defined as significant EEG event. Median reduction and duration of alpha power decrease in each channel was determined. Vasospasm was diagnosed by TCD/TCCS, identifying the maximum frequency and days of vasospasm in each territory. Results: 34 patients were included (17 male, mean age 56 ± 11 years, Hunt and Hess grade: I–V, cerebral infarction: 9). Maximum frequencies in TCD/TCCS and alpha power reduction in qEEG were correlated (r = 0.43; p = 0.015). Patients with and without infarction significantly differed in qEEG parameters (maximum alpha power decrease: 78% vs 64%, p = 0.019; summed hours of alpha power decline: 236 hours vs 39 hours, p = 0.006) but showed no significant differences in TCD/TCCS parameters. Conclusions: There was a moderate correlation of TCD/TCCS frequencies and qEEG alpha power reduction but only qEEG differentiated between patients with and without cerebral infarction. Significance: qEEG represents a non-invasive, continuous tool to identify patients at risk of cerebral infarction.
CRIS-Team Scopus Importer:2021-06-04
Keywords: Delayed cerebral ischemia; Quantitative EEG; Subarachnoid hemorrhage; Vasospasm

Amantadine treatment is associated with improved consciousness in patients with non-traumatic brain injury - Ruehl, Lena; Kuramatsu, Joji; Sembill, Jochen; Kallmünzer, Bernd; Madzar, Dominik; Gerner, Stefan; Giede-Jeppe, Antje; Balk, Stefanie; Müller, Tamara; Jäger, Jakob; Schwab, Stefan; Huttner, Hagen; et al. (Journal of Neurology Neurosurgery and Psychiatry, 2022)
Objective This study determined the effect of amantadine treatment on consciousness in patients with non-traumatic brain injury. Methods We pooled individual patient data of five single-centre observational studies to determine the effect of amantadine treatment among patients with ischaemic stroke, intracerebral haemorrhage, subarachnoid haemorrhage, community-acquired bacterial meningitis and status epilepticus, admitted between January 2012 and December 2015 and ventilated >= 7 days. Patient selection and multivariable regression modelling were used to adjust for differences in intergroup comparison and for parameters associated with consciousness. Improvement of consciousness 5 days after treatment initiation was defined as primary outcome. Secondary outcomes included Glasgow Coma Scale (GCS) at day 5 and GCS at day 10, rate of ICU delirium, epileptic seizures and all-cause mortality at 90 days. Results Overall, 84 of 294 (28.6%) eligible patients received amantadine. Amantadine treatment was associated with improvement of consciousness at day 5 (amantadine: 86.9% vs control: 54.0%; absolute difference: 32.9 (20.0-44.2); adjusted OR (aOR): 5.71 (2.50-13.05), p<0.001). Secondary outcomes showed differences in GCS 5 days (9 (8-11) vs 6 (3-9), p<0.001) and GCS 10 days (10(8-11) vs 9(6-11),p=0.003) after treatment initiation. There were no significant differences regarding all-cause mortality (aOR: 0.89 (0.44-1.82), p=0.758) and ICU delirium (aOR: 1.39 (0.58-3.31), p=0.462). Rate of epileptic seizures after initiation of amantadine treatment was numerically higher in the amantadine group (amantadine: 10.7% vs control: 3.0%; absolute difference: 7.7 (0.3-16.4); aOR: 3.68 (0.86-15.71), p=0.079). Conclusions Amantadine treatment is associated with improved consciousness among patients with different types of non-traumatic brain injury in this observational cohort analysis. Epileptic seizures should be considered as potential side effects and randomised controlled trials are needed to confirm these findings.
CRIS-Team WoS Importer:2022-02-11

Analysing Variables for 90-Day Functional-Outcome Prediction of Endovascular Thrombectomy - Rodriguez Salas, Dalia; Rieß, Christian; Martín Vicario, Celia; Taubmann, Oliver; Ditt, Hendrik; Schwab, Stefan; Dörfler, Arnd (Medical Image Understanding and Analysis. 28th Annual Conference, MIUA 2024, Manchester, UK, July 24–26, 2024, Proceedings, Part II, 2024)
Multiple studies report the impact of variables on predicting long-term functional outcomes following Endovascular Thrombectomy (EVT). Often, the variables are analyzed separately with univariate statistical analysis or combined in a linear regression or logistic regression prediction. Although such linear combinations are easy to interpret, they do not consider nonlinear relationships. Other studies do consider nonlinearities, most notably in deep learning. However, if any, they use separate methods to assess the variable importance, which might not capture their actual contribution to the prediction. In this work, we propose to use an algorithm that combines the predictive power of neural networks and the interpretation of decision trees in a single method. ForestNet is a special artificial neural network that defines its partially connected architecture based on the hierarchical variable importance given by an ensemble of decision trees, providing a means of interpretation in a more generalized fashion. On predicting 90-day favorable functional outcomes, using 10-fold cross-validation, we reach an AUC of 0.82 and 0.86 before and after EVT, respectively. A 90-day Modified Rankin Scale (mRS)<=2 defines a favorable outcome. The analysis of the variable’s contribution shows that the pre-stroke mRS, age, and the National Institutes of Health Stroke Scale (NIHSS) play the most important role in predictions before EVT. After EVT, the infarct volume from the 24h follow-up CT scan, measured directly or in terms of affected brain regions according to the ASPECT score, is the most important variable in providing a more accurate prediction than before EV
Keywords: Stroke outcome prediction; Interpretable machine learning; Thrombectomy 90-day outcome

ANDEXANET ALFA VERSUS USUAL CARE IN PATIENTS WITH DOAC ASSOCIATED INTRACEREBRAL HEMORRHAGE: A PROPENSITY-SCORE BASED HISTORICAL COMPARISON OF PATIENTS FROM ANNEXA4 AND RETRACEII - Huttner, Hagen; Gerner, Stefan; Connolly, S.; Middeldorp, S.; Milling, T.; Beyer-Westendorf, J.; Altevers, J.; Andersohn, F.; Yue, P.; Stross, L.; Schwab, Stefan (INTERNATIONAL JOURNAL OF STROKE, 2020)
CRIS-Team WoS Importer:2021-01-22

Aneurysmatic subarachnoid haemorrhage - Onur, Oezguer A.; Fink, Gereon R.; Kuramatsu, Joji; Schwab, Stefan (Neurological Research and Practice, 2019)
Introduction: Aneurysmatic Subarachnoid Haemorrhage (aSAH) is typically caused by extravasated blood in the subarachnoid space due to a ruptured aneurysm. aSAH is often life-threatening in the acute stage, but may also cause secondary brain damage due to delayed cerebral ischaemia (DCI) and other complications in the days and weeks after the initial bleeding. Rapid onset of a most severe headache is a typical sign of a non-traumatic aSAH besides a reduced level of consciousness and neurologic deficits. First steps: Immediate diagnostic steps in case of a suspected SAH are cerebral imaging (CCT, MRI) and lumbar puncture. If a SAH is confirmed, a digital subtraction angiography should be performed to detect an aneurysm. If an aneurysm is detected it should be occluded immediately after interdisciplinary consultation with neurosurgeons and neuroradiologists. Comments: If endovascular coiling and surgical clipping are both available and equally suitable, coiling should be preferred due to a better long-time outcome. Often the age of the patient, the location of the aneurysm, and the configuration of the aneurysm result in favouring one or the other technique. Special care aims at avoiding stress, increased intracranial pressure, pain, fever, emesis, and at keeping glucose levels and electrolytes in the normal range. As nimodipine is associated with a better outcome, it should be administered from the beginning. To detect vasospasm, serial transcranial doppler should be performed at least once a day for at least 14 days. If vasospasms are detected, this procedure needs to be continued until flow velocity returns to the normal range. To detect an increased intracranial pressure, external ventricular drainage or intraparenchymal probes are recommended. Regarding haemodynamics, euvolaemia and normotension should be achieved. If vasospasms and/or an increased intracranial pressure occur, mean arterial pressure needs to be adjusted to ensure an adequate cerebral perfusion pressure. Conclusions: If immediate actions are taken to treat the aneurysm and complications in the following weeks are handled with care, a favourable outcome is possible for this otherwise often devastating disease.
CRIS-Team Scopus Importer:2024-12-16
Keywords: Clipping; Coiling; Delayed cerebral ischaemia; Nimodipine; Standard operating procedure; Vasospasm

Angioedema in Stroke Patients With Thrombolysis - Fröhlich, Katharina; Macha, Kosmas; Gerner, Stefan; Bobinger, Tobias; Schmidt, Manuel; Dörfler, Arnd; Hilz, Max-Josef; Schwab, Stefan; Seifert, Frank; Kallmünzer, Bernd; Winder, Klemens (Stroke, 2019)
Background and Purpose- Oral angioedema (OA) is a rare but life-threatening complication in patients with ischemic stroke receiving intravenous thrombolysis with r-tPA (recombinant tissue-type plasminogen activator). This study intended to determine associations between thrombolysis-related OA and ischemic stroke lesion sites using a voxel-wise lesion analysis. Methods- Prospective registry data were used to identify ischemic stroke patients with thrombolysis-related OA between 2002 and 2018. For the study registry, ethics approval was obtained by the Ethics Committee of the Friedrich-Alexander Universität (FAU) Erlangen-Nürnberg (clinical registry registration: 377_17Bc). Ischemic stroke patients with thrombolysis treatment but without OA admitted in the years 2011 and 2012 comprised the control group. Ischemic lesions were manually outlined on magnetic resonance imaging (1.5T or 3T) or computed tomographic scans and transformed into stereotaxic space. We determined the lesion overlap and compared the absence or presence of OA voxel-wise between patients with and without lesions in a given voxel using the Liebermeister test. Stroke severity was rated using the National Institutes of Health Stroke Scale score, and blood pressure, heart rate, blood glucose levels, and body temperature were determined on admission. Results- Fifteen ischemic stroke patients with thrombolysis-related OA were identified. The voxel-wise analysis yielded associations between OA and ischemic lesions in the insulo-opercular region with a right hemispheric dominance. Mean blood pressure was significantly lower in patients with OA than in controls. Age, National Institutes of Health Stroke Scale scores, infarct volumes, heart rate, and blood glucose levels did not differ between patients with and without OA. Conclusions- The voxel-wise analysis linked thrombolysis-related OA to right insulo-opercular lesions. The lower blood pressure in patients with thrombolysis-related OA may reflect bradykinin effects causing vasodilatation and increasing vascular permeability.
CRIS-Team Scopus Importer:2019-07-19
Keywords: angioedema; autonomic nervous system; brain ischemia; neuroimaging; stroke; tissue-type plasminogen activator

Antagonizing dabigatran by idarucizumab in cases of ischemic stroke or intracranial hemorrhage in Germany—Updated series of 120 cases - Kermer, Pawel; Eschenfelder, Christoph C.; Diener, Hans Christoph; Grond, Martin; Abdalla, Yasser; Abraham, Alexej; Althaus, Katharina; Becks, Gebhard; Berrouschot, Jörg; Berthel, Jörg; Bode, Felix J.; Burghaus, Lothar; et al. (International Journal of Stroke, 2020)
Background: Idarucizumab is a monoclonal antibody fragment with high affinity for dabigatran reversing its anticoagulant effects within minutes. Thereby, patients with acute ischemic stroke who are on dabigatran treatment may become eligible for thrombolysis with recombinant tissue-type plasminogen activator (rt-PA). In patients on dabigatran with intracerebral hemorrhage idarucizumab could prevent lesion growth. Aims: To provide insights into the clinical use of idarucizumab in patients under effective dabigatran anticoagulation presenting with signs of acute ischemic stroke or intracranial hemorrhage. Methods: Retrospective data collected from German neurological/neurosurgical departments administering idarucizumab following product launch from January 2016 to August 2018 were used. Results: One-hundred and twenty stroke patients received idarucizumab in 61 stroke centers. Eighty patients treated with dabigatran presented with ischemic stroke and 40 patients suffered intracranial bleeding (intracerebral hemorrhage (ICH) in n = 27). In patients receiving intravenous thrombolysis with rt-PA following idarucizumab, 78% showed a median improvement of 7 points in National Institutes of Health Stroke Scale. No bleeding complications were reported. Hematoma growth was observed in 3 out of 27 patients with ICH. Outcome was favorable with a median National Institutes of Health Stroke Scale improvement of 4 points and modified Rankin score 0–3 in 61%. Six out of 40 individuals (15%) with intracranial bleeding died during hospital stay. Conclusion: Administration of rt-PA after reversal of dabigatran activity with idarucizumab in case of acute ischemic stroke seems feasible, effective, and safe. In dabigatran-associated intracranial hemorrhage, idarucizumab appears to prevent hematoma growth and to improve outcome.
CRIS-Team Scopus Importer:2020-02-04
Keywords: dabigatran; Idarucizumab; intracranial hemorrhage; ischemic stroke; outcome; thrombolysis

Anticoagulant reversal, blood pressure levels, and anticoagulant resumption in patients with anticoagulation-related intracerebral hemorrhage - Kuramatsu, Joji; Gerner, Stefan; Schellinger, Peter D.; Glahn, Joerg; Endres, Matthias; Sobesky, Jan; Flechsenhar, Julia; Neugebauer, Hermann; Juettler, Eric; Grau, Armin; Palm, Frederick; Roether, Joachim; et al. (Journal of the American Medical Association, 2015)
Although use of oral anticoagulants (OACs) is increasing, there is a substantial lack of data on how to treat OAC-associated intracerebral hemorrhage (ICH).To assess the association of anticoagulation reversal and blood pressure (BP) with hematoma enlargement and the effects of OAC resumption.Retrospective cohort study at 19 German tertiary care centers (2006-2012) including 1176 individuals for analysis of long-term functional outcome, 853 for analysis of hematoma enlargement, and 719 for analysis of OAC resumption.Reversal of anticoagulation during acute phase, systolic BP at 4 hours, and reinitiation of OAC for long-term treatment.Frequency of hematoma enlargement in relation to international normalized ratio (INR) and BP. Incidence analysis of ischemic and hemorrhagic events with or without OAC resumption. Factors associated with favorable (modified Rankin Scale score, 0-3) vs unfavorable functional outcome.Hemorrhage enlargement occurred in 307 of 853 patients (36.0%). Reduced rates of hematoma enlargement were associated with reversal of INR levels <1.3 within 4 hours after admission (43/217 [19.8%]) vs INR of >=1.3 (264/636 [41.5%]; P < .001) and systolic BP <160 mm Hg at 4 hours (167/504 [33.1%]) vs >=160 mm Hg (98/187 [52.4%]; P < .001). The combination of INR reversal <1.3 within 4 hours and systolic BP of <160 mm Hg at 4 hours was associated with lower rates of hematoma enlargement (35/193 [18.1%] vs 220/498 [44.2%] not achieving these values; OR, 0.28; 95% CI, 0.19-0.42; P < .001) and lower rates of in-hospital mortality (26/193 [13.5%] vs 103/498 [20.7%]; OR, 0.60; 95% CI, 0.37-0.95; P = .03). OAC was resumed in 172 of 719 survivors (23.9%). OAC resumption showed fewer ischemic complications (OAC: 9/172 [5.2%] vs no OAC: 82/547 [15.0%]; P < .001) and not significantly different hemorrhagic complications (OAC: 14/172 [8.1%] vs no OAC: 36/547 [6.6%]; P = .48). Propensity-matched survival analysis in patients with atrial fibrillation who restarted OAC showed a decreased HR of 0.258 (95% CI, 0.125-0.534; P < .001) for long-term mortality. Functional long-term outcome was unfavorable in 786 of 1083 patients (72.6%).Among patients with OAC-associated ICH, reversal of INR <1.3 within 4 hours and systolic BP <160 mm Hg at 4 hours were associated with lower rates of hematoma enlargement, and resumption of OAC therapy was associated with lower risk of ischemic events. These findings require replication and assessment in prospective studies.clinicaltrials.gov Identifier: NCT01829581.
EVALuna2:22354

Antiplatelet Therapy in Intracerebral Hemorrhage - Sprügel, Maximilian; Kuramatsu, Joji; Gerner, Stefan; Sembill, Jochen; Beuscher, Vanessa D.; Hagen, Manuel; Röder, Sebastian; Lücking, Hannes; Struffert, Tobias; Dörfler, Arnd; Schwab, Stefan; Huttner, Hagen (STROKE, 2019)
CRIS-Team WoS Importer:2019-08-23

Antiplatelet Therapy in Primary Spontaneous and Oral Anticoagulation-Associated Intracerebral Hemorrhage - Sprügel, Maximilian; Kuramatsu, Joji; Gerner, Stefan; Sembill, Jochen; Beuscher, Vanessa D.; Hagen, Manuel; Röder, Sebastian; Lücking, Hannes; Struffert, Tobias; Dörfler, Arnd; Schwab, Stefan; Huttner, Hagen (Stroke, 2018)
Background and Purpose- This study determined the influence of concomitant antiplatelet therapy (APT) on hematoma characteristics and outcome in primary spontaneous intracerebral hemorrhage (ICH), vitamin K antagonist (VKA)- and non-VKA oral anticoagulant-associated ICH. Methods- Data of retrospective cohort studies and a prospective single-center study were pooled. Functional outcome, mortality, and radiological characteristics were defined as primary and secondary outcomes. Propensity score matching and logistic regression analyses were performed to determine the association between single or dual APT and hematoma volume. Results- A total of 3580 patients with ICH were screened, of whom 3545 with information on APT were analyzed. Three hundred forty-six (32.4%) patients in primary spontaneous ICH, 260 (11.4%) in VKA-ICH, and 30 (16.0%) in non-VKA oral anticoagulant-associated ICH were on APT, and these patients had more severe comorbidities. After propensity score matching VKA-ICH patients on APT presented with less favorable functional outcome (modified Rankin Scale score, 0-3; APT, 48/202 [23.8%] versus no APT, 187/587 [31.9%]; P=0.030) and higher mortality (APT, 103/202 [51.0%] versus no APT, 237/587 [40.4%]; P=0.009), whereas no significant differences were present in primary spontaneous ICH and non-VKA oral anticoagulant-associated ICH. In VKA-ICH, hematoma volume was significantly larger in patients with APT (21.9 [7.4-61.4] versus 15.7 [5.7-44.5] mL; P=0.005). Multivariable regression analysis revealed an association of APT and larger ICH volumes (odds ratio, 1.80 [1.20-2.70]; P=0.005), which was more pronounced in dual APT and supratherapeutically anticoagulated patients. Conclusions- APT does not affect ICH characteristics and outcome in primary spontaneous ICH patients; however, it is associated with larger ICH volume and worse functional outcome in VKA-ICH, presumably by additive antihemostatic effects. Combination of anticoagulation and APT should, therefore, be diligently evaluated and restricted to the shortest possible time frame.
EVALuna2:34909

Antiseizure medication and perceived “fair” cost allocation: A factorial survey among neurologists, persons with epilepsy, their relatives, and a control group - Stritzelberger, Jenny; Walther, Katrin; Olmes, David; Gollwitzer, Stefanie; Graf, Wolfgang; Welte, Tamara; Lang, Johannes; Reindl, Caroline; Schwab, Stefan; Kriwy, Peter; Hamer, Hajo (Epilepsia, 2022)
Objective: Because resources are limited in modern health care systems, the decision on the allocation of expensive drugs can be supported by a public consent. This study examines how various factors influence subjectively perceived “fair” pricing of antiseizure medication (ASM) among four groups including physicians, persons with epilepsy (PWEs), their relatives, and a control group. Methods: We conducted a factorial survey. Vignettes featured a fictional PWE receiving a fictional ASM. The characteristics of the fictional PWE, ASM, and epilepsy varied. Participants were asked to assess the subjectively appropriate annual cost of ASM treatment per year for each scenario. Results: Fifty-seven PWEs (mean age (SD) 37.7 ± 12.3, 45.6% female), 44 relatives (age 48.4 ± 15.7, 51.1% female), 46 neurologists (age 37.1 ± 9.6, 65.2% female), and 47 persons in the control group (age 31.2 ± 11.2, 68.1% female) completed the questionnaire. The amount of money that respondents were willing to spend for ASM treatment was higher than currently needed in Germany and increased with disease severity among all groups. All groups except for PWEs accepted higher costs of a drug with better seizure control. Physicians and the control group, but not PWEs and their relatives, tended to do so also for minor or no side effects. Physicians reduced the costs for unemployed patients and the control group spent less money for older patients. Significance: ASM effectiveness appears to justify higher costs. However, the control group attributed less money to older PWEs and physicians allocated fewer drug costs to unemployed PWEs.
CRIS-Team Scopus Importer:2022-08-19

A Single Injection of N-Oleoyldopamine, an Endogenous Agonist for Transient Receptor Potential Vanilloid-1, Induced Brain Hypothermia, but No Neuroprotective Effects in Experimentally Induced Cerebral Ischemia in Rats - De Rink, Maria Mercedes Tejada; Naumann, Ulrike; Kollmar, Rainer; Schwab, Stefan; Dietel, Barbara; Harada, Hideki; Tauchi, Miyuki (Therapeutic Hypothermia and Temperature Management, 2019)
Targeted temperature management, or therapeutic hypothermia, is a potent neuroprotective approach after ischemic brain injury. Hypothermia should be induced as soon as possible after the onset of acute stroke to assure better outcomes. Accordingly, drugs with a fast-acting hypothermic effect sustainable through the period of emergency transportation to hospital would have clinical advantages. Activation of the transient receptor potential vanilloid-1 (TRPV1) can induce hypothermia. Our immunohistochemical investigations confirmed that TRPV1 was distributed to perivascular and periventricular regions of the rat brain, where TRPV1 can be easily detected by TRPV1 agonists. An endogenous TRPV1 selective agonist, N-oleoyldopamine (OLDA), and a synthetic antagonist, AMG 9810, were injected intraperitoneally into healthy adult male Wister rats, and brain and core temperatures and gross motor activities were monitored. Comparison with baseline temperatures showed that TRPV1 injection immediately induced mild hypothermia (p < 0.05 in brain and p < 0.01 in body), and AMG 9810 induced immediate mild hyperthermia (not significant). However, the OLDA-induced hypothermia did not decrease lesion volume after middle carotid artery occlusion in rats. Relative to vehicle, OLDA yielded poorer outcomes and AMG 9810 yielded better outcomes in neurological scores and lesion size. Our study showed that, as an agonist of TRPV1, OLDA has suitable hypothermia-inducing properties, but did not decrease lesion volume. Therefore, the search for novel TRPV1 agonists and/or antagonists providing hypothermia and neuroprotection should continue. Further investigations should also target OLDA-induced transient hypothermia combined with long-term hypothermia maintenance with surface cooling, which mimics the anticipated clinical use of this class of drug.
CRIS-Team WoS Importer:2019-06-18

A Sphingosine-1-Phosphate Receptor Modulator Attenuated Secondary Brain Injury and Improved Neurological Functions of Mice after ICH - Bobinger, Tobias; Bäuerle, Tobias; Seyler, L.; von Hörsten, Stephan; Schwab, Stefan; Huttner, Hagen; Manaenko, A. (Oxidative Medicine and Cellular Longevity, 2020)
Background. Stroke activates the immune system and induces brain infiltration by immune cells, aggravating brain injury. Poststroke immunomodulation via (S1P-)receptor modulation is beneficial; however, the S1P-modulator in clinical use (FTY-720) is unspecific, and undesirable side effects have been reported. Previously, we tested effects of a novel selective S1P-receptor modulator, Siponimod, on ICH-induced brain injury in acute stage of the disease. In the current study, we investigated whether protective effects of Siponimod, evaluated in a short-term study, will protect the brain of ICH animals at long term as well. Methods. 134 C57BL/6N mice were divided into sham and ICH-operated groups. Collagenase model of ICH was employed. ICH animals were divided into Siponimod treated and nontreated. Dose- and time-dependent effects of Siponimod were investigated. Contraplay between development of brain injury and the number of lymphocytes infiltrating the brain was investigated by forelimb placing, T-Maze test, brain water content calculation, MRI scanning, and immunostaining. Results. Depending on the therapeutic strategy, Siponimod attenuated the development of brain edema, decreased ICH-induced ventriculomegaly and improved neurological functions of animals after ICH. It was associated with less lymphocytes in the brain of ICH animals. Conclusion. Siponimod is able to decrease the brain injury and improves neurological functions of animals after ICH.
CRIS-Team Scopus Importer:2020-10-09

Association of Intraventricular Fibrinolysis With Clinical Outcomes in Intracerebral Hemorrhage: An Individual Participant Data Meta-Analysis. - Kuramatsu, Joji; Gerner, Stefan; Ziai, Wendy; Bardutzky, Juergen; Sembill, Jochen; Sprügel, Maximilian; Mrochen, Anne; Kölbl, Kathrin; Ram, Malathi; Avadhani, Radhika; Falcone, Guido J.; Selim, Magdy H.; et al. (Stroke, 2022)
BACKGROUND: In patients with intracerebral hemorrhage (ICH), the presence of intraventricular hemorrhage constitutes a promising therapeutic target. Intraventricular fibrinolysis (IVF) reduces mortality, yet impact on functional disability remains unclear. Thus, we aimed to determine the influence of IVF on functional outcomes. METHODS: This individual participant data meta-analysis pooled 1501 patients from 2 randomized trials and 7 observational studies enrolled during 2004 to 2015. We compared IVF versus standard of care (including placebo) in patients treated with external ventricular drainage due to acute hydrocephalus caused by ICH with intraventricular hemorrhage. The primary outcome was functional disability evaluated by the modified Rankin Scale (mRS; range: 0-6, lower scores indicating less disability) at 6 months, dichotomized into mRS score: 0 to 3 versus mRS: 4 to 6. Secondary outcomes included ordinal-shift analysis, all-cause mortality, and intracranial adverse events. Confounding and bias were adjusted by random effects and doubly robust models to calculate odds ratios and absolute treatment effects (ATE). RESULTS: Comparing treatment of 596 with IVF to 905 with standard of care resulted in an ATE to achieve the primary outcome of 9.3% (95% CI, 4.4-14.1). IVF treatment showed a significant shift towards improved outcome across the entire range of mRS estimates, common odds ratio, 1.75 (95% CI, 1.39-2.17), reduced mortality, odds ratio, 0.47 (95% CI, 0.35-0.64), without increased adverse events, absolute difference, 1.0% (95% CI, -2.7 to 4.8). Exploratory analyses provided that early IVF treatment (≤48 hours) after symptom onset was associated with an ATE, 15.2% (95% CI, 8.6-21.8) to achieve the primary outcome. CONCLUSIONS: As compared to standard of care, the administration of IVF in patients with acute hydrocephalus caused by intracerebral and intraventricular hemorrhage was significantly associated with improved functional outcome at 6 months. The treatment effect was linked to an early time window <48 hours, specifying a target population for future trials.
EVALuna2:505459

Association of prothrombin complex concentrate administration and hematoma enlargement in non-vitamin K antagonist oral anticoagulant-related intracerebral hemorrhage - Gerner, Stefan; Kuramatsu, Joji; Sembill, Jochen; Sprügel, Maximilian; Endres, Matthias; Haeusler, Karl Georg; Vajkoczy, Peter; Ringleb, Peter A.; Purrucker, Jan; Rizos, Timolaos; Erbguth, Frank; Schellinger, Peter D.; et al. (Annals of Neurology, 2018)
To investigate parameters associated with hematoma enlargement in non-vitamin K antagonist oral anticoagulant (NOAC)-related intracerebral hemorrhage (ICH).This retrospective cohort study includes individual patient data for 190 patients with NOAC-associated ICH over a 5-year period (2011-2015) at 19 departments of neurology across Germany. Primary outcome was the association of prothrombin complex concentrate (PCC) administration with hematoma enlargement. Subanalyses were calculated for blood pressure management and its association with the primary outcome. Secondary outcomes include associations with in-hospital mortality and functional outcome at 3 months assessed using the modified Rankin Scale.The study population for analysis of primary and secondary outcomes consisted of 146 NOAC-ICH patients with available follow-up imaging. Hematoma enlargement occurred in 49/146 (33.6%) patients with NOAC-related ICH. Parameters associated with hematoma enlargement were blood pressure >= 160mmHg within 4 hours and-in the case of factor Xa inhibitor ICH-anti-Xa levels on admission. PCC administration prior to follow-up imaging was not significantly associated with a reduced rate of hematoma enlargement either in overall NOAC-related ICH or in patients with factor Xa inhibitor intake (NOAC: risk ratio [RR] = 1.150, 95% confidence interval [CI] = 0.632-2.090; factor Xa inhibitor: RR = 1.057, 95% CI = 0.565-1.977), regardless of PCC dosage given or time interval until imaging or treatment. Systolic blood pressure levels < 160mmHg within 4 hours after admission were significantly associated with a reduction in the proportion of patients with hematoma enlargement (RR = 0.598, 95% CI = 0.365-0.978). PCC administration had no effect on mortality and functional outcome either at discharge or at 3 months.In contrast to blood pressure control, PCC administration was not associated with a reduced rate of hematoma enlargement in NOAC-related ICH. Our findings support the need of further investigations exploring new hemostatic reversal strategies for patients with factor Xa inhibitor-related ICH. Ann Neurol 2018;83:186-196.
EVALuna2:22552

Association of Surgical Hematoma Evacuation vs Conservative Treatment With Functional Outcome in Patients With Cerebellar Intracerebral Hemorrhage - Kuramatsu, Joji; Biffi, Alessandro; Gerner, Stefan; Sembill, Jochen; Sprügel, Maximilian; Leasure, Audrey; Sansing, Lauren; Matouk, Charles; Falcone, Guido J.; Endres, Matthias; Haeusler, Karl Georg; Sobesky, Jan; et al. (Journal of the American Medical Association, 2019)
Importance: The association of surgical hematoma evacuation with clinical outcomes in patients with cerebellar intracerebral hemorrhage (ICH) has not been established. Objective: To determine the association of surgical hematoma evacuation with clinical outcomes in cerebellar ICH. Design, Setting, and Participants: Individual participant data (IPD) meta-analysis of 4 observational ICH studies incorporating 6580 patients treated at 64 hospitals across the United States and Germany (2006-2015). Exposure: Surgical hematoma evacuation vs conservative treatment. Main Outcomes and Measures: The primary outcome was functional disability evaluated by the modified Rankin Scale ([mRS] score range: 0, no functional deficit to 6, death) at 3 months; favorable (mRS, 0-3) vs unfavorable (mRS, 4-6). Secondary outcomes included survival at 3 months and at 12 months. Analyses included propensity score matching and covariate adjustment, and predicted probabilities were used to identify treatment-related cutoff values for cerebellar ICH. Results: Among 578 patients with cerebellar ICH, propensity score-matched groups included 152 patients with surgical hematoma evacuation vs 152 patients with conservative treatment (age, 68.9 vs 69.2 years; men, 55.9% vs 51.3%; prior anticoagulation, 60.5% vs 63.8%; and median ICH volume, 20.5 cm3 vs 18.8 cm3). After adjustment, surgical hematoma evacuation vs conservative treatment was not significantly associated with likelihood of better functional disability at 3 months (30.9% vs 35.5%; adjusted odds ratio [AOR], 0.94 [95% CI, 0.81 to 1.09], P = .43; adjusted risk difference [ARD], -3.7% [95% CI, -8.7% to 1.2%]) but was significantly associated with greater probability of survival at 3 months (78.3% vs 61.2%; AOR, 1.25 [95% CI, 1.07 to 1.45], P = .005; ARD, 18.5% [95% CI, 13.8% to 23.2%]) and at 12 months (71.7% vs 57.2%; AOR, 1.21 [95% CI, 1.03 to 1.42], P = .02; ARD, 17.0% [95% CI, 11.5% to 22.6%]). A volume range of 12 to 15 cm3 was identified; below this level, surgical hematoma evacuation was associated with lower likelihood of favorable functional outcome (volume ≤12 cm3, 30.6% vs 62.3% [P = .003]; ARD, -34.7% [-38.8% to -30.6%]; P value for interaction, .01), and above, it was associated with greater likelihood of survival (volume ≥15 cm3, 74.5% vs 45.1% [P < .001]; ARD, 28.2% [95% CI, 24.6% to 31.8%]; P value for interaction, .02). Conclusions and Relevance: Among patients with cerebellar ICH, surgical hematoma evacuation, compared with conservative treatment, was not associated with improved functional outcome. Given the null primary outcome, investigation is necessary to establish whether there are differing associations based on hematoma volume.
CRIS-Team Scopus Importer:2019-10-15

Atrial Fibrillation Detected before or after Stroke: Role of Anticoagulation - Lyrer, Flurina; Zietz, Annaelle; Seiffge, David J.; Koga, Masatoshi; Volbers, Bastian; Wilson, Duncan; Bonetti, Bruno; Schaedelin, Sabine; Gensicke, Henrik; Yoshimura, Sohei; Macha, Kosmas; Ambler, Gareth; et al. (Annals of Neurology, 2023)
Background: Atrial fibrillation (AF) known before ischemic stroke (KAF) has been postulated to be an independent category with a recurrence risk higher than that of AF detected after stroke (AFDAS). However, it is unknown whether this risk difference is confounded by pre-existing anticoagulation, which is most common in KAF and also indicates a high ischemic stroke recurrence risk. Methods: Individual patient data analysis from 5 prospective cohorts of anticoagulated patients following AF-associated ischemic stroke. We compared the primary (ischemic stroke recurrence) and secondary outcome (all-cause death) among patients with AFDAS versus KAF and among anticoagulation-naïve versus previously anticoagulated patients using multivariable Cox, Fine-Gray models, and goodness-of-fit statistics to investigate the relative independent prognostic importance of AF-category and pre-existing anticoagulation. Results: Of 4,357 patients, 1,889 (43%) had AFDAS and 2,468 (57%) had KAF, while 3,105 (71%) were anticoagulation-naïve before stroke and 1,252 (29%) were previously anticoagulated. During 6,071 patient-years of follow-up, we observed 244 recurrent strokes and 661 deaths. Only pre-existing anticoagulation (but not KAF) was independently associated with a higher hazard for stroke recurrence in both Cox and Fine-Gray models. Models incorporating pre-existing anticoagulation showed better fit than those with AF category; adding AF-category did not result in better model fit. Neither pre-existing anticoagulation nor KAF were independently associated with death. Conclusion: Our findings challenge the notion that KAF and AFDAS are clinically relevant and distinct prognostic entities. Instead of attributing an independently high stroke recurrence risk to KAF, future research should focus on the causes of stroke despite anticoagulation to develop improved preventive treatments. ANN NEUROL 2023.
CRIS-Team Scopus Importer:2023-04-28

Attitudes toward persons with epilepsy as friends: Results of a factorial survey - Walther, Katrin; Kriwy, Peter; Stritzelberger, Jenny; Graf, Wolfgang; Gollwitzer, Stefanie; Lang, Johannes; Reindl, Caroline; Schwab, Stefan; Welte, Tamara; Hamer, Hajo (Epilepsia, 2023)
Objective: Discrimination against persons with epilepsy (PWEs) may persist. The aim of this study was to examine whether epilepsy is an obstacle to desired friendship.Methods: A factorial survey (vignettes), which is less biased by social desirability, was applied to PWEs, their relatives, and lay persons. The vignettes described a person who was varied by the dimensions of age (younger, same age, older), gender (male, female), disease (healthy, mild epilepsy, severe epilepsy [generalized toni-clonic seizures], diabetes), origin (German, non-German), contact (phone/internet, activities at home, activities outside), frequency of contacts (weekly, monthly), and distance (around the corner, 10 km away). Respondents rated their willingness to befriend the person on a 10-point Likert scale. Multivariate regression determined the contribution of each dimension on the judgment.Results: Participants were 64 PWEs (age = 37.1 +/- 14.0 years), 64 relatives of PWEs (age = 45.1 +/- 13.6 years), and 98 controls without contact with PWEs (age = 24.4 +/- 10.1 years). Controls were less interested in a friendship with a PWE with mild epilepsy (-3.4%) and even more avoided PWEs with severe epilepsy (-11.7%), whereas in PWEs with toni-clonic seizures, a mild form of epilepsy was actually conducive to friendship (+7.0%). Controls preferred females (+5.0%) and disliked younger people (-12.3%) and contacts via the internet or telephone (-7.3%). PWEs were also less interested in younger people (-5.8%), and relatives of PWEs had a lower preference for friendships with longer distance (-2.3%).Significance: PWEs still suffer from a risk of social avoidance, and this becomes more evident with generalized motor seizures.
CRIS-Team WoS Importer:2023-02-03

Automated ASPECT scoring in acute ischemic stroke: comparison of three software tools - Hölter, Philip; Mühlen, Iris; Gölitz, Philipp; Beuscher, Vanessa; Schwab, Stefan; Dörfler, Arnd (Neuroradiology, 2020)
Purpose: Various software applications offer support in the diagnosis of acute ischemic stroke (AIS), yet it remains unclear whether the performance of these tools is comparable to each other. Our study aimed to evaluate three fully automated software applications for Alberta Stroke Program Early CT (ASPECT) scoring (Syngo.via Frontier ASPECT Score Prototype V2, Brainomix e-ASPECTS® and RAPID ASPECTS) in AIS patients. Methods: Retrospectively, 131 patients with large vessel occlusion (LVO) of the middle cerebral artery or the internal carotid artery, who underwent endovascular therapy (EVT), were included. Pre-interventional non-enhanced CT (NECT) datasets were assessed in random order using the automated ASPECT software and by three experienced neuroradiologists in consensus. Interclass correlation coefficient (ICC), Bland-Altman, and receiver operating characteristics (ROC) were applied for statistical analysis. Results: Median ASPECTS of the expert consensus reading was 8 (7–10). Highest correlation was between the expert read and Brainomix (r = 0.871 (0.818, 0.909), p < 0.001). Correlation between expert read and Frontier V2 (r = 0.801 (0.719, 0.859), p < 0.001) and between expert read and RAPID (r = 0.777 (0.568, 0.871), p < 0.001) was high, respectively. There was a high correlation among the software tools (Frontier V2 and Brainomix: r = 0.830 (0.760, 0.880), p < 0.001; Frontier V2 and RAPID: r = 0.847 (0.693, 0.913), p < 0.001; Brainomix and RAPID: r = 0.835 (0.512, 0.923), p < 0.001). An ROC curve analysis revealed comparable accuracy between the applications and expert consensus reading (Brainomix: AUC = 0.759 (0.670–0.848), p < 0.001; Frontier V2: AUC = 0.752 (0.660–0.843), p < 0.001; RAPID: AUC = 0.734 (0.634–0.831), p < 0.001). Conclusion: Overall, there is a convincing yet developable grade of agreement between current ASPECT software evaluation tools and expert evaluation with regard to ASPECT assessment in AIS.
CRIS-Team Scopus Importer:2020-05-15
Keywords: Acute ischemic stroke; Aspects; Diagnostics; Software anylsis

AUTOMATED PUPILLOMETRY FOR PREDICTION OF SPACE-OCCUPYING HEMISPHERIC INFARCTION AFTER ENDOVASCULAR TREATMENT - Köhn, Julia; Kobus, Franca; Kossel, Clara-Sophie; Borutta, Matthias; Kuramatsu, Joji; Schwab, Stefan (JOURNAL OF NEUROTRAUMA, 2022)
CRIS-Team WoS Importer:2022-09-02

Automated Pupillometry Identifies Absence of Intracranial Pressure Elevation in Intracerebral Hemorrhage Patients - Giede-Jeppe, Antje; Sprügel, Maximilian; Huttner, Hagen; Borutta, Matthias; Kuramatsu, Joji; Hölter, Philip; Engelhorn, Tobias; Schwab, Stefan; Koehn, Julia (Neurocritical Care, 2020)
Introduction Although automated pupillometry is increasingly used in critical care settings, predictive value of automatically assessed pupillary parameters during different intracranial pressure (ICP) levels and possible clinical implications are unestablished. Methods This retrospective cohort study at the neurocritical care unit of the University of Erlangen-Nuremberg (2016-2018) included 23 nontraumatic supratentorial (intracerebral hemorrhage) ICH patients without signs of abnormal pupillary function by manual assessment, i.e., absent light reflex. We assessed ICP levels by an external ventricular drain simultaneously with parameters of pupillary reactivity [i.e., maximum and minimum apertures, light reflex latency (Lat), constriction and redilation velocities (CV, DV), and percentage change of apertures (per-change)] using a portable pupillometer (NeurOptics (R)). Computed tomography (CT) scans were analyzed to determine lesion location, size, intraventricular hemorrhage, hydrocephalus, midline shift, and compression or absence of the basal cisterns. We performed receiver operating characteristics analysis to investigate associations of ICP levels with pupillary parameters and to determine best cutoff values for prediction of ICP elevation. After dichotomization of assessments according to ICP values (normal: < 20 mmHg, elevated: >= 20 mmHg), prognostic performance of the determined cutoff parameters of pupillary function versus of CT-imaging findings was analyzed by calculating sensitivity, specificity, positive and negative predictive values (logistic regression, corresponding ORs with 95% CIs). Results In 23 patients (11 women, median age 59.0 (51.0-69.0) years), 1,934 assessments were available for analysis. A total of 74 ICP elevations >= 20 mmHg occurred in seven patients. Best discriminative thresholds for ICP elevation were: CV < 0.8 mm/s (AUC 0.740), per-change < 10% (AUC 0.743), DV < 0.2 mm/s (AUC 0.703), and Lat > 0.3 s (AUC 0.616). Positive predictive value of all four parameters to indicate ICP elevation ranged between 7.2 and 8.3% only and was similarly low for CT abnormalities (9.1%). We found high negative predictive values of pupillary parameters [CV: 99.2% (95% CI 98.3-99.6), per-change: 98.7% (95% CI 97.8-99.2), DV: 98.0% (95% CI 97.0-98.7), Lat: 97.0% (95% CI 96.0-97.7)], and CT abnormalities [99.7% (95% CI 99.2-99.9)], providing evidence that both techniques adequately identified ICH patients without ICP elevation. Conclusions Our data suggest an association between noninvasively detected changes in pupillary reactivity and ICP levels in sedated ICH patients. Although automated pupillometry and neuroimaging seem not sufficient to noninvasively indicate ICP elevation, both techniques, however, adequately identified ICH patients without ICP elevation. This finding may facilitate routine management by saving invasive ICP monitoring or repeated CT controls in patients with specific automated pupillometry readings.
CRIS-Team WoS Importer:2021-01-08

Automatic dementia screening and scoring by applying deep learning on clock-drawing tests - Chen, Shuqing; Stromer, Daniel; Alnasser Alabdalrahim, Harb; Schwab, Stefan; Weih, Markus; Maier, Andreas (Scientific Reports, 2020)
Dementia is one of the most common neurological syndromes in the world. Usually, diagnoses are made based on paper-and-pencil tests and scored depending on personal judgments of experts. This technique can introduce errors and has high inter-rater variability. To overcome these issues, we present an automatic assessment of the widely used paper-based clock-drawing test by means of deep neural networks. Our study includes a comparison of three modern architectures: VGG16, ResNet-152, and DenseNet-121. The dataset consisted of 1315 individuals. To deal with the limited amount of data, which also included several dementia types, we used optimization strategies for training the neural network. The outcome of our work is a standardized and digital estimation of the dementia screening result and severity level for an individual. We achieved accuracies of 96.65% for screening and up to 98.54% for scoring, overcoming the reported state-of-the-art as well as human accuracies. Due to the digital format, the paper-based test can be simply scanned by using a mobile device and then be evaluated also in areas where there is a staff shortage or where no clinical experts are available.<br

Bedside Catheter Hematoma Evacuation in Vitamin K Antagonist-Related Intracerebral Hemorrhage: A Safe and Feasible Approach - Volbers, Bastian; Niesen, Wolf Dirk; Amiri-Soltani, Samuel; Staykov, Dimitre; Shah, Mukesch Johannes; Lang, Stefan; Lücking, Hannes; Kuramatsu, Joji; Huttner, Hagen; Schwab, Stefan; Bardutzky, Jürgen (Frontiers in Neurology, 2020)
Background and Purpose: Although outcome in intracerebral hemorrhage (ICH) patients is generally not improved by surgical intervention, the use of minimally invasive surgery (MIS) has shown promising results. However, vitamin K antagonist (VKA)-related ICH patients are underrepresented in surgical treatment trials. We therefore assessed the safety and efficacy of a bedside MIS approach including local application of urokinase in VKA-related ICH. Methods: Patients with a VKA-related ICH > 20 ml who received bedside hematoma evacuation treatment (n = 21) at the University Medical Center Freiburg were retrospectively included for analysis and compared to a historical control group (n = 35) selected from an institutional database (University Medical Center Erlangen) according to identical inclusion criteria. Propensity score matching was performed to obtain comparable cohorts. The evolution of hematoma and peri-hemorrhagic edema (PHE) volumes, midline shift, and the occurrence of adverse events were analyzed. Furthermore, we assessed the modified Rankin Scale and NIHSS scores recorded at discharge. Results: Propensity score matching resulted in 16 patients per group with well-balanced characteristics. Median ICH volume at admission was 45.7 (IQR: 24.2–56.7) ml in the control group and 48.4 (IQR: 28.7–59.6) ml in the treatment group (p = 0.327). ICH volume at day 7 was less pronounced in the treatment group [MIS: 23.2 ml (IQR: 15.8–32.3) vs. control: 43.2 ml (IQR: 27.5–52.4); p = 0.013], as was the increase in midline shift up to day 7 [MIS: −3.75 mM (IQR: −4.25 to −2) vs. control: 1 mM (IQR: 0–2); p < 0.001]. No group differences were observed in PHE volume on day 7 [MIS: 42.4 ml (IQR: 25.0–72.3) vs. control: 31.0 ml (IQR: 18.8–53.8); p = 0.274] or mRS at discharge [MIS: 5 (IQR: 4–5) and 5 (IQR: 4–5); p = 0.949]. No hematoma expansion was observed. The catheter had to be replaced in 1 patient (6%). Conclusions: Bedside catheter-based hematoma evacuation followed by local thrombolysis with urokinase appears to be feasible and safe in cases of large VKA-related ICH. Further studies that assess the functional outcome associated with this technique are warranted. Clinical Trial Registration: DRKS00007908 (German Clinical Trial Register; www.drks.de).
CRIS-Team Scopus Importer:2020-09-11
Keywords: intracerebral hemorrhage; midline shift; minimally invasive surgery; peri-hemorrhagic edema; vitamin K antagonist

Bedside Ultrasound After Decompressive Craniectomy: A New Standard? - Bobinger, Tobias; Huttner, Hagen; Schwab, Stefan (Neurocritical Care, 2017)
EVALuna2:22522

Beyond Functional Impairment: Redefining Favorable Outcome in Patients with Subarachnoid Hemorrhage - Custal, Christina; Koehn, Julia; Borutta, Matthias; Mrochen, Anne; Brandner, Sebastian; Eyupoglu, Ilker Y.; Lücking, Hannes; Hölter, Philip; Kuramatsu, Joji; Kornhuber, Johannes; Schwab, Stefan; Huttner, Hagen; et al. (Cerebrovascular Diseases, 2021)
Background: For outcome assessment in patients surviving subarachnoid hemorrhage (SAH), the modified Rankin scale (mRS) represents the mostly established outcome tool, whereas other dimensions of outcome such as mood disorders and impairments in social life remain unattended so far. Objective: The aim of our study was to correlate 12-month functional and subjective health outcomes in SAH survivors. Methods: All SAH patients treated over a 5-year period received outcome assessment at 12 months, including functional scores (mRS and Barthel Index [BI]), subjective health measurement (EQ-5D), and whether they returned to work. Analyses - including utility-weighted mRS - were conducted to detect associations and correlations among different outcome measures, especially in patients achieving good functional outcome (i.e., mRS 0-2) at 12 months. Results: Of 351 SAH survivors, 287 (81.2%) achieved favorable functional outcome at 12 months. Contrary to the BI, the EQ-5D visual analog scale (VAS) showed a strong association with different mRS grades, accentuated in patients with favorable functional outcome. Despite favorable functional outcome, patients reported a high rate of impairments in activities (24.0%), pain (33.4%), and anxiety/depression (42.5%). Further, multivariable analysis revealed (i) impairments in activities (odds ratio [OR] [95% confidence interval CI]: 0.872 [0.817-0.930]), (ii) presence of depression or anxiety (OR [95% CI]: 0.836 [0.760-0.920]), and (iii) return to work (OR [95% CI]: 1.102 [0.1.013-1.198]) to be independently associated with self-reported subjective health. Conclusion: Established stroke scores mainly focusing on functional outcomes do poorly reflect the high rate of subjective impairments reported in SAH survivors, specifically in those achieving good functional outcome. Further studies are needed to investigate whether psychoeducational approaches aiming at improving coping mechanisms and perceived self-efficacy may result in higher subjective health in these patients.
CRIS-Team WoS Importer:2021-08-06

Blood biomarker changes following therapeutic hypothermia in ischemic stroke - Palà, Elena; Penalba, Anna; Bustamante, Alejandro; García-Berrocoso, Teresa; Lamana-Vallverdú, Marcel; Meisel, Christian; Meisel, Andreas; van der Worp, H. Bart; R Macleod, Malcolm; Kallmünzer, Bernd; Schwab, Stefan; Montaner, Joan (Brain and Behavior, 2023)
Introduction: Therapeutic hypothermia is a promising candidate for stroke treatment although its efficacy has not yet been demonstrated in patients. Changes in blood molecules could act as surrogate markers to evaluate the efficacy and safety of therapeutic cooling. Methods: Blood samples from 54 patients included in the EuroHYP-1 study (27 treated with hypothermia, and 27 controls) were obtained at baseline, 24 ± 2 h, and 72 ± 4 h. The levels of a panel of 27 biomarkers, including matrix metalloproteinases and cardiac and inflammatory markers, were measured. Results: Metalloproteinase-3 (MMP-3), fatty-acid-binding protein (FABP), and interleukin-8 (IL-8) increased over time in relation to the hypothermia treatment. Statistically significant correlations between the minimum temperature achieved by each patient in the hypothermia group and the MMP-3 level measured at 72 h, FABP level measured at 24 h, and IL-8 levels measured at 24 and 72 h were found. No differential biomarker levels were observed in patients with poor or favorable outcomes according to modified Rankin Scale scores. Conclusion: Although the exact roles of MMP3, FABP, and IL-8 in hypothermia-treated stroke patients are not known, further exploration is needed to confirm their roles in brain ischemia.
CRIS-Team Scopus Importer:2023-09-29
Keywords: biomarkers; hypothermia; ischemia; stroke

Brain MRI Lesions are Related to Bowel Incontinence in Multiple Sclerosis - Fröhlich, Katharina; Linker, Ralf; Engelhorn, Tobias; Dörfler, Arnd; Lee, De-Hyung; Huhn, Konstantin; Schwab, Stefan; Hilz, Max-Josef; Seifert, Frank; Winder, Klemens (Journal of Neuroimaging, 2018)
BACKGROUND AND PURPOSE: Bowel incontinence in multiple sclerosis might be associated with specific lesion sites. This study intended to determine associations between bowel incontinence and cerebral multiple sclerosis lesions using a voxel-wise lesion symptom mapping analysis. METHODS: We conducted a retrospective study of multiple sclerosis patients with self-reported bowel incontinence and matched controls. Lesions were manually outlined on T2-weighted MRI scans and transformed into stereotaxic space. We performed a voxel-wise subtraction analysis subtracting the lesion overlap of patients without from patients with bowel incontinence. Finally, we compared the absence or presence of bowel incontinence between patients with and without lesions in a given voxel using the Liebermeister test. RESULTS: A total of 51 patients were included in the study. The analysis yielded associations between bowel incontinence and lesions in the supramarginal gyrus of the left secondary somatosensory cortex and another lesion cluster in the right parahippocampal gyrus and amygdala. CONCLUSIONS: Our analysis indicates associations between bowel incontinence and lesions in the left supramarginal gyral area contributing to integrating anorectal-visceral sensation and in the right parahippocampal gyrus and amygdala contributing to generating visceral autonomic arousal states. Moreover, our results suggest left hemispheric dominance of sensory visceral integration, while limbic areas of the right hemisphere seem to contribute to the autonomic component of the defecation process. A limitation of our study is the retrospective evaluation of the bowel incontinence status based on medical records. Further research should evaluate the bowel incontinence status in multiple sclerosis patients prospectively to overcome the limitations of the current study.
EVALuna2:36318

Can flat-detector CT after successful endovascular treatment predict long-term outcome in patients with large vessel occlusion? An Alberta Stroke Programme Early CT Score–based study - Knott, Michael; Hölter, Philip; Hock, Stefan; Mühlen, Iris; Gerner, Stefan; Sprügel, Maximilian; Huttner, Hagen; Schwab, Stefan; Engelhorn, Tobias; Dörfler, Arnd (Neurological Sciences, 2022)
Purpose: Recent studies postulate a high prognostic value of the Alberta Stroke Programme Early CT Score (ASPECTS) applied on non-contrast whole-brain flat-detector CT (FDCT) after successful endovascular treatment (EVT). The aim of this study was the evaluation of long-term patient outcome after endovascular treatment using postinterventional FDCT. Methods: Using a local database (Stroke Research Consortium in Northern Bavaria, STAMINA), 517 patients with successful endovascular treatment (modified Thrombolysis in Cerebral Infarction (mTICI) ≥ 2B) due to acute ischaemic stroke (AIS) and large vessel occlusion (LVO) of the anterior circulation were recruited retrospectively. In all cases, non-contrast FDCT after EVT was analysed with special focus at ASPECTS. These results were correlated with the functional outcome in long-term (modified Rankin Scale (mRS) shift from pre-stroke to 90 days after discharge). Results: A significant difference in FDCT-ASPECTS compared to the subgroup of favourable vs. unfavourable outcome (Δ mRS) (median ASPECTS 10 (10–9) vs. median ASPECTS 9 (10–7); p = 0,001) could be demonstrated. Multivariable regression analysis revealed FDCT-ASPECTS (OR 0.234, 95% CI − 0.102–0.008, p = 0.022) along with the NHISS at admission (OR 0.169, 95% CI 0.003–0.018, p = 0.008) as independent factors for a favourable outcome. Cut-off point for a favourable outcome (Δ mRS) was identified at an ASPECTS ≥ 8 (sensitivity 90.6%, specificity 35%). Conclusion: For patients with LVO and successful EVT, FDCT-ASPECTS was found to be highly reliable in predicting long-term outcome.
CRIS-Team Scopus Importer:2022-12-02
Keywords: ASPECTS; Endovascular treatment; Flat-detector CT; Stroke

Cardioembolic Stroke Risk and Recovery After Anticoagulation-Related Intracerebral Hemorrhage - Murphy, Meredith P.; Kuramatsu, Joji; Leasure, Audrey; Falcone, Guido J.; Kamel, Hooman; Sansing, Lauren H.; Kourkoulis, Christina; Schwab, Kristin; Elm, Jordan J.; Gurol, M. Edip; Huy Tran; Greenberg, Steven M.; et al. (Stroke, 2018)
Background and Purpose- Whether to resume oral anticoagulation treatment after intracerebral hemorrhage (ICH) remains an unresolved question. Previous studies focused primarily on recurrent stroke after ICH. We sought to investigate the association between cardioembolic stroke risk, oral anticoagulation therapy resumption, and functional recovery among ICH survivors in the absence of recurrent stroke. Methods- We conducted a joint analysis of 3 observational studies: (1) the multicenter RETRACE study (German-Wide Multicenter Analysis of Oral Anticoagulation Associated Intracerebral Hemorrhage); (2) the Massachusetts General Hospital ICH study (n=166); and (3) the ERICH study (Ethnic/Racial Variations of Intracerebral Hemorrhage; n=131). We included 941 survivors of ICH in the setting of active oral anticoagulation therapy for prevention of cardioembolic stroke because of nonvalvular atrial fibrillation and without evidence of ischemic stroke and recurrent ICH at 1 year from the index event. We created univariable and multivariable models to explore associations between cardioembolic stroke risk (based on CHA2DS2-VASc scores) and functional recovery after ICH, defined as achieving modified Rankin Scale score of ≤3 at 1 year for participants with modified Rankin Scale score of >3 at discharge. Results- In multivariable analyses, the CHA2DS2-VASc score was associated with a decreased likelihood of functional recovery (odds ratio, 0.83 per 1 point increase; 95% CI, 0.79-0.86) at 1 year. Anticoagulation resumption was independently associated with a higher likelihood of recovery, regardless of CHA2DS2-VASc score (odds ratio, 1.89; 95% CI, 1.32-2.70). We found an interaction between CHA2DS2-VASc score and anticoagulation resumption in terms of association with increased likelihood of functional recovery (interaction P=0.011). Conclusions- Increasing cardioembolic stroke risk is associated with a decreased likelihood of functional recovery at 1 year after ICH, but this association was weaker among participants resuming oral anticoagulation therapy. These findings support, including recovery metrics, in future studies of anticoagulation resumption after ICH.
EVALuna2:34937

Cardiovascular autonomic dysfunction in patients with posterior circulation ischemic stroke - Wang, Ruihao; Macha, Kosmas; Koehn, Julia; Siedler, Gabriela; Winder, Klemens; Gerner, Stefan; Schwab, Stefan; Kohrmann, Martin; Hilz, Max-Josef; Kallmünzer, Bernd (JOURNAL OF THE NEUROLOGICAL SCIENCES, 2021)
CRIS-Team WoS Importer:2021-12-03

CARDIOVASCULAR AUTONOMIC MODULATION THREE MONTHS POST STROKE IMPROVES IN PATIENTS WITH ISCHEMIA IN THE RIGHT MIDDLE CEREBRAL ARTERY TERRITORY - Wang, Ruihao; Macha, Kosmas; Köhn, Julia; Marsch, Armin; Winder, Klemens; Gerner, Stefan; Koehrmann, M.; Schwab, Stefan; Kallmünzer, Bernd; Hilz, Max-Josef (INTERNATIONAL JOURNAL OF STROKE, 2020)
CRIS-Team WoS Importer:2021-01-22

Cardiovascular medication seems to promote recovery of autonomic dysfunction after stroke - Wang, Ruihao; Koehrmann, Martin; Kollmar, Rainer; Köhn, Julia; Schwab, Stefan; Kallmünzer, Bernd; Hilz, Max-Josef (Journal of Neurology, 2022)
Background Stroke may compromise cardiovascular-autonomic modulation (CAM). The longitudinal post-stroke CAM alterations remain unclear as previous studies excluded patients with cardiovascular medication. This study evaluated whether CAM dysfunction improves after several months in patients under typical clinical conditions, i.e., without excluding patients with cardiovascular medication. Methods In 82 ischemic stroke patients [33 women, 64.9 +/- 8.9 years, NIHSS-scores 2 (interquartile range 1-5)], we evaluated the applications of cardiovascular medication before stroke, during autonomic tests performed within 1 week, 3 and 6 months after stroke onset. We determined resting RR intervals (RRI), systolic, diastolic blood pressures (BPsys), respiration, parameters reflecting total CAM [RRI-standard deviation (RRI-SD), RRI-total powers], sympathetic [RRI-low-frequency powers (RRI-LF), BPsys-LF powers] and parasympathetic CAM [RMSSD, RRI-high-frequency powers (RRI-HF powers)], and baroreflex sensitivity. ANOVA or Friedman tests with post hoc analyses compared patient data with data of 30 healthy controls, significance was assumed for P < 0.05. Results More patients had antihypertensive medication after than before stroke. First-week CAM testing showed lower RRIs, RMSSD, RRI-SDs, RRI-total powers, RRI-HF powers, and baroreflex sensitivity, but higher BPsys-LF powers in patients than controls. After 3 and 6 months, patients had significantly higher RRIs, RRI-SDs, RRI-total powers, RMSSDs, RRI-HF powers, and baroreflex sensitivity, but lower BPsys-LF powers than in the 1st week; RMSSDs and RRI-HF powers no longer differed between patients and controls. However, 6-month values of RRIs, RRI-SDs, and baroreflex sensitivity were again lower in patients than controls. Conclusions Even mild strokes compromised cardiovagal modulation and baroreflex sensitivity. After 3 months, CAM had almost completely recovered. Recovery might be related to the mild stroke severity. Presumably, CAM recovery was also promoted by the increased application of cardiovascular medication. Yet, slight CAM dysfunction after 6 months suggests continuing autonomic vulnerability.
CRIS-Team WoS Importer:2022-06-24

Case report: Cerebrospinal fluid neutrophilic pleocytosis upon intrathecal triamcinolone injection - Tsaktanis, Thanos; Stritzelberger, Jenny; To, Vi Tuong Daniel; Uhl, Martin; Schwab, Stefan; Heuß, Dieter Felix; Rothhammer, Veit (Frontiers in Neurology, 2024)
Intrathecal corticosteroids, initially employed in the 1950s, faced declining use due to complications like arachnoiditis and aseptic meningitis. Triamcinolone, which is nowadays used as intrathecally applied glucocorticoid formulation, has been shown to beneficially influence spasticity without demonstrable influence on disease activity or progression. We here present the case of a patient with recurrent episodes of aseptic cerebrospinal fluid (CSF) neutrophilic pleocytosis over a year following intrathecal triamcinolone treatment. CSF analyses revealed a post-injection CSF cytokine profile resembling cytokine release reaction rather than drug hypersensitivity. This case thus highlights a potential side effect of intrathecal triamcinolone injection with yet unclear clinical relevance, underscores the need for further assessment of clinical benefits of intrathecal triamcinolone, and emphasizes potential short and long-term side effects associated with extended intrathecal triamcinolone use.
CRIS-Team Scopus Importer:2024-05-24
Keywords: chemical meningitis; inflammatory CSF syndrome; intrathecal injection of triamcinolone; side effect; spasticity; triamcinolone

Cerebral Ischemia in Patients on Direct Oral Anticoagulants - Macha, Kosmas; Marsch, Armin; Siedler, Gabriela; Breuer, Lorenz; Strasser, Erwin; Engelhorn, Tobias; Schwab, Stefan; Kallmünzer, Bernd (Stroke, 2019)
Background and Purpose- In patients with ischemic stroke on therapy with vitamin K antagonists, stroke severity and clinical course are affected by the quality of anticoagulation at the time of stroke onset, but clinical data for patients using direct oral anticoagulants (DOACs) are limited. Methods- Data from our registry including all patients admitted with acute cerebral ischemia while taking oral anticoagulants for atrial fibrillation between November 2014 and October 2017 were investigated. The activity of vitamin K antagonists was assessed using the international normalized ratio on admission and categorized according to a threshold of 1.7. DOAC plasma levels were measured using the calibrated Xa-activity (apixaban, rivaroxaban, and edoxaban) or the Hemoclot-assay (dabigatran) and categorized into low (<50 ng/mL), intermediate (50-100 ng/mL), or high (>100 ng/mL). Primary objective was the association between anticoagulant activity and clinical and imaging characteristics. Results- Four hundred sixty patients were included (49% on vitamin K antagonists and 51% on DOAC). Patients on vitamin K antagonists with low international normalized ratio values had higher scores on the National Institutes of Health Stroke Scale and a higher risk of large vessel occlusion on admission. For patients on DOAC, plasma levels were available in 75.6% and found to be low in 49 (27.7%), intermediate in 41 (23.2%), and high in 87 patients (49.2%). Low plasma levels were associated with higher National Institutes of Health Stroke Scale scores on admission (low: 8 [interquartile range, 3-15] versus intermediate: 4 [1-11] versus high: 3 [0-8]; P<0.001) and higher risk of persisting neurological deficits or cerebral infarction on imaging (85.7% versus 75.6% versus 54.0%; P<0.001). Low DOAC plasma levels were an independent predictor of large vessel occlusion (odds ratio, 3.84 [95% CI, 1.80-8.20]; P=0.001). Conclusions- The activity of anticoagulation measured by specific DOAC plasma levels on admission is associated with stroke severity and presence of large vessel occlusion.
CRIS-Team Scopus Importer:2019-07-19
Keywords: anticoagulants; atrial fibrillation; direct oral anticoagulants; ischemic stroke; plasma level

Cerebral lesions in the central pain matrix are associated with headache in multiple sclerosis - Fröhlich, Kilian; Macha, Kosmas; Siedler, Gabriela; Sekita, Alexander; Haupenthal, David; Mrochen, Anne; Wang, Ruihao; Schembs, Leah; Dörfler, Arnd; Seifert, Frank; Schwab, Stefan; Winder, Klemens (Scientific Reports, 2025)
Headache is very frequent in multiple sclerosis. However, the question whether headache is just coincidental or may be secondary due to inflammatory cerebral multiple sclerosis lesions is yet to be clarified. This study intended to evaluate the distribution of cerebral lesion sites and the potential presence of specific lesion clusters in patients with multiple sclerosis and comorbid headache using voxel-based lesion symptom mapping (VLSM). Patients with multiple sclerosis and headache were prospectively identified and included in a university neurological center between 2017 and 2023. Only patients with headache onset after first manifestation of multiple sclerosis were included. Demographic and clinical data were assessed, and lesion volumes calculated. Cerebral lesion sites were correlated voxel-wise with presence and absence of headache using non-parametric permutation testing. A cohort of multiple sclerosis patients served as controls for the VLSM-analysis. 48 multiple sclerosis patients with headache were included, as well as 92 controls without headache. Of the 48 patients with headache, 39 (81%) were female and nine (19%) were male. Mean age was significantly higher in headache patients than in controls (51 + / − 11 vs. 42 + / − 11 years, p < 0.05). EDSS, disease duration and lesion volumes did not significantly differ between both groups. Lesion overlap of all patients demonstrated a distribution of white matter lesions consistently in all subcortical brain areas. The VLSM-analysis showed associations between headache and lesion clusters in the left insula, left hippocampus and right thalamus. In our study, multiple sclerosis lesions in the left insula, left hippocampus and right thalamus were associated with headache in multiple sclerosis patients. The data therefore indicates that headache in multiple sclerosis may, in a proportion of patients, result from lesions in the central nervous systems’ pain processing network. Trial registration: No. 93_17 B, Ethics committee of the University Hospital Erlangen-Nürnberg.
CRIS-Team Scopus Importer:2025-04-01
Keywords: Cerebral lesions; Headache; Multiple sclerosis; Voxel-based lesion symptom mapping

Cerebral lesions sites in neurosarcoidosis: a lesion mapping study - Fröhlich, Kilian; Mrochen, Anne; Wang, Ruihao; Haupenthal, David; Macha, Kosmas; Siedler, Gabriela; Knott, Michael; Dörfler, Arnd; Schwab, Stefan; Winder, Klemens (Journal of Neurology, 2023)
Background and purpose: Sarcoidosis is a granulomatous disease of unknown etiology affecting the central nervous system in up to 15% of the patients. Diagnosis of neurosarcoidosis is very challenging due to the heterogeneity of its clinical manifestation. This study intended to evaluate the distribution of cerebral lesion sites and the potential presence of specific lesion clusters in neurosarcoidosis patients using voxel-based lesion symptom mapping (VLSM). Methods: Patients with neurosarcoidosis were retrospectively identified and included between 2011 and 2022. Cerebral lesion sites were correlated voxel-wise with presence and absence of neurosarcoidosis using non-parametric permutation test. Multiple sclerosis patients served as controls for the VLSM-analysis. Results: Thirty-four patients (mean age 52 ± 15 years) of whom 13 were diagnosed with possible, 19 with probable and 2 with confirmed neurosarcoidosis were identified. Lesion overlap of neurosarcoidosis patients demonstrated a distribution of white matter lesions in all brain areas, with a periventricular predilection similar to multiple sclerosis. In contrast to multiple sclerosis controls, no propensity for lesions in proximity of the corpus callosum was observed. Neurosarcoidosis lesions appeared smaller and lesion volume was lower in the neurosarcoidosis cohort. The VLSM analysis showed minor associations between neurosarcoidosis and damaged voxels in the bilateral frontobasal cortex. Conclusions: The VLSM analysis yielded significant associations in the bilateral frontal cortex, suggesting that leptomeningeal inflammatory disease with following cortical involvement is a quite specific feature in neurosarcoidosis. Lesion load was lower in neurosarcoidosis than in multiple sclerosis. However, no specific pattern of subcortical white matter lesions in neurosarcoidosis was revealed.
CRIS-Team Scopus Importer:2023-07-21
Keywords: Cerebral lesions; Neurosarcoidosis; Sarcoidosis; Voxel-based lesion symptom mapping

Cerebral lipogranuloma: A penetrating traumatic brain injury - Hagen, Manuel; Coras, Roland; Engelhorn, Tobias; Schwab, Stefan; Seifert, Frank (Neurology, 2020)
CRIS-Team Scopus Importer:2020-12-11

CEREBROSPINAL FLUID BIOMARKERS FOR CEREBRAL AMYLOID ANGIOPATHY - Sembill, Jochen; Lusse, C.; Linnerbauer, Mathias; Sprügel, Maximilian; Mrochen, Anne; Knott, Michael; Hölter, Philip; Engelhorn, Tobias; Schmidt, M.; Dörfler, Arnd; Oberstein, Timo; Maler, Juan Manuel; et al. (INTERNATIONAL JOURNAL OF STROKE, 2022)
CRIS-Team WoS Importer:2022-11-18

Cerebrospinal fluid biomarkers for cerebral amyloid angiopathy - Sembill, Jochen; Lusse, Christoph; Linnerbauer, Mathias; Sprügel, Maximilian; Mrochen, Anne; Knott, Michael; Engelhorn, Tobias; Schmidt, Manuel; Dörfler, Arnd; Oberstein, Timo; Maler, Juan Manuel; Kornhuber, Johannes; et al. (Brain Communications, 2023)
Integrating cerebrospinal fluid-biomarkers into diagnostic workup of patients with sporadic cerebral amyloid angiopathy may support early and correct identification. We aimed to identify and validate clinical- and cerebrospinal fluid-biomarkers for in vivo diagnosis of cerebral amyloid angiopathy. This observational cohort study screened 2795 consecutive patients admitted for cognitive complaints to the academic departments of neurology and psychiatry over a 10-year period (2009–2018). We included 372 patients with available hemosiderin-sensitive MR imaging and cerebrospinal fluid-based neurochemical dementia diagnostics, i.e. Aβ40, Aβ42, t-tau, p-tau. We investigated the association of clinical- and cerebrospinal fluid-biomarkers with the MRI-based diagnosis of cerebral amyloid angiopathy, applying confounder-adjusted modelling, receiver operating characteristic and unsupervised cluster analyses. We identified 67 patients with cerebral amyloid angiopathy, 76 patients with Alzheimer’s disease, 75 patients with mild cognitive impairment due to Alzheimer’s disease, 76 patients with mild cognitive impairment with unlikely Alzheimer’s disease and 78 healthy controls. Patients with cerebral amyloid angiopathy showed a specific cerebrospinal fluid pattern: average concentration of Aß40 [13 792 pg/ml (10 081–18 063)] was decreased compared to all controls (P < 0.05); Aß42 [634 pg/ml (492–834)] was comparable to Alzheimer’s disease and mild cognitive impairment due to Alzheimer’s disease (P = 0.10, P = 0.93) but decreased compared to mild cognitive impairment and healthy controls (both P < 0.001); p-tau [67.3 pg/ml (42.9–91.9)] and t-tau [468 pg/ml (275–698)] were decreased compared to Alzheimer’s disease (P < 0.001, P = 0.001) and mild cognitive impairment due to Alzheimer’s disease (P = 0.001, P = 0.07), but elevated compared to mild cognitive impairment and healthy controls (both P < 0.001). Multivariate modelling validated independent clinical association of cerebral amyloid angiopathy with older age [odds-ratio: 1.06, 95% confidence interval (1.02–1.10), P < 0.01], prior lobar intracerebral haemorrhage [14.00 (2.64–74.19), P < 0.01], prior ischaemic stroke [3.36 (1.58–7.11), P < 0.01], transient focal neurologic episodes (TFNEs) [4.19 (1.06–16.64), P = 0.04] and gait disturbance [2.82 (1.11–7.15), P = 0.03]. For cerebrospinal fluid-biomarkers per 1 pg/ml, both lower Aß40 [0.9999 (0.9998–1.0000), P < 0.01] and lower Aß42 levels [0.9989 (0.9980–0.9998), P = 0.01] provided an independent association with cerebral amyloid angiopathy controlled for all aforementioned clinical confounders. Both amyloid biomarkers showed good discrimination for diagnosis of cerebral amyloid angiopathy among adjusted receiver operating characteristic analyses (area under the receiver operating characteristic curves, Aß40: 0.80 (0.73–0.86), P < 0.001; Aß42: 0.81 (0.75–0.88), P < 0.001). Unsupervised Euclidian clustering of all cerebrospinal fluid-biomarker-profiles resulted in distinct segregation of cerebral amyloid angiopathy patients from all controls. Together, we demonstrate that a distinctive set of cerebrospinal fluid-biomarkers effectively differentiate cerebral amyloid angiopathy patients from patients with Alzheimer’s disease, mild cognitive impairment with or without underlying Alzheimer’s disease, and healthy controls. Integrating our findings into a multiparametric approach may facilitate diagnosing cerebral amyloid angiopathy, and may aid clinical decision-making, but warrants future prospective validation.
CRIS-Team Scopus Importer:2023-07-21
Keywords: biomarker; cerebral amyloid angiopathy; cerebrospinal fluid; dementia; small vessel disease

Cetuximab-Induced Aseptic Meningitis in a Patient with Colorectal Cancer: A Case Report and Review of Literature - Jäger, Jakob; Sprügel, Maximilian; Brunner, Tamara; Uhl, Martin; Schwab, Stefan; Vitali, Francesco; Wein, Axel; Volbers, Bastian (Case Reports in Neurology, 2022)
Cetuximab is a chimeric IgG1 monoclonal antibody against epidermal growth factor receptor. It is approved by the European medical agency for the treatment of RAS wild-type metastatic colorectal cancer and metastatic squamous cell cancer of the head and neck. Few cases of aseptic meningitis, primarily associated with the first administration of cetuximab in patients with squamous cell cancer, have been reported. So far, there was only 1 case in a patient with metastatic colorectal cancer. We report on a 50-year-old Caucasian patient with metastatic rectum carcinoma who suffered from headache, fever, and neck stiffness 3 h after the first administration of cetuximab (400 mg/m(2)). CSF examination revealed an excessive pleocytosis with a white blood cell count of 2,433/mu L. He was diagnosed with cetuximab-induced aseptic meningitis since clinical symptoms and CSF pleocytosis resolved within days, and further diagnostic workup revealed no infectious cause. Cetuximab-induced aseptic meningitis is a rare and severe drug reaction with predominance in treating squamous cell cancer of the head and neck. Clinical presentation and CSF findings suggest acute meningoencephalitis. In all reported cases, the course of the disease was benign and self-limited. Empiric antimicrobial and antiviral therapy are suggested until infectious causes can be ruled out. A lower dosage of cetuximab and a premedication including antihistamines and glucocorticosteroids may lower the risk of a re-occurrence if cetuximab therapy is continued.
CRIS-Team WoS Importer:2023-01-27

Characteristics in Non-Vitamin K Antagonist Oral Anticoagulant-Related Intracerebral Hemorrhage - Gerner, Stefan; Kuramatsu, Joji; Sembill, Jochen; Sprügel, Maximilian; Hagen, Manuel; Knappe, Ruben U.; Endres, Matthias; Haeusler, Karl Georg; Sobesky, Jan; Schurig, Johannes; Zweynert, Sarah; Bauer, Miriam; et al. (Stroke, 2019)
Background and Purpose Given inconclusive studies, it is debated whether clinical and imaging characteristics, as well as functional outcome, differ among patients with intracerebral hemorrhage (ICH) related to vitamin K antagonists (VKA) versus non-vitamin K antagonist (NOAC)-related ICH. Notably, clinical characteristics according to different NOAC agents and dosages are not established.
CRIS-Team WoS Importer:2019-06-18

Clinical and Imaging Characteristics in Noac-Related Intracerebral Hemorrhage. - Gerner, Stefan; Kuramatsu, Joji; Schwab, Stefan; Huttner, Hagen (STROKE, 2019)
CRIS-Team WoS Importer:2019-08-23

Clinical and radiological outcome after mechanical thrombectomy in acute ischemic stroke: What matters? - Kaschka, Iris; Kloska, Stephan; Struffert, Tobias; Engelhorn, Tobias; Gölitz, Philipp; Kurka, Natalia; Köhrmann, Martin; Schwab, Stefan; Dörfler, Arnd (Neuroradiology Journal, 2016)
Recent studies have shown the efficacy of mechanical thrombectomy in acute ischemic stroke. We sought to identify prognostic parameters for clinical and radiological outcome after mechanical thrombectomy.In 34 patients (age 72 ± 13 years, 64.7% women) with acute occlusion of the distal ICA and/or M1 segment who were treated with mechanical thrombectomy, the Spearman correlation was performed to assess potential prognostic outcome parameters (age, NIHSS, ASPECT, thrombus length (TL), clot burden score (CBS), relative filling time delay (rFTD), time to recanalization (TTR) and TICI score). The modified Rankin scale (mRS) and the Alberta Stroke Program Early CT (ASPECT) score were used for clinical and radiological outcome, respectively. Receiver operating characteristic (ROC) analysis was performed to assess parameters predicting favorable clinical (?mRS <= 2) and radiological outcome (?ASPECT <= 2).Variables associated with favorable clinical outcome included NIHSS, TL, TTR and TICI score (p <= 0.01) with NIHSS <= 15 (p = 0.001, area under the curve (AUC) 0.87), TL <= 2 cm (p = 0.017, AUC 0.75), TTR <= 231 min (p = 0.001 AUC 0.88) and TICI >= 2b (p = 0.050, AUC 0.70). Shorter TTR and higher TICI scores were associated with favorable radiological outcome (p < 0.001) with TTR <= 224 min (p = 0.023, AUC 0.77) and TICI >= 2b (p = 0.000, AUC 0.86).Fast and complete recanalization is essential to achieve a favorable radiological and functional outcome after mechanical thrombectomy in acute ischemic stroke. Age, CBS and collateral supply play a subordinate role.
EVALuna2:22544

Clinical/perfusion CT CBV mismatch as prognostic factor in intraarterial thrombectomy in acute anterior circulation stroke - Saake, Marc; Breuer, Lorenz; Gölitz, Philipp; Köhrmann, Martin; Schwab, Stefan; Dörfler, Arnd; Kloska, Stephan (Clinical Neurology and Neurosurgery, 2014)
Contradictory results were reported for the outcome after endovascular recanalization (ERT) in acute anterior circulation ischemic stroke. We assessed whether a clinical/perfusion CT cerebral blood volume (CBV) mismatch concept (CPM) can identify patients who will benefit from reperfusion therapy.Imaging and clinical data of 58 consecutive ERT cases with acute anterior circulation stroke (ICA, M1, proximal M2) undergoing intraarterial thrombectomy within 4.5h after symptom onset were analyzed retrospectively. CPM was defined as NIHSS>=8 and PCT CBV ASPECTS>=7. Minor CBV lesion was defined as PCT CBV ASPECTS>=7.All baseline characteristics other than blood glucose did not differ between the paired groups. Revascularization was achieved in 87.9% of all patients without significant difference between the paired groups. Favorable clinical outcome after 3 months (mRS<=2) resulted in 29.3% of all patients, in contrast to 47.4% of the CPM positive and 52.2% of the minor CBV lesion groups.CPM can identify patients who will benefit from reperfusion therapy in acute anterior circulation ischemic stroke.
EVALuna2:14386

Clinical/scientific notes - Möller, Sebastian; Hilz, Max-Josef; Blinzler, C.; Köhn, Julia; Dörfler, Arnd; Schwab, Stefan; Köhrmann, Martin (Neurology, 2012)
CRIS-Team Scopus Importer:2022-08-05

Clinical Studies Targeting Stroke and Ischemic Insults - Lundbye, Justin; Lyden, Patrick D.; Polderman, Kees H.; Schwab, Stefan (Therapeutic Hypothermia and Temperature Management, 2017)
EVALuna2:33131

Comparison of Two Automated Computed Tomography Perfusion Applications to Predict the Final Infarct Volume After Thrombolysis in Cerebral Infarction 3 Recanalization - Mühlen, Iris; Sprügel, Maximilian; Hölter, Philip; Hock, Stefan; Knott, Michael; Huttner, Hagen; Schwab, Stefan; Kallmünzer, Bernd; Dörfler, Arnd (Stroke, 2022)
Background: Several automated computed tomography perfusion software applications have been developed to provide support in the definition of ischemic core and penumbra in acute ischemic stroke. However, the degree of interchangeability between software packages is not yet clear. Our study aimed to evaluate 2 commonly used automated perfusion software applications (Syngo.via and RAPID) for the indication of ischemic core with respect to the follow-up infarct volume (FIV) after successful recanalization and with consideration of the clinical impact. Methods: Retrospectively, 154 patients with large vessel occlusion of the middle cerebral artery or the internal carotid artery, who underwent endovascular therapy with a consequent Thrombolysis in Cerebral Infarction 3 result within 2 hours after computed tomography perfusion, were included. Computed tomography perfusion core volumes were assessed with both software applications with different thresholds for relative cerebral blood flow (rCBF). The results were compared with the FIV on computed tomography within 24 to 36 hours after recanalization. Bland-Altman was applied to display the levels of agreement and to evaluate systematic differences. Results: Highest correlation between ischemic core volume and FIV without significant differences was found at a threshold of rCBF<38% for the RAPID software (r=0.89, P<0.001) and rCBF<25% for the Syngo software (r=0.87, P<0.001). Bland-Altman analysis revealed best agreement in these settings. In the vendor default settings (rCBF<30% for RAPID and rCBF<20% for Syngo) correlation between ischemic core volume and FIV was also high (RAPID: r=0.88, Syngo: r=0.86, P<0.001), but mean differences were significant (P<0.001). The risk of critical overestimation of the FIV was higher with rCBF<38% (RAPID) and rCBF<25% (Syngo) than in the default settings. Conclusions: By adjusting the rCBF thresholds, comparable results with reliable information on the FIV after complete recanalization can be obtained both with the RAPID and Syngo software. Keeping the software specific default settings means being more inclusive in patient selection, but forgo the highest possible accuracy in the estimation of the FIV.
CRIS-Team WoS Importer:2022-05-13

Compromised cardiovascular autonomic modulation in patient with acute ischemic stroke improves after three & six months - Wang, Ruihao; Macha, Kosmas; Köhn, Julia; Köhn, Julia; Siedler, Gabriela; Winder, Klemens; Gerner, Stefan; Schwab, Stefan; Koehrmann, M.; Kallmünzer, Bernd; Hilz, Max-Josef (EUROPEAN JOURNAL OF NEUROLOGY, 2021)
CRIS-Team WoS Importer:2021-07-23

Cooling in intracerebral hemorrhage (CINCH) trial: Protocol of a randomized German-Austrian clinical trial - Kollmar, Rainer; Juettler, Eric; Huttner, Hagen; Dörfler, Arnd; Staykov, Dimitre; Kallmünzer, Bernd; Schmutzhard, Erich; Schwab, Stefan; Broessner, Gregor (International Journal of Stroke, 2012)
Background: Intracerebral hemorrhage accounts for up to 15% of all strokes and is frequently associated with poor functional outcome and high mortality. So far, there is no clear evidence for a specific therapy, apart from general stroke unit or neurointensive care and management of secondary complications. Promising experimental and pilot clinical data support the use of therapeutic hypothermia after intracerebral hemorrhage. Aims: The study aims to determine if therapeutic hypothermia improves survival rates and reduces cerebral lesion volume after large intracerebral hemorrhage compared with conventional treatment. Material and methods: The Cooling in IntraCerebral Hemorrhage trial is a prospective, multicenter, interventional, randomized, parallel, two-arm (1:1) phase II trial with blinded end-point adjudication. Enrolment: 50 patients (age: 18 to 65 years) with large (25 to 64ml on cranial computertomography), primary intracerebral hemorrhage of the basal ganglia or thalamus within 6 to 18h after symptom onset are randomly allocated to therapeutic hypothermia for eight-days or conventional temperature management. In the therapeutic hypothermia group, a target temperature of 35·0°C is achieved by endovascular catheters and followed by slow controlled rewarming. Data analysis is based on the intent-to-treat population. The primary outcome measure of the study is the development in total lesion volume on cranial computertomography (intracerebral hemorrhage plus perihemorrhagic edema on day 8±0·5 and day 11±0·5 after intracerebral hemorrhage) and the mortality after 30 days. Secondary end-points are the in-hospital mortality, mortality, and functional outcome (modified Rankin Scale and Barthel-Index) after 90 and 180 days. Safety measures include any adverse events associated with therapeutic hypothermia. Discussion: In the face of a lack of evidence-based therapies for patients with large intracerebral hemorrhage, new promising approaches are desperately needed, but need evaluation in randomized controlled trials. Conclusion: The results of Cooling in IntraCerebral Hemorrhage trial are believed to directly influence future therapy of large intracerebral hemorrhage. © 2012 The Authors. International Journal of Stroke © 2012 World Stroke Organization.
CRIS-Team Scopus Importer:2022-08-05
Keywords: Edema; Hypothermia; Intracerebral hemorrhage; Neuroprotection; Stroke

Coregistrating magnetic source and magnetic resonance imaging for epilepsy surgery in focal cortical dysplasia - Kasper, Burkhard; Roessler, Karl; Hamer, Hajo; Dörfler, Arnd; Blümcke, Ingmar; Coras, Roland; Rösch, Julie; Mennecke, Angelika; Wellmer, Joerg; Sommer, Bjoern; Lorber, Bogdan; Lang, Johannes D.; et al. (NeuroImage: Clinical, 2018)
Background: Epilepsy surgery for focal cortical dysplasia type II (FCD II) offers good chances for seizure freedom, but remains a challenge with respect to lesion detection, defining the epileptogenic zone and the optimal resection strategy. Integrating results from magnetic source imaging from magnetoencephalography (MEG) with magnetic resonance imaging (MRI) including MRI postprocessing may be useful for optimizing these goals. Methods: We here present data from 21 adult FCD II patients, investigated during a 10 year period and evaluated including magnetic source imaging. 16 patients had epilepsy surgery, i.e. histopathologically verified FCD II, and a long follow up. We present our analysis of epileptogenic zones including MEG in relation to structural data according to MRI data and relate these results to surgical outcomes. Results: FCD II in our cohort was characterized by high MEG yield and localization accuracy and MEG showed impact on surgical success-rates. MEG source localizations were detected in 95.2% of patients and were as close as 12.3 ± 8,1 mm to the MRI-lesion. After a mean follow up of >3 years, we saw >80% Engel I outcomes, with more favourable outcomes when the MEG source was completely resected (Fishers exact test 0,033). Conclusion: We argue for a high value of conducting a combined MEG-MRI approach in the presurgical workup and the resection strategy in patients with FCD II related epilepsy.
EVALuna2:35523

Correction to: Expression of Inflammatory Mediators in Biofilm Samples and Clinical Association in Multiple Sclerosis Patients in Remission—A Pilot Study (Life, (2024), 14, 3, (367), 10.3390/life14030367) - Fehlhofer, Jakob Paul; Ries, Jutta; Nickel, Florian; Rothhammer, Veit; Schwab, Stefan; Kesting, Marco Rainer; Buchbender, Mayte (Life, 2024)
The reference 22 was deleted in the original publication [1]. With this correction, the order of some references has been adjusted accordingly. The authors state that the scientific conclusions are unaffected. This correction was approved by the Academic Editor. The original publication has also been updated.
CRIS-Team Scopus Importer:2024-09-06

Correction to: Neck cooling induces blood pressure increase and peripheral vasoconstriction in healthy persons (Neurological Sciences, (2020), 41, 9, (2521-2529), 10.1007/s10072-020-04349-x) - Köhn, Julia; Wang, Ruihao; de Rojas Leal, Carmen; Kallmünzer, Bernd; Winder, Klemens; Köhrmann, Martin; Kollmar, Rainer; Schwab, Stefan; Hilz, Max-Josef (Neurological Sciences, 2021)
The article “Neck cooling induces blood pressure increase and peripheral vasoconstriction in healthy persons”, written by Julia Koehn, Ruihao Wang, Carmen de Rojas Leal, Bernd Kallmünzer, Klemens Winder, Martin Köhrmann, Rainer Kollmar, Stefan Schwab and Max J. Hilz, was originally published Online First without Open Access. After publication in volume 41, issue 9, page 2521–2529 the authors decided to opt for Open Choice and to make the article an Open Access publication. Therefore, the copyright of the article has been changed to © The Author(s) 2020 and the article is forthwith distributed under the terms of the Creative Commons Attribution 4.0 International License, which permits use, sharing, adaptation, distribution and reproduction in any medium or format, as long as you give appropriate credit to the original author(s) and the source, provide a link to the Creative Commons licence, and indicate if changes were made. The images or other third party material in this article are included in the article’s Creative Commons licence, unless indicated otherwise in a credit line to the material. If material is not included in the article’s Creative Commons licence and your intended use is not permitted by statutory regulation or exceeds the permitted use, you will need to obtain permission directly from the copyright holder. To view a copy of this licence, visit http:// creat iveco mmons. org/ licen ses/ by/4.0. The original article has been corrected.
CRIS-Team Scopus Importer:2021-07-16

Correlation between clinical severity and extent of autonomic cardiovascular impairment in the acute phase of subarachnoid hemorrhage - Borutta, Matthias; Gerner, Stefan T.; Möser, Philip; Hölter, Philip; Engelhorn, Tobias; Dörfler, Arnd; Huttner, Hagen B.; Schwab, Stefan; Kuramatsu, Joji; Köhn, Julia (Journal of Neurology, 2022)
Background and aim: To assess associations between clinical severity and possible dysfunction of autonomic cardiovascular modulation within the acute phase after spontaneous subarachnoid hemorrhage (SAH). Methods: In this prospective observational study, in 51 patients with spontaneous SAH, Hunt-and-Hess scores (H&H) were assessed and cardiovascular autonomic modulation was monitored within 24 h after SAH-onset. From 5 min time-series of R–R-intervals (RRI) and blood-pressure (BP) recordings, we calculated autonomic parameters including time-domain [RRI-coefficient-of-variation (RRI-CV) and square-root-of-the-mean-squared-differences-of-successive-RRIs (RMSSD)] and frequency-domain parameters [low- and high-frequency-powers of RRI- and BP-modulation (RRI-LF-, RRI-HF-, SBP-LF-powers) and RRI-total-powers]. Data were compared to those of 20 healthy volunteers. Results: RRI- and BP-values did not differ between groups. Yet, parameters of sympathetic (RRI-LF-powers 141.0 (18.9–402.4) ms2 vs 442.3 (246.8–921.2) ms2, p = 0.001) and total autonomic modulation (RRI-CV 2.4 (1.2–3.7) ms2 vs 3.7 (3.1–5.3) ms2, p = 0.001) were significantly lower in patients than in controls. Subgroup analyses (patients with H&H < 3 vs H&H ≥ 3) and Spearman-rank-correlations revealed increasing loss of sympathetic (RRI-LF-powers 338.6 (179.7–710.4) ms2 vs 72.1 (10.1–175.9) ms2, p = 0.001, rho = − 0.524) and total autonomic modulation (RRI-CV 3.5 (2.3–5.4) ms2 vs 1.6 (1.0–2.8) ms2, p < 0.001, rho = − 0.519) with higher H&H-scores. Multiple-logistic-regression underlined the significant influence of H&H-scores on sympathetic (RRI-LF-powers, p = 0.033) and total autonomic modulation (RRI-CV, p = 0.040) compared to possible confounders (e.g., age, intubation). Conclusion: Within the acute phase, spontaneous SAH induces a decrease in sympathetic and total autonomic cardiovascular modulation. Higher H&H-scores were associated with increasing autonomic dysfunction and may therefore augment the risk of cardiovascular complications and poor clinical outcome.
CRIS-Team Scopus Importer:2022-08-05
Keywords: Autonomic nervous system; Heart rate variability; Hunt and Hess; Subarachnoid hemorrhage

Corrigendum: Feasibility and Diagnostic Accuracy of Ischemic Stroke Territory Recognition Based on Two-dimensional Projections of Three-dimensional Diffusion MRI Data - Wrosch, Jana Katharina; Volbers, Bastian; Gölitz, Philipp; Gilbert, Daniel; Schwab, Stefan; Dörfler, Arnd; Kornhuber, Johannes; Groemer, Teja Wolfgang (Frontiers in Neurology, 2017)
[This corrects the article on p. 239 in vol. 6, PMID: 26635717.].
EVALuna2:22534

Corticosteroids in patients with vestibular neuritis: An updated meta-analysis - Bogdanova, Anna; Dlugaiczyk, Julia; Heckmann, Josef Georg; Schwab, Stefan (Acta Neurologica Scandinavica, 2022)
Vestibular neuritis is a common neuro-otological entity. Therapeutically, corticosteroids are advised, although the evidence is limited. The objective of this review is to update meta-analyses of clinical trials that address the question of whether patients with vestibular neuritis treated with corticosteroids show better recovery than control patients. The electronic databases Medline, Scopus and Cochrane were searched for clinical trials for the years 1970-2020 without language restriction. Data were extracted, and outcome parameters were subjected to conventional and cumulative meta-analysis using a commercially available software program (). Finally, 15 trials with 363 participants in the treatment and 489 in the control groups were identified and could be included. Eight studies were judged to be at high risk of bias. The odds ratio (OR) for good outcome in the acute phase was 3.1 (95% CI 1.2-7.8; p = .015) in favour of steroid treatment leading to the number needed to treat (NNT) = 6 (95% CI 4-23). The odds ratio (OR) for restoration of vestibular function in the follow-up was 2.4 (95% CI 1.3-4.4; p = .004) for the benefit of steroid treatment resulting in a NNT = 7 (95% CI 5-18). The results of the cumulative statistics did not differ. The risk of adverse effects was higher in patients treated with steroids with an OR of 10.9 (95% CI 1.3-93.8; p = .015) and an estimated number needed to harm (NNH) = 4 (95% CI 3-19). The advantage for corticosteroids remained when differentiating between patients who participated in randomized or non-randomized clinical trials. Steroid treatment in vestibular neuritis resulted in a statistically significant benefit compared to control therapies. However, broad heterogeneity of the studies, mostly low-grade quality of studies, high risk of bias and broad confidence intervals put the findings into perspective allowing only a careful judgement of some benefit of corticosteroids. The findings, however, support the call for an adequately powered and well-designed randomized controlled trial to re-evaluate the effectiveness of corticosteroids.
CRIS-Team WoS Importer:2022-09-09

Dabigatran Plasma Levels in Acute Cerebrovascular Events - Volbers, Bastian; Köhrmann, Martin; Kallmünzer, Bernd; Kurka, Natalia; Breuer, Lorenz; Ringwald, Juergen; Schwab, Stefan (Journal of Stroke and Cerebrovascular Diseases, 2016)
Oral anticoagulation with dabigatran was shown to be effective for stroke prevention in patients with nonvalvular atrial fibrillation without the need for laboratory monitoring. However, a recent publication based on data of the Randomized Evaluation of Long-Term Anticoagulation Therapy study reported that ischemic stroke and bleeding outcomes are correlated with dabigatran plasma concentration (DPC). DPC was determined at a prespecified time point and correlated with cardiovascular events at any time during follow-up. Because of the known variability of DPC, among others depending on renal function, this approach might compromise data evaluation. We report on dabigatran plasma levels in acute cerebrovascular events.Consecutive patients with acute ischemic stroke (AIS) or intracerebral hemorrhage (ICH) while taking dabigatran were retrospectively identified if admission DPC was available. DPC was determined using the diluted thrombin time (Hemoclot (HYPHEN BioMed, Neuville sur Oise, France)). Creatinine clearance (CrCl) was determined by measuring creatinine in plasma and 24-hour urine.Fifteen AIS and 4 ICH patients were included. Median DPC on admission was significantly higher in ICH patients than in AIS patients (135 ng/mL [interquartile range IQR 79-218] and 69.1 ng/mL [IQR 20.6-85.0], respectively; P = .035). Increased CrCl (values above published normal range) was correlated with lower median DPC (60 ng/mL [IQR 10-69] versus 100 ng/mL [IQR 79-157] in patients with normal CrCl, P = .01).Higher DPC was found in ICH patients than in AIS patients in temporal proximity to the event. Both decreased and increased renal functions seem to have an important influence on DPC.
EVALuna2:15996

Demyelinating disease and anti-N-methyl-D-aspartate receptor immunoglobulin G antibodies: a case report - Waschbisch, Anne; Kallmünzer, Bernd; Schwab, Stefan; Gölitz, Philipp; Vincent, Angela; Lee, De Hyung; Linker, Ralf (BMC Research Notes, 2014)
Anti-N-methyl-D-aspartate receptor immunoglobulin G antibodies directed against the GluN1 subunit are considered highly specific for anti-N-methyl-D-aspartate receptor encephalitis, a severe clinical syndrome characterized by seizures, psychiatric symptoms, orofacial dyskinesia and autonomic dysfunction.Here we report a 33 year old Caucasian male patient with clinically definite multiple sclerosis who was found to be positive for anti-N-methyl-D-aspartate receptor antibodies. Rituximab therapy was initiated. On the 18 months follow-up visit the patient was found to be clinically stable, without typical signs of anti-N-methyl-D-aspartate receptor encephalitis.Our findings add to the growing evidence for a possible association between anti-N-methyl-D-aspartate receptor encephalitis and demyelinating diseases.
EVALuna2:22345

Dexamethasone in Patients with Spontaneous Intracerebral Hemorrhage: An Updated Meta-Analysis - Wintzer, Stephanie; Heckmann, Josef Georg; Huttner, Hagen; Schwab, Stefan (Cerebrovascular Diseases, 2020)
Background: Spontaneous intracerebral hemorrhage (ICH) is a frequent cerebrovascular disorder and still associated with high mortality and poor clinical outcomes. The purpose of this review was to update a 15-year-old former meta-Analysis on randomized clinical trials (RCTs) addressing the question of whether ICH patients treated with dexamethasone have better outcomes than controls. Methods: The electronic databases PubMed, SCOPUS, and Cochrane as well as web platforms on current clinical trials were searched for the years 1970-2020 without constriction on language. Data were extracted and outcomes were pooled for conventional and cumulative meta-Analysis using a commercial software program (www.Meta-Analysis.com). Results: Finally, 7 RCTs were identified and analyzed including 248 participants in the dexamethasone groups and 242 in the control groups. Five studies showed a high risk of bias. The overall relative risk (RR) for death was 1.32 (95% confidence interval [CI] 0.99-1.76; p = 0.06) and did not differ significantly between the 2 groups. After exclusion of studies with high risk of bias, the RR for death was 1.37 (95% CI 0.54-3.42; p = 0.51). The RR for poor outcome did not differ significantly between the 2 groups analyzed for all included studies (RR = 0.69; 95% CI 0.47-1; p = 0.05) and after exclusion of studies with high risk of bias (RR = 0.7; 95% CI 0.45-1.08; p = 0.11). The RR for complications did not differ significantly including all studies (RR = 1.29; 95% CI 0.77-2.17; p = 0.34) and after exclusion of studies with high risk of bias (RR = 1.27; 95% CI 0.18-8.89; p = 0.81). The cumulative statistics delivered no other results; however, it pointed out fewer complications over time in the dexamethasone group. Conclusion: Clear evidence of a beneficial or negative effect of dexamethasone is still lacking. Modern RCTs or observational studies with propensity design are necessary to evaluate the efficacy and safety of treatment with dexamethasone in patients with ICH.
CRIS-Team Scopus Importer:2020-10-02

Diagnostic value of prehospital ECG in acute stroke patients - Bobinger, Tobias; Kallmnzer, Bernd; Kopp, Markus; Kurka, Natalia; Heider, Stefan; Schwab, Stefan; Köhrmann, Martin; Arnold, Martin (Neurology, 2017)
To investigate the diagnostic yield of prehospital ECG monitoring provided by emergency medical services in the case of suspected stroke.Consecutive patients with acute stroke admitted to our tertiary stroke center via emergency medical services and with available prehospital ECG were prospectively included during a 12-month study period. We assessed prehospital ECG recordings and compared the results to regular 12-lead ECG on admission and after continuous ECG monitoring at the stroke unit.Overall, 259 patients with prehospital ECG recording were included in the study (90.3% ischemic stroke, 9.7% intracerebral hemorrhage). Atrial fibrillation (AF) was detected in 25.1% of patients, second-degree or greater atrioventricular block in 5.4%, significant ST-segment elevation in 5.0%, and ventricular ectopy in 9.7%. In 18 patients, a diagnosis of new-onset AF with direct clinical consequences for the evaluation and secondary prevention of stroke was established by the prehospital recordings. In 2 patients, the AF episodes were limited to the prehospital period and were not detected by ECG on admission or during subsequent monitoring at the stroke unit. Of 126 patients (48.6%) with relevant abnormalities in the prehospital ECG, 16.7% received medical antiarrhythmic therapy during transport to the hospital, and 6.4% were transferred to a cardiology unit within the first 24 hours in the hospital.In a selected cohort of patients with stroke, the in-field recordings of the ECG detected a relevant rate of cardiac arrhythmia. The results can add to the in-hospital evaluation and should be considered in prehospital care of acute stroke.
EVALuna2:22506

Diagnostik Lumbar Puncture - Step by Step - Siedler, Gabriela; Kallmünzer, Bernd; Schwab, Stefan (Deutsche Medizinische Wochenschrift, 2019)
Performing a diagnostic lumbar puncture is an essential clinical skill for the clinician. The procedure is of high importance for both, the emergency care for patients with suspected infection of the cerebral nervous system or subarachnoidal hemorrhage, as well as the elective diagnostic work up of chronic disease including multiple sclerosis and dementia. Furthermore the technique's principles are applied for spinal anesthesia or the intrathecal administration of drugs. This article describes a Standard Operating Procedure for the lumbar puncture step by step. Based on the latest evidence, it particularly focusses on clinically relevant questions and practical aspects.
EVALuna2:204469

Die Relevanz der neuen DIVI-Empfehlung zur Struktur und Ausstattung von Intensivstationen für die Neuromedizin - Waydhas, Christian; Hoffmann, Florian; van den Hooven, Thomas; Markewitz, Andreas; Riessen, Reimer; Schwab, Stefan; Unterberg, Andreas (Der Nervenarzt, 2023)
EVALuna2:536993

Direct Oral Anticoagulant Plasma Levels for the Management of Acute Ischemic Stroke - Marsch, Armin; Macha, Kosmas; Siedler, Gabriela; Breuer, Lorenz; Strasser, Erwin; Engelhorn, Tobias; Dörfler, Arnd; Schwab, Stefan; Kallmünzer, Bernd (Cerebrovascular Diseases, 2019)
Introduction: The management of acute ischemic stroke in patients on direct oral anticoagulants (DOACs) is challenging. However, the substance-specific plasma level could guide treatment decisions on recanalization therapies. We present a plasma-level-based protocol for emergency treatment of stroke patients on oral anticoagulants. Bleeding complications and clinical outcome for patients on DOACs are reported and compared to patients on vitamin K antagonists (VKAs). Methods: In patients with acute ischemic stroke and suspected use of DOACs within 48 h prior to hospital admission, plasma levels were measured using the calibrated Xa-activity (apixaban, edoxaban, rivaroxaban) or the Hemoclot®-assay (dabigatran). Levels <50 ng/mL were supportive for thrombolysis, while high values >100 ng/mL excluded patients from recombinant tissue plasminogen activator use. For patients on VKAs, the cutoff was set at international normalized ratio of 1.7. Endovascular thrombectomy of a large vessel occlusion was performed independently from coagulation testing. Consecutive patients were included in an observational registry. Results: Five hundred and twenty-two patients (261 on VKAs and 261 on DOACs) were included. Thirty patients (11.5%) on VKAs and 24 (9.2%) on DOACs received thrombolysis, followed by mechanical thrombectomy in 10 and 14 patients, respectively. Seventeen patients in each group received thrombectomy only. Symptomatic intracranial hemorrhage associated with thrombolysis occurred in 1 patient on VKA (3.3%) and 1 on DOAC (4.2%; p = 0.872). The turnaround time of specific assays did not show a significant delay in comparison to standard coagulation parameters. Conclusion: DOAC plasma levels could support decisions on emergency treatment of ischemic stroke. Systemic thrombolysis below suggested thresholds appears preliminary feasible and safe without an excess in bleeding complications.
CRIS-Team Scopus Importer:2019-09-24

Direct oral anticoagulants versus Vitamin K antagonists after a recent ischemic stroke or TIA- a pooled individual patient data analysis - Seiffge, David; Paciaroni, Maurizio; Wilson, Duncan; Koga, Masatoshi; Macha, Kosmas; Cappellari, Manuel; Schaedelin, Sabine; Shakeshaft, Clare; Takagi, Masahito; Tsivgoulis, Georgios; Bonetti, Bruno; Kallmünzer, Bernd; et al. (NEUROLOGY, 2019)
CRIS-Team WoS Importer:2019-08-02

Direct oral anticoagulants versus vitamin K antagonists after recent ischemic stroke in patients with atrial fibrillation - Seiffge, David J.; Paciaroni, Maurizio; Wilson, Duncan; Koga, Masatoshi; Macha, Kosmas; Cappellari, Manuel; Schaedelin, Sabine; Shakeshaft, Clare; Takagi, Masahito; Tsivgoulis, Georgios; Bonetti, Bruno; Kallmünzer, Bernd; et al. (Annals of Neurology, 2019)
Objective: We compared outcomes after treatment with direct oral anticoagulants (DOACs) and vitamin K antagonists (VKAs) in patients with atrial fibrillation (AF) and a recent cerebral ischemia. Methods: We conducted an individual patient data analysis of seven prospective cohort studies. We included patients with AF and a recent cerebral ischemia (<3 months before starting oral anticoagulation) and a minimum follow-up of 3 months. We analyzed the association between type of anticoagulation (DOAC versus VKA) with the composite primary endpoint (recurrent ischemic stroke [AIS], intracerebral hemorrhage [ICH], or mortality) using mixed-effects Cox proportional hazards regression models; we calculated adjusted hazard ratios (HRs) with 95% confidence intervals (95% CIs). Results: We included 4,912 patients (median age, 78 years [interquartile range IQR, 71–84]; 2,331 [47.5%] women; median National Institute of Health Stroke Severity Scale at onset, 5 [IQR, 2–12]); 2,256 (45.9%) patients received VKAs and 2,656 (54.1%) DOACs. Median time from index event to starting oral anticoagulation was 5 days (IQR, 2–14) for VKAs and 5 days (IQR, 2–11) for DOACs (p = 0.53). There were 262 acute ischemic strokes (AISs; 4.4%/year), 71 intracranial hemorrrhages (ICHs; 1.2%/year), and 439 deaths (7.4%/year) during the total follow-up of 5,970 patient-years. Compared to VKAs, DOAC treatment was associated with reduced risks of the composite endpoint (HR, 0.82; 95% CI, 0.67–1.00; p = 0.05) and ICH (HR, 0.42; 95% CI, 0.24–0.71; p < 0.01); we found no differences for the risk of recurrent AIS (HR, 0.91; 95% CI, 0.70–1.19; p = 0.5) and mortality (HR, 0.83; 95% CI, 0.68–1.03; p = 0.09). Interpretation: DOAC treatment commenced early after recent cerebral ischemia related to AF was associated with reduced risk of poor clinical outcomes compared to VKA, mainly attributed to lower risks of ICH. ANN NEUROL 2019.
CRIS-Team Scopus Importer:2019-05-17

Disability-Adjusted Life-Years Associated with Intracerebral Hemorrhage and Secondary Injury - Haupenthal, David; Kuramatsu, Joji; Volbers, Bastian; Sembill, Jochen; Mrochen, Anne; Balk, Stefanie; Hölter, Philip; Lücking, Hannes; Engelhorn, Tobias; Dörfler, Arnd; Schwab, Stefan; Huttner, Hagen; et al. (JAMA Network Open, 2021)
Importance: Intracerebral hemorrhage (ICH) contributes significantly to the global burden of disease. Objective: To examine the association of ICH and secondary injury with disability-adjusted life-years (DALYs) for the individual patient. Design, Setting, and Participants: This cohort study was conducted using data from the Universitätsklinikum Erlangen Cohort of Patients With Spontaneous Intracerebral Hemorrhage study. Consecutive patients admitted to a single tertiary care center from January 1, 2006, to December 31, 2015, were included. The sample comprised patients with oral anticoagulation-associated ICH (OAC-ICH) or primary spontaneous ICH (non-OAC-ICH). Statistical analysis was conducted from October 1 to December 31, 2020. Exposures: ICH occurrence and secondary injury. Main Outcomes and Measures: DALYs, years of life lost (YLL), and years lived with disability (YLD) were analyzed by hematoma location, ICH volume, and secondary injury (ie, hematoma expansion [HE], intraventricular hemorrhage [IVH], and perihemorrhagic edema [PHE]). Results: Among 1322 patients with ICH, 615 (46.5%) were women and the mean (SD) age at hospital admission was 71 (13) years; ICH was associated with a mean (SD) of 9.46 (8.08) DALYs, 5.72 (8.29) YLL, and 3.74 (5.95) YLD. There were statistically significant differences in mean (SD) DALYs by extent of hematoma volume (< 10 mL ICH: 7.05 [6.79] DALYs; 10-30 mL ICH: 9.91 [8.35] DALYs; >30 mL ICH: 12.42 [8.47] DALYs; P <.001) and ICH location (deep location: 10.60 [8.35] DALYs; lobar location: 8.18 [7.63] DALYs; cerebellum: 8.14 [6.80] DALYs; brainstem: 12.63 [9.21] DALYs; P <.001). Regarding population-level disease burden of secondary injuries after ICH, there was a statistically significant difference in mean (SD) by injury type, with 0.94 (3.19) DALYs for HE, 2.45 (4.16) DALYs for IVH, and 1.96 (2.66) DALYs for PHE (P <.001) among the entire ICH cohort. Regarding individual-level exposure to secondary injuries after ICH, there were a mean (SD) 7.14 (6.62) DALYs for HE, 4.58 (4.75) DALYs for IVH, and 3.35 (3.28) DALYs for PHE among patients with ICH affected by secondary injuries. Conclusions and Relevance: These findings suggest that there is a high burden of disability associated with ICH and secondary injuries, and the findings may guide public health strategies. The study findings further suggest that IVH and PHE may be relevant for the overall outcome of patients with ICH, that DALYs may represent a viable outcome parameter for studies to evaluate treatment outcomes in ICH research, and that IVH and PHE may represent potential treatment targets..
CRIS-Team Scopus Importer:2021-07-30

Disseminated Multifocal Intracerebral Bleeding Events in Three Coronavirus Disease 2019 Patients on Extracorporeal Membrane Oxygenation As Rescue Therapy. - Bihlmaier, Karl; Coras, Roland; Willam, Carsten; Grampp, Steffen; Jabari, Samir; Eichhorn, Philip; Haller, Florian; Kuramatsu, Joji; Schwab, Stefan; Castellanos, Ixchel; Birkholz, Torsten; Schüttler, Jürgen; et al. (Critical Care Explorations, 2020)
Objectives: To describe three coronavirus disease 2019 patients suffering from acute respiratory distress syndrome under venovenous extracorporeal membrane oxygenation therapy and tight anticoagulation monitoring presenting a novel pattern of multifocal brain hemorrhage in various degrees in all cerebral and cerebellar lobes. Design: Clinical observation of three patients. Post mortem examinations. Setting: Two ICUs at the University Hospital Erlangen. Patients: Three patients (medium age 56.6 yr, two male with hypertension and diabetes, one female with no medical history) developed severe acute respiratory distress syndrome on the basis of a severe acute respiratory syndrome coronavirus 2 infection. All required mechanical ventilation and venovenous extracorporeal membrane oxygenation support. Interventions: Clinical observation, CT, data extraction from electronic medical records, and post mortem examinations. Main Results: We report on an unusual multifocal bleeding pattern in the white matter in three cases with severe acute respiratory distress syndrome due to coronavirus disease 2019 undergoing venovenous extracorporeal membrane oxygenation therapy. Bleeding pattern with consecutive herniation was found in CT scans as well as in neuropathologic post mortem examinations. Frequency for this unusual brain hemorrhage in coronavirus disease 2019 patients with extracorporeal membrane oxygenation therapy at our hospital is currently 50%, whereas bleeding events in extracorporeal membrane oxygenation patients generally occur at 10-15%. Conclusions: Multifocality and high frequency of the unusual white matter hemorrhage pattern suggest a coherence to coronavirus disease 2019. Neuropathological analyses showed circumscribed thrombotic cerebrovascular occlusions, which eventually led to microvascular and later on macrovascular disseminated bleeding events. However, signs of cerebrovascular inflammation could not be detected. Polymerase chain reaction analyses of brain tissue or cerebrospinal fluid remained negative. Increased susceptibility for fatal bleeding events should be taken into consideration in terms of systemic anticoagulation strategies in coronavirus disease 2019.
EVALuna2:313697
Keywords: acute respiratory distress syndrome; cerebral microhemorrhage; coronavirus disease 2019; extracorporeal membrane oxygenation; intracerebral bleeding

Distinct Effects of Chronic Dopaminergic Stimulation on Hippocampal Neurogenesis and Striatal Doublecortin Expression in Adult Mice - Salvi, Rachele; Steigleder, Tobias; Schlachetzki, Johannes; Waldmann, Elisabeth; Schwab, Stefan; Winner, Beate; Winkler, Jürgen; Kohl, Zacharias (Frontiers in Neuroscience, 2016)
While adult neurogenesis is considered to be restricted to the hippocampal dentate gyrus (DG) and the subventricular zone (SVZ), recent studies in humans and rodents provide evidence for newly generated neurons in regions generally considered as non-neurogenic, e.g., the striatum. Stimulating dopaminergic neurotransmission has the potential to enhance adult neurogenesis in the SVZ and the DG most likely via D2/D3 dopamine (DA) receptors. Here, we investigated the effect of two distinct preferential D2/D3 DA agonists, Pramipexole (PPX), and Ropinirole (ROP), on adult neurogenesis in the hippocampus and striatum of adult naïve mice. To determine newly generated cells in the DG incorporating 5-bromo-2'-deoxyuridine (BrdU) a proliferation paradigm was performed in which two BrdU injections (100 mg/kg) were applied intraperitoneally within 12 h after a 14-days-DA agonist treatment. Interestingly, PPX, but not ROP significantly enhanced the proliferation in the DG by 42% compared to phosphate buffered saline (PBS)-injected control mice. To analyze the proportion of newly generated cells differentiating into mature neurons, we quantified cells co-expressing BrdU and Neuronal Nuclei (NeuN) 32 days after the last of five BrdU injections (50 mg/kg) applied at the beginning of 14-days DA agonist or PBS administration. Again, PPX only enhanced neurogenesis in the DG significantly compared to ROP- and PBS-injected mice. Moreover, we explored the pro-neurogenic effect of both DA agonists in the striatum by quantifying neuroblasts expressing doublecortin (DCX) in the entire striatum, as well as in the dorsal and ventral sub-regions separately. We observed a significantly higher number of DCX(+) neuroblasts in the dorsal compared to the ventral sub-region of the striatum in PPX-injected mice. These results suggest that the stimulation of hippocampal and dorsal striatal neurogenesis may be up-regulated by PPX. The increased generation of neural cells, both in constitutively active and quiescent neurogenic niches, might be related to the proportional higher D3 receptor affinity of PPX, non-dopaminergic effects of PPX, or altered motor behavior.
EVALuna2:5538

DIVI-Recommendations on the infrastruture of adult intensive care units - Waydhas, Christian; Riessen, Reimer; Markewitz, Andreas; Hoffmann, Florian; Frey, Lorenz; Boettiger, Bernd W.; Brenner, Sebastian; Brenner, Thorsten; Deffner, Teresa; Deininger, Matthias Manfred; Janssens, Uwe; Kluge, Stefan; et al. (Medizinische Klinik - Intensivmedizin und Notfallmedizin, 2023)
This document on the Structure and Equipment for Intensive Care Units of the German Association for Intensive and Emergency Care (DIVI) aims at providing guidance and recommendations for the requirements of (infra)structure, personal, and organization of intensive care units. The recommendations are based on a systematic literature search and a formal consensus process from a group of multi-disciplinary and multiprofessional specialists from the DIVI. The recommendations comprise a 3-staged level of intensive care units, a 3-staged level of care with respect to severity of illness, the staffing requirement of physicians, nurses, physiotherapists, pharmacists, psychologists, and other specialists. Furthermore, proposals concerning the equipment and the construction of ICUs are supplied.
CRIS-Team WoS Importer:2023-05-26

Doppler pulsatility index in spontaneous intracerebral hemorrhage - Kiphuth, Ines C.; Huttner, Hagen; Dörfler, Arnd; Schwab, Stefan; Köhrmann, Martin (European neurology, 2013)
Background and Purpose: Elevated intracranial pressure (ICP) as a result of intracerebral hemorrhage (ICH) and perihematomal edema often leads to tissue shift, which can be identified in cross-sectional imaging and presents a known predictor of functional outcome. Pulsatility indices (PIs) of the intracranial arteries as measured by transcranial Doppler sonography (TCD) may serve as surrogate parameters for ICP. This study aims to investigate whether PI correlates with ICP and midline shift and serves as a reliable predictor of functional outcome in patients with ICH. Methods: Within a 1-year period between April 2009 and April 2010, 136 patients with acute spontaneous, supratentorial ICH were admitted to our tertiary care hospital. One-hundred and twenty-four patients fulfilled the inclusion criteria and were eligible for analysis. TCD and transcranial duplex sonography were performed on admission and at least once more during hospital stay. Functional outcome was assessed 6 months after discharge. Correlation analyses, logistic regression analyses and receiver operating characteristic curves were calculated. Results: One-hundred and twenty-four patients were included in the analysis. Six-month mortality amounted to 39.5%. The ICH score and PIs of the middle cerebral artery were independent predictors of outcome 6 months after discharge. Conclusions: Early PI monitoring by TCD correlated with ICP and may be used to predict the outcome after 6 months. Copyright © 2013 S. Karger AG, Basel.
CRIS-Team Scopus Importer:2022-08-05
Keywords: Functional outcome; Intracerebral hemorrhage; Midline shift; Pulsatility index; Transcranial duplex sonography

Dressing Apraxia as Initial Manifestation of Creutzfeldt-Jakob Disease - Heckmann, Josef G.; Vachalova, Ivana; Vynogradova, Irina; Schwab, Stefan (Tremor and Other Hyperkinetic Movements, 2020)
Background: Creutzfeldt-Jakob disease (CJD) is a rare prion disease characterized by rapidly progressive dementia.
CRIS-Team WoS Importer:2020-07-24

Early Initiation of Anticoagulation with Direct Oral Anticoagulants in Patients after Transient Ischemic Attack or Ischemic Stroke - Macha, Kosmas; Volbers, Bastian; Bobinger, Tobias; Kurka, Natalia; Breuer, Lorenz; Huttner, Hagen; Schwab, Stefan; Köhrmann, Martin (Journal of Stroke and Cerebrovascular Diseases, 2016)
Direct oral anticoagulants (DOACs) are increasingly used for secondary prevention of cardioembolic stroke. While DOACs are associated with a long-term reduced risk of intracranial hemorrhage compared to vitamin K antagonists, pivotal trials avoided the very early period after stroke and few data exist on early initiation of DOAC therapy post stroke.We retrospectively analyzed data from our prospective database of all consecutive transient ischemic attack (TIA) or ischemic stroke patients with atrial fibrillation treated with DOACs during hospital stay. As per our institutional treatment algorithm for patients with cardioembolic ischemia DOACs are started immediately in TIA and minor stroke (group 1), within days 3-5 in patients with infarcts affecting one third or less of the middle cerebral artery, the anterior cerebral artery, or the posterior cerebral artery territories (group 2) as well as in infratentorial stroke (group 3) and after 1-2 weeks in patients with large infarcts (> 1/3 MCA territory, group 4). We investigated baseline characteristics, time to initiation of DOAC therapy after symptom onset, and hemorrhagic complications.In 243 included patients, administration of DOAC was initiated 40.5 hours (interquartile range [IQR] 23.0-65.5) after stroke onset in group 1 (n = 41) and after 76.7 hours (IQR 48.0-134.0), 108.4 hours (IQR 67.3-176.4), and 161.8 hours (IQR 153.9-593.8) in groups 2-4 (n = 170, 28, and 4), respectively. Two cases of asymptomatic intracranial hemorrhage (.8%) and 1 case of symptomatic intracranial hemorrhage (.4%) were observed, both in group 2.No severe safety issues were observed in early initiation of DOACs for secondary prevention after acute stroke in our in-patient cohort.
EVALuna2:22461

Economic burden of disease and mortality of intracranial haemorrhage under oral FXai: a German claims data analysis - Huttner, Hagen B.; Scherg, Felix; Kopke, Katarina; Schultze, Michael; Kossack, Nils; Gerner, Stefan T.; Kuramatsu, Joji; Schwab, Stefan (Neurological Research and Practice, 2025)
Background: Intracranial haemorrhage (ICH) is one of the most serious complications of anticoagulant therapy with oral factor Xa inhibitors (FXai). To meet an urgent medical need of optimising treatment pathways, we assessed the frequency of ICH during oral FXai treatment, as well as the associated burden on the German healthcare system. Methods: Our study was based on a claims database comprising over 4 million people with statutory health insurance in Germany. The study included people initiating oral FXai treatment for the first time between 2016 and 2021, and who experienced ICH during a three-year treatment period. For a balanced comparison of hospitalisations, costs, and mortality, propensity score matching between patients with and without ICH was performed. Results: During the study period, 78,086 patients had started oral FXai therapy, of which 530 experienced ICH during the therapy. The incidence rate of ICH was highest within the first 90 days after the start of oral FXai therapy during follow-up with 0.64 events per 100 patient-years (PY; 95% CI: 0.52–0.77%). Three-month mortality rates were significantly higher among patients who had experienced an ICH event (39.4%; 95% CI: 35.4–43.8%), as opposed to patients without ICH (5.9%; 95% CI: 4.2–8.3%). This difference prevailed during follow-up, while mortality increased at roughly equal rates in both patient groups. Patients with ICH were on average hospitalised for 40.4 days/PY (95% CI: 35.7 days – 45.2 days) in the first year after the event; comparable patients without ICH were hospitalised for 10.8 days/PY (95% CI: 8.3 days – 13.2 days). Annual total costs per patient were €37,328 (95% CI: €32,243–€42,412) for patients with ICH, and €10,564 (95% CI: €9,298–€11,831) for patients without ICH. Hospitalisation costs were the main driver with 86.1% versus 50.8%, respectively. Conclusions: Incidence rates of ICH during oral FXai therapy were within the range of other published real-world data. Duration of hospitalisations, associated costs, and mortality were high and significantly higher for patients with ICH than for comparable patients without ICH. The high burden on the healthcare system highlights the need for preventive measures and more efficient treatment pathways for patients with ICH under oral FXai therapy.
CRIS-Team Scopus Importer:2025-04-11
Keywords: Anticoagulation; Direct oral anticoagulant; DOAC; ICH; Intracranial haemorrhage; Oral factor Xa inhibitor; Oral FXai

Effectiveness of Lumbar Cerebrospinal Fluid Drain Among Patients With Aneurysmal Subarachnoid Hemorrhage: A Randomized Clinical Trial. - Wolf, Stefan; Mielke, Dorothee; Barner, Christoph; Malinova, Vesna; Kerz, Thomas; Wostrack, Maria; Czorlich, Patrick; Salih, Farid; Engel, Doortje C.; Ehlert, Angelika; Staykov, Dimitre; Alturki, Abdulrahman Y.; et al. (JAMA Neurology, 2023)
IMPORTANCE: After aneurysmal subarachnoid hemorrhage, the use of lumbar drains has been suggested to decrease the incidence of delayed cerebral ischemia and improve long-term outcome. OBJECTIVE: To determine the effectiveness of early lumbar cerebrospinal fluid drainage added to standard of care in patients after aneurysmal subarachnoid hemorrhage. DESIGN, SETTING, AND PARTICIPANTS: The EARLYDRAIN trial was a pragmatic, multicenter, parallel-group, open-label randomized clinical trial with blinded end point evaluation conducted at 19 centers in Germany, Switzerland, and Canada. The first patient entered January 31, 2011, and the last on January 24, 2016, after 307 randomizations. Follow-up was completed July 2016. Query and retrieval of data on missing items in the case report forms was completed in September 2020. A total of 20 randomizations were invalid, the main reason being lack of informed consent. No participants meeting all inclusion and exclusion criteria were excluded from the intention-to-treat analysis. Exclusion of patients was only performed in per-protocol sensitivity analysis. A total of 287 adult patients with acute aneurysmal subarachnoid hemorrhage of all clinical grades were analyzable. Aneurysm treatment with clipping or coiling was performed within 48 hours. INTERVENTION: A total of 144 patients were randomized to receive an additional lumbar drain after aneurysm treatment and 143 patients to standard of care only. Early lumbar drainage with 5 mL per hour was started within 72 hours of the subarachnoid hemorrhage. MAIN OUTCOMES AND MEASURES: Primary outcome was the rate of unfavorable outcome, defined as modified Rankin Scale score of 3 to 6 (range, 0 to 6), obtained by masked assessors 6 months after hemorrhage. RESULTS: Of 287 included patients, 197 (68.6%) were female, and the median (IQR) age was 55 (48-63) years. Lumbar drainage started at a median (IQR) of day 2 (1-2) after aneurysmal subarachnoid hemorrhage. At 6 months, 47 patients (32.6%) in the lumbar drain group and 64 patients (44.8%) in the standard of care group had an unfavorable neurological outcome (risk ratio, 0.73; 95% CI, 0.52 to 0.98; absolute risk difference, -0.12; 95% CI, -0.23 to -0.01; P = .04). Patients treated with a lumbar drain had fewer secondary infarctions at discharge (41 patients [28.5%] vs 57 patients [39.9%]; risk ratio, 0.71; 95% CI, 0.49 to 0.99; absolute risk difference, -0.11; 95% CI, -0.22 to 0; P = .04). CONCLUSION AND RELEVANCE: In this trial, prophylactic lumbar drainage after aneurysmal subarachnoid hemorrhage lessened the burden of secondary infarction and decreased the rate of unfavorable outcome at 6 months. These findings support the use of lumbar drains after aneurysmal subarachnoid hemorrhage. TRIAL REGISTRATION: ClinicalTrials.gov Identifier: NCT01258257.
EVALuna2:536995

Effects of a 4-Step Standard Operating Procedure for the Treatment of Fever in Patients With Acute Stroke - Lee, Hanna; Hedtmann, Günter; Schwab, Stefan; Kollmar, Rainer (Frontiers in Neurology, 2021)
Background and Purpose: Fever in the acute phase of stroke leads to an unfavorable clinical outcome and increased mortality. However, no specific form of effective fever treatment has been established, so far. We analyzed the effectiveness of our in-house standard operating procedure (SOP) of fever treatment. Methods: This SOP was analyzed for a period of 33 weeks. Patients with cerebral ischemia (ischemic stroke, transient ischemic attack) or cerebral hemorrhage (intracerebral, subarachnoid) and body temperature elevation of ≥ 37.5°C within the first 6 days after admission were eligible for inclusion in the analysis. The results of SOP group, who's data have been collected prospectively were then compared with a historical control group that had been treated conventionally 1 year earlier in the same period. The data of control group have been collected in retrospect. The primary endpoint was the total duration of the fever for the first 6 days after admission to the stroke unit. Results: A total of 130 patients (mean age of 78 ± 12) received 370 antipyretic interventions. Sequential application of paracetamol (n = 245), metamizole (n = 53) and calf compress (n = 15) led to significant reduction in body temperature. In patients who did not respond to these applications, normothermia could be achieved after infusion of the cooled saline solution. Normothermia could be achieved within 120 min in more than 90% of the cases treated by the SOP. The SOP reduced the fever duration in the 6 days significantly, from 12.2 ± 2.7 h [95% confidence interval (CI) for mean] in the control group to 3.9 ± 1.0 h (95% CI) in the SOP group (p < 0.001). The SOP was rated to be reasonable and effective. Conclusion: Our in-house SOP is cost-efficient and effective for fever treatment in stroke patients, that can be implemented by local health care professionals.
CRIS-Team Scopus Importer:2021-04-02
Keywords: acute stroke; fever; fever treatment; hyperthermia; standard operating procedure

Efficacy and safety of combined intraventricular fibrinolysis with lumbar drainage for prevention of permanent shunt dependency after intracerebral hemorrhage with severe ventricular involvement: A randomized trial and individual patient data meta-analysi - Staykov, Dimitre; Kuramatsu, Joji; Bardutzky, Juergen; Volbers, Bastian; Gerner, Stefan; Kloska, Stephan; Dörfler, Arnd; Schwab, Stefan; Huttner, Hagen (Annals of Neurology, 2017)
Intraventricular hemorrhage (IVH) is a negative prognostic factor in intracerebral hemorrhage (ICH) and is associated with permanent shunt dependency in a substantial proportion of patients post-ICH. IVH treatment by intraventricular fibrinolysis (IVF) was recently linked to reduced mortality rates in the CLEAR III study and IVF represents a safe and effective strategy to hasten clot resolution that may reduce shunt rates. Additionally, promising results from observational studies reported reductions in shunt dependency for a combined treatment approach of IVF plus lumbar drains (LDs). The present randomized, controlled trial investigated efficacy and safety of a combined strategy-IVF plus LD versus IVF alone-on shunt dependency in patients with ICH and severe IVH.This randomized, open-label, parallel-group study included patients aged 18 to 85 years, prehospital modified Rankin Scale <=3, ICH volume < 60ml, Glasgow Coma Scale of <9, and severe IVH with tamponade of the third and fourth ventricles requiring placement of external ventricular drainage (EVD). Over a 3-year recruitment period, patients were allocated to either standard treatment (control group receiving IVF consisting of 1mg of recombinant human tissue plasminogen activator every 8 hours until clot clearance of third and fourth ventricles) or a combined treatment approach of IVF and-upon clot clearance of third and fourth ventricles-subsequent placement of an LD for drainage of cerebrospinal fluid (CSF; intervention group). The primary endpoint consisted of permanent shunt placement indicated after a total of three unsuccessful EVD clamping attempts or need for CSF drainage longer than 14 days in both groups. Secondary endpoints included IVF- and LD-related safety, such as bleeding or infections, and functional outcome at 90 and 180 days. Conducted endpoint analyses used individual patient data meta-analyses. The study was registered at clinicaltrials.gov (NCT01041950).The trial was stopped upon predefined interim analysis after 30 patients because of significant efficacy of tested intervention. The primary endpoint was analyzed without dropouts and was reached in 43% (7 of 16) of the control group versus 0% (0 of 14) of the intervention group (p = 0.007). Meta-analyses were based on overall 97 patients, 45 patients receiving IVF plus LD versus 42 with IVF only. Meta-analyses on shunt dependency showed an absolute risk reduction of 24% for the intervention (LD, 2.2% [1 of 45] vs no-LD, 26.2% [11 of 42]; odds ratio [OR] = 0.062; confidence interval [CI], 0.011-0.361; p = 0.002). Secondary endpoints did not show significant differences for CSF infections (OR = 0.869;CI, 0.445-1.695; p = 0.680) and functional outcome at 90 days (OR = 0.478; CI, 0.190-1.201; p = 0.116), yet bleeding complications were significantly reduced in favor of the intervention (OR = 0.401; CI, 0.302-0.532; p < 0.001).The present trial and individual patient data meta-analyses provide evidence that, in patients with severe IVH, as compared to IVF alone, a combined approach of IVF plus LD treatment is feasible and safe and significantly reduces rates of permanent shunt dependency for aresorptive hydrocephalus post-ICH. ANN NEUROL 2017;81:93-103.
EVALuna2:22478

Endogenous endophthalmitis complicating Streptococcus equi subspecies zooepidemicus meningitis: a case report - Madžar, Dominik; Hagge, Mareike; Möller, Sebastian; Regensburger, Martin; Lee, De Hyung; Schwab, Stefan; Jantsch, Jonathan (BMC Research Notes, 2015)
Streptococcus equi subspecies zooepidemicus (Streptococcus zooepidemicus) is a rare cause of meningitis in humans. Humans mainly get infected by contact with an animal source or by ingestion of unpasteurized dairy products. In rare cases, bacterial meningitis can be complicated by endogenous endophthalmitis which is frequently associated with a poor visual prognosis.A 73 year old male Caucasian patient presented with clinical signs indicative of bacterial meningitis. Blood and cerebrospinal fluid cultures yielded beta-hemolytic, catalase-negative cocci. The strain was identified as Streptococcus zooepidemicus. The patient was likely infected by contact with a sick horse. Under antibiotic treatment, his general condition improved rapidly. Early after hospital admission, however, he began seeing a black spot in his left eye's central visual field. An ophthalmological examination revealed signs of endogenous endophthalmitis and so the patient underwent vitrectomy. Despite treatment, the visual acuity of his left eye remained severely impaired. He showed no further neurological deficits at hospital discharge.Meningitis caused by Streptococcus zooepidemicus is rare with only 27 previously published adult cases in the literature. Of note, this report constitutes the third description of endogenous endophthalmitis associated with Streptococcus zooepidemicus meningitis. Thus, endogenous endophthalmitis may represent a comparatively common complication of meningitis caused by this microorganism.
EVALuna2:22366

Endovascular treatment in patients with large vessel occlusion: reduced mortality despite minimal penumbra - Schmidt, Manuel; Breuer, Lorenz; Kallmünzer, Bernd; Schwab, Stefan; Dörfler, Arnd; Engelhorn, Tobias; Hölter, Philip (Neuroradiology, 2019)
Purpose: In patients with acute ischemic stroke (AIS) caused by large vessel occlusion (LVO), endovascular treatment (EVT) is highly effective for emergency revascularization. However, data on functional outcome are lacking for patients, which show no or minimal mismatch between ischemic core and penumbra. Methods: Forty-five patients with AIS due to LVO of the anterior circulation were retrospectively analyzed within 6 h since onset when administered to our department. In all patients, there was no relevant penumbra according to CT perfusion (CTP). Functional outcome, defined by the modified Rankin Scale (mRS) at 30 and 90 days, was analyzed according to LVO treatment (EVT versus non-EVT). Confounding was addressed by multivariable regression analyses. Results: mRS values at 30 days (p = 0.002) and 90 days (p = 0.005) after AIS occurrence were significantly lower in patients who had received EVT. There was no significant difference regarding good functional outcome, as measured by mRS of 0–2 at 30 (p = 0.432) and 90 days, respectively (p = 0.186). Mortality was significantly reduced in patients undergoing EVT at 30-day (p < 0.001) and at 90-day follow-up (p = 0.003), respectively. Multivariable regression analyses revealed that EVT was associated with reduced mortality at 30 (OR 0.091; CI (0.013–0.612); p = 0.014) and 90 days (OR 0.134; CI (0.021–0.857); p = 0.034) after AIS. Conclusions: Despite a small and highly selected patient collective, our study indicates that AIS patients with minimal penumbra in CTP might benefit from EVT in terms of reduced mortality at 30 and 90 days after AIS. However, in this group of patients, we could not prove favorable functional outcome at 30 and 90 days, despite receiving EVT.
CRIS-Team Scopus Importer:2019-09-17
Keywords: CTP; Endovascular treatment; Mortality; Penumbra; Stroke

Endovascular treatment of large vessel occlusion acute ischemic stroke: Is there a place for hypothermia? - Macha, Kosmas; Schwab, Stefan (European Journal of Neurology, 2021)
CRIS-Team WoS Importer:2021-06-25

Erectile dysfunction (ED) after ischemic stroke: association between prevalence and site of lesion - Koehn, Julia; Crodel, Carl; Deutsch, Martina; Kolominsky-Rabas, Peter; Hoesl, Katharina M.; Köhrmann, Martin; Schwab, Stefan; Hilz, Max-Josef (Clinical Autonomic Research, 2015)
Stroke may cause or worsen erectile dysfunction (ED). Post-stroke ED prevalence and association with stroke location are not well established. Therefore, we assessed post-stroke ED prevalence in relation to ischemic lesion locations and stroke severity.In 57 men (62.6 ± 10.5 years) who had ischemic stroke within 24 months prior to evaluation, we used the five-item International Index of Erectile Function questionnaire (IIEF5) to evaluate ED prevalence after stroke and retrospectively 3 months prior to stroke. IIEF5 scores range from 5 to 25; scores below 22 indicate ED. We estimated stroke severity upon hospital admission, using the National Institute of Health Stroke Scale (NIHSS), and determined stroke location from cranial computed tomography or magnetic resonance imaging. We compared pre- and post-stroke results with those of 22 control persons (61.7 ± 11.2 years), calculated correlations between IIEF5 scores and NIHSS scores, and compared ED prevalence with stroke locations (significance: p < 0.05).ED was reported by 45/57 patients after stroke, 26/57 patients before stroke, and 6/22 control persons. Patients' IIEF5 values were significantly lower [median 16 interquartile range (IQR) 3.5-20.5] after than before stroke (median 23, IQR 19.0-24.0) and lower than in controls (median 24, IQR 19.8-25.0). Pre- and post-stroke IIEF5 scores did not correlate with the patients' NIHSS scores at stroke onset (p > 0.05). ED was associated with middle cerebral artery infarction in 27/34, posterior cerebral artery infarction in 4/5, anterior cerebral artery infarction in 1/1, basal ganglia infarction in 3/3, brain stem infarction in 8/10, cerebellar infarction in 2/5, and lesions in more than one region in 1/1 patients.Disruption of the central network assuring erection might contribute to increased ED severity and prevalence after stroke. Anti-erectile effects of functional and psychological impairment or medication added after stroke may also contribute to ED but must be evaluated in larger patients groups.
EVALuna2:22368

Erratum to 'Clinical/perfusion CT CBV mismatch as prognostic factor in intraarterial thrombectomy in acute anterior circulation stroke' (Clinical Neurology and Neurosurgery (2014) 121, (39-45)) - Saake, Marc; Breuer, Lorenz; Gölitz, Philipp; Köhrmann, Martin; Schwab, Stefan; Dörfler, Arnd; Kloska, Stephan (Clinical Neurology and Neurosurgery, 2014)
CRIS-Team Scopus Importer:2022-08-05

EuroHYP-1: European multicenter, randomized, phase III clinical trial of therapeutic hypothermia plus best medical treatment vs. best medical treatment alone for acute ischemic stroke - Van Der Worp, H. Bart; Macleod, Malcolm R.; Bath, Philip M. W.; Demotes, Jacques; Durand-Zaleski, Isabelle; Gebhardt, Bernd; Gluud, Christian; Kollmar, Rainer; Krieger, Derk W.; Lees, Kennedy R.; Molina, Carlos; Montaner, Joan; et al. (International Journal of Stroke, 2014)
Cooling reduced infarct size and improved neurological outcomes in animal studies modeling ischemic stroke, and also improved outcome in randomized clinical trials in patients with hypoxic-ischemic brain injury after cardiac arrest. Cooling awake patients with ischemic stroke has been shown feasible in phase II clinical trials.To determine whether systemic cooling to a target body temperature between 34·0 and 35·0°C, started within six-hours of symptom onset and maintained for 24 h, improves functional outcome at three-months in patients with acute ischemic stroke.International, multicenter, phase III, randomized, open-label clinical trial with blinded outcome assessment in 1500 patients aged 18 years or older with acute ischemic stroke and a National Institutes of Health Stroke Scale score of 6 up to and including 18. In patients randomized to hypothermia, cooling to a target body temperature of 34-35°C will be started within six-hours after symptom onset with rapid intravenous infusion of refrigerated normal saline or a surface cooling technique and maintained for 24 h with a surface or endovascular technique. Patients randomized to hypothermia will receive pethidine and buspirone to prevent shivering and discomfort.Score on the modified Rankin Scale at 91 days, as analyzed with ordinal logistic regression and expressed as a common odds ratio.With 750 patients per intervention group, this trial has 90% power to detect 7% absolute improvement at the 5% significance level. The full trial protocol is available at http://www.eurohyp1.eu. ClinicalTrials.gov Identifier: NCT01833312.
EVALuna2:22308

EUROHYP-1: EUROPEAN, MULTICENTRE, RANDOMISED, PHASE III CLINICAL TRIAL OF THERAPEUTIC HYPOTHERMIA PLUS BEST MEDICAL TREATMENT VS BEST MEDICAL TREATMENT ALONE FOR ACUTE ISCHAEMIC STROKE - Petersson, J.; Van Der Worp, H. B.; Macleod, M. R.; Kollmar, R.; Krieger, D. W.; Staykov, D.; Szabo, I.; Kallmünzer, Bernd; Schwab, Stefan (2018)
EVALuna2:36384

European Cooperative Acute Stroke Study-4: Extending the time for thrombolysis in emergency neurological deficits ECASS-4: ExTEND - Amiri, Hemasse; Bluhmki, Erich; Bendszus, Martin; Eschenfelder, Christoph C.; Donnan, Geoffrey A.; Leys, Didier; Molina, Carlos; Ringleb, Peter A.; Schellinger, Peter D.; Schwab, Stefan; Toni, Danilo; Wahlgren, Nils; et al. (International Journal of Stroke, 2016)
Thrombolytic therapy with recombinant tissue plasminogen activator (rt-PA) is an effective and approved therapy for acute ischemic stroke within 4.5 h of onset except for USA, Canada, Croatia, and Moldovia with a current 3 h label. We hypothesized that ischemic stroke patients selected with significant penumbral mismatch on magnetic resonance imaging (MRI) at 4.5-9 h after onset of stroke will have improved clinical outcomes when given intravenous rt-PA (alteplase) compared to placebo.ECASS-4: ExTEND is an investigator driven, phase 3, randomized, multi-center, double-blind, placebo-controlled study. Ischemic stroke patients presenting within 4.5 and 9 h of stroke onset, who fulfil clinical requirements (National Institutes of Health Stroke Score (NIHSS) 4-26 and pre-stroke modified Rankin Scale (mRS) 0-1) will undergo MRI. Patients who meet imaging criteria (infarct core volume <100 ml, perfusion lesion: infarct core mismatch ratio >1.2 and perfusion lesion minimum volume of 20 ml) additionally will be randomized to either rt-PA or placebo.The primary outcome measure will be the categorical shift in the mRS at day 90. Clinical secondary outcomes will be disability at day 90 dichotomized as favorable outcome mRS 0-1 at day 90. Tertiary endpoints include reduction in the NIHSS by 11 or more points or reaching 0-1 at day 90, reperfusion and recanalization at 24 h post stroke as well as depression, life quality, and cognitive impairment at day 90. Safety endpoints will include symptomatic intracranial hemorrhage (ICH) and death.
EVALuna2:22431

Evaluation of Functional Recovery Following Thrombectomy in Patients With Large Vessel Occlusion and Prestroke Disability - Sprügel, Maximilian; Sembill, Jochen; Kremer, Svenja; Gerner, Stefan; Knott, Michael; Hock, Stefan; Engelhorn, Tobias; Dörfler, Arnd; Huttner, Hagen; Schwab, Stefan (JAMA Network Open, 2022)
IMPORTANCE It is uncertain whether thrombectomy is associated with benefits in patients with prestroke disability.
CRIS-Team WoS Importer:2022-09-02

Evaluation of simplified wireless EEG recordings in the neurological emergency room - Welte, Tamara; Janner, Felix; Lindner, Sara; Gollwitzer, Stephanie; Stritzelberger, Jenny; Lang, Johannes; Reindl, Caroline; Sprügel, Maximilian; Olmes, David; Schwab, Stefan; Blinzler, Christian; Hamer, Hajo (PLoS ONE, 2024)
Objective In the neurological emergency room (nER), timely electroencephalography (EEG) diagnostic is often crucial in patients with altered state of consciousness as well as in patients presenting with a first seizure. Yet, routine-EEG (rEEG) is often not available, especially during off-hours. Methods We analyzed the value of a commercially available, simplified wireless eight-channel EEG recording (swEEG, CerebAir® EEG headset, Nihon Kohden), applied by non-EEG-specialized medical students, in patients presenting in our nER with (suspicion of) epileptic seizures and/or loss of or altered state of consciousness between 08/2019 and 08/2022. We evaluated the feasibility and validity compared to a standard rEEG (21 electrodes according to the international 10/20 system) and also included the clinical follow-up of the patients. Results 100 patients were included in our analysis (mean age 57.6 ± 20.4 years; 61 male). Median time of electrode application was 7 minutes (range 4–20 minutes), with significantly longer duration in patients with altered level of consciousness (median 8 minutes, p = 0.035). Electrode impedances also differed according to state of consciousness (p = 0.032), and were higher in females (p<0.001). 55 patients received additional rEEG, either during their acute nER stay (25) and/or during the next days (38). Considering normal EEG findings vs. pathological slowing vs. epileptiform activity, swEEG matched first rEEG results in 48/55 cases (87.3%). Overall, swEEG detected the same or additional pathological EEG patterns in 52/ 55 cases (94.5%). In 7/75 patients (9.3%) who did not receive rEEG, or had their rEEG scheduled to a later time point during their hospital stay, swEEG revealed important additional pathological findings (e.g. status epilepticus, interictal epileptiform discharges), which would have triggered acute therapeutic consequences or led to further diagnostics and investigations. Conclusion The introduced swEEG represents a practicable, valuable technique to be quickly applied by non-EEG-specialized ER staff to initiate timely diagnostic and guide further investigations and treatment in the nER. Moreover, it may help to avoid under-diagnostic with potentially harmful consequences caused by skipped or postponed regular 10/20 EEG examinations, and ultimately improve the outcome of patients.
CRIS-Team Scopus Importer:2024-11-15

Evidence-based guidelines for the management of large hemispheric infarction : a statement for health care professionals from the Neurocritical Care Society and the German Society for Neuro-intensive Care and Emergency Medicine - Torbey, Michel T.; Boesel, Julian; Rhoney, Denise H.; Rincon, Fred; Staykov, Dimitre; Amar, Arun P.; Varelas, Panayiotis N.; Juettler, Eric; Olson, Daiwai; Huttner, Hagen; Zweckberger, Klaus; Sheth, Kevin N.; et al. (Neurocritical Care, 2015)
Large hemispheric infarction (LHI), also known as malignant middle cerebral infarction, is a devastating disease associated with significant disability and mortality. Clinicians and family members are often faced with a paucity of high quality clinical data as they attempt to determine the most appropriate course of treatment for patients with LHI, and current stroke guidelines do not provide a detailed approach regarding the day-to-day management of these complicated patients. To address this need, the Neurocritical Care Society organized an international multidisciplinary consensus conference on the critical care management of LHI. Experts from neurocritical care, neurosurgery, neurology, interventional neuroradiology, and neuroanesthesiology from Europe and North America were recruited based on their publications and expertise. The panel devised a series of clinical questions related to LHI, and assessed the quality of data related to these questions using the Grading of Recommendation Assessment, Development and Evaluation guideline system. They then developed recommendations (denoted as strong or weak) based on the quality of the evidence, as well as the balance of benefits and harms of the studied interventions, the values and preferences of patients, and resource considerations.
EVALuna2:22397

Evidence for postnatal neurogenesis in the human amygdala - Röder, Sebastian; Burkardt, Petra; Rost, Fabian; Rode, Julian; Brusch, Lutz; Coras, Roland; Englund, Elisabet; Håkansson, Karl; Possnert, Göran; Salehpour, Mehran; Primetzhofer, Daniel; Csiba, László; et al. (Communications Biology, 2022)
The human amygdala is involved in processing of memory, decision-making, and emotional responses. Previous studies suggested that the amygdala may represent a neurogenic niche in mammals. By combining two distinct methodological approaches, lipofuscin quantification and 14C-based retrospective birth dating of neurons, along with mathematical modelling, we here explored whether postnatal neurogenesis exists in the human amygdala. We investigated post-mortem samples of twelve neurologically healthy subjects. The average rate of lipofuscin-negative neurons was 3.4%, representing a substantial proportion of cells substantially younger than the individual. Mass spectrometry analysis of genomic 14C-concentrations in amygdala neurons compared with atmospheric 14C-levels provided evidence for postnatal neuronal exchange. Mathematical modelling identified a best-fitting scenario comprising of a quiescent and a renewing neuronal population with an overall renewal rate of >2.7% per year. In conclusion, we provide evidence for postnatal neurogenesis in the human amygdala with cell turnover rates comparable to the hippocampus.
CRIS-Team Scopus Importer:2022-04-29

Expression of Inflammatory Mediators in Biofilm Samples and Clinical Association in Multiple Sclerosis Patients in Remission—A Pilot Study - Fehlhofer, Jakob Paul; Ries, Jutta; Nickel, Florian; Rothhammer, Veit; Schwab, Stefan; Kesting, Marco Rainer; Buchbender, Mayte (Life, 2024)
Multiple sclerosis (MS) is a chronic inflammatory autoimmune disease of unknown etiology that affects the central nervous system and can lead to neurological impairment. Our aim was to determine whether MS patients also show inflammatory changes in the oral cavity more frequently than healthy individuals. For this purpose, we examined plaque samples for various mediators and their correlation with clinical findings. A study group (MS) and a control group were examined and compared. The plaque samples were analyzed for the expression of interleukins (IL-2, -6, -10), matrix metalloproteinases (MMP-7, MMP-9), and a surface antigen CD90 by quantitative real-time PCR. The clinical parameters examined were the Mombelli plaque index; bleeding on probing (BOP) index; periodontal pocket depth; and decayed, missing, and filled tooth (DMFT) index. The expression of MMP9 was significantly (p = 0.035) higher in the control group. The expression of IL-2 was increased four-fold in the MS group; however, this difference was not statistically significant. The mean PD (p < 0.001) and BOP index (p = 0.029) values were increased in the study group. The clinical parameters of the BOP index and PD were significantly amplified in the MS patients. However, no causal relationship between the investigated inflammatory mediators and the clinical findings could be established in this case series.
CRIS-Team Scopus Importer:2024-05-24
Keywords: cytokine expression; multiple sclerosis; oral hygiene; periodontitis

Extended Multimodal Flat Detector CT Imaging in Acute Ischemic Stroke: A Pilot Study - Hölter, Philip; Lang, Stefan; Beuscher, Vanessa; Kallmünzer, Bernd; Manhart, Michael; Schwab, Stefan; Dörfler, Arnd (Journal of Digital Imaging, 2023)
By using Flat detector computed tomography (FD-CT), a one-stop-shop approach in the diagnostic workup of acute ischemic stroke (AIS) might be achieved. Although information on upstream vessels is warranted, dedicated FD-CT protocols which include the imaging of the cervical vasculature are still lacking. We aimed to prospectively evaluate the implementation of a new multimodal FD-CT protocol including cervical vessel imaging in AIS patients. In total, 16 patients were included in this study. Eight patients with AIS due to large vessel occlusion (LVO) prospectively received a fully multimodal FD-CT imaging, including non-enhanced flat detector computed tomography (NE-FDCT), dynamic perfusion flat detector computed tomography (FD-CTP) and flat detector computed tomography angiography (FD-CTA) including cervical imaging. For comparison of time metrics and image quality, eight AIS patients, which received multimodal CT imaging, were included retrospectively. Although image quality of NE-FDCT and FD-CTA was rated slightly lower than NE-CT and CTA, all FD-CT datasets were of diagnostic quality. Intracerebral hemorrhage exclusion and LVO detection was reliably possible. Median door-to-image time was comparable for the FD-CT group and the control group (CT:30 min, IQR27-58; FD-CT:44.5 min, IQR31-55, p = 0.491). Door-to-groin-puncture time (CT:79.5 min, IQR65-90; FD-CT:59.5 min, IQR51-67; p = 0.016) and image-to-groin-puncture time (CT:44 min, IQR30-50; FD-CT:14 min, IQR12-18; p < 0.001) were significantly shorter, when patients were directly transferred to the angiosuite, where FD-CT took place. Our study indicates that using a new fully multimodal FD-CT approach including imaging of cervical vessels for first-line imaging in AIS patients is feasible and comparable to multimodal CT imaging with substantial potential to streamline the stroke workflow.
CRIS-Team Scopus Importer:2023-02-03
Keywords: Flat Detector Computed Tomography; Interventional; Stroke; Workflow

Extending the time window for intravenous thrombolysis in acute ischemic stroke using magnetic resonance imaging-based patient selection - Ringleb, Peter; Bendszus, Martin; Bluhmki, Erich; Donnan, Geoffrey; Eschenfelder, Christoph; Fatar, Marc; Kessler, Christof; Molina, Carlos; Leys, Didier; Muddegowda, Girish; Poli, Sven; Schellinger, Peter; et al. (International Journal of Stroke, 2019)
Background: Intravenous thrombolysis with alteplase within a time window up to 4.5 h is the only approved pharmacological treatment for acute ischemic stroke. We studied whether acute ischemic stroke patients with penumbral tissue identified on magnetic resonance imaging 4.5–9 h after symptom onset benefit from intravenous thrombolysis compared to placebo. Methods: Acute ischemic stroke patients with salvageable brain tissue identified on a magnetic resonance imaging were randomly assigned to receive standard dose alteplase or placebo. The primary end point was disability at 90 days assessed by the modified Rankin scale, which has a range of 0–6 (with 0 indicating no symptoms at all and 6 indicating death). Safety end points included death, symptomatic intracranial hemorrhage, and other serious adverse events. Results: The trial was stopped early for slow recruitment after the enrollment of 119 (61 alteplase, 58 placebo) of 264 patients planned. Median time to intravenous thrombolysis was 7 h 42 min. The primary endpoint showed no significant difference in the modified Rankin scale distribution at day 90 (odds ratio alteplase versus placebo, 1.20; 95% CI, 0.63–2.27, P = 0.58). One symptomatic intracranial hemorrhage occurred in the alteplase group. Mortality at 90 days did not differ significantly between the two groups (11.5 and 6.8%, respectively; P = 0.53). Conclusions: Intravenous alteplase administered between 4.5 and 9 h after the onset of symptoms in patients with salvageable tissue did not result in a significant benefit over placebo. (Supported by Boehringer Ingelheim, Germany; ISRCTN 71616222).
CRIS-Team Scopus Importer:2019-05-02
Keywords: Alteplase; endovascular; intravenous thrombolysis; magnetic resonance imaging; thrombolysis; time window

Extending thrombolysis to 4·5–9 h and wake-up stroke using perfusion imaging: a systematic review and meta-analysis of individual patient data - Johnston, C.; Burns, R.; McNeil, John; Tress, Brian M.; Campbell, Bruce C.V.; Williams, M.; Ma, Henry; Ringleb, Peter A.; Parsons, Mark W.; Churilov, Leonid; Bendszus, Martin; Hsu, Chung; et al. (Lancet, 2019)
Background: Stroke thrombolysis with alteplase is currently recommended 0–4·5 h after stroke onset. We aimed to determine whether perfusion imaging can identify patients with salvageable brain tissue with symptoms 4·5 h or more from stroke onset or with symptoms on waking who might benefit from thrombolysis. Methods: In this systematic review and meta-analysis of individual patient data, we searched PubMed for randomised trials published in English between Jan 1, 2006, and March 1, 2019. We also reviewed the reference list of a previous systematic review of thrombolysis and searched ClinicalTrials.gov for interventional studies of ischaemic stroke. Studies of alteplase versus placebo in patients (aged ≥18 years) with ischaemic stroke treated more than 4·5 h after onset, or with wake-up stroke, who were imaged with perfusion-diffusion MRI or CT perfusion were eligible for inclusion. The primary outcome was excellent functional outcome (modified Rankin Scale [mRS] score 0–1) at 3 months, adjusted for baseline age and clinical severity. Safety outcomes were death and symptomatic intracerebral haemorrhage. We calculated odds ratios, adjusted for baseline age and National Institutes of Health Stroke Scale score, using mixed-effects logistic regression models. This study is registered with PROSPERO, number CRD42019128036. Findings: We identified three trials that met eligibility criteria: EXTEND, ECASS4-EXTEND, and EPITHET. Of the 414 patients included in the three trials, 213 (51%) were assigned to receive alteplase and 201 (49%) were assigned to receive placebo. Overall, 211 patients in the alteplase group and 199 patients in the placebo group had mRS assessment data at 3 months and thus were included in the analysis of the primary outcome. 76 (36%) of 211 patients in the alteplase group and 58 (29%) of 199 patients in the placebo group had achieved excellent functional outcome at 3 months (adjusted odds ratio [OR] 1·86, 95% CI 1·15–2·99, p=0·011). Symptomatic intracerebral haemorrhage was more common in the alteplase group than the placebo group (ten [5%] of 213 patients vs one [<1%] of 201 patients in the placebo group; adjusted OR 9·7, 95% CI 1·23–76·55, p=0·031). 29 (14%) of 213 patients in the alteplase group and 18 (9%) of 201 patients in the placebo group died (adjusted OR 1·55, 0·81–2·96, p=0·66). Interpretation: Patients with ischaemic stroke 4·5–9 h from stroke onset or wake-up stroke with salvageable brain tissue who were treated with alteplase achieved better functional outcomes than did patients given placebo. The rate of symptomatic intracerebral haemorrhage was higher with alteplase, but this increase did not negate the overall net benefit of thrombolysis. Funding: None.
CRIS-Team Scopus Importer:2019-07-16

Ex vivo radiosensitivity is increased in non-cancer patients taking valproate - Stritzelberger, Jenny; Lainer, Jennifer; Gollwitzer, Stefanie; Graf, Wolfgang; Jost, Tina; Lang, Johannes; Müller, Tamara; Schwab, Stefan; Fietkau, Rainer; Hamer, Hajo; Distel, Luitpold (BMC Neurology, 2020)
Background: Valproate (VPA) is a commonly prescribed antiepileptic drug for patients experiencing epileptic seizures due to brain tumors. VPA increases radiation sensitivity in various tumor cells in vitro due to complex mechanisms. This could make tumors more vulnerable to ionizing radiation or overcome radioresistance. Yet, clinical data on possible improvement of tumor control by adding VPA to tumor therapy is controversial. Potentially radiosensitizing effects of VPA on healthy tissue remain unclear. To determine individual radiosensitivity, we analyzed blood samples of individuals taking VPA. Methods: Ex vivo irradiated blood samples of 31 adult individuals with epilepsy were studied using 3-color fluorescence in situ hybridization. Aberrations in chromosomes 1, 2 and 4 were analyzed. Radiosensitivity was determined by the mean breaks per metaphase (B/M) and compared to age-matched (2:1) healthy donors. Results: The patient cohort (n = 31; female: 38.7%) showed an increase of their average B/M value compared to healthy individuals (n = 61; female: 56.9%; B/M: 0.480 ± 0.09 vs. 0.415 ± 0.07; p =.001). The portion of radiosensitive (B/M > 0.500) and distinctly radiosensitive individuals (B/M > 0.600) was increased in the VPA group (54.9% vs. 11.3 and 9.7% vs. 0.0%; p <.001). In 3/31 patients, radiosensitivity was determined prior to and after VPA treatment and radiosensitivity was increased by VPA-treatment. Conclusions: In our study, we confirmed that patients treated with VPA had an increased radiosensitivity compared to the control group. This could be considered in patients taking VPA prior to the beginning of radiotherapy to avoid toxic side effects of VPA-treatment.
CRIS-Team Scopus Importer:2020-11-06
Keywords: 3-colour fluorescence-in-situ-hybridization; Breaks per metaphase; Individual radiosensitivity; Valproate

Fatal Liver and Bone Marrow Toxicity by Combination Treatment of Dichloroacetate and Artesunate in a Glioblastoma Multiforme Patient: Case Report and Review of the Literature - Uhl, Martin; Schwab, Stefan; Efferth, Thomas (Frontiers in Oncology, 2016)
A 52-year-old male patient was treated with standard radiochemotherapy with temozolomide for glioblastoma multiforme (GBM). After worsening of his clinical condition, further tumor-specific treatment was unlikely to be successful, and the patient seeked help from an alternative practitioner, who administered a combination of dichloroacetate (DCA) and artesunate (ART). A few days later, the patient showed clinical and laboratory signs of liver damage and bone marrow toxicity (leukopenia, thrombocytopenia). Despite successful restoration of laboratory parameters upon symptomatic treatment, the patient died 10 days after the infusion. DCA bears a well-documented hepatotoxic risk, while ART can be considered as safe concerning hepatotoxicity. Bone marrow toxicity can appear upon ART application as reduced reticulocyte counts and disturbed erythropoiesis. It can be assumed that the simultaneous use of both drugs caused liver injury and bone marrow toxicity. The compassionate use of DCA/ART combination therapy outside of clinical trials cannot be recommended for GBM treatment.
EVALuna2:22527

Feasibility and Diagnostic Accuracy of Ischemic Stroke Territory Recognition Based on Two-Dimensional Projections of Three-Dimensional Diffusion MRI Data. - Wrosch, Jana Katharina; Volbers, Bastian; Gölitz, Philipp; Gilbert, Daniel; Schwab, Stefan; Dörfler, Arnd; Kornhuber, Johannes; Groemer, Teja W. (Frontiers in Neurology, 2015)
This study was conducted to assess the feasibility and diagnostic accuracy of brain artery territory recognition based on geoprojected two-dimensional maps of diffusion MRI data in stroke patients. In this retrospective study, multiplanar diffusion MRI data of ischemic stroke patients was used to create a two-dimensional map of the entire brain. To guarantee correct representation of the stroke, a computer-aided brain artery territory diagnosis was developed and tested for its diagnostic accuracy. The test recognized the stroke-affected brain artery territory based on the position of the stroke in the map. The performance of the test was evaluated by comparing it to the reference standard of each patient’s diagnosed stroke territory on record. This study was designed and conducted according to Standards for Reporting of Diagnostic Accuracy (STARD). The statistical analysis included diagnostic accuracy parameters, cross-validation, and Youden Index optimization. After cross-validation on a cohort of 91 patients, the sensitivity of this territory diagnosis was 81% with a specificity of 87%. With this, the projection of strokes onto a two-dimensional map is accurate for representing the affected stroke territory and can be used to provide a static and printable overview of the diffusion MRI data. The projected map is compatible with other two-dimensional data such as EEG and will serve as a useful visualization tool.
Keywords: computer-aided detection and diagnosis; diffusion-weighted imaging; dimensionality reduction; magnetic resonance imaging; stroke territories; validation; visualization

Feasibility of certified quality management in a comprehensive stroke care network using telemedicine: STENO project - Handschu, Rene; Scibor, Mateusz; Wacker, Angela; Stark, David Rianto; Köhrmann, Martin; Erbguth, Frank; Oschmann, Patrick; Schwab, Stefan; Marquardt, Lars (International Journal of Stroke, 2014)
Stroke care networks with and without telemedicine have been established in several countries over the last decade to provide specialized stroke expertise to patients in rural areas. Acute consultation is a first step in the management of stroke, but not the only one. Methods of standardization of care and treatment are much needed. So far, quality management systems have only been used for single stroke units. To the best of our knowledge, we are the first stroke network worldwide to aim for certification of a network-wide quality management system.The Stroke Network Using Telemedicine in Northern Bavaria (STENO), currently with 20 associated medical institutions, is one of the world's largest stroke networks, caring for over 5000 stroke patients each year. In 2010, we initiated the implementation of a network-wide 'total' quality management system according to ISO standard 9001:2008 in cooperation with the German Stroke Society and a third-party certification organization (LGA InterCert).Certification according to ISO 9001:2008 was awarded in March 2011 and maintained over a complete certification cycle of 3 years without major deviation from the norm in three external third-party audits. Thrombolysis rate significantly increased from 8·2% (2009) to 12·8% (2012).Certified quality management within a large stroke network using telemedicine is possible and might improve stroke care procedures and thrombolysis rates. Outcome studies comparing conventional stroke care and telestroke care are inevitable.
EVALuna2:22263

Fibrinolysis Treatment for Cerebral Intraventricular Hemorrhage: A Temporal and Spatial Voxel-Based Analysis - Strinitz, Marc; Kuramatsu, Joji; Kaschka, Iris; Kloska, Stephan; Dörfler, Arnd; Schwab, Stefan; Huttner, Hagen; Seifert, Frank (Journal of Neuroimaging, 2016)
A voxel-based statistical approach on computer tomographic data in patients with intracerebral hemorrhage (ICH) and acute intraventricular hemorrhage (IVH) was used to evaluate spatial and temporal patterns of intraventricular blood in patients treated with intraventricular fibrinolysis (IVF) or without.IVH shapes were systematically assessed three dimensionally in patients with supratentorial ICH at three intervals of time (day of admission, day 4 ± 1, day 7+). The boundaries of the intraventricular blood clot were delineated on computed tomography (CT) scans using dedicated software. The CT scan and the IVH shape were transferred into stereotaxic space. In a second step, voxel-based statistics on group level were used to correlate the distribution of intraventricular blood with the interval and the treatment group.Altogether 45 patients, 29 with IVF therapy and 16 without, were eligible to be included into this study. We found significant (false discovery rate [FDR] correction, q < .05) reduction of the intraventricular blood between day of admission and day 7 + for the third and fourth ventricle and parts of both lateral ventricles. In addition, we were able to show a significant difference between the IVF therapy and the conventionally treated group at day 4 ± 1 for the third ventricle.The data indicate that voxel-based analysis on group level can be used to compare the time course and the distribution of intraventricular hemorrhage. This technique could be an interesting tool for future research on ICH with IVH.
EVALuna2:22457

Gaps Between Aims and Achievements in Therapeutic Modification of Neuronal Damage ("Neuroprotection") - Wiendl, Heinz; Elger, Christian; Foerstl, Hans; Hartung, Hans-Peter; Oertel, Wolfgang; Reichmann, Heinz; Schwab, Stefan (Neurotherapeutics, 2015)
The term "neuroprotection" is often misused, overused, or misunderstood. A reasonable definition of neuroprotection refers to the preservation of "neuronal structure and/or function." Although our knowledge about the cellular and molecular mechanisms of neurodegeneration has expanded, experimental systems and animal models that mimic the process or allow translation into clinical success remain limited. This editorial discusses reasons for this gap and strategies to close it. Experimental models can only mirror certain aspects of disease mechanisms in humans. Therefore, findings in these models need to be linked with patient data to improve real-life relevance. Successful neuroprotection depends on finding the right "window of opportunity" which varies from very short (stroke) to very long (Alzheimer's disease), necessitating the need to focus on strategies for very early disease recognition. This need challenges the strategies to be chosen, trial approaches and methodologies, and the allocation of resources. Additionally, outcome measures are often not well suited to assess neuroprotection. To this end, surrogate measures, including biomarkers, are useful endpoints to demonstrate evidence of target directed therapeutic utility. Finally, studies have shown that neuroprotection is not likely to succeed when targeting only one pathway. These obstacles have reduced the level of enthusiasm for neuroprotection in certain disease areas (e.g., stroke). Academia, industry, regulatory authorities, funding agencies and patient organizations have to cooperate to a greater extent in order to overcome these impediments and to encourage nonclassical concepts. These concepts will be interdisciplinary in order to achieve meaningful disease modification.
EVALuna2:22435

Good outcome of brain stem progressive multifocal leukoencephalopathy in an immunosuppressed renal transplant patient: Importance of early detection and rapid immune reconstitution - Sauer, Rolf; Gölitz, Philipp; Jacobi, Johannes; Schwab, Stefan; Linker, Ralf; Lee, De-Hyung (Journal of the Neurological Sciences, 2017)
Progressive multifocal leukoencephalopathy (PML) is a rare, opportunistic and often fatal disease of the CNS which may occur under immunosuppression in transplant patients. Brain stem PML is associated with a particularly bad prognosis. Here, we present a case of a renal transplant patient treated with mycophenolate mofetil (MMF) and tacrolimus who developed brain stem PML with limb ataxia, dysarthria and dysphagia. Diagnosis was established by typical MRI features and detection of JCV-DNA in the CSF. Immune reconstitution after stopping MMF and tacrolimus led to a complete and sustained remission of symptoms with improvement of the brain stem lesion over a follow-up over 20months. In summary, early detection of PML and consequent treatment may improve neurological outcomes even in brain stem disease with a notorious bad prognosis.
EVALuna2:22499

Granulocyte colony-stimulating factor does not promote neurogenesis after experimental intracerebral haemorrhage - Kallmünzer, Bernd; Tauchi, Miyuki; Schlachetzki, Johannes; Machold, Kristin; Schmidt, Ariana; Winkler, Jürgen; Schwab, Stefan; Kollmar, Rainer (International Journal of Stroke, 2014)
Hematopoietic growth factors have been suggested to induce neuroprotective and regenerative effects in various animal models of cerebral injury. However, the pathways involved remain widely unexplored.This study aimed to investigate effects of local and systemic administration of granulocyte colony-stimulating factor on brain damage, functional recovery, and cerebral neurogenesis in an intracerebral haemorrhage whole blood injection model in rats.Eight-week-old male Wistar rats (n = 100) underwent induction of striatal intracerebral haemorrhage by autologous whole blood injection or sham procedure and were randomly assigned to either (a) systemic treatment with granulocyte colony-stimulating factor (60 ?g/kg) for five-days; (b) single intracerebral injection of granulocyte colony-stimulating factor (60 ?g/kg) into the cavity; or (c) application of vehicle for five-days. Bromodeoxyuridine-labelling and immunohistochemistry were used to analyze proliferation and survival of newly born cells in the sub-ventricular zone and the hippocampal dentate gyrus. Moreover, functional deficits and lesion volume were assessed until day 42 after intracerebral haemorrhage.Differences in lesion size or hemispheric atrophy between granulocyte colony-stimulating factor-treated and control groups did not reach statistical significance. Neither systemic, nor local granulocyte colony-stimulating factor administration induced neurogenesis within the dentate gyrus or the sub-ventricular zone. The survival of newborn cells in these regions was prevented by intracerebral granulocyte colony-stimulating factor application. A subtle benefit in functional recovery at day 14 after intracerebral haemorrhage induction was observed after granulocyte colony-stimulating factor treatment.There was a lack of neuroprotective or neuroregenerative effects of granulocyte colony-stimulating factor in the present rodent model of intracerebral haemorrhage. Conflicting results from functional outcome assessment require further research.
EVALuna2:22279

Heart Failure in Ischemic Stroke: Relevance for Acute Care and Outcome - Siedler, Gabriela; Sommer, Kim; Macha, Kosmas; Marsch, Armin; Breuer, Lorenz; Stoll, Svenja; Engelhorn, Tobias; Dörfler, Arnd; Schwab, Stefan; Kallmünzer, Bernd; Arnold, Martin (Stroke, 2019)
Background and Purpose- Heart failure (HF) in patients with acute ischemic stroke constitutes the source of various detrimental pathophysiologic mechanisms including prothrombotic and proinflammatory states, worsening of cerebral tissue oxygenation, and hemodynamic impairment. In addition, HF might affect the safety and efficacy of the acute recanalization stroke therapies. Methods- Patients treated with intravenous recombinant tissue-type plasminogen activator or mechanical recanalization at a universitary stroke center were included into a prospective registry. Patients received cardiological evaluation, including echocardiography, during acute care. Functional outcome was assessed after 90 days by structured telephone interviews. Safety and efficacy of intravenous thrombolysis and mechanical thrombectomy were investigated among patients with HF and compared with patients with normal cardiac function after propensity score matching. Results- One thousand two hundred nine patients were included. HF was present in 378 patients (31%) and an independent predictor of unfavorable functional outcome. Recanalization rates were equal among patients with HF after intravenous thrombolysis and after mechanical recanalization or combined treatment. The rate of secondary intracranial hemorrhage was not different (7% versus 8%; P=0.909 after thrombolysis and 15% versus 20%, P=0.364 after mechanical recanalization or combined therapy). Early mortality within 48 hours after admission was equal (<1.5% in both groups). Conclusions- In this real-world cohort of patients with stroke, HF was an independent predictor of unfavorable functional long-term outcome, while the safety and efficacy of intravenous thrombolysis and mechanical recanalization appeared unaffected.
EVALuna2:204477

Hematoma enlargement characteristics in deep versus lobar intracerebral hemorrhage - Sembill, Jochen; Kuramatsu, Joji; Gerner, Stefan; Sprügel, Maximilian; Röder, Sebastian; Madžar, Dominik; Hagen, Manuel; Lücking, Hannes; Dörfler, Arnd; Schwab, Stefan; Huttner, Hagen; Hölter, Philip (Annals of Clinical and Translational Neurology, 2020)
Objective: Hematoma enlargement (HE) is associated with clinical outcomes after supratentorial intracerebral hemorrhage (ICH). This study evaluates whether HE characteristics and association with functional outcome differ in deep versus lobar ICH. Methods: Pooled analysis of individual patient data between January 2006 and December 2015 from a German-wide cohort study (RETRACE, I + II) investigating ICH related to oral anticoagulants (OAC) at 22 participating centers, and from one single-center registry (UKER-ICH) investigating non-OAC-ICH patients. Altogether, 1954 supratentorial ICH patients were eligible for outcome analyses, which were separately conducted or controlled for OAC, that is, vitamin-K-antagonists (VKA, n = 1186) and non-vitamin-K-antagonist-oral-anticoagulants (NOAC, n = 107). Confounding was addressed using propensity score matching, cox regression modeling and multivariate modeling. Main outcomes were occurrence, extent, and timing of HE (>33%/>6 mL) and its association with 3-month functional outcome. Results: Occurrence of HE was not different after deep versus lobar ICH in patients with non-OAC-ICH (39/356 [11.0%] vs. 36/305 [11.8%], P = 0.73), VKA-ICH (249/681 [36.6%] vs. 183/505 [36.2%], P = 0.91), and NOAC-ICH (21/69 [30.4%] vs. 12/38 [31.6%], P = 0.90). HE extent did not differ after non-OAC-ICH (deep:+59% [40–122] vs. lobar:+74% [37–124], P = 0.65), but both patients with VKA-ICH and NOAC-ICH showed greater HE extent after deep ICH [VKA-ICH, deep: +94% [54–199] vs. lobar: +56% [35–116], P < 0.001; NOAC-ICH, deep: +74% [56–123] vs. lobar: +40% [21–49], P = 0.001). Deep compared to lobar ICH patients had higher HE hazard during first 13.5 h after onset (Hazard ratio [HR]: 1.85 [1.03–3.31], P = 0.04), followed by lower hazard (13.5–26.5 h, HR: 0.46 [0.23–0.89], P = 0.02), and equal hazard thereafter (HR: 0.96 [0.56–1.65], P = 0.89). Odds ratio for unfavorable outcome was higher after HE in deep (4.31 [2.71–6.86], P < 0.001) versus lobar ICH (2.82 [1.71–4.66], P < 0.001), and only significant after small-medium (1st volume-quarter, deep: 3.09 [1.52–6.29], P < 0.01; lobar: 3.86 [1.35–11.04], P = 0.01) as opposed to large-sized ICH (4th volume-quarter, deep: 1.09 [0.13–9.20], P = 0.94; lobar: 2.24 [0.72–7.04], P = 0.17). Interpretation: HE occurrence does not differ among deep and lobar ICH. However, compared to lobar ICH, HE after deep ICH is of greater extent in OAC-ICH, occurs earlier and may be of greater clinical relevance. Overall, clinical significance is more apparent after small–medium compared to large-sized bleedings.
CRIS-Team Scopus Importer:2020-03-17

Hematoma Expansion and Clinical Outcomes in Patients With Factor-Xa Inhibitor-Related Atraumatic Intracereoral Hemorrhage Treated Within the ANNEXA-4 Trial Versus Real-World Usual Care - Huttner, Hagen; Gerner, Stefan; Kuramatsu, Joji; Connolly, Stuart J.; Beyer-Westendorf, Jan; Demchuk, Andrew M.; Middeldorp, Saskia; Zotova, Elena; Altevers, Julia; Andersohn, Frank; Christoph, Mary J.; Yue, Patrick; et al. (Stroke, 2022)
BACKGROUND AND PURPOSE: It is unestablished whether andexanet alfa, compared with guideline-based usual care including prothrombin complex concentrates, is associated with reduced hematoma expansion (HE) and mortality in patients with factor-Xa inhibitor-related intracerebral hemorrhage (ICH). We compared the occurrence of HE and clinical outcomes in patients treated either with andexanet alfa or with usual care during the acute phase of factor-Xa inhibitor-related ICH.
CRIS-Team WoS Importer:2022-02-04

Hematoma expansion in intracerebral hemorrhage – the right target? - Haupenthal, David; Schwab, Stefan; Kuramatsu, Joji (Neurological Research and Practice, 2023)
Background: The avoidance of hematoma expansion is the most important therapeutic goal during acute care of patients with intracerebral hemorrhage. Hematoma expansion occurs in up to 20–40% of patients and leads to poorer patient outcome in one of the most severe sub-types of stroke. Main text: At current, randomized controlled trials have failed to provide evidence for interventions that effectively improve functional outcome in patients with intracerebral hemorrhage. Hence, hematoma expansion may serve as important surrogate target that appears causally linked with a poorer prognosis. Therefore, reduction of hematoma expansion rates will eventually translate to improved patient outcome overall. Recent years have shed light on the importance of early and aggressive treatment in order to reduce the risk for hematoma expansion in these patients. Time measures and imaging markers have been identified that may allow patient selection at very high risk for hematoma expansion. Conclusions: Refinements in patient selection may increase chance for randomized trials to show true benefit. Therefore, this current review article will critically evaluate and discuss available evidence associated with hematoma expansion in patients with intracerebral hemorrhage.
CRIS-Team Scopus Importer:2023-08-11
Keywords: Blood pressure management; Hematoma enlargement; Hematoma expansion; Hemostatic therapies; Intracerebral hemorrhage

Heparin for prophylaxis of venous thromboembolism in intracerebral haemorrhage - Sprügel, Maximilian; Sembill, Jochen; Kuramatsu, Joji; Gerner, Stefan; Hagen, Manuel; Röder, Sebastian; Endres, Matthias; Haeusler, Karl Georg; Sobesky, Jan; Schurig, Johannes; Zweynert, Sarah; Bauer, Miriam; et al. (Journal of Neurology Neurosurgery and Psychiatry, 2019)
Objective: To determine the occurrence of intracranial haemorrhagic complications (IHC) on heparin prophylaxis (low-dose subcutaneous heparin, LDSH) in primary spontaneous intracerebral haemorrhage (ICH) (not oral anticoagulation-associated ICH, non-OAC-ICH), vitamin K antagonist (VKA)-associated ICH and non-vitamin K antagonist oral anticoagulant (NOAC)-associated ICH. Methods: Retrospective cohort study (RETRACE) of 22 participating centres and prospective single-centre study with 1702 patients with VKA-associated or NOAC-associated ICH and 1022 patients with non-OAC-ICH with heparin prophylaxis between 2006 and 2015. Outcomes were defined as rates of IHC during hospital stay among patients with non-OAC-ICH, VKA-ICH and NOAC-ICH, mortality and functional outcome at 3 months between patients with ICH with and without IHC. Results: IHC occurred in 1.7% (42/2416) of patients with ICH. There were no differences in crude incidence rates among patients with VKA-ICH, NOAC-ICH and non-OAC-ICH (log-rank p=0.645; VKA-ICH: 27/1406 (1.9%), NOAC-ICH 1/130 (0.8%), non-OAC-ICH 14/880 (1.6%); p=0.577). Detailed analysis according to treatment exposure (days with and without LDSH) revealed no differences in incidence rates of IHC per 1000 patient-days (LDSH: 1.43 (1.04-1.93) vs non-LDSH: 1.32 (0.33-3.58), conditional maximum likelihood incidence rate ratio: 1.09 (0.38-4.43); p=0.953). Secondary outcomes showed differences in functional outcome (modified Rankin Scale=4-6: IHC: 29/37 (78.4%) vs non-IHC: 1213/2048 (59.2%); p=0.019) and mortality (IHC: 14/37 (37.8%) vs non-IHC: 485/2048 (23.7%); p=0.045) in disfavour of patients with IHC. Small ICH volume (OR: volume <4.4 mL: 0.18 (0.04-0.78); p=0.022) and low National Institutes of Health Stroke Scale (NIHSS) score on admission (OR: NIHSS <4: 0.29 (0.11-0.78); p=0.014) were significantly associated with fewer IHC. Conclusions: Heparin administration for venous thromboembolism (VTE) prophylaxis in patients with ICH appears to be safe regarding IHC among non-OAC-ICH, VKA-ICH and NOAC-ICH in this observational cohort analysis. Randomised controlled trials are needed to verify the safety and efficacy of heparin compared with other methods for VTE prevention.
CRIS-Team Scopus Importer:2019-05-02
Keywords: cerebrovascular disease; critical care; intracerebral heamorrhage; stroke

High-resolution diffusion tensor-imaging indicates asymmetric microstructural disorganization within substantia nigra in early Parkinson's disease - Knossalla, Frauke; Kohl, Zacharias; Winkler, Jürgen; Schwab, Stefan; Schenk, Thomas; Engelhorn, Tobias; Dörfler, Arnd; Gölitz, Philipp (Journal of Clinical Neuroscience, 2018)
BACKGROUND AND PURPOSE: Parkinson's disease (PD) is characterised by neuropathological degenerative changes in the substantia nigra (SN). Our study aimed to evaluate whether high-resolution diffusion tensor-imaging (DTI) can detect anatomical biomarkers in early-stage PD, and has the potential to visualize asymmetry effects comparable to the 123I-FP-CIT SPECT (DaTSCAN). METHODS: Ten early-stage PD patients with mild disease severity and ten age- and gender-matched healthy controls were examined with a high-resolution DTI protocol at a 3 Tesla MRI scanner to assess fractional anisotropy (FA) values in the ventral, middle and dorsal region of SN. In addition, a subgroup of 5 PD patients underwent a DaTSCAN. RESULTS: PD subjects showed reduced FA values in all SN regions compared to controls, but post hoc analysis revealed a significant reduction (p = .032) in the dorsal region. There was no significant correlation between clinical data and FA values. Subgroup analysis of PD patients with asymmetric radioligand uptake in the DaTSCAN demonstrated also significant asymmetric FA values (p = .027) in the dorsal region of SN. CONCLUSIONS: Our results provide preliminary evidence that high-resolution DTI can detect in early-stage PD patients with mild disease severity an anatomical biomarker in the dorsal region of SN, indicating microstructural disorganization. This biomarker, discriminating potentially in vivo between patients and healthy people, could be valuable for early PD diagnosis. If asymmetric radioligand uptake in the DaTSCAN was present, also asymmetry effects in the dorsal region of SN were obtained by DTI. These findings might contribute to improve effectiveness in diagnosing and monitoring PD.
EVALuna2:34272

Immunological and clinical consequences of splenectomy in a multiple sclerosis patient treated with natalizumab - Lee, De-Hyung; Waschbisch, Anne; Laemmer, Alexandra B.; Dörfler, Arnd; Schwab, Stefan; Linker, Ralf (Journal of Neuroinflammation, 2013)
Objective: Here we report a case of a splenectomized white woman with natalizumab-associated progressive multifocal leukoencephalopathy (PML), occurring as early as after 11 infusions and provide blood fluorescence-activated cell sorting (FACS) analyses before and after natalizumab treatment.Design: This is a report of a single case with immunological studies.Methods: Methods comprised neurologic examination, magnetic resonance imaging, and cerebrospinal fluid (CSF) studies as well as immune cell FACS analyses from blood.Results: Diagnosis of PML was established after positive John Cunningham virus (JCV) DNA was detected in the CSF. An immune reconstitution inflammatory syndrome was treated with repeated cycles of steroid pulses and intravenous immunoglobulins. Reduced numbers of memory B cells, which might play an important role in antiviral immune response, were detected in the blood. Moreover the percentage of CD19+ B cells was elevated in our post-splenectomy patient as compared to a control cohort of multiple sclerosis (MS) patients under natalizumab therapy.Conclusion: Splenectomy may increase the risk for the development of natalizumab-associated PML via effects on the B cell compartment. It may be regarded as a risk factor in MS patients independent from the duration of disease. © 2013 Lee et al.; licensee BioMed Central Ltd.
CRIS-Team Scopus Importer:2022-08-05
Keywords: CD19 positive B cells; Multiple sclerosis; Natalizumab; Progressive multifocal leukoencephalopathy; Splenectomy

Impact of heart rate dynamics on mortality in the early phase after ischemic stroke: a prospective observational trial - Kallmünzer, Bernd; Bobinger, Tobias; Kopp, Markus; Kurka, Natalia; Hilz, Max-Josef; Schwab, Stefan; Köhrmann, Martin; Arnold, Martin (Journal of Stroke and Cerebrovascular Diseases, 2015)
Growing evidence suggests that the heart rate (HR) at rest is an independent predictor of cardiovascular mortality. In ischemic stroke, continuous monitoring of HR is the standard of care, but systematic data on its dynamics and prognostic value during the acute phase are limited.In this prospective observational study, HR was measured by continuous electrocardiographic monitoring on admission and during the first 72 hours of care among patients who were awake with ischemic stroke and survived until discharge. Functional outcome was assessed after 90 days.Data from 702 consecutive patients were analyzed (median age, 73 years, 54% men). The time course of HR was initially characterized by a rapid decline during the first 12 hours after admission. Among patients who survived until day 90, this was followed by a continuous downward trend in HR, whereas death after discharge was associated with a secondary increase and a reversal point 12 hours after admission. After adjustment for established risk factors, this secondary increase during the acute period was an independent predictor of death (hazard ratio, 3.73; 95% confidence interval, 1.47-9.43; P = .005).A secondary rise of HR during care for acute ischemic stroke is an early sign of fatality and may represent a surrogate for an unfavorable sympathetic disinhibition. Further research is warranted to clarify the role of targeted HR reduction after ischemic stroke (http://clinicaltrials.gov/, unique identifier NCT01858779).
EVALuna2:12023

Impact of Hypothermia Initiation and Duration on Perihemorrhagic Edema Evolution After Intracerebral Hemorrhage - Volbers, Bastian; Herrmann, Sabrina; Willfarth, Wolfgang; Lücking, Hannes; Kloska, Stephan; Dörfler, Arnd; Huttner, Hagen; Kuramatsu, Joji; Schwab, Stefan; Staykov, Dimitre (Stroke, 2016)
Intracerebral hemorrhage (ICH) causes high morbidity and mortality. Recently, perihemorrhagic edema (PHE) has been suggested as an important prognostic factor. Therapeutic hypothermia may be a promising therapeutic option to treat PHE. However, no data exist about the optimal timing and duration of therapeutic hypothermia in ICH. We examined the impact of therapeutic hypothermia timing and duration on PHE evolution.In this retrospective, single-center, case-control study, we identified patients with ICH treated with mild endovascular hypothermia (target temperature 35°C) from our institutional database. Patients were grouped according to hypothermia initiation (early: days 1-2 and late: days 4-5 after admission) and hypothermia duration (short: 4-8 days and long: 9-15 days). Patients with ICH matched for ICH volume, age, ICH localization, and intraventricular hemorrhage were identified as controls. Relative PHE, temperature, and intracranial pressure course were analyzed. Clinical outcome on day 90 was assessed using the modified Rankin scale (0-3=favorable and 4-6=poor).Thirty-three patients with ICH treated with hypothermia and 37 control patients were included. Early hypothermia initiation led to relative PHE decrease between admission and day 3, whereas median relative PHE increased in control patients (-0.05 [interquartile range, -0.4 to 0.07] and 0.07 [interquartile range, -0.07 to 0.26], respectively; P=0.007) and patients with late hypothermia initiation (0.22 [interquartile range 0.12-0.27]; P=0.037). After day 3, relative PHE increased in all groups without difference. Outcome was not different between patients treated with hypothermia and controls.Early hypothermia initiation after ICH onset seems to have an important impact on PHE evolution, whereas our data suggest only limited impact later than day 3 after onset.
EVALuna2:22477

Impact of the coronavirus disease 2019 pandemic on stroke teleconsultations in Germany in the first half of 2020 - Vollmuth, Christoph; Miljukov, Olga; Abu-Mugheisib, Mazen; Angermaier, Anselm; Barlinn, Jessica; Busetto, Loraine; Grau, Armin J.; Guenther, Albrecht; Gumbinger, Christoph; Hubert, Nikolai; Hüttemann, Katrin; Klingner, Carsten; et al. (European Journal of Neurology, 2021)
Background and purpose: The effects of the coronavirus disease 2019 (COVID-19) pandemic on telemedical care have not been described on a national level. Thus, we investigated the medical stroke treatment situation before, during, and after the first lockdown in Germany. Methods: In this nationwide, multicenter study, data from 14 telemedical networks including 31 network centers and 155 spoke hospitals covering large parts of Germany were analyzed regarding patients' characteristics, stroke type/severity, and acute stroke treatment. A survey focusing on potential shortcomings of in-hospital and (telemedical) stroke care during the pandemic was conducted. Results: Between January 2018 and June 2020, 67,033 telemedical consultations and 38,895 telemedical stroke consultations were conducted. A significant decline of telemedical (p < 0.001) and telemedical stroke consultations (p < 0.001) during the lockdown in March/April 2020 and a reciprocal increase after relaxation of COVID-19 measures in May/June 2020 were observed. Compared to 2018–2019, neither stroke patients' age (p = 0.38), gender (p = 0.44), nor severity of ischemic stroke (p = 0.32) differed in March/April 2020. Whereas the proportion of ischemic stroke patients for whom endovascular treatment (14.3% vs. 14.6%; p = 0.85) was recommended remained stable, there was a nonsignificant trend toward a lower proportion of recommendation of intravenous thrombolysis during the lockdown (19.0% vs. 22.1%; p = 0.052). Despite the majority of participating network centers treating patients with COVID-19, there were no relevant shortcomings reported regarding in-hospital stroke treatment or telemedical stroke care. Conclusions: Telemedical stroke care in Germany was able to provide full service despite the COVID-19 pandemic, but telemedical consultations declined abruptly during the lockdown period and normalized after relaxation of COVID-19 measures in Germany.
CRIS-Team Scopus Importer:2021-04-02
Keywords: COVID-19; SARS-CoV-2; stroke; survey; telemedicine

Impaired renal function in stroke patients with atrial fibrillation - Sauer, Eva-Maria; Sauer, Rolf; Kallmuenzer, Bernd; Blinzler, Christian; Breuer, Lorenz; Huttner, Hagen; Schwab, Stefan; Köhrmann, Martin (Journal of Stroke and Cerebrovascular Diseases, 2014)
Stroke patients with atrial fibrillation (AF) are prone to have comorbidities such as impaired renal function. Because poly-pharmacotherapy is often required in those patients, renal function is important to consider in light of renally cleared medications such as direct oral anticoagulants. In this study, we analyzed frequency and predictors for impaired renal function and its impact on functional outcome in stroke patients with underlying AF.We analyzed 272 patients with acute ischemic stroke and AF of our prospective, observational stroke database. Estimated glomerular filtration rate (eGFR) was calculated on admission and during hospitalization from the equation of the Modification Diet for Renal Disease. Outcome measures included mortality and functional outcome at 90 days, assessed as modified Rankin Scale (mRS) score.On admission, impaired renal function was found in 41.5% (n = 113) and was associated with worse 90-day outcome (mRS score <= 2: 26.5% versus 45.9%, P = .001) and a higher mortality rate (23.9% versus 14.5%, P = .043). Multivariate logistic regression identified older age and history of myocardial infarction as independent predictors of renal dysfunction on admission (P < .05). Normalization of eGFR during hospitalization was achieved in 55.8%.In patients with acute ischemic stroke and AF, impaired renal function on admission is frequent and associated with worse outcome. Normalization of eGFR can often be achieved during hospitalization, but in everyday life, fluctuations of renal function because of infection or dehydration have to be considered. Careful monitoring of renal status is indispensable and should influence drug treatment decisions.
EVALuna2:22248

Implant for Augmentation of Cerebral Blood Flow Trial-1 (ImpACT-1). A single-arm feasibility study evaluating the safety and potential benefit of the Ischemic Stroke System for treatment of acute ischemic stroke - Khurana, Dheeraj; Kaul, Subhash; Schneider, Dietmar; Csanyi, Attila; Adam, Ilona; Ichaporia, Nasli R.; Griewing, Bernd; Csiba, Laszlo; Valikovics, Attila; Puri, Vinod; Diener, Hans Christoph; Schwab, Stefan; et al. (PLoS ONE, 2019)
BACKGROUND: The Ischemic Stroke System is a novel device designed to deliver stimulation to the sphenopalatine ganglion(SPG).The SPG sends parasympathetic innervations to the anterior cerebral circulation. In rat stroke models, SPG stimulation results in increased cerebral blood flow, reduced infarct volume, protects the blood brain barrier, and improved neurological outcome. We present here the results of a prospective, multinational, single-arm, feasibility study designed to assess the safety, tolerability, and potential benefit of SPG stimulation inpatients with acute ischemic stroke(AIS). METHODS: Patients with anterior AIS, baseline NIHSS 7-20 and ability to initiate treatment within 24h from stroke onset, were implanted and treated with the SPG stimulation. Patients were followed up for 90 days. Effect was assessed by comparing the patient outcome to a matched population from the NINDS rt-PA trial placebo patients. RESULTS: Ninety-eight patients were enrolled (mean age 57years, mean baseline NIHSS 12 and mean treatment time from stroke onset 19h). The observed mortality rate(12.2%), serious adverse events (SAE)incidence(23.5%) and nature of SAE were within the expected range for the population. The modified intention to treat cohort consisted of 84 patients who were compared to matched patients from the NINDS placebo arm. Patients treated with SPG stimulation had an average mRS lower by 0.76 than the historical controls(CMH test p = 0.001). CONCLUSION: The implantation procedure and the SPG stimulation, initiated within 24hr from stroke onset, are feasible, safe, and tolerable. The results call for a follow-up randomized trial (funded by BrainsGate; clinicaltrials.gov number, NCT03733236).
CRIS-Team Scopus Importer:2019-07-30

Improvement and stabilization of cardiovascular autonomic modulation three months after acute ischemic stroke - Wang, Ruihao; Macha, Kosmas; Köhn, Julia; Marsch, Armin; Winder, K.; Gerner, Stefan; Koehrmann, M.; Schwab, Stefan; Kallmünzer, Bernd; Hilz, Max-Josef (EUROPEAN JOURNAL OF NEUROLOGY, 2020)
CRIS-Team WoS Importer:2020-06-16

Incidence and relative risk of stroke in the diabetic and the non-diabetic population between 1998 and 2014: A community-based stroke register - Icks, Andrea; Claessen, Heiner; Kvitkina, Tatjana; Narres, Maria; Weingaertner, Michael; Schwab, Stefan; Kolominsky-Rabas, Peter (PLoS ONE, 2017)
One major objective of the St. Vincent Declaration was to reduce excess risk of stroke in people with diabetes mellitus. The aim of this study is to estimate the trend of incidence and relative risk of stroke in the diabetic and the non-diabetic populations in Germany over a 17-year period. We estimated age-sex standardised incidence rates of all stroke and ischaemic stroke in people with and without diabetes based on an ongoing prospective community-based stroke register covering 105,000 inhabitants. Time trends were analysed using Poisson regression. In total, 3,111 individuals (diabetes: 28.4%, men 46.9%, mean age 73.1 years (SD 13.2)) had a first stroke, 84.9% of which were ischaemic stroke. Among people with diabetes we observed a significant reduction in all stroke incidence by 1.5% per year (relative risk: 0.985; 95% confidence interval 0.972-0.9995) Likewise, this incidence tended to decrease for ischaemic stroke by 1% per year (0.993; 0.979-1.008). In contrast, the incidence rate for all stroke remained nearly stable among people without diabetes (1.003; 0.993-1.013) and for ischaemic stroke (1.002; 0.991-1.013). The relative risk comparing diabetic and non-diabetic population decreased for all stroke (two percent annual reduction) but not for ischaemic stroke. Time trends were similar for both sexes regarding all and ischaemic strokes. We found a reduction in risk of stroke in the diabetic population while this rate did not materially change in the non-diabetic population.
EVALuna2:33129

Incidence, temporal profile and neuroanatomic correlates of poststroke epilepsy - Winder, Klemens; Bobinger, Tobias; Seifert, Frank; Mrochen, Anne; Haupenthal, David; Knott, Michael; Dörfler, Arnd; Hilz, Max-Josef; Schwab, Stefan; Fröhlich, Kilian (Journal of Neuroimaging, 2023)
Background and Purpose: The relationship between ischemic stroke site and occurrence of poststroke epilepsy (PSE) is incompletely understood. This study intended to evaluate incidence and temporal profiles of seizures and to correlate ischemic lesion sites with PSE using voxel-based lesion symptom mapping (VLSM). Methods: Patients with imaging-confirmed first-ever ischemic stroke without prior history of epilepsy were prospectively included. Demographic data, cardiovascular risk factors, and National Institute of Health Stroke Scale (NIHSS) scores were assessed. Data on seizures and modified Rankin scale scores were determined within a 90-day period after stroke onset. Ischemic lesion sites were correlated voxel wise with occurrence of PSE using nonparametric permutation test. Age- and sex-matched patients with first-ever ischemic strokes without PSE after 90 days served as controls for the VLSM analysis. Results: The stroke database contained 809 patients (mean age: 68.4 ± 14.2 years) with first-ever imaging-confirmed ischemic strokes without history of epilep. Incidence of PSE after 90-day follow-up was 2.8%. Five additional patients were admitted to the emergency department with a seizure after 90-day follow-up. Fifty percent of the seizures occurred in the acute phase after stroke. PSE patients had higher NIHSS scores and infarct volumes compared to controls without PSE (p <.05). PSE patients had infarcts predominantly involving the cerebral cortex. The hemisphere-specific VLSM analysis shows associations between PSE and damaged voxels in the left-hemispheric temporo-occipital transition zone. Conclusions: The data indicate that PSE occurs in a small proportion of patients with rather large ischemic strokes predominantly involving the cerebral cortex. Especially patients with ischemic lesions in the temporo-occipital cortex are vulnerable to develop PSE.
CRIS-Team Scopus Importer:2023-05-19
Keywords: ischemic stroke; poststroke epilepsy; voxel-based lesion symptom mapping

Individual participant data analysis comparing acute stroke patients with anterior versus posterior circulation dissections - Zhang, Yanan; Zhang, Yang; Fröhlich, Kilian; Mrochen, Anne; Mühlen, Iris; Lang, Stefan; Lehmann, Sophie; Gerner, Stefan T.; Huttner, Hagen B.; Schwab, Stefan; He, Li; Bobinger, Tobias (Clinical Neurology and Neurosurgery, 2024)
Background: Cervical artery dissection (CAD) is a relevant etiology of transient ischemic attacks and strokes. Several trials explored the significance of specific antithrombotic treatments, i.e. oral anticoagulation (OAC) versus antiplatelet treatment (APT), on recurrent ischemic complications and clinical outcomes. As overall incidence rates of complications were low there is still controversy which antithrombotic treatment should be used. However, up to now there has been no systematic investigation among CAD-patients with ischemic stroke specifically comparing clinical course and outcome of patients with anterior versus posterior CAD. Methods: We performed an individual participant data analysis of patients with CAD and ischemic stroke. Over a five-year period we pooled data from three sites (i.e. West China Hospital, Chengdu, China as well as Erlangen and Giessen University Hospitals, Germany) and enrolled patients with CAD-associated ischemic stroke. Patient demographics, clinical and in-hospital measures as well as radiological data were retrieved from institutional databases. Clinical follow-up was over 6 months and included data on recurrent ischemic strokes and hemorrhages as well as clinical functional outcome assessed by the modified Rankin Scale dichotomized into favourable (mRS=0–2) and unfavourable. Results: A total of 203 patients with CAD were included of which n=112 had anterior and n=91 had posterior CAD. Patients with posterior CAD were younger (46.0 vs. 41.0 y; p<0.001) than patients with anterior CAD and showed less often arterial hypertension. (42.0 % vs. 28.6 %; p<0.048). Antithrombotic treatment with APT and OAC was similarily distributed among patients with anterior and posterior CAD and not significantly differently related to ischemic or hemorrhagic complications during follow-up (all p=n.s.). Main difference between Chinese and German patients were mode of antithrombotic treatment consisting predominantly of APT in China compared to OAC in Germany. Functional outcome overall was good, yet worse in patients with anterior CAD compared to posterior CAD (80.2 % favorable in anterior CAD vs. 92.2 % in posterior CAD (p=0.014). Conclusion: This study provides evidence that anterior and posterior CAD show baseline imbalances regarding age and comorbidity which may affect clinical outcome. There are no signals of superiority or harm of any specific mode of antithrombotic treatment nor relevant discrepancies in clinical outcome among Chinese and German CAD-associated stroke patients.
CRIS-Team Scopus Importer:2024-06-21
Keywords: Acute ischemic stroke; Antiplatelet treatment; Cervical artery dissections; Clinical outcome; Oral anticoagulation

Influence of antithrombotic pre-treatment and time window on hemorrhagic complications of ivt in ischemic stroke - Macha, Kosmas; Hölter, Philip; Sembill, Jochen; Hock, Stefan; Siedler, Gabriela; Mühlen, Iris; Haupenthal, David; Schwab, Stefan; Kallmünzer, Bernd; Dörfler, Arnd (EUROPEAN JOURNAL OF NEUROLOGY, 2022)
CRIS-Team WoS Importer:2022-07-22

Influence of Early Enteral Nutrition on Clinical Outcomes in Neurocritical Care Patients With Intracerebral Hemorrhage - Peng, Jianhua; Volbers, Bastian; Sprugel, Maximilian I.; Hölter, Philip; Engelhorn, Tobias; Jiang, Yong; Kuramatsu, Joji; Huttner, Hagen; Dörfler, Arnd; Schwab, Stefan; Gerner, Stefan (Frontiers in Neurology, 2021)
Objective: Early enteral nutrition (EEN) represents the current standard of care for patients treated in general intensive care units (ICU). Specific nutritional recommendations for patients receiving dedicated neurocritical care are not established. This study investigated associations of EEN with clinical outcomes for patients suffering from intracerebral hemorrhage treated at a neurological ICU (NICU).
CRIS-Team WoS Importer:2021-05-14

Influence on Outcome and Treatment of Intracerebral Hematoma in Patients with Atraumatic Subarachnoid Hemorrhage - Gerner, Stefan; Kuramatsu, Joji; Reichl, Jonathan; Eyüpoglu, Ilker Yasin; Dörfler, Arnd; Engelhorn, Tobias; Schwab, Stefan; Huttner, Hagen (CEREBROVASCULAR DISEASES, 2019)
CRIS-Team WoS Importer:2020-02-21

In-hospital management of intracerebral hemorrhage Innerklinische Versorgung von intrazerebralen Blutungen - Sembill, Jochen; Schwab, Stefan (Medizinische Klinik - Intensivmedizin und Notfallmedizin, 2024)
Background: Intracerebral hemorrhage (ICH) is a medical emergency with high morbidity and mortality. General and specific therapeutic approaches aim to improve the patient’s outcome. Objectives: The objective of this article is to present the current scientific state regarding the in-hospital care of patients with ICH. Materials and methods: This narrative review presents and analyzes the current evidence regarding treatment options for ICH. Results: The primary focus of acute therapy is to prevent the prognostically unfavorable enlargement of the hematoma. This is associated with specific computed tomographic markers, as well as the initial hematoma volume, the use of anticoagulants, and a shorter time from symptom onset. An elevated blood pressure should be promptly and precisely lowered to a systolic value below 140 mm Hg, and the inhibition of coagulation must be immediately antagonized. This should be constituted into a treatment bundle with optimal adjustment of vital parameters and implementation of basic intensive care measures. Intraventricular hemorrhage can be effectively treated by external ventricular drainage and intraventricular fibrinolysis, with or without additional lumbar drainage. Minimally invasive procedures for hematoma removal have the potential to improve outcomes in lobar ICH. A realistic prognostic assessment forms the basis for informed treatment decisions regarding ICH. Conclusions: In recent years, the evidence supporting aggressive therapeutic approaches in ICH has become increasingly robust, with reliable results now available regarding the efficacy of individual or combined measures.
CRIS-Team Scopus Importer:2025-02-04
Keywords: Anticoagulants; Cerebral intraventricular hemorrhage; Critical care; Hypertension; Prognosis

Interferon Beta and vitamin d synergize to induce immunoregulatory receptors on peripheral blood monocytes of multiple sclerosis patients - Waschbisch, Anne; Sanderson, Nicholas; Krumbholz, Markus; Vlad, George; Theil, Diethilde; Schwab, Stefan; Mäurer, Mathias Eckhard; Derfuss, Tobias (PLoS ONE, 2014)
Immunoglobulin-like transcript (ILT) 3 and 4 are inhibitory receptors that modulate immune responses. Their expression has been reported to be affected by interferon, offering a possible mechanism by which this cytokine exerts its therapeutic effect in multiple sclerosis, a condition thought to involve excessive immune activity. To investigate this possibility, we measured expression of ILT3 and ILT4 on immune cells from multiple sclerosis patients, and in post-mortem brain tissue. We also studied the ability of interferon beta, alone or in combination with vitamin D, to induce upregulation of these receptors in vitro, and compared expression levels between interferon-treated and untreated multiple sclerosis patients. In vitro interferon beta treatment led to a robust upregulation of ILT3 and ILT4 on monocytes, and dihydroxyvitamin D3 increased expression of ILT3 but not ILT4. ILT3 was abundant in demyelinating lesions in postmortem brain, and expression on monocytes in the cerebrospinal fluid was higher than in peripheral blood, suggesting that the central nervous system milieu induces ILT3, or that ILT3 positive monocytes preferentially enter the brain. Our data are consistent with involvement of ILT3 and ILT4 in the modulation of immune responsiveness in multiple sclerosis by both interferon and vitamin D.
EVALuna2:22287

Intraventricular fibrinolysis does not increase perihemorrhagic edema after intracerebral hemorrhage - Volbers, Bastian; Wagner, Irina; Willfarth, Wolfgang; Dörfler, Arnd; Schwab, Stefan; Staykov, Dimitre (Stroke, 2013)
BACKGROUND AND PURPOSE - : Additional intraventricular hemorrhage leads to higher mortality and worse functional outcome after intracerebral hemorrhage (ICH). Intraventricular fibrinolysis (IVF) with recombinant tissue plasminogen activator (rtPA) is an emerging treatment strategy for such patients. However, experimental studies suggest that rtPA may exert proedematous effects and lead to increased perihemorrhagic edema (PHE) after ICH. We aimed to compare the course of PHE after ICH between patients who received IVF with rtPA and controls matched for ICH volume. METHODS - : Patients were identified retrospectively from our institutional ICH database. Sixty-four patients with ICH and intraventricular hemorrhage who were treated with IVF were compared with 64 controls, who did not receive IVF, matched for ICH volume. The course of PHE was assessed on computed tomography scans (day 1, days 2 and 3, days 4-6, 7-9, and 10-12) using a threshold-based semiautomatic volumetric algorithm. Relative PHE was calculated as a ratio of PHE volume and initial ICH volume. RESULTS - : The matching algorithm resulted in similar mean ICH volumes in both groups (20.01±17.5 mL, IVF vs 20.08±17.1 mL, control). Intraventricular hemorrhage volume was larger in the IVF group (26.8±19.2 mL vs 9.2±13.4 mL). The mean total rtPA dose used for IVF was 8±6 mg. PHE increased over time in both groups until day 12. At all investigated time points, there was no significant difference in relative PHE between the IVF group and controls (F=0.39; P=0.844). CONCLUSIONS - : IVF with rtPA did not lead to a relevant increase in PHE after ICH. rtPA doses used in the current study seem to be safe regarding PHE. © 2013 American Heart Association, Inc.
CRIS-Team Scopus Importer:2022-08-05
Keywords: intracerebral hemorrhage; intraventricular fibrinolysis; intraventricular hemorrhage; perihemorrhagicedema; recombinant tissue-type plasminogen activator; semiautomatic volumetry; X-ray computed tomography

Intraventricular fibrinolysis has no effects on shunt dependency and functional outcome in endovascular-treated aneurysmal SAH - Gerner, Stefan; Kuramatsu, Joji; Abel, Henning; Kloska, Stephan; Lücking, Hannes; Eyüpoglu, Ilker Yasin; Dörfler, Arnd; Schwab, Stefan; Huttner, Hagen (Neurocritical Care, 2014)
Intraventricular fibrinolysis (IVF) in subarachnoid hemorrhage (SAH) is an emerging strategy aiming to hasten clot lysis, treat hydrocephalus, and reduce permanent shunt rates. Because of clinical heterogeneity of investigated patient effects of IVF on permanent shunt incidence and functional outcome are widely debated. The present study is the first to investigate solely endovascular-treated SAH patients.Overall, 88 consecutive patients with aneurysmal SAH requiring external ventricular drain placement and endovascular aneurysm closure were included. Functional outcome and shunt dependency were assessed 90 days after event. A matched controlled sub-analysis was carried out to investigate the effects of IVF treatment (n = 14; matching criteria: age, neuro-status and imaging). Multivariate modeling was performed to identify independent predictors for permanent shunt dependency.In IVF-patients neurological status was significantly poorer [Hunt&Hess: IVF = 4(3-5) vs. non-IVF = 3(1-5); p = 0.035] and the extent of ventricular hemorrhage was increased [Graeb Score: IVF = 7(6-8) vs. non-IVF = 3(1-4); p <= 0.001]. Consecutive matched controlled sub-analysis revealed no significant therapeutic effect of IVF with respect to shunt dependency rate and functional outcome. Multivariate analysis revealed Graeb score [OR = 1.34(1.02-1.76); p = 0.035] and sepsis [OR = 11.23(2.28-55.27); p = 0.003] as independent predictors for shunt dependency, whereas IVF did not exert significant effects (p = 0.820).In endovascular-treated SAH patients IVF neither reduced permanent shunt dependency nor influenced functional outcome. Despite established effects on intraventricular clot resolution IVF appears less powerful in SAH as compared to ICH. Given the reported positive effects of lumbar drainage (LD) in SAH, a prospective analysis of a combined treatment approach of IVF and subsequent lumbar drain sOeems warranted aiming to reduce permanent shunting and improve functional outcome.
EVALuna2:22283

Invasiveness and Clinical Outcomes of Off-Hour Admissions in Patients with Intracerebral Hemorrhage - Mrochen, Anne; Sprügel, Maximilian; Gerner, Stefan; Madžar, Dominik; Kuramatsu, Joji; Lücking, Hannes; Schwab, Stefan; Huttner, Hagen; Hölter, Philip (Journal of Stroke and Cerebrovascular Diseases, 2019)
BACKGROUND: Whether time of hospital admission-during or outside regular working hours-affects functional outcome in intracerebral hemorrhage (ICH) is unestablished as previous analyses have focused on mortality only. We here investigate whether on- versus off-hour hospital admission in ICH is associated with levels of invasiveness and clinical outcomes. METHODS: Based on the UKER registry (NCT03183167) we grouped ICH-patients according to on- versus off-hour hospital admission. Primary outcome measures was functional outcome after 3 months using the modified Rankin scale (mRS) dichotomized into favorable (mRS = 0-3) and unfavorable (mRS = 4-6). Multivariate regression analyses were used to adjust for baseline imbalances, and subgroup analyses were performed to explore associations of on- versus off-hour admission with invasiveness of therapeutic interventions. RESULTS: A total of 438/1269 (34.5%) of ICH-patients were admitted during regular working hours. Mortality rates were not significantly different among patients with on- versus off-hour admission. On-hour patients showed a significantly larger proportion of patients with favorable outcome (on-hour: mRS = 0-3 after 3 months: 176/416 (42.3%) versus off-hour: 265/784 (33.8%); P = .004). Analysis of invasive therapeutic interventions revealed that likelihood of favorable outcome was significantly increased among on-hour admitted patients who did not require neurosurgical interventions (no external ventricular drain n = 349, OR: 1.67[1.13-2.48], P < .05; no hematoma evacuation surgery n = 423, OR: 1.51[1.07-2.14], P < .05). CONCLUSION: This study verified an "off-hour effect" in ICH that relates to functional outcome, rather than mortality, and which may be linked to different levels of invasive therapeutic interventions in patients admitted during off-hour.
EVALuna2:206735

Ischemic stroke and dose adjustment of oral Factor Xa inhibitors in patients with atrial fibrillation - Stoll, Svenja; Macha, Kosmas; Marsch, Armin; Gerner, Stefan; Siedler, Gabriela; Fröhlich, Kilian; Volbers, Bastian; Strasser, Erwin; Schwab, Stefan; Kallmünzer, Bernd (Journal of Neurology, 2020)
Background: Oral Factor Xa inhibitors for the prevention of stroke in atrial fibrillation require dose adjustment based on certain clinical criteria, but the off-label use of the reduced doses is common. Methods: Data from an observational registry including patients admitted with acute cerebral ischemia while taking oral Factor Xa inhibitors for atrial fibrillation between April 2016 and December 2018 were investigated. The dose regimen of the Xa inhibitor was classified as “appropriate”, “underdosed” and “overdosed” in conformity with the European Medicines Agency labelling. The effect of underdosing on the functional factor Xa plasma level on admission, the clinical stroke severity and the functional outcome after 3 months were investigated. Results: 254 patients with cerebral ischemia while on Factor Xa inhibitors were included. The dose regimen of the Factor Xa inhibitor was appropriate in 166 patients (65%), underdosed in 67 patients (26%) and overdosed in 21 patients (8%). Underdosing was associated with female sex, diabetes mellitus and higher CHA2DS2–Vasc scores. Underdosing independently predicted lower anti-Xa plasma levels on admission [median 69.4 ng/ml (IQR 0.0–121.6) vs. 129.2 ng/ml (65.5–207.2); p < 0.001], was associated with higher NIHSS scores on admission [median 5 (IQR 1–10) vs. 3 (1–7); p = 0.041] and worse functional outcome after 3 months (favorable outcome 26.9% vs. 46.9%; p = 0.025). Conclusion: One in three patients with ischemic stroke during treatment with oral Xa inhibitors used inappropriate dose regimens. Underdosing was associated with lower functional plasma levels, higher clinical stroke severity and worse functional outcome.
CRIS-Team Scopus Importer:2020-03-31
Keywords: Atrial fibrillation; Direct oral anticoagulants; Dose reduction; Plasma levels; Stroke

Ischemic stroke associated with the use of a synthetic cannabinoid (spice) - Möller, Sebastian; Luecke, Caroline; Struffert, Tobias; Schwarze, Bernhard; Gerner, Stefan; Schwab, Stefan; Köhrmann, Martin; Machold, Kristin; Philipsen, Alexandra; Mueller, Helge H. (Asian Journal of Psychiatry, 2017)
Synthetic cannabinoids, i.e. "spice", are psychoactive drugs with increasing use worldwide. Spice may have harmful neuropsychiatric and physical side effects. Here, we present the case of a 25-year-old man with ischemic stroke after smoking spice on the previous evening. Diagnostic work-up was negative for other common causes of stroke. Toxicology screen unveiled the cannabimimetic ADB-FUBINACA in the drug sample and in patient's urine. The cardiac sympathomimetic effect of spice might have triggered an unnoticed episode of tachyarrhythmia and resulted in stroke via cardioembolic etiology. Thus, in absence of other risk factors, a careful patient history of spice use is recommended for patients with acute neurological deficits.
EVALuna2:22545

Ischemic Stroke despite Oral Anticoagulant Therapy in Patients with Atrial Fibrillation - Seiffge, David J.; De Marchis, Gian Marco; Koga, Masatoshi; Paciaroni, Maurizio; Wilson, Duncan; Cappellari, Manuel; Macha, Kosmas; Tsivgoulis, Georgios; Ambler, Gareth; Arihiro, Shoji; Bonati, Leo H.; Bonetti, Bruno; et al. (Annals of neurology, 2020)
Objective: It is not known whether patients with atrial fibrillation (AF) with ischemic stroke despite oral anticoagulant therapy are at increased risk for further recurrent strokes or how ongoing secondary prevention should be managed. Methods: We conducted an individual patient data pooled analysis of 7 prospective cohort studies that recruited patients with AF and recent cerebral ischemia. We compared patients taking oral anticoagulants (vitamin K antagonists [VKA] or direct oral anticoagulants [DOAC]) prior to index event (OACprior) with those without prior oral anticoagulation (OACnaive). We further compared those who changed the type (ie, from VKA or DOAC, vice versa, or DOAC to DOAC) of anticoagulation (OACchanged) with those who continued the same anticoagulation as secondary prevention (OACunchanged). Time to recurrent acute ischemic stroke (AIS) was analyzed using multivariate competing risk Fine–Gray models to calculate hazard ratios (HRs) and 95% confidence intervals (CIs). Results: We included 5,413 patients (median age = 78 years [interquartile range (IQR) = 71–84 years]; 5,136 [96.7%] had ischemic stroke as the index event, median National Institutes of Health Stroke Scale on admission = 6 [IQR = 2–12]). The median CHA2DS2-Vasc score (congestive heart failure, hypertension, age≥ 75 years, diabetes mellitus, stroke/transient ischemic attack, vascular disease, age 65–74 years, sex category) was 5 (IQR = 4–6) and was similar for OACprior (n = 1,195) and OACnaive (n = 4,119, p = 0.103). During 6,128 patient-years of follow-up, 289 patients had AIS (4.7% per year, 95% CI = 4.2–5.3%). OACprior was associated with an increased risk of AIS (HR = 1.6, 95% CI = 1.2–2.3, p = 0.005). OACchanged (n = 307) was not associated with decreased risk of AIS (HR = 1.2, 95% CI = 0.7–2.1, p = 0.415) compared with OACunchanged (n = 585). Interpretation: Patients with AF who have an ischemic stroke despite previous oral anticoagulation are at a higher risk for recurrent ischemic stroke despite a CHA2DS2-Vasc score similar to those without prior oral anticoagulation. Better prevention strategies are needed for this high-risk patient group. ANN NEUROL 2020.
CRIS-Team Scopus Importer:2020-03-10

Is Hypothermia Helpful in Severe Subarachnoid Hemorrhage? An Exploratory Study on Macro Vascular Spasm, Delayed Cerebral Infarction and Functional Outcome after Prolonged Hypothermia - Kuramatsu, Joji; Kollmar, Rainer; Gerner, Stefan; Madzar, Dominik; Pisarcikova, Andrea; Staykov, Dimitre; Kloska, Stephan; Dörfler, Arnd; Eyüpoglu, Ilker Yasin; Schwab, Stefan; Huttner, Hagen (Cerebrovascular Diseases, 2015)
Therapeutic hypothermia (TH) is an established treatment after cardiac arrest and growing evidence supports its use as neuroprotective treatment in stroke. Only few and heterogeneous studies exist on the effect of hypothermia in subarachnoid hemorrhage (SAH). A novel approach of early and prolonged TH and its influence on key complications in poor-grade SAH, vasospasm and delayed cerebral ischemia (DCI) was evaluated.This observational matched controlled study included 36 poor-grade (Hunt and Hess Scale >3 and World Federation of Neurosurgical Societies Scale >3) SAH patients. Twelve patients received early TH (<48 h after ictus), mild (35°C), prolonged (7 ± 1 days) and were matched to 24 patients from the prospective SAH database. Vasospasm was diagnosed by angiography, macrovascular spasm serially evaluated by Doppler sonography and DCI was defined as new infarction on follow-up CT. Functional outcome was assessed at 6 months by modified Rankin Scale (mRS) and categorized as favorable (mRS score 0-2) versus unfavorable (mRS score 3-6) outcome.Angiographic vasospasm was present in 71.0% of patients. TH neither influenced occurrence nor duration, but the degree of macrovascular spasm as well as peak spastic velocities were significantly reduced (p < 0.05). Frequency of DCI was 87.5% in non-TH vs. 50% in TH-treated patients, translating into a relative risk reduction of 43% and preventive risk ratio of 0.33 (95% CI 0.14-0.77, p = 0.036). Favorable functional outcome was twice as frequent in TH-treated patients 66.7 vs. 33.3% of non-TH (p = 0.06).Early and prolonged TH was associated with a reduced degree of macrovascular spasm and significantly decreased occurrence of DCI, possibly ameliorating functional outcome. TH may represent a promising neuroprotective therapy possibly targeting multiple pathways of DCI development, notably macrovascular spasm, which strongly warrants further evaluation of its clinical impact.
EVALuna2:22357

Isolated meningomyeloradiculitis following infection with tick borne encephalitis virus - Racz, Attila; Schaller, Gerd; Lunkenheimer, Jens; Engelhorn, Tobias; Dörfler, Arnd; Sperling, Wolfgang; Schwab, Stefan; Maihöfner, Christian (Clinical Neurology and Neurosurgery, 2012)
CRIS-Team Scopus Importer:2022-08-05
Keywords: Meningomyeloradiculitis; Myelitis; Polyradiculitis; Tick borne encephalitis virus

It is all about timing: decompressive hemicraniectomy for malignant middle-cerebral-artery infarction - Macha, Kosmas; Schwab, Stefan (Arquivos De Neuro-Psiquiatria, 2023)
CRIS-Team Scopus Importer:2023-06-30

IV Thrombolysis for Acute Ischemic Stroke with Unknown Onset in Patients on Oral Anticoagulation - Macha, Kosmas; Sembill, Jochen; Mühlen, Iris; Engelhorn, Tobias; Dörfler, Arnd; Schwab, Stefan; Kallmünzer, Bernd (Cerebrovascular Diseases, 2024)
Introduction: IV thrombolysis (IVT) is established in the unknown or extended time window based on multimodal imaging. Further, increasing evidence exists regarding IVT in patients on oral anticoagulation including direct oral anticoagulants (DOACs). However, data on IVT in ischemic stroke patients on oral anticoagulation with unknown time of stroke onset are sparse. Methods: This study bases on the longitudinal cohort study Stroke Research Consortium in Northern Bavaria (STAMINA; ClinicalTrials.gov Identifier: NCT04357899). Acute ischemic stroke patients treated with IVT in the unknown or extended time window from January 2015 to December 2019 were included. Patient selection was based on multimodal CT or MRI. Patients on oral anticoagulation (vitamin-K antagonist [VKA] or DOAC within 48 h) were eligible for IVT based on INR measurement (VKA) or plasma levels (DOAC) according to an institutional protocol. Primary outcomes were the incidence of any and symptomatic intracranial hemorrhage. Results: Of 170 ischemic stroke patients treated with IVT in the unknown or extended time window, 151 had no oral anticoagulation at stroke onset and 19 were on oral anticoagulation (6 on VKA and 13 on DOAC). The risk of symptomatic ICH according to ECASS II criteria was similar between the patients with and without oral anticoagulation (1 [5.3%] vs. 4 [2.7%], p = 0.453). After adjustment for confounding factors, pre-medication with oral anticoagulation was not associated with symptomatic ICH (aOR 1.02 [0.09-11.02], p = 0.988). Conclusion: IVT for ischemic stroke with unknown onset appeared safe in selected patients on oral anticoagulation with both DOAC and VKA.
CRIS-Team Scopus Importer:2024-12-06
Keywords: Direct oral anticoagulant; Ischemic stroke; IV thrombolysis; Unknown onset; Vitamin-K antagonist

IV-Thrombolysis in Ischemic Stroke With Unknown Time of Onset—Safety and Outcomes in Posterior vs. Anterior Circulation Stroke - Macha, Kosmas; Hölter, Philip; Siedler, Gabriela; Wang, Ruihao; Knott, Michael; Stoll, Svenja; Engelhorn, Tobias; Dörfler, Arnd; Schwab, Stefan; Mühlen, Iris; Kallmünzer, Bernd (Frontiers in Neurology, 2021)
Background: rt-PA for ischemic stroke in the unknown or extended time window beyond the first 4. 5 h after symptom onset is safe and effective for certain patients after selection by multimodal neuroimaging. However, the evidence for this approach comes mainly from patients with anterior circulation stroke (ACS), while the data on posterior circulation stroke (PCS) are scarce. Methods: Ischemic stroke patients treated with IV-thrombolysis in the unknown or extended time window between January 2011 and May 2019 were identified from an institutional registry. The patients were categorized into PCS or ACS based on clinico-radiological findings. We analyzed the hemorrhagic complications, clinical and imaging efficacy outcomes, and mortality rates by comparing the PCS and ACS patient groups. Adjusted outcome analyses were performed after propensity score matching for the relevant factors. Results: Of the 182 patients included, 38 (20.9%) had PCS and 144 (79.1%) had ACS. Symptomatic acute large vessel occlusion (LVO) was present in 123 patients on admission [27 (22.0%) PCS and 96 (78.0%) ACS]. The score on the National Institutes of Health Stroke Scale (NIHSS), the time from last seen normal, and the door-to-needle times were similar in PCS and ACS. In patients with LVO, the NIHSS score was lower [8 (5–15) vs. 14 (9–18), p = 0.005], and infarction visible on follow-up imaging was less common [70.4 vs. 87.5%; aRD, −18.9% (−39.8 to −2.2%)] in the PCS patient group. There was a trend toward a lower risk for intracranial hemorrhage (ICH) following intravenous thrombolysis in PCS vs. ACS, without reaching a statistical significance [5.3 vs. 16.9%; aRD, −10.4% (−20.4 to 4.0%)]. The incidence of symptomatic ICH [according to the ECASS III criteria: 2.6 vs. 3.5%; aRD, −2.9% (−10.3 to 9.2%)], efficacy outcomes, and mortality rates were similar in PCS and ACS patients. Conclusions: In this real-world clinical cohort, the safety and the efficacy of rt-PA for ischemic stroke in the unknown or extended time window did not show relevant differences between PCS and ACS, with a trend toward less hemorrhagic complications in PCS. The findings reconfirm the clinician in the usage of rt-PA beyond the first 4.5 h also in selected patients with PCS.
CRIS-Team Scopus Importer:2021-10-01
Keywords: anterior circulation stroke; extended time window; IV-thrombolysis; posterior circulation stroke; wake-up stroke

Lesion correlates of secondary paroxysmal dyskinesia in multiple sclerosis - Fröhlich, Katharina; Winder, Klemens; Linker, Ralf; Huhn, Konstantin; Engelhorn, Tobias; Dörfler, Arnd; Lee, De-Hyung; Schwab, Stefan; Seifert, Frank (Journal of Neurology, 2018)
Secondary paroxysmal dyskinesia is a rare but life-quality-compromising symptom in multiple sclerosis (MS) and might be associated with particular MS lesions. The present study intended to determine associations between paroxysmal dyskinesia and the MS-associated lesion site using a voxelwise lesion analysis. We conducted a retrospective study and sought MS patients with documented paroxysmal dyskinesia and controls without paroxysmal dyskinesia matched for age, disease severity, and disease duration in a local database. The MS lesions were analysed on T2-weighted magnetic resonance imaging scans (1.5 or 3 T), manually outlined, and transformed into stereotaxic space. We determined the lesion overlap and compared the absence or presence of paroxysmal dyskinesia voxelwise between patients with and without lesions in a given voxel using the Liebermeister test with 4000 permutations. From 15,869 MS patient records screened, we identified 25 patients with paroxysmal dyskinesia. The voxelwise analysis in 22 subjects yielded associations between paroxysmal dyskinesia and MS lesions in the internal capsule, the basal ganglia, and another prominent lesion cluster in the posterior periventricular white matter. Our voxelwise analysis shows associations between paroxysmal dyskinesia and MS lesions in the internal capsule and basal ganglia, areas contributing to motor sequence programming. This association in another lesion site located in the posterior thalamic radiation suggests that lesions in subcortical sensory pathways may also contribute to paroxysmal dyskinesia in MS.
EVALuna2:34912

Lesion mapping of stroke-related erectile dysfunction - Winder, Klemens; Seifert, Frank; Köhrmann, Martin; Crodel, Carl; Kloska, Stephan; Dörfler, Arnd; Hoesl, Katharina M.; Schwab, Stefan; Hilz, Max-Josef (Brain, 2017)
Acute ischaemic stroke in brain areas contributing to male sexual function may impair erectile function depending on the lesion site. This study intended to determine associations between stroke-related erectile dysfunction and cerebral ischaemic lesion sites using voxel-based lesion mapping. In 52 males (mean age 60.5 ± 10.5 years) with first-ever ischaemic strokes, we assessed erectile function after and retrospectively 3 months prior to the stroke using scores of the 5-item International Index of Erectile Function-5 questionnaire. We assessed cardiovascular risk factors and determined clinical stroke severity and infarct volumes as well as total brain volume by neuroimaging. We calculated correlations between patient age, clinical stroke severity, infarct volumes as well as brain volumes and the difference between erectile dysfunction scores before and after stroke. Moreover, we compared patient age, prevalence of cardiovascular risk factors, clinical stroke severity, infarct volumes and brain volumes of patients with unchanged and deteriorated erectile function after stroke. The infarcts were manually outlined and transformed into stereotaxic space. We determined the lesion overlap and performed subtraction analyses of lesions. In a voxel-based lesion analysis, the difference between erectile dysfunction scores before and after stroke was correlated with the lesion site using t-test statistics. Finally, we conducted a region of interest-based multivariate linear regression analysis that was adjusted for potential confounding factors including patient age, clinical stroke severity, imaging modality, lesion size and brain volume. In 32 patients (61.5%) erectile dysfunction scores declined after the stroke and therefore had stroke-related erectile dysfunction. Deterioration of erectile dysfunction scores was not associated with patient age, clinical stroke severity, infarct volume, brain volume, and cardiovascular risk factors. The voxel-wise subtraction analysis showed associations between stroke-related erectile dysfunction and lesion sites in the right occipito-parietal cortex and thalamus, as well as in the left insula and adjacent temporo-parietal areas. Using voxel-wise t-test statistics, we showed associations between deterioration of erectile function and lesion sites in the right occipital and thalamic region, and the left parietal association area. The linear regression analysis showed that stroke-related erectile dysfunction remained associated with lesions of the right occipital and left parietal association areas after adjusting for confounding factors. In conclusion, our voxel-wise analysis indicates that deteriorating erectile function after stroke is associated with lesions in the right occipito-parietal and thalamic areas integrating visual and somatosensory information, as well as lesions in the left insular and adjacent parieto-temporal areas contributing to generating and mapping visceral arousal states.
EVALuna2:22497

Letter by Kallmünzer et al Regarding Article, "safety of Intravenous Thrombolysis among Patients Taking Direct Oral Anticoagulants: A Systematic Review and Meta-Analysis" - Kallmünzer, Bernd; Pott, Michael; Schwab, Stefan (Stroke, 2020)
CRIS-Team Scopus Importer:2020-07-17

Limited versus Whole-Brain Perfusion for the Indication of Thrombolysis in the Extended Time Window of Acute Cerebral Ischemia - Breuer, Lorenz; Knott, Michael; Struffert, Tobias; Kloska, Stephan; Kurka, Natalia; Schwab, Stefan; Dörfler, Arnd; Köhrmann, Martin; Engelhorn, Tobias (Journal of Stroke and Cerebrovascular Diseases, 2015)
Perfusion computed tomography (PCT) has emerged as alternative to magnetic resonance imaging (MRI) for assessment of patients clinically qualifying for off-label thrombolysis within 4.5 to 9 hours after onset of ischemic stroke. However, disadvantage of PCT is its often limited anatomic coverage with only 2 or 3 slices when using a 4- to 64-section scanner. Our purpose was therefore to evaluate the value of 2- and 3-slice perfusion compared to whole-brain perfusion.One hundred twenty-five patients undergoing MRI beyond 4.5 hours after symptom onset with supratentorial perfusion deficit were selected retrospectively. Accordingly to PCT slice positioning, 2 or 3 slices of the whole-brain perfusion weighted imaging data set were depicted. Volumes of infarct (using cerebral blood volume) and penumbra (using time-to-peak and cerebral blood volume) were calculated, and results were compared with 2- and 3-slice-derived volumes, respectively.Whole-brain imaging revealed a mismatch of more than 20% in 68.8% of patients (defined as 100%). Two-slice imaging detected a perfusion deficit in 72% and a mismatch in 48.8% (sensitivity = 70.9%). Three-slice imaging detected a perfusion deficit in 76% and a mismatch in 50.4% (sensitivity = 73.3%). Although there was no significant difference between 2- and 3-slice imaging (P > .23), both techniques revealed significantly less patients with mismatch compared to whole-brain coverage (P < .01).Two- and 3-slice imaging like obtained with PCT on most installed CT systems to assess perfusion deficits with subsequent mismatch calculation in acute stroke outside the 4.5-hour time window is significantly inferior to whole-brain coverage and, hence, has to be considered as a less-than-ideal solution.
EVALuna2:22358

Liquorpunktion – Schritt für Schritt - Siedler, Gabriela; Kallmünzer, Bernd; Schwab, Stefan (Deutsche Medizinische Wochenschrift, 2019)
Performing a diagnostic lumbar puncture is an essential clinical skill for the clinician. The procedure is of high importance for both, the emergency care for patients with suspected infection of the cerebral nervous system or subarachnoidal hemorrhage, as well as the elective diagnostic work up of chronic disease including multiple sclerosis and dementia. Furthermore the technique's principles are applied for spinal anesthesia or the intrathecal administration of drugs. This article describes a Standard Operating Procedure for the lumbar puncture step by step. Based on the latest evidence, it particularly focusses on clinically relevant questions and practical aspects.
CRIS-Team Scopus Importer:2019-10-08
Keywords: atraumatic needle; cerebrospinal fluid analysis; diagnostic lumbar puncture; post-lumbar; puncture headache

Long-term outcome after epilepsy surgery in older adults - Lang, Johannes D.; Grell, Laura; Hagge, Mareike; Onugoren, Muejgan Dogan; Gollwitzer, Stephanie; Graf, Wolfgang; Schwarz, Michael; Coras, Roland; Blümcke, Ingmar; Sommer, Bjoern; Roessler, Karl; Buchfelder, Michael; et al. (Seizure-European Journal of Epilepsy, 2018)
PURPOSE: The incidence of epilepsy in older adults is growing, as does the incidence of comorbidities. Therefore, when it comes to epilepsy surgery in medically intractable epilepsy, age is often seen as a limiting factor. To investigate the outcome after epilepsy surgery in a population of older adults, we compared the benefit for patients aged 50-59 years with those aged 60 years and older in respect of efficacy and safety. METHOD: Patients aged ≥50 years with medically intractable epilepsy who underwent epilepsy surgery from 1990 to 2013 were selected from the database of a German epilepsy center. All of them received a standardised and detailed presurgical diagnostic evaluation. Follow-up included at least four scheduled visits with EEG, MRI and neuropsychological testing. Outcome was assessed using the Engel outcome scale. RESULTS: 79 patients aged between 50 and 67 years were followed-up for a median of 4.7 years (2-16 years). 68% of patients were free of disabling seizures (Engel class I, ≥60 years: 75%) and 58% were seizure-free (Engel class IA, ≥60 years: 70%). 90% of our patients suffered from temporal lobe epilepsy (TLE), 9% from frontal lobe epilepsy (FLE) and one occipital lobe epilepsy (OLE). After surgery, 9% discontinued or tapered their medication. Permanent surgical complications occurred in 10% of cases and transient neurological deficits were seen in 11%. Older patients had a higher risk for postoperative hygroma (≥60 years 15%; <60 years 8%) and were more prone to postoperative memory deficits (≥60 years 45%), especially after resection of the dominant temporal lobe. Verbal and figural memory testing did not differ significantly between the groups. CONCLUSIONS: The results support the view that in selected older patients, epilepsy surgery shows equal or even higher success rates as compared to younger patients. However, patients of older age may be at greater risk for postoperative hygroma and memory deficits, especially after dominant temporal lobe resections.
EVALuna2:34593

Long-Term Survival, Burden of Disease, and Patient-Centered Outcomes in Maximally Treated Intracerebral Hemorrhage - Mrochen, Anne; Sprügel, Maximilian; Sekita, Alexander; Balk, Stefanie; Haupenthal, David; Gerner, Stefan; Lücking, Hannes; Dörfler, Arnd; Macha, Kosmas; Schwab, Stefan; Kuramatsu, Joji; Sembill, Jochen (Annals of Clinical and Translational Neurology, 2025)
Objective: Increasing evidence shows that patients with intracerebral hemorrhage (ICH) can achieve better-than-expected outcomes with aggressive therapy. However, real-world long-term data, patient-centered outcomes, and societal measures after maximal ICH treatment are lacking. This study aimed to analyze 5-year survival, utility-weighted functional outcomes, and burden of disease in maximally treated ICH patients, stratified by max-ICH Score. Methods: This study investigated consecutive patients with spontaneous ICH included in the single-center Longitudinal Cohort Study on ICH Care (UKER-ICH, NCT03183167, 2006–2015). We included all patients without early care limitations, hereinafter referred to as maximally treated. We analyzed the stratification by max-ICH Score of cumulative 5-year survival using Kaplan–Meier estimates and COX regression modeling, disease burden using disability-adjusted life years (DALYs), and patient-centered outcome at 12 months using the Utility-Weighted modified Rankin Scale (UW-mRS). Results: The 5-year survival rate of the included 1022 maximally treated patients was 53%, stratified by max-ICH Score (0 points: 85%, 1: 91%, 2: 69%, 3: 59%, 4: 47%, 5: 32%, 6: 29%, 7: 18%, ≥ 8: 0%, log-rank p < 0.001). The mean number of DALYs was 8.94 (±8.15, standard deviation [SD]), consisting of 4.27 years of life lost (±7.79, SD) and 4.67 years lived with disability (±6.38, SD). Patients with a max-ICH Score of 5 had the highest burden of disease (12.76 [±9.43, SD]). The mean UW-mRS at 12 months was 0.45 (±0.37, SD) and decreased with increasing max-ICH Score (0: 0.80 [±0.23], 1: 0.73 [±0.29], 2: 0.67 [±0.29], 3: 0.50 [±0.34], 4: 0.39 [±0.34], 5: 0.25 [±0.30], 6: 0.19 [±0.28], 7: 0.16 [±0.26], ≥ 8: 0.08 [±0.22], p < 0.001). Interpretation: These observational data, stratified by max-ICH Score, provide patients and treating physicians with an initial severity assessment in terms of potential long-term patient-centered outcomes and burden of disease following maximal treatment.
CRIS-Team Scopus Importer:2025-04-25
Keywords: intracerebral hemorrhage prognosis; patient-centered outcomes; stroke disability burden

Magnetoencephalography for epileptic focus localization in a series of 1000 cases. - Rampp, Stefan; Stefan, Hermann; Wu, Xintong; Kaltenhäuser, Martin; Maess, Burkhard; Schmitt, Friedhelm C.; Wolters, Carsten H.; Hamer, Hajo; Kasper, Burkhard S.; Schwab, Stefan; Blümcke, Ingmar; Rössler, Karl; et al. (Brain, 2019)
The aim of epilepsy surgery in patients with focal, pharmacoresistant epilepsies is to remove the complete epileptogenic zone to achieve long-term seizure freedom. In addition to a spectrum of diagnostic methods, magnetoencephalography focus localization is used for planning of epilepsy surgery. We present results from a retrospective observational cohort study of 1000 patients, evaluated using magnetoencephalography at the University Hospital Erlangen over the time span of 28 years. One thousand consecutive cases were included in the study, evaluated at the University Hospital Erlangen between 1990 and 2018. All patients underwent magnetoencephalography as part of clinical workup for epilepsy surgery. Of these, 405 underwent epilepsy surgery after magnetoencephalography, with postsurgical follow-ups of up to 20 years. Sensitivity for interictal epileptic activity was evaluated, in addition to concordance of localization with the consensus of presurgical workup on a lobar level. We evaluate magnetoencephalography characteristics of patients who underwent epilepsy surgery versus patients who did not proceed to surgery. In operated patients, resection of magnetoencephalography localizations were related to postsurgical seizure outcomes, including long-term results after several years. In comparison, association of lesionectomy with seizure outcomes was analysed. Measures of diagnostic accuracy were calculated for magnetoencephalography resection and lesionectomy. Sensitivity for interictal epileptic activity was 72% with significant differences between temporal and extra-temporal lobe epilepsy. Magnetoencephalography was concordant with the presurgical consensus in 51% and showed additional or more focal involvement in an additional 32%. Patients who proceeded to surgery showed a significantly higher percentage of monofocal magnetoencephalography results. Complete magnetoencephalography resection was associated with significantly higher chances to achieve seizure freedom in the short and long-term. Diagnostic accuracy was significant in temporal and extra-temporal lobe cases, but was significantly higher in extra-temporal lobe epilepsy (diagnostic odds ratios of 4.4 and 41.6). Odds ratios were also higher in non-lesional versus lesional cases (42.0 versus 6.2). The results show that magnetoencephalography provides non-redundant information, which significantly contributes to patient selection, focus localization and ultimately long-term seizure freedom after epilepsy surgery. Specifically in extra-temporal lobe epilepsy and non-lesional cases, magnetoencephalography provides excellent accuracy.
EVALuna2:204465

Magnetoencephalography for epileptic focus localization in a series of 1000 cases - Rampp, Stefan; Stefan, Hermann; Wu, Xueqing; Kaltenhäuser, Martin; Maess, Burkhard; Schmitt, Friedhelm C.; Wolters, Carsten H.; Hamer, Hajo; Kasper, Burkhard; Schwab, Stefan; Dörfler, Arnd; Blümcke, Ingmar; et al. (Brain, 2019)
The aim of epilepsy surgery in patients with focal, pharmacoresistant epilepsies is to remove the complete epileptogenic zone to achieve long-term seizure freedom. In addition to a spectrum of diagnostic methods, magnetoencephalography focus localization is used for planning of epilepsy surgery. We present results from a retrospective observational cohort study of 1000 patients, evaluated using magnetoencephalography at the University Hospital Erlangen over the time span of 28 years. One thousand consecutive cases were included in the study, evaluated at the University Hospital Erlangen between 1990 and 2018. All patients underwent magnetoencephalography as part of clinical workup for epilepsy surgery. Of these, 405 underwent epilepsy surgery after magnetoencephalography, with postsurgical follow-ups of up to 20 years. Sensitivity for interictal epileptic activity was evaluated, in addition to concordance of localization with the consensus of presurgical workup on a lobar level. We evaluate magnetoencephalography characteristics of patients who underwent epilepsy surgery versus patients who did not proceed to surgery. In operated patients, resection of magnetoencephalography localizations were related to postsurgical seizure outcomes, including long-term results after several years. In comparison, association of lesionectomy with seizure outcomes was analysed. Measures of diagnostic accuracy were calculated for magnetoencephalography resection and lesionectomy. Sensitivity for interictal epileptic activity was 72% with significant differences between temporal and extra-temporal lobe epilepsy. Magnetoencephalography was concordant with the presurgical consensus in 51% and showed additional or more focal involvement in an additional 32%. Patients who proceeded to surgery showed a significantly higher percentage of monofocal magnetoencephalography results. Complete magnetoencephalography resection was associated with significantly higher chances to achieve seizure freedom in the short and long-term. Diagnostic accuracy was significant in temporal and extra-temporal lobe cases, but was significantly higher in extra-temporal lobe epilepsy (diagnostic odds ratios of 4.4 and 41.6). Odds ratios were also higher in non-lesional versus lesional cases (42.0 versus 6.2). The results show that magnetoencephalography provides non-redundant information, which significantly contributes to patient selection, focus localization and ultimately long-term seizure freedom after epilepsy surgery. Specifically in extra-temporal lobe epilepsy and non-lesional cases, magnetoencephalography provides excellent accuracy.
CRIS-Team Scopus Importer:2019-10-08
Keywords: epilepsy; epilepsy surgery; long-term outcome; magnetic source imaging; magnetoencephalography

MANAGEMENT OF INSUFFICIENT FUNCTIONAL ANTITHROMBOTIC ACTIVITY DURING TREATMENT WITH DIRECT ORAL ANTICOAGULANTS FOR STROKE PREVENTION - Macha, Kosmas; Stoll, Svenja; Siedler, Gabriela; Volbers, Bastian; Strasser, Erwin; Schwab, Stefan; Kallmünzer, Bernd (INTERNATIONAL JOURNAL OF STROKE, 2020)
CRIS-Team WoS Importer:2021-01-22

Management of Stroke in Patients with Left Ventricular Assist Devices - Giede-Jeppe, Antje; Röder, Sebastian; Macha, Kosmas; Huttner, Hagen; Gerner, Stefan; Fröhlich, Kilian; Heim, Christian; Schwab, Stefan; Kallmünzer, Bernd (Journal of Stroke and Cerebrovascular Diseases, 2020)
Introduction: The number of patients with left ventricular assist devices (LVAD) is rapidly growing in industrialized countries. While cerebrovascular events comprise a significant complication, data on stroke etiology, clinical management and functional outcome are scarce. Methods: Consecutive LVAD patients with ischemic or hemorrhagic stroke receiving treatment at an university stroke center between 2010 and 2018 were included into an institutional registry. Clinical characteristics, causes, management and functional outcome of stroke occurring within this cohort are reported. Acceptable functional outcome was defined as mRS 0-3. Results: N = 30 acute strokes occurred in 20 patients (77% ischemic, 23% hemorrhagic, mean age 57 ± 13 years, 10% female, 8 patients (40%) had more than one event). 87% of all events happened with non-pulsatile devices, on average 9 (IQR 3-22) months after the implantation. All patients used oral anticoagulation with a Vitamin-K antagonist in combination with anti-platelets. The international normalized ratio (INR)-values were outside the therapeutic range in 39% of ischemic strokes and in 57% of hemorrhagic strokes. Ischemic strokes were predominantly of cardioembolic origin (92%) and of mild to moderate clinical severity (median NIHSS 6 (IQR 4-10). None qualified to receive intravenous thrombolysis or intra-arterial endovascular therapy. 61% of IS-patients showed an acceptable functional outcome after three months. 4/7 patients with hemorrhagic stroke received immediate reversal of anticoagulation without any thrombotic complications. Conclusion: The majority of LVAD patients with ischemic stroke had an acceptable functional outcome after three months. Future clinical research is warranted to improve therapeutic strategies for acute care and stroke prevention.
CRIS-Team Scopus Importer:2020-08-21
Keywords: Functional outcome; Intracerebral hemorrhage; Ischemic stroke; Left ventricular assist devices

Management of therapeutic anticoagulation in patients with intracerebral haemorrhage and mechanical heart valves - Kuramatsu, Joji; Sembill, Jochen; Gerner, Stefan; Sprügel, Maximilian; Hagen, Manuel; Röder, Sebastian; Endres, Matthias; Haeusler, Karl Georg; Sobesky, Jan; Schurig, Johannes; Zweynert, Sarah; Bauer, Miriam; et al. (European Heart Journal, 2018)
Aims Evidence is lacking regarding acute anticoagulation management in patients after intracerebral haemorrhage (ICH) with implanted mechanical heart valves (MHVs). Our objective was to investigate anticoagulation reversal and resumption strategies by evaluating incidences of haemorrhagic and thromboembolic complications, thereby defining an optimal time-window when to restart therapeutic anticoagulation (TA) in patients with MHV and ICH. Methods and results We pooled individual patient- data (n = 2504) from a nationwide multicentre cohort-study (RETRACE, conducted at 22 German centres) and eventually identified MHV-patients (n = 137) with anticoagulation-associated ICH for outcome analyses. The primary outcome consisted of major haemorrhagic complications analysed during hospital stay according to treatment exposure (restarted TA vs. no-TA). Secondary outcomes comprised thromboembolic complications, the composite outcome (haemorrhagic and thromboembolic complications), timing of TA, and mortality. Adjusted analyses involved propensity-score matching and multivariable cox-regressions to identify optimal timing of TA. In 66/137 (48%) of patients TA was restarted, being associated with increased haemorrhagic (TA = 17/66 (26%) vs. no-TA = 4/71 (6%); P < 0.01) and a trend to decreased thromboembolic complications (TA = 1/66 (2%) vs. no-TA = 7/71 (10%); P = 0.06). Controlling treatment crossovers provided an incidence rate-ratio [hazard ratio (HR) 10.31, 95% confidence interval (CI) 3.67-35.70; P < 0.01] in disadvantage of TA for haemorrhagic complications. Analyses of TA-timing displayed significant harm until Day 13 after ICH (HR 7.06, 95% CI 2.33-21.37; P < 0.01). The hazard for the composite-balancing both complications, was increased for restarted TA until Day 6 (HR 2.51, 95% CI 1.10-5.70; P = 0.03). Conclusion Restarting TA within less than 2 weeks after ICH in patients with MHV was associated with increased haemorrhagic complications. Optimal weighing-between least risks for thromboembolic and haemorrhagic complications-provided an earliest starting point of TA at Day 6, reserved only for patients at high thromboembolic risk.
EVALuna2:34917

MEG Node Degree Differences in Patients with Focal Epilepsy vs. Controls-Influence of Experimental Conditions - Vogel, Stephan; Kaltenhaeuser, Martin; Kim, Cora; Müller-Voggel, Nadia; Rössler, Karl; Dörfler, Arnd; Schwab, Stefan; Hamer, Hajo; Buchfelder, Michael; Rampp, Stefan (Brain Sciences, 2021)
Drug-resistant epilepsy can be most limiting for patients, and surgery represents a viable therapy option. With the growing research on the human connectome and the evidence of epilepsy being a network disorder, connectivity analysis may be able to contribute to our understanding of epilepsy and may be potentially developed into clinical applications. In this magnetoencephalographic study, we determined the whole-brain node degree of connectivity levels in patients and controls. Resting-state activity was measured at five frequency bands in 15 healthy controls and 15 patients with focal epilepsy of different etiologies. The whole-brain all-to-all imaginary part of coherence in source space was then calculated. Node degree was determined and parcellated and was used for further statistical evaluation. In comparison to controls, we found a significantly higher overall node degree in patients with lesional and non-lesional epilepsy. Furthermore, we examined the conditions of high/reduced vigilance and open/closed eyes in controls, to analyze whether patient node degree levels can be achieved. We evaluated intraclass-correlation statistics (ICC) to evaluate the reproducibility. Connectivity and specifically node degree analysis could present new tools for one of the most common neurological diseases, with potential applications in epilepsy diagnostics.
CRIS-Team WoS Importer:2022-01-07

Meningioma growth dynamics assessed by radiocarbon retrospective birth dating - Huttner, Hagen B.; Bergmann, Olaf; Salehpour, Mehran; El Cheikh, Raouf; Nakamura, Makoto; Tortora, Angelo; Heinke, Paula; Coras, Roland; Englund, Elisabet; Eyüpoglu, Ilker Yasin; Kuramatsu, Joji; Röder, Sebastian; et al. (EBioMedicine, 2018)
It is not known how long it takes from the initial neoplastic transformation of a cell to the detection of a tumor, which would be valuable for understanding tumor growth dynamics. Meningiomas show a broad histological, genetic and clinical spectrum, are usually benign and considered slowly growing. There is an intense debate regarding their age and growth pattern and when meningiomas should be resected. We have assessed the age and growth dynamics of 14 patients with meningiomas (WHO grade I: n=6 with meningothelial and n=6 with fibrous subtype, as well as n=2 atypical WHO grade II meningiomas) by combining retrospective birth-dating of cells by analyzing incorporation of nuclear-bomb-test-derived 14C, analysis of cell proliferation, cell density, MRI imaging and mathematical modeling. We provide an integrated model of the growth dynamics of benign meningiomas. The mean age of WHO grade I meningiomas was 22.1±6.5years, whereas atypical WHO grade II meningiomas originated 1.5±0.1years prior to surgery (p<0.01). We conclude that WHO grade I meningiomas are very slowly growing brain tumors, which are resected in average two decades after time of origination.
EVALuna2:34031

Mild prolonged hypothermia for large intracerebral hemorrhage - Staykov, Dimitre; Wagner, Irina; Volbers, Bastian; Dörfler, Arnd; Schwab, Stefan; Kollmar, Rainer (Neurocritical Care, 2013)
Background: Perihemorrhagic edema (PHE) develops after intracerebral hemorrhage (ICH). It can worsen the clinical situation by its additional mass effect. Therapeutic hypothermia (TH) might be an effective method to control PHE, but has not been sufficiently studied in ICH patients. Methods: We report data on n = 25 consecutive patients with large supratentorial ICH (volume > 25 ml) who were treated by mild TH of 35 C for 8-10 days. Body temperature was controlled by endovascular cooling catheters. We followed the clinical course during hospital stay and measured volumes of ICH and PHE in regularly performed serial cranial computed tomography. Outcome was assessed after 3 and 12 months. These data were compared to a historical group of n = 25 patients with large ICH. Results: While PHE continuously increased in the historical control group up to day 10, PHE volumes in the hypothermia group remained stable. There was a significant difference from day 3 after symptom onset. Shivering (36 %) and pneumonia (96 %) were the most frequent complications during TH. Mortality rate was 8.3 % in TH versus 16.7 % in the control group after 3 months and 28 versus 44 % after 1 year. Conclusions: These data support the promising results of our first case series on TH in large ICH. TH prevents the development of PHE and its complications. Side effects of TH appeared often, but could be treated sufficiently. Therefore, TH might represent a new therapy for PHE after large ICH, but has to be further tested in randomized trials. © 2012 Springer Science+Business Media, LLC.
CRIS-Team Scopus Importer:2022-08-05
Keywords: Hypothermia; Intracerebral hemorrhage; Perihemorrhagic edema

Monitoring in the follow up of patients after EVT. Could pupillometry replace repetitive CT-control? - Köhn, Julia; Borutta, Matthias; Giede-Jeppe, Antje; Hagen, Manuel; Kuramatsu, Joji; Schwab, Stefan; Huttner, Hagen (Journal für Anasthesie und Intensivbehandlung, 2021)
CRIS-Team Scopus Importer:2024-12-16

Monitoring of direct oral anticoagulants plasma levels for secondary stroke prevention - Siedler, Gabriela; Macha, Kosmas; Stoll, Svenja; Plechschmidt, Johannes; Wang, Ruihao; Gerner, Stefan; Strasser, Erwin; Schwab, Stefan; Kallmünzer, Bernd (Journal of Thrombosis and Haemostasis, 2022)
Background: Patients with atrial fibrillation have a relevant risk for ischemic stroke despite the recommended use of direct oral anticoagulants (DOAC). The risk correlates with the functional DOAC plasma levels in clinical trials, but the value of their measurement in community use remains undetermined. Objectives: We aim to investigate the clinical implications and the prognostic value of DOAC plasma level measurement during steady state. Methods: In this observational clinical cohort study among patients with ischemic stroke and atrial fibrillation, 397 individuals on oral anticoagulants for secondary stroke prevention were included between 2016 and 2020. The functional DOAC plasma levels were measured during steady state. Early stroke recurrence within 3 months was recorded as the main outcome parameter. Results: Three hundred ninety-seven patients (201 female, mean age 78 [±9] years, median CHA2DS2VASc-Score 6 [interquartile range 5–7]) were included. Mean DOAC plasma trough level was 95.9 (±66.9) ng/ml. A high glomerular filtration rate (GFR) was an independent predictor of lower levels in a multivariate model (R coefficient: −0.174, P =.014). During follow-up, 10 patients (3%) suffered from early ischemic stroke recurrence despite the use of DOAC, while 10 clinically relevant bleeding complications occurred (3%). Ischemic stroke recurrence was associated with numerical lower plasma levels for patients on apixaban and dabigatran after propensity score matching. Conclusions: Monitoring of DOAC plasma levels could help to identify patients with increased risk for stroke recurrence and should be considered for certain subgroups, including patients with high GFR.
CRIS-Team Scopus Importer:2022-03-18
Keywords: atrial fibrillation; cardioembolic stroke; direct oral anticoagulants; ischemic stroke; secondary prevention

Multicenter Validation of the max-ICH Score in Intracerebral Hemorrhage - Sembill, Jochen; Castello, Juan P.; Sprügel, Maximilian; Gerner, Stefan; Lücking, Hannes; Dörfler, Arnd; Schwab, Stefan; Huttner, Hagen; Biffi, Alessandro; Kuramatsu, Joji; Hölter, Philip (Annals of Neurology, 2020)
Objective: Outcome prognostication unbiased by early care limitations (ECL) is essential for guiding treatment in patients presenting with intracerebral hemorrhage (ICH). The aim of this study was to determine whether the max-ICH (maximally treated ICH) Score provides improved and clinically useful prognostic estimation of functional long-term outcomes after ICH. Methods: This multicenter validation study compared the prognostication of the max-ICH Score versus the ICH Score regarding diagnostic accuracy (discrimination and calibration) and clinical utility using decision curve analysis. We performed a joint investigation of individual participant data of consecutive spontaneous ICH patients (n = 4,677) from 2 retrospective German-wide studies (RETRACE I + II; anticoagulation-associated ICH only) conducted at 22 participating centers, one German prospective single-center study (UKER-ICH; nonanticoagulation-associated ICH only), and 1 US-based prospective longitudinal single-center study (MGH; both anticoagulation- and nonanticoagulation-associated ICH), treated between January 2006 and December 2015. Results: Of 4,677 included ICH patients, 1,017 (21.7%) were affected by ECL (German cohort: 15.6% [440 of 2,377]; MGH: 31.0% [577 of 1,283]). Validation of long-term functional outcome prognostication by the max-ICH Score provided good and superior discrimination in patients without ECL compared with the ICH Score (area under the receiver operating curve [AUROC], German cohort: 0.81 [0.78–0.83] vs 0.74 [0.72–0.77], p < 0.01; MGH: 0.85 [0.81–0.89] vs 0.78 [0.74–0.82], p < 0.01), and for the entire cohort (AUROC, German cohort: 0.84 [0.82–0.86] vs 0.80 [0.77–0.82], p < 0.01; MGH: 0.83 [0.81–0.85] vs 0.77 [0.75–0.79], p < 0.01). Both scores showed no evidence of poor calibration. The clinical utility investigated by decision curve analysis showed, at high threshold probabilities (0.8, aiming to avoid false-positive poor outcome attribution), that the max-ICH Score provided a clinical net benefit compared with the ICH Score (14.1 vs 2.1 net predicted poor outcomes per 100 patients). Interpretation: The max-ICH Score provides valid and improved prognostication of functional outcome after ICH. The associated clinical net benefit in minimizing false poor outcome attribution might potentially prevent unwarranted care limitations in patients with ICH. ANN NEUROL 2020.
CRIS-Team Scopus Importer:2020-12-25

Multimodal CT or MRI for IV thrombolysis in ischemic stroke with unknown time of onset - Macha, Kosmas; Hölter, Philip; Siedler, Gabriela; Knott, Michael; Schwab, Stefan; Dörfler, Arnd; Kallmünzer, Bernd; Engelhorn, Tobias (Neurology, 2020)
OBJECTIVE: To investigate differences in procedure times, safety, and efficacy outcomes comparing 2 different protocols to enable thrombolysis in the extended or unknown time window after stroke onset with either multimodal CT or MRI. METHODS: Patients with ischemic stroke in the extended or unknown time window who received IV thrombolysis between January 2011 and May 2019 were identified from an institutional registry. Imaging-based selection was done by multimodal CT or MRI according to institutional treatment algorithms. RESULTS: IV thrombolysis was performed in 100 patients (54.3%) based on multimodal CT imaging and in 84 patients (45.7%) based on MRI. Baseline clinical data, including stroke severity and time from last seen normal to hospital admission, were similar in patients with CT and MRI. Door-to-needle times were shorter in patients with CT-based selection (median [interquartile range] 45 [37-62] minutes vs 75 [59-90] minutes; mean difference [95% confidence interval (CI)] -28 minutes [-35 to -21]). No differences were detected regarding the incidence of symptomatic intracranial hemorrhage (2 [2.0%] vs 4 [4.8%]; adjusted odds ratio [aOR] [95% CI] 0.47 [0.08-2.83]) and favorable outcome at day 90 (25 [33.8%] vs 33 [42.9%]; aOR 0.95 [0.45-2.02]). CONCLUSION: IV thrombolysis in ischemic stroke in the unknown or extended time window appeared safe in CT- and MRI-selected patients, while the use of CT imaging led to faster door-to-needle times. CLASSIFICATION OF EVIDENCE: This study provides Class IV evidence that for patients with ischemic stroke in the extended or unknown time window, imaging-based selection for IV thrombolysis by multimodal CT compared to MRI led to shorter door-to-needle times.
CRIS-Team Scopus Importer:2020-12-11

Multiple Sclerosis relapses are not associated with exercise - Tallner, Alexander; Waschbisch, Anne; Wenny, Ingrid; Schwab, Stefan; Hentschke, Christian; Pfeifer, Klaus; Mäurer, Mathias (Multiple Sclerosis Journal, 2012)

Neck cooling induces blood pressure increase and peripheral vasoconstriction in healthy persons - Koehn, Julia; Wang, Ruihao; de Rojas Leal, Carmen; Kallmünzer, Bernd; Winder, Klemens; Köhrmann, Martin; Kollmar, Rainer; Schwab, Stefan; Hilz, Max-Josef (Neurological Sciences, 2020)
Introduction: Noninvasive temperature modulation by localized neck cooling might be desirable in the prehospital phase of acute hypoxic brain injuries. While combined head and neck cooling induces significant discomfort, peripheral vasoconstriction, and blood pressure increase, localized neck cooling more selectively targets blood vessels that supply the brain, spares thermal receptors of the face and skull, and might therefore cause less discomfort cardiovascular side effects compared to head- and neck cooling. The purpose of this study is to assess the effects of noninvasive selective neck cooling on cardiovascular parameters and cerebral blood flow velocity (CBFV). Methods: Eleven healthy persons (6 women, mean age 42 ± 11 years) underwent 90 min of localized dorsal and frontal neck cooling (EMCOOLS Brain.Pad™) without sedation. Before and after cooling onset, and after every 10 min of cooling, we determined rectal, tympanic, and neck skin temperatures. Before and after cooling onset, after 60- and 90-min cooling, we monitored RR intervals (RRI), systolic, diastolic blood pressures (BPsys, BPdia), laser Doppler skin blood flow (SBF) at the index finger pulp, and CBFV at the proximal middle cerebral artery (MCA). We compared values before and during cooling by analysis of variance for repeated measurements with post hoc analysis (significance: p < 0.05). Results: Neck skin temperature dropped significantly by 9.2 ± 4.5 °C (minimum after 40 min), while tympanic temperature decreased by only 0.8 ± 0.4 °C (minimum after 50 min), and rectal temperature by only 0.2 ± 0.3 °C (minimum after 60 min of cooling). Index finger SBF decreased (by 83.4 ± 126.0 PU), BPsys and BPdia increased (by 11.2 ± 13.1 mmHg and 8.0 ± 10.1 mmHg), and heart rate slowed significantly while MCA-CBFV remained unchanged during cooling. Conclusions: While localized neck cooling prominently lowered neck skin temperature, it had little effect on tympanic temperature but significantly increased BP which may have detrimental effects in patients with acute brain injuries.
CRIS-Team Scopus Importer:2020-04-03
Keywords: Blood pressure increase; Cerebral blood flow velocity; Hypothermia; Neck cooling

Neuroanatomical correlates of severe cardiac arrhythmias in acute ischemic stroke - Seifert, Frank; Kallmünzer, Bernd; Gutjahr, Isabell; Breuer, Lorenz; Winder, Klemens; Kaschka, Iris; Kloska, Stephan; Dörfler, Arnd; Hilz, Max-Josef; Schwab, Stefan; Köhrmann, Martin (Journal of Neurology, 2015)
Neurocardiological interactions can cause severe cardiac arrhythmias in patients with acute ischemic stroke. The relationship between the lesion location in the brain and the occurrence of cardiac arrhythmias is still discussed controversially. The aim of the present study was to correlate the lesion location with the occurrence of cardiac arrhythmias in patients with acute ischemic stroke. Cardiac arrhythmias were systematically assessed in patients with acute ischemic stroke during the first 72 h after admission to a monitored stroke unit. Voxel-based lesion-symptom mapping (VLSM) was used to correlate the lesion location with the occurrence of clinically relevant severe arrhythmias. Overall 150 patients, 56 with right-hemispheric and 94 patients with a left-hemispheric lesion, were eligible to be included in the VLSM study. Severe cardiac arrhythmias were present in 49 of these 150 patients (32.7%). We found a significant association (FDR correction, q < 0.05) between lesions in the right insular, right frontal and right parietal cortex as well as the right amygdala, basal ganglia and thalamus and the occurrence of cardiac arrhythmias. Because left- and right-hemispheric lesions were analyzed separately, the significant findings rely on the 56 patients with right-hemispheric lesions. The data indicate that these areas are involved in central autonomic processing and that right-hemispheric lesions located to these areas are associated with an elevated risk for severe cardiac arrhythmias.
EVALuna2:22355

Neuroanatomic Correlates of Angioedema in stroke patients with thrombolysis - Winder, K.; Kallmünzer, Bernd; Dörfler, Arnd; Hilz, Max-Josef; Schwab, Stefan; Seifert, F.; Fröhlich, Kilian (EUROPEAN JOURNAL OF NEUROLOGY, 2020)
CRIS-Team WoS Importer:2020-06-16

Neuroanatomic correlates of poststroke hyperglycemia - Winder, Klemens; Seifert, Frank; Ohnemus, Tessa; Sauer, Eva-Maria; Kloska, Stephan; Dörfler, Arnd; Hilz, Max-Josef; Schwab, Stefan; Köhrmann, Martin (Annals of Neurology, 2015)
A study was undertaken to determine associations between ischemic stroke sites and poststroke hyperglycemia (PSH).Nondiabetic patients with first ever ischemic stroke confirmed by imaging were prospectively included. Blood glucose level (BGL), National Institute of Health Stroke Scale (NIHSS) score, and clinical parameters were assessed on admission. BGL was dichotomized for elevated versus normal levels using a cutoff value of >7.0 mmol/l. Clinical parameters were correlated with BGL and were compared between patient groups with elevated versus normal glucose values. A voxel-based lesion symptom mapping (VLSM) analysis adjusted for confounding variables was performed correlating sites of ischemic lesions with PSH.Of 1,281 stroke patients screened, 229 (mean age = 66.3 ± 15.9 years) met the inclusion criteria. Patients with elevated BGL were older, had higher NIHSS scores, and had larger infarcts compared to those without elevated glucose levels. Spearman rank analysis showed correlations between BGL and age, infarct size, heart rate (HR), and NIHSS scores (p <= 0.05). The VLSM analysis adjusted for these confounding factors demonstrated associations between PSH and damaged voxels in right hemispheric insular and opercular areas.The data indicate that damage in the right insulo-opercular areas contributes to PSH. The association between sympathetically mediated increase of HR and BGL suggests disinhibition of sympathetic outflow as a possible mechanism for PSH.
EVALuna2:22352

Neurocritical care in Germany: need for guidance - Huttner, Hagen; Schwab, Stefan (Neurocritical Care, 2014)
EVALuna2:22285

Neurointensive care medicine-from where, where to? - Stummer, W.; Schwab, Stefan; Fink, G. R. (Der Nervenarzt, 2018)
EVALuna2:201956

Neuromyelitis optica presenting with relapses under treatment with natalizumab: a case report - Lee, De Hyung; Laemmer, Alexandra B.; Waschbisch, Anne; Struffert, Tobias; Maihöfner, Christian; Schwab, Stefan; Linker, Ralf (Journal of Medical Case Reports, 2014)
Neuromyelitis optica is an inflammatory demyelinating disease of the central nervous system. To date, optimal therapeutic approaches for neuromyelitis optica have yet to be defined. Natalizumab is highly effective in relapsing-remitting multiple sclerosis and might be considered as an option.Here, we describe a 67-year-old Caucasian man with definite neuromyelitis optica with detection of anti-aquaporin-4 antibodies over the course of the disease. After initially discussing the diagnosis of multiple sclerosis at an outside hospital, our patient received interferon beta 1a as well as repeated corticosteroid pulses without success. Under subsequent therapy with natalizumab, he continued to present relapses. It was not until discontinuation of natalizumab, repeated cycles of plasma exchanges and initiation of therapy with rituxan that the disease course started to stabilize. Although B cells were completely depleted, our patient experienced another severe myelitis relapse during further follow-up and an additional immunosuppressive therapy with cyclophosphamide was started. Under this regimen, no further relapses occurred over the next 24 months.This case adds further evidence to the previously discussed notion that natalizumab, while highly effective in multiple sclerosis, may not work sufficiently in neuromyelitis optica. It further advocates for repetitive testing of anti-aquaporin-4 antibodies before and after treatment initiation.
EVALuna2:22348

No sex differences in long-term functional outcome after intracerebral hemorrhage - De Ridder, Inger; Kuramatsu, Joji; Gerner, Stefan; Madzar, Dominik; Lücking, Hannes; Kloska, Stephan; Dippel, Diederik; Schwab, Stefan; Huttner, Hagen (International Journal of Stroke, 2017)
Background There is conflicting evidence about the influence of sex on outcome after spontaneous intracerebral hemorrhage (sICH) and the majority of the research focused on mortality and short-term outcome only. We investigated sex differences in long-term functional outcome after sICH. Methods We used data from a prospective hospital registry and included all consecutive patients with ICH admitted to our institution between January 2006 and July 2014. Functional outcome was assessed by modified Rankin Scale evaluated 3 and 12 months after ICH. We explored the influence of sex on long-term functional outcome using multivariable regression models and additionally by means of propensity score matching. Results We analyzed 823 patients, of whom 380 (46%) women. Women were on average three years older (p < 0.001), men had more often deep hematomas (p = 0.01). Unadjusted mortality rates were significantly increased in women at three months (42% vs. 35%; odds ratio (OR): 1.35; 95% confidence interval (CI): 1.02-1.80). After adjusting for baseline prognostic factors there were no differences between men and women in short- and long-term mortality (OR = 1.01; 95% CI = 0.66-1.54 and OR = 1.04; 95%CI = 0.69-1.57, respectively) and short- and long-term unfavorable outcome (OR = 1.02; 95%CI = 0.67-1.55 and OR = 0.96; 95% CI = 0.62-1.48, respectively). Conclusion We found no sex-related differences in long-term functional outcome in patients with sICH. The apparently worse functional outcome in women can be explained by differences in age.
EVALuna2:22516

On Admission Lymphopenia in ICH Patients Is Associated with Increased Mortality and Poor Functional Outcome - Giede-Jeppe, Antje; Bobinger, Tobias; Gerner, Stefan; Lücking, Hannes; Kloska, Stephan; Kuramatsu, Joji; Schwab, Stefan; Huttner, Hagen (2016)
EVALuna2:22586

Oral Anticoagulants in the Oldest Old with Recent Stroke and Atrial Fibrillation - Polymeris, Alexandros A.; Macha, Kosmas; Paciaroni, Maurizio; Wilson, Duncan; Koga, Masatoshi; Cappellari, Manuel; Schaedelin, Sabine; Zietz, Annaelle; Peters, Nils; Seiffge, David J.; Haupenthal, David; Gaßmann, Luise; et al. (Annals of Neurology, 2021)
Objective To investigate the safety and effectiveness of direct oral anticoagulants (DOAC) versus vitamin K antagonists (VKA) after recent stroke in patients with atrial fibrillation (AF) aged >= 85 years. Methods Individual patient data analysis from seven prospective stroke cohorts. We compared DOAC versus VKA treatment among patients with AF and recent stroke (<3 months) aged >= 85 versus <85 years. Primary outcome was the composite of recurrent stroke, intracranial hemorrhage (ICH) and all-cause death. We used simple, adjusted, and weighted Cox regression to account for confounders. We calculated the net benefit of DOAC versus VKA by balancing stroke reduction against the weighted ICH risk. Results In total, 5,984 of 6,267 (95.5%) patients were eligible for analysis. Of those, 1,380 (23%) were aged >= 85 years and 3,688 (62%) received a DOAC. During 6,874 patient-years follow-up, the impact of anticoagulant type (DOAC versus VKA) on the hazard for the composite outcome did not differ between patients aged >= 85 (HR >= 85y = 0.65, 95%-CI [0.52, 0.81]) and < 85 years (HR<85y = 0.79, 95%-CI [0.66, 0.95]) in simple (p(interaction) = 0.129), adjusted (p(interaction) = 0.094) or weighted (p(interaction) = 0.512) models. Analyses on recurrent stroke, ICH and death separately were consistent with the primary analysis, as were sensitivity analyses using age dichotomized at 90 years and as a continuous variable. DOAC had a similar net clinical benefit in patients aged >= 85 (+1.73 to +2.66) and < 85 years (+1.90 to +3.36 events/100 patient-years for ICH-weights 1.5 to 3.1). Interpretation The favorable profile of DOAC over VKA in patients with AF and recent stroke was maintained in the oldest old. ANN NEUROL 2021
CRIS-Team WoS Importer:2021-12-10

Oral Anticoagulation and Functional Outcome after Intracerebral Hemorrhage - Biffi, Alessandro; Kuramatsu, Joji; Leasure, Audrey; Kamel, Hooman; Kourkoulis, Christina; Schwab, Kristin; Ayres, Alison M.; Elm, Jordan; Gurol, M. Edip; Greenberg, Steven M.; Viswanathan, Anand; Anderson, Christopher D.; et al. (Annals of Neurology, 2017)
Oral anticoagulation treatment (OAT) resumption is a therapeutic dilemma in intracerebral hemorrhage (ICH) care, particularly for lobar hemorrhages related to amyloid angiopathy. We sought to determine whether OAT resumption after ICH is associated with long-term outcome, accounting for ICH location (ie, lobar vs nonlobar).We meta-analyzed individual patient data from: (1) the multicenter RETRACE study (n = 542), (2) a U.S.-based single-center ICH study (n = 261), and (3) the Ethnic/Racial Variations of Intracerebral Hemorrhage study (n = 209). We determined whether, within 1 year from ICH, OAT resumption was associated with: (1) mortality, (2) favorable functional outcome (modified Rankin Scale = 0-3), and (3) stroke incidence. We separately analyzed nonlobar and lobar ICH cases using propensity score matching and Cox regression models.We included 1,012 OAT-related ICH survivors (633 nonlobar and 379 lobar). Among nonlobar ICH survivors, 178/633 (28%) resumed OAT, whereas 86/379 (23%) lobar ICH survivors did. In multivariate analyses, OAT resumption after nonlobar ICH was associated with decreased mortality (hazard ratio [HR] = 0.25, 95% confidence interval [CI] = 0.14-0.44, p < 0.0001) and improved functional outcome (HR = 4.22, 95% CI = 2.57-6.94, p < 0.0001). OAT resumption after lobar ICH was also associated with decreased mortality (HR = 0.29, 95% CI = 0.17-0.45, p < 0.0001) and favorable functional outcome (HR = 4.08, 95% CI = 2.48-6.72, p < 0.0001). Furthermore, OAT resumption was associated with decreased all-cause stroke incidence in both lobar and nonlobar ICH (both p < 0.01).These results suggest novel evidence of an association between OAT resumption and outcome following ICH, regardless of hematoma location. These findings support conducting randomized trials to explore risks and benefits of OAT resumption after ICH. Ann Neurol 2017;82:755-765.
EVALuna2:22551

Parenchymatous hematoma in patients with atraumatic subarachnoid hemorrhage: Characteristics, treatment, and clinical outcomes - Gerner, Stefan; Hülsbrink, Robert; Reichl, Jonathan; Mrochen, Anne; Eyüpoglu, Ilker Yasin; Brandner, Sebastian; Dörfler, Arnd; Engelhorn, Tobias; Kuramatsu, Joji; Schwab, Stefan; Huttner, Hagen (International Journal of Stroke, 2020)
Background: Data regarding the influence of concomitant parenchymatous hematoma (PH) on long-term outcomes in patients with atraumatic subarachnoid hemorrhage (SAH) are scarce. Further, it is not established if these patients benefit from surgical intervention. Aim: The aim of this study was to determine the influence of concomitant PH in SAH patients on functional long-term outcome, and whether these patients may benefit from surgical hematoma evacuation. Methods: Over a 5-year period, all consecutive patients with SAH treated at the Departments of Neurology, Neuroradiology, and Neurosurgery, at the University Hospital Erlangen (Germany) were recorded. In addition to the clinical and imaging characteristics of SAH, we documented the presence, location, and volume of PH as well as treatment parameters. Outcome assessment at 12 months included functional outcome (modified Rankin scale (mRS), favorable = 0–2), health-related quality of life, and long-term complications. For outcome analysis, a propensity score matching (ratio 1:1, caliper 0.1) was performed to compare SAH patients with and without PH. Sub-analyses were performed regarding PH treatment (surgical evacuation vs. conservative). Results: A total of 494 patients with atraumatic SAH were available. Eighty-five (17.2%) had PH on initial imaging. SAH patients with PH had a worse clinical condition on admission and had a greater extent of subarachnoid/intraventricular hemorrhage. Median PH volume was 11.0 ml (5.4–31.8) with largest volumes observed in patients with ruptured middle cerebral artery (MCA)-aneurysm (31.7 ml (16.3–43.2)). After propensity-score matching (PSM), patients with PH had worse functional outcomes at 12 months (modified Rankin scale (mRS) 0–2: PH 31.8% vs. ØPH57.7% p < 0.001), and a lower rate of self-reported health compared to patients without PH (EQ-5D VAS: PH 50(30–70) vs. ØPH 80(65–95); p < 0.001). In PH patients, surgical evacuation was associated with a higher rate of favorable outcome at 12 months compared to those treated conservatively (surgery 14/28 (50.0%) vs. conservative 14/57 (24.6%); adjusted odds-ratio (OR; 95%CI): 1.34 (1.08–1.66); p = 0.001), irrespective of aneurysm location. Subgroup-analysis revealed positive associations of surgical hematoma evacuation with outcome in subgroups with larger PH volumes (>10 ml; OR (95%CI): 1.39 (1.09–1.79)), frontal PH location (OR 1.59 (1.14–2.23)), and early surgery (within 600 min after onset; OR 1.42 (1.03–1.94)). Conclusions: Concomitant PH occurs frequently in patients with SAH and is associated with functional impairment after 1 year. Surgical evacuation of PH may improve outcomes in these patients, irrespective of aneurysm-location.
CRIS-Team Scopus Importer:2020-11-27
Keywords: Cerebral hemorrhage; complications; intracerebral hemorrahage; subarachnoid hemorrhage; surgery; treatment

Peak Troponin I Levels Are Associated with Functional Outcome in Intracerebral Hemorrhage - Gerner, Stefan; Auerbeck, Katrin; Sprügel, Maximilian; Sembill, Jochen; Madzar, Dominik; Gölitz, Philipp; Kuramatsu, Joji; Schwab, Stefan; Huttner, Hagen; Hölter, Philip (Cerebrovascular Diseases, 2018)
Background: Troponin I is a widely used and reliable marker of myocardial damage and its levels are routinely measured in acute stroke care. So far, the influence of troponin I elevations during hospital stay on functional outcome in patients with atraumatic intracerebral hemorrhage (ICH) is unknown. Methods: Observational single-center study including conservatively treated ICH patients over a 9-year period. Patients were categorized according to peak troponin I level during hospital stay (<= 0.040, 0.041-0.500, > 0.500 ng/mL) and compared regarding baseline and hematoma characteristics. Multivariable analyses were performed to investigate independent associations of troponin levels during hospital stay with functional outcome -assessed using the modified Rankin Scale (mRS; favorable 0-3/unfavorable 4-6) -and mortality after 3 and 12 months. To account for possible con-founding propensity score (PS)-matching (1: 1; caliper 0.1) was performed accounting for imbalances in baseline characteristics to investigate the impact of troponin I values on outcome. Results: Troponin elevations (> 0.040 ng/mL) during hospital stay were observed in 308 out of 745 (41.3%) patients and associated with poorer status on admission (Glasgow Coma Scale/National Institute of Health Stroke Scale). Multivariable analysis revealed troponin I levels during hospital stay to be independently associated with unfavorable outcome after 12 months (risk ratio [95% CI]: 1.030 [1.009-1.051] per increment of 1.0 ng/mL; p = 0.005), but not with mortality. After PS-matching, patients with troponin I elevation (= 0.040 ng/mL) versus those without had a significant higher rate of -unfavorable outcome after 3 and 12 months (mRS 4-6 at 3 months: < 0.04 ng/mL: 159/265 [60.0%] versus = 0.04 ng/mL: 199/266 [74.8%]; p < 0.001; at 12 months: < 0.04 ng/mL: 141/248 [56.9%] versus <= 0.04 ng/mL: 179/251 [71.3%]; p = 0.001). Conclusions: Troponin I elevations during hospital stay occur frequently in ICH patients and are independently associated with functional outcome after 3 and 12 months but not with mortality. (c) 2018 S. Karger AG, Basel
EVALuna2:34936

Pearls & Oy-sters: Moyamoya Vasculopathy and Its Association With Congenital Heart Disease - Osterloh, Justus; Heim, Christian; Siedler, Gabriela; Engelhorn, Tobias; Dörfler, Arnd; Schwab, Stefan; Kallmünzer, Bernd (Neurology, 2021)
CRIS-Team Scopus Importer:2021-06-25

Perihemorrhagic edema revisiting hematoma volume, location and surface - Sprügel, Maximilian; Kuramatsu, J. B.; Volbers, Bastian; Koelbl, K.; Gerner, Stefan; Lücking, Hannes; Dörfler, Arnd; Schwab, Stefan; Huttner, Hagen; Hölter, Philip (JOURNAL OF CEREBRAL BLOOD FLOW AND METABOLISM, 2019)
CRIS-Team WoS Importer:2019-07-19

Perihemorrhagic edema: Revisiting hematoma volume, location, and surface - Sprügel, Maximilian; Kuramatsu, Joji; Volbers, Bastian; Gerner, Stefan; Sembill, Jochen; Madžar, Dominik; Bobinger, Tobias; Kölbl, Kathrin; Lücking, Hannes; Dörfler, Arnd; Schwab, Stefan; Huttner, Hagen; et al. (Neurology, 2019)
OBJECTIVE: To determine the influence of intracerebral hemorrhage (ICH) location and volume and hematoma surface on perihemorrhagic edema evolution. METHODS: Patients with ICH of the prospective Universitätsklinikum Erlangen Cohort of Patients With Spontaneous Intracerebral Hemorrhage (UKER-ICH) cohort study (NCT03183167) between 2010 and 2013 were analyzed. Hematoma and edema volume during hospital stay were volumetrically assessed, and time course of edema evolution and peak edema correlated to hematoma volume, location, and surface to verify the strength of the parameters on edema evolution. RESULTS: Overall, 300 patients with supratentorial ICH were analyzed. Peak edema showed a high correlation with hematoma surface (R2 = 0.864, p < 0.001) rather than with hematoma volumes, regardless of hematoma location. Smaller hematomas with a higher ratio of hematoma surface to volume showed exponentially higher relative edema (R2 = 0.755, p < 0.001). Multivariable logistic regression analysis revealed a cutoff ICH volume of 30 mL, beyond which an increase of total mass lesion volume (combined volume of hematoma and edema) was not associated with worse functional outcome. Specifically, peak edema was associated with worse functional outcome in ICH <30 mL (odds ratio [OR] 2.63, 95% confidence interval [CI] 1.68-4.12, p < 0.001), contrary to ICH ≥30 mL (OR 1.20, 95% CI 0.88-1.63, p = 0.247). There were no significant differences between patients with lobar and those with deep ICH after adjustment for hematoma volumes. CONCLUSIONS: Peak perihemorrhagic edema, although influencing mortality, is not associated with worse functional outcomes in ICH volumes >30 mL. Although hematoma volume correlates with peak edema extent, hematoma surface is the major parameter for edema evolution. The effect of edema on functional outcome is therefore more pronounced in smaller and irregularly shaped hematomas, and these patients may particularly benefit from edema-modifying therapies.
CRIS-Team Scopus Importer:2019-09-27

Peripheral pulse measurement after ischemic stroke: A feasibility study - Kallmünzer, Bernd; Bobinger, Tobias; Kahl, Nicolas; Kopp, Markus; Kurka, Natalia; Hilz, Max-Josef; Marquardt, Lars; Schwab, Stefan; Köhrmann, Martin (Neurology, 2014)
To investigate feasibility and diagnostic accuracy of measurement of the peripheral pulse (MPP) at the radial artery as a simple, noninvasive screening tool for paroxysmal atrial fibrillation (pAF) in patients after acute ischemic stroke.Two hundred fifty-six patients with acute ischemic stroke and the patients' relatives at a tertiary stroke center were prospectively included. Participants were instructed for characteristics of atrial fibrillation (AF) in MPP using standardized educational material. Measurements of participants as well as a health care professional were then compared with simultaneous blinded ECG to evaluate diagnostic accuracy parameters.MPP by the health care professional or patients' relatives had a diagnostic sensitivity of 96.5% and 76.5%, respectively, with 94.0% and 92.9% specificity for the detection of AF. Self-measurements were reliably performed by 89.1% of competent patients with a diagnostic sensitivity of 54.1% and 96.2% specificity. False-positive results were limited to 6 cases (2.7%) with a positive predictive value of 76.9% and a negative predictive value of 90.0%.With a low rate of false-positive results, MPP offers an easy, ubiquitously available, noninvasive, first-step screening tool to guide ECG diagnostics for pAF after ischemic stroke. The data warrant a prospective trial evaluating the efficacy of MPP-guided ECG diagnostics in secondary prevention after stroke, which is now underway.This study provides Class I evidence that MPP by patients or relatives accurately distinguishes AF from normal heart rhythm as compared with continuous ECG.
EVALuna2:22299

PERIPHERAL PULSE MEASUREMENTS FOR THE DETECTION OF SILENT ATRIAL FIBRILLATION: RESULTS FROM THE PROSPECTIVE, CONTROLLED TRIAL "KNOW YOUR PULSE POST STROKE" - Kallmünzer, Bernd; Macha, Kosmas; Wang, Ruihao; Siedler, Gabriela; Stoll, Svenja; Marsch, Armin; Gerner, Stefan; Winder, Klemens; Koehn, J.; Schwab, Stefan; Koehrmann, M. (INTERNATIONAL JOURNAL OF STROKE, 2020)
CRIS-Team WoS Importer:2021-01-22

Physical Activity in Multiple Sclerosis: A Comparative Study of Vitamin D, BDNF and Regulatory T Cell Populations - Waschbisch, Anne; Wenny, Ingrid; Tallner, Alexander; Schwab, Stefan; Pfeifer, Klaus; Mäurer, Mathias (European neurology, 2012)

Pivotal Role for CD16+ Monocytes in Immune Surveillance of the Central Nervous System - Waschbisch, Anne; Schröder, Sina; Schraudner, Dana; Sammet, Laura; Weksler, Babette; Melms, Arthur; Pfeifenbring, Sabine; Stadelmann, Christine; Schwab, Stefan; Linker, Ralf A. (Journal of Immunology, 2016)
Monocytes represent a heterogeneous population of primary immune effector cells. At least three different subsets can be distinguished based on expression of the low-affinity Fc?RIII: CD14(++)CD16 -: classical monocytes, CD14(++)CD16(+) intermediate monocytes, and CD14(+)CD16 ++: non-classical monocytes. Whereas CD16 -: classical monocytes are considered key players in multiple sclerosis (MS), little is known on CD16(+) monocytes and how they contribute to the disease. In this study, we examined the frequency and phenotype of monocyte subpopulations in peripheral blood, cerebrospinal fluid (CSF), and brain biopsy material derived from MS patients and controls. Furthermore, we addressed a possible monocyte dysfunction in MS and analyzed migratory properties of monocyte subsets using human brain microvascular endothelial cells. Our ex vivo studies demonstrated that CD16(+) monocyte subpopulations are functional but numerically reduced in the peripheral blood of MS patients. CD16(+) monocytes with an intermediate-like phenotype were found to be enriched in CSF and dominated the CSF monocyte population under noninflammatory conditions. In contrast, an inversed CD16(+) to CD16 -: CSF monocyte ratio was observed in MS patients with relapsing-remitting disease. Newly infiltrating, hematogenous CD16(+) monocytes were detected in a perivascular location within active MS lesions, and CD16(+) monocytes facilitated CD4(+) T cell trafficking in a blood -: brain barrier model. Our findings support an important role of CD16(+) monocytes in the steady-state immune surveillance of the CNS and suggest that CD16(+) monocytes shift to sites of inflammation and contribute to the breakdown of the blood-brain barrier in CNS autoimmune diseases.
EVALuna2:22432

Posterior circulation ischemic stroke not involving the brainstem is associated with cardiovascular autonomic dysfunction - Wang, Ruihao; Kohrmann, Martin; Kollmar, Rainer; Köhn, Julia; Schwab, Stefan; Kallmünzer, Bernd; Hilz, Max-Josef (European Journal of Neurology, 2022)
Background and purpose Ischemic stroke may induce cardiovascular autonomic dysfunction, but most previous studies have included patients with anterior circulation ischemic stroke or brainstem stroke. It remains unclear whether posterior circulation ischemic stroke (PCIS) without brainstem involvement also compromises cardiovascular autonomic modulation (CAM). Therefore, we aimed to assess CAM in PCIS patients with and without brainstem involvement. Methods In four subgroups of 61 PCIS patients (14 occipital lobe, 16 thalamic, 12 cerebellar, and 19 brainstem strokes) and 30 healthy controls, we recorded RR intervals (RRIs), systolic (SBP) and diastolic blood pressure (DBP), and respiration at supine rest during the first week after stroke onset. We calculated parameters reflecting total CAM (RRI-standard deviation [RRI-SD], RRI-total powers), predominantly sympathetic CAM (RRI-low-frequency [LF] powers and SBP-LF powers] and parasympathetic CAM (root mean square of successive RRI differences [RMSSD], RRI-high-frequency [HF] powers), sympathetic-parasympathetic balance (RRI-LF/HF ratios), and baroreflex sensitivity (BRS). Values were compared among the four PCIS groups and controls using one-way ANOVA Kruskal-Wallis tests, with post-hoc analyses. Significance was assumed for p < 0.05. Results In each PCIS subgroup, values for RRI, RRI-SD, RMSSD, RRI-HF powers, and BRS were significantly lower, while SBP-LF powers were higher than in the controls. Only in patients with occipital lobe stroke were RRI-LF/HF ratios significantly higher than in controls. Otherwise, autonomic variables did not differ among the four PCIS subgroups. Conclusions During the first week after stroke onset, our PCIS patients with occipital lobe, thalamic, cerebellar, or brainstem strokes all had reduced cardiovagal modulation, compromised baroreflex, and increased peripheral sympathetic modulation. The RRI-LF/HF ratios suggest that sympathetic predominance is slightly more prominent after occipital lobe stroke. PCIS may trigger cardiovascular autonomic dysfunction even without brainstem involvement.
CRIS-Team WoS Importer:2022-06-24

Pre- and Postictal Changes in the Innate Immune System: Cause or Effect? - Lang, Johannes; Olmes, David G.; Proske, Manuel; Hagge, Mareike; Dogan Onugoren, Mujgan; Rothhammer, Veit; Schwab, Stefan; Hamer, Hajo (European neurology, 2021)
Introduction: Recent studies have shown that inflammatory processes might play a role in epileptogenesis. Their role in ictogenesis is much less clear. The aim of this study was to investigate peri-ictal changes of the innate immune system by analyzing changes of immune cells, as well as pro- and anti-inflammatory cytokines. Methods: Patients with active epilepsy admitted for video-EEG monitoring for presurgical evaluation were included. Blood was sampled every 20 min for 5 h on 3 consecutive days until a seizure occurred. After a seizure, additional samples were drawn immediately, as well as 1 and 24 h later. To analyze the different populations of peripheral blood mononuclear cells, all samples underwent FACS for CD3, CD4, CD8, CD56, CD14, CD16, and CD19. For cytokine analysis, we used a custom bead-based multiplex immunoassay for IFN-gamma, IL-1 beta, IL-1RA, IL-4, IL-6, IL-10, IL-12, IL-17, MCP-1, MIP-1 alpha, and TNF alpha. Results: Fourteen patients with focal seizures during the sampling period were included. Natural killer (NK) cells showed a negative correlation (rho = -0.3362, p = 0.0195) before seizure onset and an immediate increase to 1.95-fold afterward. T helper (T-H) and B cells decreased by 2 and 8%, respectively, in the immediate postictal interval. Nonclassical and intermediate monocytes decreased not until 1 day after the seizures, and cytotoxic T (T-C) cells showed a long-lasting postictal increase by 4%. IL-10 and MCP-1 increased significantly after seizures, and IL-12 decreased in the postictal phase. Discussion/Conclusion: Our study argues for a role of the innate immune system in the pre- and postictal phases. NK cells might be involved in preictal changes or be altered as an epiphenomenon in the immediate preictal interval.
CRIS-Team WoS Importer:2021-07-09

Prediction of Recurrent Ischemic Stroke Using Registry Data and Machine Learning Methods: The Erlangen Stroke Registry - Vodencarevic, Asmir; Weingärtner, Michael; Caro, J. Jaime; Ukalovic, Dubravka; Zimmermann-Rittereiser, Marcus; Schwab, Stefan; Kolominsky-Rabas, Peter (Stroke, 2022)
BACKGROUND: There have been multiple efforts toward individual prediction of recurrent strokes based on structured clinical and imaging data using machine learning algorithms. Some of these efforts resulted in relatively accurate prediction models. However, acquiring clinical and imaging data is typically possible at provider sites only and is associated with additional costs. Therefore, we developed recurrent stroke prediction models based solely on data easily obtained from the patient at home. METHODS: Data from 384 patients with ischemic stroke were obtained from the Erlangen Stroke Registry. Patients were followed at 3 and 12 months after first stroke and then annually, for about 2 years on average. Multiple machine learning algorithms were applied to train predictive models for estimating individual risk of recurrent stroke within 1 year. Double nested cross-validation was utilized for conservative performance estimation and models' learning capabilities were assessed by learning curves. Predicted probabilities were calibrated, and relative variable importance was assessed using explainable artificial intelligence techniques. RESULTS: The best model achieved the area under the curve of 0.70 (95% CI, 0.64-0.76) and relatively good probability calibration. The most predictive factors included patient's family and housing circumstances, rehabilitative measures, age, high calorie diet, systolic and diastolic blood pressures, percutaneous endoscopic gastrotomy, number of family doctor's home visits, and patient's mental state. CONCLUSIONS: Developing fairly accurate models for individual risk prediction of recurrent ischemic stroke within 1 year solely based on registry data is feasible. Such models could be applied in a home setting to provide an initial risk assessment and identify high-risk patients early.
CRIS-Team Scopus Importer:2022-07-08
Keywords: ischemic stroke; machine learning; probability; recurrence; registries

Presence of Concomitant Systemic Cancer is Not Associated with Worse Functional Long-Term Outcome in Patients with Intracerebral Hemorrhage - Spuergel, Maximilian I.; Kuramatsu, Joji; Gerner, Stefan; Sembill, Jochen; Hartwich, Julius; Giede-Jeppe, Antje; Madzar, Dominik; Beuscher, Vanessa D.; Lücking, Hannes; Struffert, Tobias; Schwab, Stefan; Huttner, Hagen; et al. (Cerebrovascular Diseases, 2017)
Data on clinical characteristics and outcome of patients with intracerebral hemorrhage (ICH) and concomitant systemic cancer disease are very limited.Nine hundred and seventy three consecutive primary ICH patients were analyzed using our prospective institutional registry over a period of 9 years (2006-2014). We compared clinical and radiological parameters as well as outcome - scored using the modified Rankin Scale (mRS) and analyzed in a dichotomized fashion as favorable outcome (mRS = 0-3) and unfavorable outcome (mRS = 4-6) - of ICH patients with and without cancer. Relevant imbalances in baseline clinical and radiological characteristics were adjusted using propensity score (PS) matching.Prevalence of systemic cancer among patients with ICH was 8.5% (83/973). ICH patients with cancer were older (77 [70-82] vs. 72 [63-80] years; p = 0.002), had more often prior renal dysfunction (19/83 [22.9%] vs.107/890 [12.0%]; p = 0.005), and smaller hemorrhage volumes (10.1 [4.8-24.3] vs. 15.3 [5.4-42.9] mL; p = 0.017). After PS-matching there were no significant differences neither in mortality nor in functional outcome both at 3 months (mortality: 33/81 [40.7%] vs. 55/158 [34.8%]; p = 0.368; mRS = 0-3: 28/81 [34.6%] vs. 52/158 [32.9%]; p = 0.797) and 12 months (mortality: 39/78 [50.0%] vs. 70/150 [46.7%]; p = 0.633; mRS = 0-3: 25/78 [32.1%] vs. 53/150 [35.3%]; p = 0.620) among patients with and without concomitant systemic cancer. ICH volume tended to be highest in patients with hematooncologic malignancy and smallest in urothelial cancer.Patients with ICH and concomitant systemic cancer on average are older; however, they show smaller ICH volumes compared to patients without cancer. Yet, mortality and functional outcome is not different in ICH patients with and without cancer. Thus, the clinical history or the de novo diagnosis of concomitant malignancies in ICH patients should not lead to unjustified treatment restrictions.
EVALuna2:22553

Prevalence and impact on outcome of electrocardiographic early repolarization patterns among stroke patients: a prospective observational study - Bobinger, Tobias; Kallmünzer, Bernd; Kopp, Markus; Kurka, Natalia; Hilz, Max-Josef; Huttner, Hagen; Schwab, Stefan; Köhrmann, Martin; Arnold, Martin (Clinical Research in Cardiology, 2015)
Early repolarization pattern (ER) gained attention as a risk factor for ventricular arrhythmia and sudden cardiac death in the general population. While electrocardiographic abnormalities are frequent findings in stroke patients, data on ER pattern in this population are lacking.We assessed the prevalence of ER pattern in consecutive acute stroke patients at a tertiary stroke center. Functional outcome after 90 days was analyzed to determine the effect of an ER pattern on mortality. Multivariate logistic regression analysis was used to identify factors associated with an ER pattern.Out of 1141 consecutive stroke patients 771 patients remained for analysis after application of exclusion criteria. ER was observed in 62 (8.04%) patients. ER was more prevalent among subjects with intracerebral and subarachnoidal hemorrhage (13.0%) than among patients with ischemic stroke (7.0%; p = 0.024). Multiple regression analysis revealed QRS-duration (OR 0.972 95% CI 0.950-0.994, p = 0.012), QT-duration (OR 1.009, 95% CI 1.004-1.014, p = 0.001) and mechanical ventilation on admission (OR 0.320, 95% CI 0.136-0.752, p = 0.009) as independent predictors for ER. Overall ER on admission was not associated with increased mortality at 3-month follow-up (ER 11.3% vs. non-ER 9.2%; p = 0.582).ER is frequently found among patients with acute cerebrovascular events and is more prevalent in patients with hemorrhagic compared to ischemic events. Our study yields no evidence that ER is associated with worse outcome or mortality after stroke.
EVALuna2:12024

Prevalence, utilization, and costs of antiepileptic drugs for epilepsy in Germany – a nationwide population-based study in children and adults - Hamer, Hajo; Dodel, Richard; Strzelczyk, Adam; Balzer-Geldsetzer, Monika; Reese, Jens-Peter; Schöffski, Oliver; Graf, Wolfgang; Schwab, Stefan; Knake, Susanne; Oertel, Wolfgang; Rosenow, Felix; Kostev, Karel (Journal of Neurology, 2012)
<h2 class="Heading" style="border: 0px; font-weight: 400; font-stretch: inherit; font-size: 24px; line-height: 1.2; font-family: Georgia, 'New Century Schoolbook', 'Nimbus Roman No9 L', serif; margin: 7px 0px; padding: 0px; vertical-align: baseline; outline: 0px; letter-spacing: 0.02em; width: 580px; color: rgb(51, 51, 51);"> Nationwide analyses of drug use can provide a prevalence estimate of the underlying disease and can help in understanding the characteristics of treatment. This study aimed for such analyses regarding the utilization of antiepileptic drugs (AED) for epilepsy in Germany. In 2009, all 4,115,705 AED prescriptions of all German patients with statutory health insurance (70,011,508 persons) were retrospectively analyzed. The IMS® LRx database served as data source, which accesses nationwide pharmacy data centers processing all German prescription data. To establish the age and sex-specific percentage of patients taking AED because of epilepsy, we used a second database, Disease Analyzer®, which covered a representative sample of the German population (7.2 million patients) and contained ICD10 codes alongside with prescription data. The period prevalence of patients taking AED because of epilepsy was 9.1/1,000 (children/adolescents: 5.2/1,000; elderly: 12.5/1,000). Of the patients, 83.1 % took at least one of four AED: valproate (29.8 %), carbamazepine (26.4 %), lamotrigine (21.4 %), and levetiracetam (16.9 %). Oxcarbazepine and sultiame were popular with pediatricians. Elderly patients frequently received phenytoin and primidone. More than half of the patients were treated by family physicians; 68 % took AED in monotherapy and 7.9 % received >2 AED (children/adolescents: 12.5 %). The costs for AED prescribed for epilepsy amounted to €285.1 Mio (median AED costs/patient: €158/a). The German 2009 prevalence of epileptic patients taking AED was 9.1/1,000. Family physicians cared for the majority of patients. Prevalence and prescribing patterns changed with age. Costs of AED against epilepsy added up to 1 % of total medication costs in Germany.
WiSo-Import:2015-03-26:4184
Keywords: Epilepsy; Prevalence; Antiepileptic drugs; Costs; Children; Elderly

Prognostic Accuracy of CTP Summary Maps in Patients with Large Vessel Occlusive Stroke and Poor Revascularization after Mechanical Thrombectomy-Comparison of Three Automated Perfusion Software Applications - Mühlen, Iris; Borutta, Matthias; Siedler, Gabriela; Engelhorn, Tobias; Hock, Stefan; Knott, Michael; Hölter, Philip; Volbers, Bastian; Schwab, Stefan; Dörfler, Arnd (Tomography, 2022)
Background: Innovative automated perfusion software solutions offer support in the management of acute stroke by providing information about the infarct core and penumbra. While the performance of different software solutions has mainly been investigated in patients with successful recanalization, the prognostic accuracy of the hypoperfusion maps in cases of futile recanalization has hardly been validated. Methods: In 39 patients with acute ischemic stroke (AIS) due to large vessel occlusion (LVO) in the anterior circulation and poor revascularization (thrombolysis in cerebral infarction (TICI) 0-2a) after mechanical thrombectomy (MT), hypoperfusion analysis was performed using three different automated perfusion software solutions (A: RAPID, B: Brainomix e-CTP, C: Syngo.via). The hypoperfusion volumes (HV) as Tmax > 6 s were compared with the final infarct volumes (FIV) on follow-up CT 36-48 h after futile recanalization. Bland-Altman analysis was applied to display the levels of agreement and to evaluate systematic differences. Based on the median hypoperfusion intensity ratio (HIR, volumetric ratio of tissue with a Tmax > 10 s and Tmax > 6 s) patients were dichotomized into high- and low-HIR groups. Subgroup analysis with favorable (<0.6) and unfavorable (>= 0.6) HIR was performed with respect to the FIV. HIR was correlated to clinical baseline and outcome parameters using Pearson's correlation. Results: Overall, there was good correlation without significant differences between the HVs and the FIVs with package A (r = 0.78, p < 0.001) being slightly superior to B and C. However, levels of agreement were very wide for all software applications in Bland-Altman analysis. In cases of large infarcts exceeding 150 mL the performance of the automated software solutions generally decreased. Subgroup analysis revealed the FIV to be generally underestimated in patients with HIR >= 0.6 (p < 0.05). In the subgroup with favorable HIR, however, there was a trend towards an overestimation of the FIV. Nevertheless, packages A and B showed good correlation between the HVs and FIVs without significant differences (p > 0.2), while only package C significantly overestimated the FIV (-54.6 +/- 56.0 mL, p = 0.001). The rate of modified Rankin Scale (mRS) 0-3 after 3 months was significantly higher in favorable vs. unfavorable HIR (42.1% vs. 13.3%, p = 0.02). Lower HIR was associated with higher Alberta Stroke Program Early CT Score (ASPECTS) at presentation and on follow-up imaging, lower risk of malignant edema, and better outcome (p < 0.05). Conclusion: Overall, the performance of the automated perfusion software solutions to predict the FIV after futile recanalization is good, with decreasing accuracy in large infarcts exceeding 150 mL. However, depending on the HIR, FIV can be significantly over- and underestimated, with Syngo showing the widest range. Our results indicate that the HIR can serve as valuable parameter for outcome predictions and facilitate the decision whether or not to perform MT in delicate cases.
CRIS-Team WoS Importer:2022-07-08

PROPHYLACTIC AND PROLONGED HYPOTHERMIA IN POOR-GRADESAH REDUCES DEGREE OF VASOSPASM AND RATE OF DELAYED CEREBRAL INFARCTIONS - Kuramatsu, J. B.; Kollmar, Rainer; Staykov, Dimitre; Kloska, Stephan; Dörfler, Arnd; Eyüpoglu, Ilker Yasin; Schwab, Stefan; Huttner, Hagen (2016)
EVALuna2:22484

Propofol-related urine discoloration in a patient with fatal atypical intracerebral hemorrhage treated with hypothermia - Regensburger, Martin; Huttner, Hagen; Dörfler, Arnd; Schwab, Stefan; Staykov, Dimitre (SpringerPlus, 2014)
Introduction: Mild therapeutic hypothermia is an increasingly recognised treatment option to reduce perihemorrhagic edema in severe intracerebral hemorrhage. Case description: We report the case of a 77-year old woman with atypical intracerebral hemorrhage that was treated with mild hypothermia in addition to osmotic therapy. The patient’s urine subsequently showed a green discoloration. Urine discoloration was completely reversible upon discontinuation of propofol. Discussion and evaluation: Propofol-related urine discoloration may have been provoked by hypothermia. Due to the benign nature of this side effect, propofol should be stopped and gastrointestinal function should be supported. Conclusion: More studies are needed to show a causal role of hypothermia and related decreased enzymatic function.
CRIS-Team Scopus Importer:2021-08-17
Keywords: Enterohepatic circulation; Hypothermia; Intracerebral hemorrhage; Liver enzyme function; Urine discoloration

Psychogenic nonepileptic seizures: clinical characteristics and outcome - Volbers, Bastian; Walther, Katrin; Kurzbuch, Katrin; Erdmann, Laura; Gollwitzer, Stephanie; Lang, Johannes; Onugoren, Muejgan Dogan; Schwarz, Michael; Schwab, Stefan; Hamer, Hajo (Brain and Behavior, 2022)
Background: Clinical characteristics, outpatient situation, and outcome in patients with psychogenic nonepileptic seizures (PNES) remain to be elucidated. Methods: Patients diagnosed with PNES after video-electroencephalography (EEG) monitoring (VEM) 03/2000–01/2016 at the Erlangen Epilepsy Center were surveyed between June 2016 and February 2017. Primary outcome was PNES cessation defined as no PNES episodes within > = 12 months prior to the interview. Secondary outcome variables included quality of life (QoL) and dependency. Sensitivity analysis included patients with proven PNES during VEM without comorbid epilepsy. Results: Ninety-nine patients were included (median age 38 (interquartile range (IQR 29–52)) years; 68 (69%) females, follow-up 4 (IQR 2.1–7.7) years). Twenty-eight (28%) patients suffered from comorbid epilepsy. Twenty-five (25%) patients reported PNES cessation. Older age at symptom onset (odds ratio (OR) related to PNES cessation: 0.95 (95% CI 0.90–0.99)), comorbid epilepsy (OR 0.16 (95% CI 0.03–0.83)), anxiety disorder (OR 0.15 (95% CI 0.04–0.61)), and tongue biting (OR 0.22 (95% CI 0.03–0.91)) remained independently associated with ongoing PNES activity after adjustment. Sensitivity analysis (n = 63) revealed depressive disorder (OR 0.03 (95% CI 0.003–0.34)) instead of anxiety as independent predictor, while this seemed relevant only in patients older than 26 years at onset (OR 0.04 (95% CI 0.002–0.78) versus OR 0.21 (95% CI 0.02–1.84) in patients younger than 26 years). PNES cessation was associated with increased median QoL (8 (IQR 7–9) versus 5.5 (IQR 4–7); p <.001) and an increased frequency of financial independency (14 (56%) versus 21 (28%); p =.01). Conclusions: We found poor outcomes in PNES especially in older patients at onset with comorbid depressive disorder. Comorbid epilepsy also seems to be a major risk factor of ongoing PNES activity, which in turn affects patients’ daily living.
CRIS-Team Scopus Importer:2022-04-22
Keywords: activities of daily living; mental disorders; nonepileptic seizures; patient-relevant outcome; prognosis

Psychological long-term outcome in patients with psychogenic nonepileptic seizures - Walther, Katrin; Volbers, Bastian; Erdmann, Laura; Onugoren, Muejgan Dogan; Gollwitzer, Stephanie; Kasper, Burkhard; Kurzbuch, Katrin; Lang, Johannes; Schwab, Stefan; Schwarz, Michael; Hamer, Hajo (Epilepsia, 2019)
Objective To examine the long-term outcome of psychological status, personality, and health-related quality of life (HRQoL) in patients with psychogenic nonepileptic seizures (PNES) and to define predictors of favorable outcome of cessation of PNES. Method Patients diagnosed with PNES during video-electroencephalography (EEG) monitoring at the Erlangen Epilepsy Center were contacted 1-16 years after communicating the diagnosis. Follow-up information from each participant was obtained by interview (PNES outcome) and by self-reported questionnaires of psychological symptoms (Beck Depression Inventory-II, Symptom Checklist-90-Standard, Dissociative Symptoms questionnaire), personality traits (Freiburg Personality Inventory-Revised), and HRQoL (36-Item Short Form Health Survey). Results Fifty-two patients participated in the study (mean age +/- standard deviation [SD] 40.5 +/- 14.0 years; 75% female, follow-up: 5.3 +/- 4.2 years). Nineteen patients (37%) were free of PNES for the past 12 months. Patients with persisting PNES were older at disease onset (32.9 vs 22.3 years, P < 0.01) and diagnosis (40.5 vs 27.2 years, P < 0.001), and showed worse psychological functioning, lower extraversion and life satisfaction, and higher inhibitedness and worse HRQoL than PNES-free patients. Patients with cessation of PNES were within the normal range in all dimensions. Cessation of PNES was best predicted by younger age at PNES onset and higher extraversion. Significance Outcome of PNES is poor, psychopathology is high, and HRQoL is low in patients with persistent PNES but may normalize with PNES cessation. High introversion and older age at PNES onset are risk factors for persistent PNES.
CRIS-Team WoS Importer:2019-04-16

Psychosocial long-term outcome in patients with psychogenic non-epileptic seizures - Walther, Katrin; Volbers, Bastian; Erdmann, Laura; Kurzbuch, Katrin; Lang, Johannes; Müller, Tamara; Reindl, Caroline; Schwarz, Michael; Schwab, Stefan; Hamer, Hajo (Seizure-European Journal of Epilepsy, 2020)
Purpose: To evaluate psychosocial long-term outcome in patients diagnosed with psychogenic nonepileptic seizures (PNES) and to predict outcome of PNES, economic status, and quality of life (QoL) at follow-up. Methods: Patients diagnosed with PNES in the video-EEG-monitoring unit at our Epilepsy center between 2002–2016 were contacted by phone 1–16 years after communicating the diagnosis. Patients underwent a structured interview asking for current PNES status, psychosocial situation (economic status, marital status, setting of living, driving), depression, and QoL. Results: Of 70 PNES patients without comorbid epilepsy (age: 41.1 ± 13.5 years; 74 % female, follow-up: 5.2 ± 4.2 years), 23 patients (33 %) reported to be free of PNES during the last 12 months. Patients with cessation of PNES were younger at PNES onset (p < .01) and diagnosis (p < .01) and had a higher education (p < .05). At follow-up, the proportion of economically active patients only increased in individuals with cessation of PNES (p < .001) while an increased number of patients with persisting PNES relied on governmental support (p < .001). Cessation of PNES was associated with better mood (p < .01) and QoL (p < .001). In multiple regression models, cessation of PNES was only predicted by younger age at onset, while good economic outcome was determined by younger age and good economic status at diagnosis and cessation of PNES at follow-up. Good QoL at follow-up was predicted by low depressive symptoms, freedom of PNES, and economic activity at follow-up. Conclusion: Long-term outcome in patients with PNES remains to be poor and the majority of patients continue to have PNES. Cessation of PNES was associated with good economic outcome, mood, and QoL.
CRIS-Team Scopus Importer:2020-11-27
Keywords: Employment; Long-term outcome; Marital status; Mood; Psychogenic non-epileptic seizures; Quality of life

Psychosocial outcome in epilepsy after extratemporal surgery - Walther, Katrin; Onugoren, Muejgan Dogan; Buchfelder, Michael; Gollwitzer, Stephanie; Graf, Wolfgang; Kasper, Burkhard; Kriwy, Peter; Kurzbuch, Katrin; Lang, Johannes; Roessler, Karl; Schwab, Stefan; Schwarz, Michael; et al. (Epilepsy and Behavior, 2018)
OBJECTIVE: Only limited data exist on psychosocial long-term outcome after epilepsy surgery in patients with extratemporal epilepsy. The aim of this study was to investigate psychosocial outcome after extratemporal epilepsy surgery and to assess factors predicting favorable outcome. METHOD: Sixty-five out of 104 eligible patients who had undergone extratemporal epilepsy surgery at our epilepsy center between 1990 and 2015 (mean age: 42.2. years; 75% of the resections in the frontal lobe) completed a questionnaire asking about seizure status, employment status, marital and living situation, driving status, depressive symptoms, and quality of life (QOL). Follow-up was on average 9.2years after surgery (range: 1-26years). RESULTS: Thirty-eight (58%) patients were free of disabling seizures (Engel class I), and 28 (43%) have not experienced any seizures after surgery (Engel class IA). Employment rate in the primary labor market remained at 45%, but more patients lost employment (14%) than gained employment (8%). Postoperative employment was predicted by preoperative employment (p=.007), seizure freedom (p=.025), older age at seizure onset (p=.018), younger age at follow-up (p=.035), and female gender (p=.048). Seizure-free patients were more likely to be driving; have a partner, particularly in males; and have lower depressive scores. Quality of life at follow-up was best predicted by employment (p=.012), partnership (p=.025), and seizure freedom (p=.025). In contrast, recurrence of seizures and early seizure onset were associated with poor psychosocial outcome, particularly in men. CONCLUSION: The study provides support that extratemporal surgery can lead to improved QOL and favorable psychosocial outcome. Seizure freedom is important but not the only determinant of good psychosocial outcome.
EVALuna2:35520

Pupillometry in the follow-up of patients undergoing EVT - prediction of space-occupying hemispheric infarction - Kossel, Clara-Sophie; Kobus, Franca; Borutta, Matthias; Kärtner, Maximilian; Kuramatsu, Joji; Engelhorn, Tobias; Schwab, Stefan; Köhn, Julia (Journal of Neurology, 2023)
Background: Despite benefits of endovascular treatment (EVT) for large vessel occlusion (LVO) ischemic stroke, space-occupying brain edema (BE) represents a detrimental complication. In critical-care settings, CT-imaging is needed for monitoring these patients. Yet, bed-side techniques with the potential to predict whether patients develop BE or not would facilitate a time- and cost-efficient patient care. We assessed clinical significance of automated pupillometry in the follow-up of patients undergoing EVT. Methods: From 10/2018 to 10/2021, neurocritical-care-unit patients were retrospectively enrolled after EVT of anterior circulation LVO. We monitored parameters of pupillary reactivity [light-reflex-latency (Lat), constriction- and redilation-velocities (CV, DV), percentage-change-of-apertures (per-change); NeurOptics-pupilometer®] up to every hour on day 1–3 of ICU stay. BE was defined as midline shift ≥ 5 mm on follow-up imaging 3–5 days after EVT. We calculated mean values of intra-individual differences between successive pairs of parameters (mean-deltas), determined best discriminative cut-off values for BE development (ROC-analyses), and evaluated prognostic performance of pupillometry for BE development (sensitivity/specificity/positive-/negative-predictive-values). Results: 3241 pupillary assessments of 122 patients [67 women, 73 years (61.0–85.0)] were included. 13/122 patients developed BE. Patients with BE had significantly lower CVs, DVs, and smaller per-changes than patients without BE. On day 1 after EVT mean-deltas of CV, DV, and per-changes were significantly lower in patients with than without BE. Positive-predictive-values of calculated thresholds to discriminate both groups were considerably low, yet, we found high negative-predictive-values for CV, DV, per-changes, and mean-deltas (max.: 98.4%). Conclusion: Our data suggest associations between noninvasively detected changes in pupillary reactivity and BE early after LVO-EVT. Pupillometry may identify patients who are unlikely to develop BE and may not need repetitive follow-up-imaging or rescue-therapy.
CRIS-Team Scopus Importer:2023-06-30
Keywords: Automated pupillometry; Endovascular treatment; Ischemic stroke; Large vessel occlusion; Pupillary reactivity

Quantitative 1H and 23Na muscle MRI in Facioscapulohumeral muscular dystrophy patients - Gerhalter, Teresa; Marty, Benjamin; Gast, Lena; Porzelt, Katharina; Heiß, Rafael; Uder, Michael; Schwab, Stefan; Carlier, Pierre G.; Nagel, Armin Michael; Türk, Matthias (Journal of Neurology, 2020)
Objective: Our aim was to assess the role of quantitative 1H and 23Na MRI methods in providing imaging biomarkers of disease activity and severity in patients with Facioscapulohumeral muscular dystrophy (FSHD). Methods: We imaged the lower leg muscles of 19 FSHD patients and 12 controls with a multimodal MRI protocol to obtain STIR-T2w images, fat fraction (FF), water T2 (wT2), water T1 (wT1), tissue sodium concentration (TSC), and intracellular-weighted sodium signal (inversion recovery (IR) and triple quantum filter (TQF) sequence). In addition, the FSHD patients underwent muscle strength testing. Results: Imaging biomarkers related with water mobility (wT1 and wT2) and ion homeostasis (TSC, IR, TQF) were increased in muscles of FSHD patients. Muscle groups with FF > 10% had higher wT2, wT1, TSC, IR, and TQF values than muscles with FF < 10%. Muscles with FF < 10% resembled muscles of healthy controls for these MRI disease activity measures. However, wT1 was increased in few muscles without fat replacement. Furthermore, few STIR-negative muscles (n = 11/76) exhibited increased wT1, TSC, IR or TQF. Increased wT1 as well as 23Na signals were also present in muscles with normal wT2. Muscle strength was related to the mean FF and all imaging biomarkers of tibialis anterior except wT2 were correlated with dorsal flexion. Conclusion: The newly evaluated imaging biomarkers related with water mobility (wT1) and ion homeostasis (TSC, IR, TQF) showed different patterns compared to the established markers like FF in muscles of FSHD patients. These quantitative biomarkers could thus contain valuable complementary information for the early characterization of disease progression.
CRIS-Team Scopus Importer:2020-10-23
Keywords: Facioscapulohumeral muscular dystrophy; Quantitative MRI; Sodium MRI; Triple quantum filter; Water T

Quantitative Corticospinal Tract Assessment in Acute Intracerebral Hemorrhage - Volbers, Bastian; Mennecke, Angelika; Kästle, Nicola; Huttner, Hagen; Schwab, Stefan; Schmidt, Manuel; Engelhorn, Tobias Martin; Dörfler, Arnd (Translational Stroke Research, 2020)
Intracerebral hemorrhage (ICH) prognostication during the acute phase is often subjective among physicians and often affects treatment decisions. The present study explores objective imaging parameters using quantitative corticospinal tract (CST) fiber reconstruction during the acute phase of ICH and correlates these parameters with functional outcome and patient recovery. We prospectively enrolled nonsurgical spontaneous supratentorial ICH patients and obtained an MRI scan on day 5 ± 1. Q-space diffeomorphic reconstruction was performed using DSI Studio, and quantitative anisotropy (QA) was calculated. The CST was reconstructed based on QA. The dichotomized modified Rankin Scale score on day 90 (favorable outcome = 0–2) and Barthel Index (favorable recovery = 100 on day 90 or improvement between discharge and day 90 > 60%) were assessed. Thirty-three patients, median age 72 years (interquartile range (IQR) 64–83), 21 female (64%), 21 (64%) with lobar hemorrhage, median ICH volume on admission 15.0 (IQR 7.0–27.4) mL, were included. Sixteen patients (48%) had a favorable outcome and 24 (73%) had a favorable recovery. The mean number of ipsilesional reconstructed CST fiber pathways was higher in patients with favorable outcomes (153 (standard deviation (SD) 103) vs. 60 (SD 39), p = 0.003) and predicted outcome after adjustment (Exp(B) = 1.016 (95% CI = 1.002–1.030)). QA in the ipsilesional posterior limb of the internal capsule showed a trend towards an association with favorable outcome (Exp(B) = 1.194 (95% CI = 0.991–1.439 (adjusted))). The total (ipsilesional + contralesional) number of reconstructed fiber pathways was associated with favorable recovery (Exp(B) = 1.025 (95% CI = 1.003–1.047 (adjusted))). Quantitative tractography parameters assessed in the acute phase of ICH may represent a promising predictor of long-term outcome and recovery. This might facilitate prognostic evaluation and organization of rehabilitation.
CRIS-Team Scopus Importer:2020-10-02
Keywords: All rehabilitation; DWI; Intracerebral hemorrhage; MRI; Outcome research

Quantitative EEG After Subarachnoid Hemorrhage Predicts Long-Term Functional Outcome - Gollwitzer, Stephanie; Müller, Tamara; Hopfengärtner, Rüdiger; Rampp, Stephan; Merkel, Jasmin; Hagge, Mareike; Jukic, Jelena; Lang, Johannes; Madžar, Dominik; Onugoren, Müjgan Dogan; Huttner, Hagen; Schwab, Stefan; et al. (Journal of Clinical Neurophysiology, 2019)
PURPOSE: Delayed cerebral ischemia is a major complication after subarachnoid hemorrhage. Our previous study showed that alpha power reduction in continuous quantitative EEG predicts delayed cerebral ischemia. In this prospective cohort, we aimed to determine the prognostic value of alpha power in quantitative EEG for the long-term outcome of patients with subarachnoid hemorrhage. METHODS: Adult patients with nontraumatic subarachnoid hemorrhage were included if admitted early enough for EEG to start within 72 hours after symptom onset. Continuous six-channel EEG was applied. Unselected EEG signals underwent automated artifact rejection, power spectral analysis, and detrending. Alpha power decline of ≥40% for ≥5 hours was defined as critical EEG event based on previous findings. Six-month outcome was obtained using the modified Rankin scale. RESULTS: Twenty-two patients were included (14 male; mean age, 59 years; Hunt and Hess grade I-IV; duration of EEG monitoring, median 14 days). Poor outcome (modified Rankin scale, 2-5) was noted in 11 of 16 patients (69%) with critical EEG events. All six patients (100%) without EEG events achieved an excellent outcome (modified Rankin scale 0, 1) (P = 0.0062; sensitivity 100%, specificity 54.5%). Vasospasm detected with transcranial Doppler/Duplex sonography appeared 1.5 days after EEG events and showed weaker association with outcome (P = 0.035; sensitivity 100%, specificity 45.5%). There was no significant association between EEG events and ischemic lesions on imaging (P = 0.1). Also, no association between ischemic lesions and outcome was seen (P = 0.64). CONCLUSIONS: Stable alpha power in quantitative EEG reflects successful therapy and predicts good functional outcome after subarachnoid hemorrhage. Critical alpha power reduction indicates an increased risk of poor functional outcome.
CRIS-Team Scopus Importer:2019-05-03

Quantitative EEG may predict weaning failure in ventilated patients on the neurological intensive care unit - Welte, Tamara; Gabriel, Maria; Hopfengaertner, Ruediger; Rampp, Stefan; Gollwitzer, Stephanie; Lang, Johannes; Stritzelberger, Jenny; Reindl, Caroline; Madzar, Dominik; Sprügel, Maximilian; Huttner, Hagen; Kuramatsu, Joji; et al. (Scientific Reports, 2022)
Neurocritical patients suffer from a substantial risk of extubation failure. The aim of this prospective study was to analyze if quantitative EEG (qEEG) monitoring is able to predict successful extubation in these patients. We analyzed EEG-monitoring for at least six hours before extubation in patients receiving mechanical ventilation (MV) on our neurological intensive care unit (NICU) between November 2017 and May 2019. Patients were divided in 2 groups: patients with successful extubation (SE) versus patients with complications after MV withdrawal (failed extubation; FE), including reintubation, need for non-invasive ventilation (NIV) or death. Bipolar six channel EEG was applied. Unselected raw EEG signal underwent automated artefact rejection and Short Time Fast Fourier Transformation. The following relative proportions of global EEG spectrum were analyzed: relative beta (RB), alpha (RA), theta (RT), delta (RD) as well as the alpha delta ratio (ADR). Coefficient of variation (CV) was calculated as a measure of fluctuations in the different power bands. Mann–Whitney U test and logistic regression were applied to analyze group differences. 52 patients were included (26 male, mean age 65 ± 17 years, diagnosis: 40% seizures/status epilepticus, 37% ischemia, 13% intracranial hemorrhage, 10% others). Successful extubation was possible in 40 patients (77%), reintubation was necessary in 6 patients (12%), 5 patients (10%) required NIV, one patient died. In contrast to FE patients, SE patients showed more stable EEG power values (lower CV) considering all EEG channels (RB: p < 0.0005; RA: p = 0.045; RT: p = 0.045) with RB as an independent predictor of weaning success in logistic regression (p = 0.004). The proportion of the EEG frequency bands (RB, RA RT, RD) of the entire EEG power spectrum was not significantly different between SE and FE patients. Higher fluctuations in qEEG frequency bands, reflecting greater fluctuation in alertness, during the hours before cessation of MV were associated with a higher rate of complications after extubation in this cohort. The stability of qEEG power values may represent a non-invasive, examiner-independent parameter to facilitate weaning assessment in neurocritical patients.
CRIS-Team Scopus Importer:2022-05-20

Radiopacity of intracerebral hemorrhage correlates with perihemorrhagic edema - Wagner, Irina; Volbers, Bastian; Hilz, Max-Josef; Schwab, Stefan; Staykov, Dimitre; Dörfler, Arnd (European Journal of Neurology, 2012)
Background: Experimental evidence indicates that iron plays a key role in edema formation after intracerebral hemorrhage (ICH). We investigated the relationship between ICH radiopacity on CT as a marker of hematoma iron content and perihemorrhagic edema (PHE) after ICH. Methods: We retrospectively investigated patients with spontaneous lobar and ganglionic supratentorial ICH who received follow-up CT scans during the first 7days after symptom onset (d1, d2-4, d5-7). Measurements of ICH and edema volumes were taken using a semiautomatic threshold-based volumetric algorithm. Radiopacity of the blood clot was determined using the mean Hounsfield unit (HU) count of the ICH. Results: A total of 117 patients aged 71.92±11.55years with spontaneous ICH (34.63±32.44ml) were included in the analysis. Mean ICH radiopacity was 59.7±3.4HU. We found significantly larger relative PHE at d2-4 (1.7±0.9 vs. 1.3±0.8; P=0.032) and d5-7 (2.0±1.3 vs. 1.3±0.9; P=0.007) and larger peak relative PHE (2.3±1.6 vs. 1.6±1.1; P=0.006) in patients with ICH radiopacity >60HU (n=59), as compared to patients with ICH radiopacity <60HU (n=58). Conclusions: Higher ICH radiopacity, reflecting higher in vivo hematoma iron content, is associated with more PHE after ICH. © 2011 The Author(s). European Journal of Neurology © 2011 EFNS.
CRIS-Team Scopus Importer:2022-08-05
Keywords: Intracerebral hemorrhage; Perihemorrhagic edema; Radiopacity

Recommendations for the management of cerebral and cerebellar infarction with swelling: a statement for healthcare professionals from the American Heart Association/American Stroke Association - Wijdicks, Eelco F. M.; Sheth, Kevin N.; Carter, Bob S.; Greer, David M.; Kasner, Scott E.; Kimberly, W. Taylor; Schwab, Stefan; Smith, Eric E.; Tamargo, Rafael J.; Wintermark, Max (Stroke, 2014)
There are uncertainties surrounding the optimal management of patients with brain swelling after an ischemic stroke. Guidelines are needed on how to manage this major complication, how to provide the best comprehensive neurological and medical care, and how to best inform families facing complex decisions on surgical intervention in deteriorating patients. This scientific statement addresses the early approach to the patient with a swollen ischemic stroke in a cerebral or cerebellar hemisphere.The writing group used systematic literature reviews, references to published clinical and epidemiology studies, morbidity and mortality reports, clinical and public health guidelines, authoritative statements, personal files, and expert opinion to summarize existing evidence and to indicate gaps in current knowledge. The panel reviewed the most relevant articles on adults through computerized searches of the medical literature using MEDLINE, EMBASE, and Web of Science through March 2013. The evidence is organized within the context of the American Heart Association framework and is classified according to the joint American Heart Association/American College of Cardiology Foundation and supplementary American Heart Association Stroke Council methods of classifying the level of certainty and the class and level of evidence. The document underwent extensive American Heart Association internal peer review.Clinical criteria are available for hemispheric (involving the entire middle cerebral artery territory or more) and cerebellar (involving the posterior inferior cerebellar artery or superior cerebellar artery) swelling caused by ischemic infarction. Clinical signs that signify deterioration in swollen supratentorial hemispheric ischemic stroke include new or further impairment of consciousness, cerebral ptosis, and changes in pupillary size. In swollen cerebellar infarction, a decrease in level of consciousness occurs as a result of brainstem compression and therefore may include early loss of corneal reflexes and the development of miosis. Standardized definitions should be established to facilitate multicenter and population-based studies of incidence, prevalence, risk factors, and outcomes. Identification of patients at high risk for brain swelling should include clinical and neuroimaging data. If a full resuscitative status is warranted in a patient with a large territorial stroke, admission to a unit with neurological monitoring capabilities is needed. These patients are best admitted to intensive care or stroke units attended by skilled and experienced physicians such as neurointensivists or vascular neurologists. Complex medical care includes airway management and mechanical ventilation, blood pressure control, fluid management, and glucose and temperature control. In swollen supratentorial hemispheric ischemic stroke, routine intracranial pressure monitoring or cerebrospinal fluid diversion is not indicated, but decompressive craniectomy with dural expansion should be considered in patients who continue to deteriorate neurologically. There is uncertainty about the efficacy of decompressive craniectomy in patients >=60 years of age. In swollen cerebellar stroke, suboccipital craniectomy with dural expansion should be performed in patients who deteriorate neurologically. Ventriculostomy to relieve obstructive hydrocephalus after a cerebellar infarct should be accompanied by decompressive suboccipital craniectomy to avoid deterioration from upward cerebellar displacement. In swollen hemispheric supratentorial infarcts, outcome can be satisfactory, but one should anticipate that one third of patients will be severely disabled and fully dependent on care even after decompressive craniectomy. Surgery after a cerebellar infarct leads to acceptable functional outcome in most patients.Swollen cerebral and cerebellar infarcts are critical conditions that warrant immediate, specialized neurointensive care and often neurosurgical intervention. Decompressive craniectomy is a necessary option in many patients. Selected patients may benefit greatly from such an approach, and although disabled, they may be functionally independent.
EVALuna2:22286

Recommendations on the structure, personal, and organization of intensive care units - Waydhas, Christian; Riessen, Reimer; Markewitz, Andreas; Hoffmann, Florian; Frey, Lorenz; Böttiger, Bernd W.; Brenner, Sebastian; Brenner, Thorsten; Deffner, Teresa; Deininger, Matthias M.; Janssens, Uwe; Kluge, Stefan; et al. (Frontiers in Medicine, 2023)
Background: Intensive care units (ICU) are central facilities of medical care in hospitals world-wide and pose a significant financial burden on the health care system. Objectives: To provide guidance and recommendations for the requirements of (infra)structure, personal, and organization of intensive care units. Design and setting: Development of recommendations based on a systematic literature search and a formal consensus process from a group of multidisciplinary and multiprofessional specialists from the German Interdisciplinary Association of Intensive Care and Emergency Medicine (DIVI). The grading of the recommendation follows the report from an American College of Chest Physicians Task Force. Results: The recommendations cover the fields of a 3-staged level of intensive care units, a 3-staged level of care with respect to severity of illness, qualitative and quantitative requirements of physicians and nurses as well as staffing with physiotherapists, pharmacists, psychologists, palliative medicine and other specialists, all adapted to the 3 levels of ICUs. Furthermore, proposals concerning the equipment and the construction of ICUs are supplied. Conclusion: This document provides a detailed framework for organizing and planning the operation and construction/renovation of ICUs.
CRIS-Team Scopus Importer:2023-09-29
Keywords: guideline; intensive care medicine; organization; personal; quality of care; recommendation; structural requirements

Re-evaluation of the stroke prognostication using age and NIH Stroke Scale index (SPAN-100 index) in IVT patients - the-SPAN 10065 index - Möbius, Cornelia; Blinzler, Christian; Schwab, Stefan; Koehrmann, Martin; Breuer, Lorenz (BMC Neurology, 2018)
BACKGROUND: The SPAN-100 index adds patient age and baseline NIHSS-score and was introduced to predict clinical outcome after acute ischemic stroke (AIS). Even with high NIHSS-scores younger patients cannot reach a SPAN-100-positive status (index ≥100). We aimed to evaluate the SPAN-100 index among a large, contemporary cohort of i.v.-thrombolysed AIS-patients and exclusively among older patients who can at least theoretically achieve SPAN-100-positivity. METHODS: The SPAN-100 index was applied to AIS-patients receiving i.v.-thrombolysis (IVT) in our institution between 01/2006 and 01/2013. Clinical outcome and symptomatic intracerebral hemorrhage rates were compared between SPAN-100-positive and -negative patients. Furthermore we excluded patients < 65 years, without any theoretical chance to achieve SPAN-100-positivity, and re-evaluated the index (SPAN65-100 index). RESULTS: SPAN-100-positive IVT-patients (124/1002) had a 9-fold increased risk for unfavorable outcome compared to SPAN-negative patients (OR 9.39; 95% CI 5.87-15.02; p < 0.001). The odds ratio for mortality was 7.48 (95% CI 4.90-11.43; p < 0.001). No association was found between SPAN-100-positivity and sICH-incidence (OR 0.88; 95% CI 0.31-2.53; p = 0.810). SPAN65-100-positivity (124/741) was associated with an 8-fold increased risk for unfavorable outcome (OR 7.6; 95% CI 4.71-12.22; p < 0.001) but not associated with higher sICH-rates (OR 0.86; 95% CI 0.29-2.53; p < 0.001). CONCLUSIONS: Also for patients ≥65 years the SPAN-100 index can be a fast, easy method to predict clinical outcome of IVT-patients in everyday practice. However, it should not be used to determine the risk of sICH after IVT. Based on a SPAN-positive status IVT should not be withheld from AIS-patients merely because of feared sICH-complications.
EVALuna2:35513

Regional Differences in Thrombectomy Rates : Secondary use of Billing Codes in the MIRACUM (Medical Informatics for Research and Care in University Medicine) Consortium - Haverkamp, Christian; Ganslandt, Thomas; Horki, Petar; Boeker, Martin; Dörfler, Arnd; Schwab, Stefan; Berkefeld, Joachim; Pfeilschifter, Waltraud; Niesen, Wolf-Dirk; Egger, Karl; Kaps, Manfred; Brockmann, Marc A.; et al. (Clinical Neuroradiology, 2018)
Mechanical thrombectomy, in addition to intravenous (i.v.) thrombolysis is recommended for treatment of acute stroke in patients with large vessel occlusions (LVO) in the anterior circulation up to 6 h after symptom onset. We compared thrombectomy rates of eight university hospitals of the MIRACUM consortium to analyze the implementation of this guideline in clinical routine.Anonymized billing data in a standardized format were loaded into a local i2b2 data warehouse by applying already existing extract, transform and load (ETL) routines. A locally executed uniform SQL (structured query language) query delivered aggregated site data for all inpatients with a discharge diagnosis of ischemic stroke (ICD-10 I63) containing counts for type of acute treatment, type of admission and age groups, which were centrally analyzed with R.From 2014 to 2016, the thrombectomy rate almost doubled from a mean of 4.7% to 9.6%, although significant differences between centers exist (range in 2016: 5.8-17%). The number of drip-and-ship procedures increased in 3 out of 8 centers. There was no evidence for a decrease in thrombectomy rates during weekends/holiday or among patients older than 80 years, but this age group is more likely to receive i.v. recombinant tissue plasminogen activator (rtPA).The observed increase of thrombectomy rates and drip-and-ship procedures without a significant difference between weekdays and weekends or patients of different ages is substantiating a rapid implementation of stroke guidelines within the analyzed neurovascular centers. The prototype of the MIRACUM Data Integration Center already contributes to health services research in Germany.
EVALuna2:196

Reliability and limitations of automated arrhythmia detection in telemetric monitoring after stroke - Kurka, Natalia; Bobinger, Tobias; Kallmünzer, Bernd; Koehn, Julia; Schellinger, Peter D.; Schwab, Stefan; Köhrmann, Martin (Stroke, 2015)
Guidelines recommend continuous ECG monitoring in patients with cerebrovascular events. Studies on intensive care units (ICU) demonstrated high sensitivity but high rates of false alarms of monitoring systems resulting in desensitization of medical personnel potentially endangering patient safety. Data on patients with acute stroke are lacking.One-hundred fifty-one consecutive patients with acute cerebrovascular events were prospectively included. Automatically identified arrhythmia events were analyzed by manual ECG analysis. Muting of alarms was registered. Sensitivity was evaluated by beat-to-beat analysis of the entire recorded ECG data in a subset of patients. Ethics approval was obtained by University of Erlangen-Nuremberg.A total of 4809.5 hours of ECG registration and 22 509 alarms were analyzed. The automated detection algorithm missed no events but the overall rate of false alarms was 27.4%. Only 0.6% of all alarms indicated acute life-threatening events and 91.4% of these alarms were incorrect. Transient muting of acoustic alarms was observed in 20.5% patients.Continuous ECG monitoring using automated arrhythmia detection is highly sensitive in acute stroke. However, high rates of false alarms and alarms without direct therapeutic consequence cause desensitization of personnel. Therefore, acoustic alarms may be limited to life-threatening events but standardized manual evaluation of all alarms should complement automated systems to identify clinically relevant arrhythmias.
EVALuna2:22266

Restarting Therapeutic Anticoagulation in Patients with Intracerebral Hemorrhage and Mechanical Heart Valves - Kuramatsu, Joji; Sembill, Jochen; Schwab, Stefan; Huttner, Hagen (2018)
EVALuna2:35518

Resumption of oral anticoagulation after spontaneous intracerebral hemorrhage - Sembill, Jochen; Kuramatsu, Joji; Schwab, Stefan; Huttner, Hagen (Neurological Research and Practice, 2019)
Background: Given an ageing population the incidence of both patients suffering from intracerebral hemorrhage (ICH) and those requiring oral anticoagulation will increase. Up to now there are no results from randomized trials available whether or not, and when, ICH survivors should resume OAC. This review summarizes the most important observational studies, and initiated ongoing trials, to help guiding physicians in daily routine decision making. Findings: Several large observational studies and meta-analyses verified that OAC resumption was associated with a significant reduction of thromboembolic complications and mortality without leading to increased rates of recurrent ICH. OAC resumption seemed further associated with improved functional recovery and favorable long-term outcome. Given the general bleeding risk reduction in patients using Non–vitamin K antagonist oral anticoagulants (NOAC) compared to Vitamin-K-antagonist (VKA), NOAC use should also be preferred after ICH, although specific comparative studies are pending. Patients with lobar ICH need special attention as these patients showed increased ICH recurrence rates, why decision making should include extended diagnostic work-up evaluating cerebral microbleed burden, cortical subarachnoid hemorrhage and superficial siderosis. Further, patients with mechanical heart valves need specific consideration as restarting VKA may be unsafe until two weeks, whereas optimal balancing of hemorrhagic with thromboembolic complications may allow earlier re-initiation one week after ICH. In patients with atrial fibrillation, resumption generally should take place between 4 and 8 weeks after ICH depending on a patient’s individual risk profile. Left atrial appendage occlusion (LAAO) might represent an alternative strategy in high-risk patients. Ongoing clinical trials will clarify whether OAC resumption versus LAAO versus no antithrombotic therapy may represent the best possible secondary stroke prevention in ICH survivors with atrial fibrillation. Conclusions: According to observational data OAC resumption after ICH seems beneficial and safe. Ongoing clinical trials will create evidence regarding treatment effects of pharmaceutical resumption and interventional alternatives. Yet, individual decision making weighing the patient’s individual thromboembolic versus hemorrhagic risks remains essential.
CRIS-Team Scopus Importer:2024-12-16
Keywords: Intracerebral hemorrhage; Intracranial hemorrhage; Oral anticoagulation; Resumption; Secondary prophylaxis; Stroke prevention

Safety of Heparin for Prophylaxis of Venous Thromboembolism in Oral Anticoagulation-Associated Intracerebral Hemorrhage. - Sembill, Jochen; Sprügel, Maximilian; Kuramatsu, Joji; Gerner, Stefan; Dörfler, Arnd; Schwab, Stefan; Huttner, Hagen (STROKE, 2019)
CRIS-Team WoS Importer:2019-08-23

Serelaxin activates eNOS, suppresses inflammation, attenuates developmental delay and improves cognitive functions of neonatal rats after germinal matrix hemorrhage - Xu, Ming M.; Seyler, L.; Bäuerle, Tobias; Kalinichenko, Liubov; Müller, Christian P.; Huttner, Hagen; Schwab, Stefan; Manaenko, A. (Scientific Reports, 2020)
Germinal matrix hemorrhage (GMH) is a detrimental form of neonatal CNS injury. Following GMH-mediated eNOS inhibition, inflammation arises, contributing to GMH-induced brain injury. We investigated the beneficial effects of Serelaxin, a clinical tested recombinant Relaxin-2 protein, on brain injury after GMH in rats. We investigated whether effects of Serelaxin are mediated by its ability to activate the GMH-suppressed eNOS pathway resulting in attenuation of inflammatory marker overproduction. GMH was induced by intraparenchymal injection of bacterial collagenase (0.3U). Seven day old Sprague–Dawley rat pups (P7) were used (n = 63). GMH animals were divided in vehicle or serelaxin treated (3 µg once, 30 µg once, 30 µg multiple, i.p., starting 30 after GMH and then daily). Sham operated animals were used. We monitored the developmental profile working memory and spatial function (T-maze and open field test respectively). At day 28, all rats underwent MRI-scans for assessment of changes in cortical thickness and white matter loss. Effects of Serelaxin on eNOS pathway activation and post-GMH inflammation were evaluated. We demonstrated that Serelaxin dose-dependently attenuated GMH-induced developmental delay, protected brain and improved cognitive functions of rats after GMH. That was associated with the decreased post-GMH inflammation, mediated at least partly by amelioration of GMH-induced eNOS inhibition.
CRIS-Team Scopus Importer:2020-05-29

Serial Pupillometer Readings Predicting Intracranial Pressure Crisis - Giede-Jeppe, Antje; Koehn, Julia; Gerner, Stefan; Kuramatsu, Joji; Huttner, Hagen; Schwab, Stefan (2018)
EVALuna2:35517

Serotonin transporter gene and stress reactivity in unipolar depression : Role of the HPA system as endophenotype of the SLC6A4 gene - Welper, H.; Aller, A.; Guttenthaler, V.; Hoefels, S.; Lennertz, L.; Pfeiffer, U.; Schwab, Stefan; Zobel, A. (Der Nervenarzt, 2014)
A length polymorphism in the promoter region of the serotonin transporter gene (5-HTTLPR) is associated with both depression and hypothalamic-pituitary-adrenal (HPA) system activity. A dysregulation of the HPA system is considered to be a candidate endophenotype of depression. The objective of the present study was an investigation of a possible gene-endophenotype-interaction between 5-HTTLPR and HPA system activity in a sample of inpatients with major depression.A total of 237 inpatients with major depression were genotyped for 5-HTTLPR and participated in a combined dexamethasone-corticotropin-releasing hormone test (Dex-CRH test) as well as using the Hamilton score (Hamilton rating scale for depression) to determine the severity of the psychopathology.Patients with the ss-genotype showed a significantly higher HPA -system activity in comparison to patients with the lI-genotype, but no association between 5-HTTLPR and the severity of psychopathology could be detected.The results of the current study demonstrate an influence of 5-HTTLPR on dysregulation of the HPA system in patients with major depression and support the hypothesis that 5-HTTLPR- and HPA-system-interaction constitutes an important component in the pathogenesis of depression.
EVALuna2:23614

Severity assessment in maximally treated ICH patients: The max-ICH score - Sembill, Jochen; Gerner, Stefan; Volbers, Bastian; Bobinger, Tobias; Lücking, Hannes; Kloska, Stephan; Schwab, Stefan; Huttner, Hagen; Kuramatsu, Joji (Neurology, 2017)
As common prognostication models in intracerebral hemorrhage (ICH) are developed variably including patients with early (<24 hours) care limitations (ECL), we investigated its interaction with prognostication in maximally treated patients and sought to provide a new unbiased severity assessment tool.This observational cohort study analyzed consecutive ICH patients (n = 583) from a prospective registry over 5 years. We characterized the influence of ECL on overall outcome by propensity score matching and on conventional prognostication using receiver operating characteristic analyses. We established the max-ICH score based on independent predictors of 12-month functional outcome in maximally treated patients and compared it to existing models.Prevalence of ECL was 19.2% (n = 112/583) and all of these patients died. Yet propensity score matching displayed that 50.7% (n = 35/69) theoretically could have survived, with 18.8% (n = 13/69) possibly reaching favorable outcome (modified Rankin Scale score 0-3). Conventional prognostication seemed to be confounded by ECL, documented by a decreased predictive validity (area under the curve [AUC] 0.67, confidence interval [CI] 0.61-0.73 vs AUC 0.80, CI 0.76-0.83; p < 0.01), overestimating poor outcome (mortality by 44.8%, unfavorable outcome by 10.1%) in maximally treated patients. In these patients, the novel max-ICH score (0-10) integrates strength-adjusted predictors, i.e., NIH Stroke Scale score, age, intraventricular hemorrhage, anticoagulation, and ICH volume (lobar and nonlobar), demonstrating improved predictive accuracy for functional outcome (12 months: AUC 0.81, CI 0.77-0.85; p < 0.01). The max-ICH score may more accurately delineate potentials of aggressive care, showing favorable outcome in 45.4% (n = 214/471) and a long-term mortality rate of only 30.1% (n = 142/471).Care limitations significantly influenced the validity of common prognostication models resulting in overestimation of poor outcome. The max-ICH score demonstrated increased predictive validity with minimized confounding by care limitations, making it a useful tool for severity assessment in ICH patients.
EVALuna2:22564

Sex differences in perihemorrhagic edema evolution after spontaneous intracerebral hemorrhage - Wagner, Irina; Volbers, Bastian; Kloska, Stephan; Schwab, Stefan; Staykov, Dimitre; Dörfler, Arnd (European Journal of Neurology, 2012)
Background and purpose: Clinical data on sex differences in perihemorrhagic edema (PHE) after intracerebral hemorrhage (ICH) are lacking. Methods: Patients with spontaneous supratentorial ICH who had received standard conservative treatment were identified retrospectively. PHE development was assessed over a 14-day period on follow-up CT scans (days 1, 2-4, 5-7, 8-11, and 12-14). ICH and PHE volumes were assessed semiautomatically and compared between men and women. Results: A total of 387 patients (233 men) were included. Starting at days 2-4, women showed lower PHE values (P<0.05;/ days 2-4, 8-11) or a trend toward significance (P≤0.1; days 5-7, 12-14). Conclusions: Female sex may predict lower PHE volumes. © 2012 The Author(s) European Journal of Neurology © 2012 EFNS.
CRIS-Team Scopus Importer:2022-08-05
Keywords: Gender; Intracerebral hemorrhage; Perihemorrhagic edema

Shortage of antiseizure medication in Germany: How big is the problem? - Steidl, Josephine; Krebs, Sabine; Kostev, Karel; Schwab, Stefan; Hamer, Hajo (Epilepsy and Behavior, 2025)
Objectives: We determined the frequency of drug shortages of antiseizure medication (ASM) availability in Germany. Methods: Retrospective and descriptive analysis of databases of 2 pharmaceutical wholesalers in Germany with a market share of about 45% of the German market in July 2023 (chosen arbitrarily) focusing on antiseizure drug shortages (i.e. demand could not be met entirely) and disruptions (i.e. demand could not be met at all) on the level of formulations, ASM and of manufacturers. Results: 98/909 (10.8%) of formulations of ASM with Wholesaler A were listed with drug shortages and 131/872 (15%) of formulations were reported with drug shortages at Wholesaler B. 19 of 222 (8.6%) entire ASM at Wholesaler A and 12/213 (5.6%) of ASM with Wholesaler B were reported with drug shortages. 41/62 (66.1%) manufacturers at wholesaler A and 36/57 (63.2%) manufacturers at wholesaler B reported shortages. The three compounds affected most frequently by drug shortages were pregabalin, levetiracetam and carbamazepine. 1.7% (Wholesaler A) and 12.9% (Wholesaler B) of formulations were listed with disruptions. 16.7% (40/239) of ASM with drug shortages/disruptions were brand-name ASM and 83.3% (199/239) were generic ASM. Conclusions: 11% to 15% of ASM formulations had drug shortages in Germany in July 2023. Generic ASM were more frequently affected than brand-name ASM. About 2/3 of manufacturers were reported to have drug shortages.
CRIS-Team Scopus Importer:2024-12-06
Keywords: Antiseizure medication; Drug shortages; Epilepsy

Siponimod (BAF-312) Attenuates Perihemorrhagic Edema And Improves Survival in Experimental Intracerebral Hemorrhage - Bobinger, Tobias; Manaenko, Anatol; Burkardt, Petra; Beuscher, Vanessa; Sprügel, Maximilian; Röder, Sebastian; Bäuerle, Tobias; Seyler, Lisa; Nagel, Armin Michael; Linker, Ralf; Engelhorn, Tobias; Dörfler, Arnd; et al. (Stroke, 2019)
Background and Purpose- Perihemorrhagic edema (PHE) is associated with poor outcome after intracerebral hemorrhage (ICH). Infiltration of immune cells is considered a major contributor of PHE. Recent studies suggest that immunomodulation via S1PR (sphingosine-1-phosphate receptor) modulators improve outcome in ICH. Siponimod, a selective modulator of sphingosine 1-phosphate receptors type 1 and type 5, demonstrated an excellent safety profile in a large study of patients with multiple sclerosis. Here, we investigated the impact of siponimod treatment on perihemorrhagic edema, neurological deficits, and survival in a mouse model of ICH. Methods- ICH was induced by intracranial injection of 0.075 U of bacterial collagenase in 123 mice. Mice were randomly assigned to different treatment groups: vehicle, siponimod given as a single dosage 30 minutes after the operation or given 3× for 3 consecutive days starting 30 minutes after operation. The primary outcome of our study was evolution of PHE measured by magnetic resonance-imaging on T2-maps 72 hours after ICH, secondary outcomes included evolution of PHE 24 hours after ICH, survival and neurological deficits, as well as effects on circulating blood cells and body weight. Results- Siponimod significantly reduced PHE measured by magnetic resonance imaging (P=0.021) as well as wet-dry method (P=0.04) 72 hours after ICH. Evaluation of PHE 24 hours after ICH showed a tendency toward attenuated brain edema in the low-dosage group (P=0.08). Multiple treatments with siponimod significantly improved neurological deficits measured by Garcia Score (P=0.03). Survival at day 10 was improved in mice treated with multiple dosages of siponimod (P=0.037). Mice treated with siponimod showed a reduced weight loss after ICH (P=0.036). Conclusions- Siponimod (BAF-312) attenuated PHE after ICH, increased survival, and reduced ICH-induced sensorimotor deficits in our experimental ICH-model. Findings encourage further investigation of inflammatory modulators as well as the translation of BAF-312 to a human study of ICH patients.
EVALuna2:204480

Siponimod reduces perihemorrhagic edema and improves neurological outcome in experimental intracerebral hemorrhage - Bobinger, Tobias; Manaenko, A.; Baeurele, T.; Seyler, L.; Nagel, Armin Michael; Engelhorn, Tobias; Dörfler, Arnd; Kuramatsu, J. B.; Schwab, Stefan; Huttner, Hagen (JOURNAL OF CEREBRAL BLOOD FLOW AND METABOLISM, 2019)
CRIS-Team WoS Importer:2019-07-19

Specific Lobar Affection Reveals a Rostrocaudal Gradient in Functional Outcome in Spontaneous Intracerebral Hemorrhage - Gerner, Stefan; Kuramatsu, Joji; Möller, Sebastian; Huber, Angelika; Lücking, Hannes; Kloska, Stephan; Madzar, Dominik; Sembill, Jochen; Schwab, Stefan; Huttner, Hagen (Stroke, 2017)
Several studies have reported a better functional outcome in lobar intracerebral hemorrhage (ICH) compared with deep location. However, among lobar ICH, a correlation of hemorrhage site-involving the specific lobes-with functional outcome has not been established.Conservatively treated patients with supratentorial ICH, admitted to our hospital over a 5-year period (2008-2012), were retrospectively analyzed. Lobar patients were classified as isolated or overlapping ICH according to affected lobes. Demographic, clinical, and radiological characteristics were recorded and compared among lobar ICH patients using above subclassification. Functional outcome-dichotomized into favorable (modified Rankin Scale, 0-3) and unfavorable (modified Rankin Scale, 4-6)-was assessed after 3 and 12 months. Multivariate regression analysis was performed to identify predictors for favorable outcome.Of overall 553 patients, 260 had lobar ICH. In isolated lobar ICH, median hematoma-volume decreased from rostral (frontal, 22.4 mL [7.3-55.5 mL]) to caudal (occipital, 7.1 mL [5.2-16.4 mL]; P=0.045), whereas the proportion of patients with favorable outcome increased (frontal: 23/63 [36.5%] versus occipital: 10/12 [83.3%]; P=0.003). Patients with overlapping lobar ICH had larger ICH volumes than isolated lobar ICH (overlapping, 48.9 mL [22.6-78.5 mL] versus 15.3 mL [5.0-44.6 mL]; P<0.001) and poorer clinical status on admission (Glasgow Coma Scale and National Institutes of Health Stroke Scale). Correlations with anatomic aspects provided evidence of a rostrocaudal gradient with increasing gray/white-matter ratio and decreasing hematoma-volume and rate of hematoma enlargement from frontal to occipital ICH location. Multivariate analysis revealed affection of occipital lobe (odds ratio, 3.75 [1.38-10.22]) and affection of frontal lobe (odds ratio, 0.52 [0.28-0.94]) to be independent predictors for favorable outcome and unfavorable outcome, respectively.Among patients with lobar ICH radiological and outcome characteristics differed according to location. Especially affection of the frontal lobe was frequent and associated with unfavorable outcome after 3 months.
EVALuna2:22482

Spectral properties of bursts in therapeutic burst suppression predict successful treatment of refractory status epilepticus - Gollwitzer, Stephanie; Hopfengärtner, Rüdiger; Rampp, Stefan; Welte, Tamara; Madžar, Dominik; Lang, Johannes; Reindl, Caroline; Stritzelberger, Jenny; Köhn, Julia; Kuramatsu, Joji; Schwab, Stefan; Huttner, Hagen B.; et al. (Epilepsy and Behavior, 2024)
Burst suppression (BS) on EEG induced by intravenous anesthesia (IVAT) is standard therapy for refractory status epilepticus (RSE). If BS has any independent therapeutic effect on RSE is disputed. We aimed to define EEG characteristics of BS predicting termination or recurrence of status after weaning. All RSE patients treated with IVAT while undergoing continuous EEG monitoring on the neurological intensive care unit between 2014 and 2019 were screened for inclusion. A one hour-period of visually preselected BS-EEG was analyzed. Bursts were segmented by a special thresholding technique and underwent power spectral analysis. Out of 48 enrolled patients, 25 (52.1 %) did not develop seizure recurrence (group Non SE) after weaning from IVAT; in 23 patients (47.9 %), SE reestablished (group SE). In group Non SE, bursts contained higher amounts of EEG delta power (91.59 % vs 80.53 %, p < 0.0001), while faster frequencies were more pronounced in bursts in group SE (theta: 11.38 % vs 5.41 %, p = 0.0008; alpha: 4.89 % vs 1.82 %, p < 0.0001; beta: 3.23 % vs 1.21 %, p = 0.0002). Spectral profiles of individual bursts closely resembled preceding seizure patterns in group SE but not in group Non SE. Accordingly, persistence of spectral composition of initial ictal patterns in bursts, suggests ongoing SE, merely interrupted but not altered by BS. Fast oscillations in bursts indicate a high risk of status recurrence after weaning from IVAT. EEG guided individualized sedation regimes might therefore be superior to standardized anesthesia protocols.
CRIS-Team Scopus Importer:2024-11-08
Keywords: Intravenous anesthesia; Multimodal monitoring; Quantitative EEG

Statistical analysis plan for the EuroHYP-1 trial: European multicentre, randomised, phase III clinical trial of the therapeutic hypothermia plus best medical treatment versus best medical treatment alone for acute ischaemic stroke - Winkel, Per; Bath, Philip M.; Gluud, Christian; Lindschou, Jane; Van Der Worp, H. Bart; Macleod, Malcolm R.; Szabo, Istvan; Durand-Zaleski, Isabelle; Schwab, Stefan (Trials, 2017)
BACKGROUND: Cooling may reduce infarct size and improve neurological outcomes in patients with ischaemic stroke. In phase II trials, cooling awake patients with ischaemic stroke has been shown to be feasible and safe, but the effects in functional outcomes has not yet been investigated in an adequately sized randomised clinical trial. METHODS/DESIGN: The EuroHYP-1 trial is a multinational, randomised, superiority phase III clinical trial with masked outcome assessment testing the benefits and harms of therapeutic cooling in awake adult patients with acute ischaemic stroke. The outcomes dealt with here include the primary outcome the Rankin score (mRS) at day 91 +/-14 days after randomisation. The secondary and exploratory outcomes at day 91 +/-14 days unless otherwise stated encompassing: (1) death or dependency, defined as mRS score > 2; (2) death; (3) National Institutes of Health Stroke Score; (4) brain infarct size at 48 +/-24 hours; (5) EQ-5D-5 L score, and (6) WHODAS 2.0 score. Other outcomes are: the primary safety outcome serious adverse events; and the incremental cost-effectiveness, and cost utility ratios. The analysis sets include (1) the intention-to-treat population, and (2) the per protocol population. The sample size is estimated to 800 patients (5% type 1 and 20% type 2 errors). All analyses are adjusted for the protocol-specified stratification variables (nationality of centre), and the minimisation variables. In the analysis, we use ordinal regression (the primary outcome), logistic regression (binary outcomes), general linear model (continuous outcomes), and the Poisson or negative binomial model (rate outcomes). DISCUSSION: Major adjustments compared with the original statistical analysis plan encompass: (1) adjustment of analyses by nationality; (2) power calculations for the secondary outcomes; (3) to address the multiplicity problem using of a fixed-sequence testing procedure starting with the primary outcome followed by the secondary outcomes ordered according to falling power; (4) assignment of worst possible score to patients who are not alive at the planned date of measurement of the continuous scores; (5) improved imputations; (6) outline of a supplementary exploratory analysis of the temperature measurements and time to death; and (7) substantial reduction of sample size. TRIAL REGISTRATION: Clinicaltrials.gov, identifier: NCT01833312 . 4 April 2013.
EVALuna2:33128

Status epilepticus in patients with glioblastoma: Clinical characteristics, risk factors, and epileptological outcome - Stritzelberger, Jenny; Gesmann, Anna; Fuhrmann, Imke; Balk, Stefanie; Reindl, Caroline; Madzar, Dominik; Uhl, Martin; Welte, Tamara; Brandner, Sebastian; Eisenhut, Felix; Dörfler, Arnd; Coras, Roland; et al. (Seizure-European Journal of Epilepsy, 2023)
Purpose: Epilepsy is a common comorbidity in patients with glioblastoma, however, clinical data on status epilepticus (SE) in these patients is sparse. We aimed to investigate the risk factors associated with the occurrence and adverse outcomes of SE in glioblastoma patients. Methods: We retrospectively analysed electronic medical records of patients with de-novo glioblastoma treated at our institution between 01/2006 and 01/2020 and collected data on patient, tumour, and SE characteristics. Results: In the final cohort, 292/520 (56.2 %) patients developed seizures, with 48 (9.4 % of the entire cohort and 16.4 % of patients with epilepsy, PWE) experiencing SE at some point during the course of their disease. SE was the first symptom of the tumour in 6 cases (1.2 %) and the first manifestation of epilepsy in 18 PWE (6.2 %). Most SE episodes occurred postoperatively (n = 37, 77.1 %). SE occurrence in PWE was associated with postoperative seizures and drug-resistant epilepsy. Adverse outcome (in-house mortality or admission to palliative care, 10/48 patients, 20.8 %), was independently associated with higher status epilepticus severity score (STESS) and Charlson Comorbidity Index (CCI), but not tumour progression. 32/48 SE patients (66.7 %) were successfully treated with first- and second-line agents, while escalation to third-line agents was successful in 6 (12.5 %) cases. Conclusion: Our data suggests a link between the occurrence of SE, postoperative seizures, and drug-resistant epilepsy. Despite the dismal oncological prognosis, SE was successfully treated in 79.2 % of the cases. Higher STESS and CCI were associated with adverse SE outcomes.
CRIS-Team Scopus Importer:2023-09-29
Keywords: Glioblastoma; Status epilepticus; Status epilepticus severity score (STESS)

STROKE CARE PERFORMANCE MEASURES DURING THE COVID-19 PANDEMIC - OVER THE WAVES - Gaßmann, Luise; Haupenthal, David; Kallmünzer, Bernd; Köhn, Julia; Schwab, Stefan; Kuramatsu, Joji (INTERNATIONAL JOURNAL OF STROKE, 2022)
CRIS-Team WoS Importer:2022-11-18

STROKE SIMULATION TRAINING IN A RURAL TELESTROKE NETWORK SETTING IN NORTHERN BAVARIA (STENO): PRELIMINARY RESULTS - Volbers, Bastian; Schwab, Stefan (INTERNATIONAL JOURNAL OF STROKE, 2022)
CRIS-Team WoS Importer:2022-11-18

Supratentorial lesions contribute to trigeminal neuralgia in multiple sclerosis - Fröhlich, Katharina; Winder, Klemens; Linker, Ralf; Engelhorn, Tobias; Dörfler, Arnd; Lee, De-Hyung; Hilz, Max-Josef; Schwab, Stefan; Seifert, Frank (Cephalalgia, 2018)
Background It has been proposed that multiple sclerosis lesions afflicting the pontine trigeminal afferents contribute to trigeminal neuralgia in multiple sclerosis. So far, there are no imaging studies that have evaluated interactions between supratentorial lesions and trigeminal neuralgia in multiple sclerosis patients. Methods We conducted a retrospective study and sought multiple sclerosis patients with trigeminal neuralgia and controls in a local database. Multiple sclerosis lesions were manually outlined and transformed into stereotaxic space. We determined the lesion overlap and performed a voxel-wise subtraction analysis. Secondly, we conducted a voxel-wise non-parametric analysis using the Liebermeister test. Results From 12,210 multiple sclerosis patient records screened, we identified 41 patients with trigeminal neuralgia. The voxel-wise subtraction analysis yielded associations between trigeminal neuralgia and multiple sclerosis lesions in the pontine trigeminal afferents, as well as larger supratentorial lesion clusters in the contralateral insula and hippocampus. The non-parametric statistical analysis using the Liebermeister test yielded similar areas to be associated with multiple sclerosis-related trigeminal neuralgia. Conclusions Our study confirms previous data on associations between multiple sclerosis-related trigeminal neuralgia and pontine lesions, and showed for the first time an association with lesions in the insular region, a region involved in pain processing and endogenous pain modulation.
EVALuna2:34503

Surgical hematoma evacuation of cortical intracerebral hemorrhage ≥10 ml reduces risk of subsequent epilepsy by more than 70%: A retrospective monocenter study - Welte, Tamara; Steidl, Josephine; Stritzelberger, Jenny; Gollwitzer, Stephanie; Lang, Johannes; Reindl, Caroline; Rampp, Stefan; Maslarova, Anna; Brandner, Sebastian; Hock, Stefan; Mühlen, Iris; Dörfler, Arnd; et al. (European Journal of Neurology, 2022)
Aim: The aim of this study was to re-evaluate risk factors for post-ICH epilepsy (PICHE) and examine the impact of surgical hematoma evacuation on epilepsy development after ICH. Background and purpose: Epilepsy is a common complication after intracerebral hemorrhage (ICH). Information on risk factors is still scarce and the role of ICH evacuation remains uncertain. Methods: We retrospectively included patients with spontaneous ICH treated in our hospital in 2006–2019. Patients' medical records were analyzed. In addition, mailed questionnaires and telephone interviews were used to complete the dataset. Uni- and multivariable hazard ratios (HRs) were applied to investigate risk factors for PICHE and the impact of surgical ICH evacuation. Results: Among 587 ICH patients available for analyses, 139 (23.7%) developed PICHE (mean follow-up 1795 ± 1378 days). The median time of epilepsy onset was 7 months after ICH (range 1–132 months). Risk factors associated with PICHE were cortical hemorrhage (multivariable HR 1.65 [95% CI 1.14–2.37]; p = 0.008), ICH volume > 10 ml (multivariable HR 1.91 [95% CI 1.33–2.73]; p < 0.001) and acute symptomatic seizures (multivariable HR 1.81 [95% CI 1.20–2.75]; p = 0.005). Patients with cortical ICH > 10 ml who underwent surgical hematoma evacuation were less likely to develop epilepsy than those with conservative treatment alone (multivariable HR 0.26 [95% CI 0.08–0.84]; p = 0.025). Conclusions: Post-ICH epilepsy is frequent and predicted by large cortical ICH and acute symptomatic seizures. Hematoma evacuation reduced the risk of PICHE by more than 70% in patients with large cortical ICH. This finding could be considered in the clinical decision making on the acute treatment of ICH.
CRIS-Team Scopus Importer:2022-10-21
Keywords: CAVE score; hematoma evacuation; intracerebral hemorrhage; post-stroke epilepsy

Systemic inflammatory response syndrome and long-term outcome after intracerebral hemorrhage - Hagen, Manuel; Sembill, Jochen; Sprügel, Maximilian; Gerner, Stefan; Madžar, Dominik; Lücking, Hannes; Hölter, Philip; Schwab, Stefan; Huttner, Hagen; Kuramatsu, Joji (Neurology, Neuroimmunology and Neuroinflammation, 2019)
ObjectiveTo investigate whether the systemic inflammatory response syndrome (SIRS) without infection as surrogate of a systemic immune response is associated with poor long-term functional outcome in patients with spontaneous intracerebral hemorrhage (ICH).MethodsWe analyzed consecutive patients with spontaneous ICH from our prospective cohort study (2018-2015). SIRS was defined according to standard criteria: i.e., 2 or more of the following parameters during hospitalization: body temperature <36°C or >38°C, respiratory rate >20 per minute, heart rate >90 per minute, or white blood cell count <4,000/L or >12,000/L in the absence of infection. The primary outcome consisted of the modified Rankin Scale (mRS) at 3 and 12 months investigated by adjusted ordinal shift analyses. Bias and confounding were addressed by propensity score matching and multivariable regression models.ResultsOf 780 patients with ICH, 21.8% (n = 170) developed SIRS during hospitalization. Patients with SIRS showed more severe ICH compared with those without; i.e., larger ICH volumes (18.3 cm3, interquartile range [IQR 4.6-47.2 cm3] vs 7.4 cm3, IQR [2.4-18.6 cm3]; p < 0.01), increased intraventricular hemorrhage (57.6%, n = 98/170 vs 24.8%, n = 79/319; p < 0.01), and poorer neurologic admission status (NIH Stroke Scale score 16, IQR [7-30] vs 6, IQR [3-12]; p < 0.01). ICH severity-adjusted analyses revealed an independent association of SIRS with poorer functional outcome after 3 (OR 1.80, 95% CI [1.08-3.00]; p = 0.025) and 12 months (OR 1.76, 95% CI [1.04-2.96]; p = 0.034). Increased ICH volumes on follow-up imaging (OR 1.38, 95% CI [1.01-1.89]; p = 0.05) and previous liver dysfunction (OR 3.01, 95% CI [1.03-10.19]; p = 0.04) were associated with SIRS.ConclusionsIn patients with ICH, we identified SIRS to be predictive of poorer long-term functional outcome over the entire range of mRS estimates. Clinically relevant associations with SIRS were documented for previous liver dysfunction and hematoma enlargement.
CRIS-Team Scopus Importer:2019-10-29

Targeted Temperature Management: Peltier's Element-Based Focal Brain Cooling Protects Penumbra Neurons from Progressive Damage in Experimental Cerebral Ischemia - Tauchi, Miyuki; De Rink, Maria Mercedes Tejada; Fujioka, Hiroshi; Okayama, Satoko; Nakamura, Kei-Ichiro; Dietel, Barbara; Achenbach, Stephan; Kollmar, Rainer; Schwab, Stefan; Ushijima, Kazuo; Harada, Hideki (Therapeutic Hypothermia and Temperature Management, 2018)
Targeted temperature management (TTM), or therapeutic hypothermia, is one of the most potent neuroprotective approaches after ischemic and traumatic brain injuries. TTM has been applied clinically with various methods, but effective achievement and maintenance of the target temperature remain challenging. Furthermore, timing of cooling and target body and brain temperature to optimize effectiveness for neuroprotection and to minimize side effects are yet to be standardized. Focal brain cooling is a potential strategy to minimize adverse effects of systemic TTM. In this study, we report on a focal brain cooling device for animals and its effectiveness of focal cooling in several animal models of ischemic cerebral stroke. A focal brain cooling device was constructed using a Peltier's element, a thermoelectric heat pump. The device was validated for its cooling ability, and optimal settings to induce an effective intracranial temperature were determined using male Sprague-Dawley rats. Transient and permanent middle cerebral artery occlusions were experimentally induced, and focal brain cooling was applied using the device varying the timing and duration of cooling. The stroke-induced infarct and edema volumes were evaluated from Nissl-stained cryosections. The focal brain cooling device was able to decrease and subsequently maintained cerebral hypothermia in free-moving rats without altering the core temperature. The device with validated intracranial temperatures produced neuroprotective effects in the acute phase of ischemic neural death, reperfusion injury, progressing damage to the penumbra, and edema formation. In conclusion, our validated focal cooling device enabled rapid and accurate cerebral TTM in rats. Using this device, we were able to test the neuroprotective effect of focal TTM in several pathological stages of cerebral ischemia, which warrants further studies to develop clinically feasible TTM procedures for patients with cerebral stroke.
EVALuna2:36338

Teleneurology in stroke management: costs of service in different organizational models - Handschu, Rene; Scibor, Mateusz; Nueckel, Martin; Asshoff, Dirk; Willaczek, Barbara; Erbguth, Frank; Schwab, Stefan; Daumann, Frank (Journal of Neurology, 2014)
Telemedicine is in increasing use in clinical neuroscience such as acute stroke care, especially by applying remote audiovisual communication for patient evaluation. However, telephone consultation was also used linking stroke centres to smaller hospitals. We compared costs of telestroke services using audiovisual and telephone communication in different organizational models. Within a small network in Northern Bavaria video-based teleconsultation (VTC) and telephone advice (TA) was provided for evaluation of acute stroke patients on a weekly rotation. The costs of the admissions process with or without one of both methods of telemedicine were calculated and compared from the perspective of the spoke hospital. Different levels of service and network size were modelled and costs of transfers as well as loss of revenues were calculated. Yearly total labour costs were 415,000 EUR for an on-site service VTC-service compared to 61,000 EUR in an on-call service. Additional costs for one teleconsultation were 109.55 EUR in VTC and 49.82 EUR in TA (VTC/TA ratio 2.2). The ratio decreased to 0.8 when accounting for costs of transfer and loss of reimbursement for all patients transferred as transfer of patients to the stroke centre was more frequent after TA (9.1 vs. 14.9%full-time on-site ser). Costs of one QALY gained by using VTC instead of TA ranged from 115.00 EUR to 515.86 EUR depending on the different models. In the first view TA looks like the less expensive method as it is easy to access and works without additional costs. When accounting for all disadvantages TA becomes slightly more expensive. In telestroke care VTC should be recommended as the method of choice also from an economic perspective.
EVALuna2:22264

The Acute Care of Stroke Patients in German Stroke Units-an Analysis of DRG Data From 2021 and 2022. - Neumann-Haefelin, Tobias; Bartig, Dirk; Faiss, Jürgen; Schwab, Stefan; Nabavi, Darius (Deutsches Ärzteblatt international, 2024)
EVALuna2:581207

The age and genomic integrity of neurons after cortical stroke in humans - Huttner, Hagen B.; Bergmann, Olaf; Salehpour, Mehran; Racz, Attila; Tatarishvili, Jemal; Lindgren, Emma; Csonka, Tamas; Csiba, Laszlo; Hortobagyi, Tibor; Mehes, Gabor; Englund, Elisabet; Solnestam, Beata Werne; et al. (Nature Neuroscience, 2014)
It has been unclear whether ischemic stroke induces neurogenesis or neuronal DNA rearrangements in the human neocortex. Using immunohistochemistry; transcriptome, genome and ploidy analyses; and determination of nuclear bomb test-derived (14)C concentration in neuronal DNA, we found neither to be the case. A large proportion of cortical neurons displayed DNA fragmentation and DNA repair a short time after stroke, whereas neurons at chronic stages after stroke showed DNA integrity, demonstrating the relevance of an intact genome for survival.
EVALuna2:22305

The anesthetic approach for endovascular recanalization therapy depends on the lesion site in acute ischemic stroke - Fröhlich, Kilian; Siedler, Gabriela; Stoll, Svenja; Macha, Kosmas; Kinfe, Thomas Mehari; Dörfler, Arnd; Eisenhut, Felix; Engelhorn, Tobias; Hölter, Philip; Lang, Stefan; Mühlen, Iris; Schmidt, Manuel; et al. (Neuroradiology, 2021)
Purpose Endovascular therapy (EVT) of large-vessel occlusion in acute ischemic stroke (AIS) may be performed in general anesthesia (GA) or conscious sedation (CS). We intended to determine the contribution of ischemic cerebral lesion sites on the physician's decision between GA and CS using voxel-based lesion symptom mapping (VLSM). Methods In a prospective local database, we sought patients with documented AIS and EVT. Age, stroke severity, lesion volume, vigilance, and aphasia scores were compared between EVT patients with GA and CS. The ischemic lesions were analyzed on CT or MRI scans and transformed into stereotaxic space. We determined the lesion overlap and assessed whether GA or CS is associated with specific cerebral lesion sites using the voxel-wise Liebermeister test. Results One hundred seventy-nine patients with AIS and EVT were included in the analysis. The VLSM analysis yielded associations between GA and ischemic lesions in the left hemispheric middle cerebral artery territory and posterior circulation areas. Stroke severity and lesion volume were significantly higher in the GA group. The prevalence of aphasia and aphasia severity was significantly higher and parameters of vigilance lower in the GA group. Conclusions The VLSM analysis showed associations between GA and ischemic lesions in the left hemispheric middle cerebral artery territory and posterior circulation areas including the thalamus that are known to cause neurologic deficits, such as aphasia or compromised vigilance, in AIS-patients with EVT. Our data suggest that higher disability, clinical impairment due to neurological deficits like aphasia, or reduced alertness of affected patients may influence the physician's decision on using GA in EVT.
CRIS-Team WoS Importer:2021-07-23

The course of tumor-related epilepsy in glioblastoma patients: A retrospective analysis - Stritzelberger, Jenny; Gesmann, Anna; Fuhrmann, Imke; Uhl, Martin; Brandner, Sebastian; Welte, Tamara; Schembs, Leah; Dörfler, Arnd; Coras, Roland; Adler, Werner; Schwab, Stefan; Putz, Florian; et al. (Epilepsy and Behavior, 2024)
Purpose: Many patients with glioblastoma suffer from tumor-related seizures. However, there is limited data on the characteristics of tumor-related epilepsy achieving seizure freedom. The aim of this study was to characterize the course of epilepsy in patients with glioblastoma and the factors that influence it. Methods: We retrospectively analyzed the medical records of glioblastoma patients treated at the University Hospital Erlangen between 01/2006 and 01/2020. Results: In the final cohort of patients with glioblastoma (n = 520), 292 patients (56.2 %) suffered from tumor-related epilepsy (persons with epilepsy, PWE). Levetiracetam was the most commonly used first-line antiseizure medication (n = 245, 83.9 % of PWE). The onset of epilepsy was preoperative in 154/292 patients (52.7 %). 136 PWE (46.6 %) experienced only one single seizure while 27/292 PWE (9.2 %) developed drug-resistant epilepsy. Status epilepticus occurred in 48/292 patients (16.4 %). Early postoperative onset (within 30 days of surgery) of epilepsy and total gross resection (compared with debulking) were independently associated with a lower risk of further seizures. We did not detect dose-dependent pro- or antiseizure effects of radiochemotherapy. Conclusion: Tumor-related epilepsy occurred in more than 50% of our cohort, but drug-resistant epilepsy developed in less than 10% of cases. Epilepsy usually started before tumor surgery.
CRIS-Team Scopus Importer:2024-07-19
Keywords: Glioblastoma; Radiochemotherapy; Surgery; Tumor-related epilepsy

The Effect of Climatic Factors on the Provocation of Epileptic Seizures - Treib, Philipp; Treib, Sebastian; Adler, Werner; Hamer, Hajo; Schwab, Stefan; Stefan, Hermann; Hammen, Thilo; Treib, Johannes (Deutsches Ärzteblatt international, 2021)
CRIS-Team WoS Importer:2022-03-04

The hyperintense acute reperfusion marker on fluid-attenuated inversion recovery magnetic resonance imaging is caused by gadolinium in the cerebrospinal fluid - Köhrmann, Martin; Struffert, Tobias; Frenzel, Thomas; Schwab, Stefan; Dörfler, Arnd (Stroke, 2012)
Background and PurposeS-: The hyperintense acute reperfusion marker (HARM) on fluid-attenuated inversion recovery MRI is believed to be caused by gadolinium-based contrast agents crossing a disrupted blood-brain barrier. However, this hypothesis has never been directly verified in humans. Methods-: In this study, we analyzed cerebrospinal fluid samples of patients with HARM on imaging regarding the presence and concentration of gadolinium-based contrast agents. Results-: Gadobutrol was found in concentrations of approximately 50 μmol/L. Using phantom MRI experiments, we demonstrate that the detected concentrations are consistent with the observed HARM imaging pattern. Conclusions-: Our study yields first direct evidence in humans that the imaging phenomenon HARM is indeed caused by leakage of gadolinium-based contrast agents into the cerebrospinal fluid. © 2011 American Heart Association. All rights reserved.
CRIS-Team Scopus Importer:2022-08-05
Keywords: FLAIR; hyperintensive acute reperfusion marker; MRI

The Impact of Burst Motor Cortex Stimulation on Cardiovascular Autonomic Modulation in Chronic Pain: A Feasibility Study for a New Approach to Objectively Monitor Therapeutic Effects - Borutta, Matthias; Köhn, Julia; Souza de Oliveira, Daniela; Del Vecchio, Alessandro; Engelhorn, Tobias; Schwab, Stefan; Buchfelder, Michael; Kinfe, Thomas Mehari (Pain and Therapy, 2023)
Introduction: Chronic refractory pain of various origin occurs in 30–45% of pain patients, and a considerable proportion remains resistant to pharmacological and behavioral therapies, requiring adjunctive neurostimulation therapies. Chronic pain is known to stimulate sympathetic outflow, yet the impact of burst motor cortex stimulation (burstMCS) on objectifiable autonomic cardiovascular parameters in chronic pain remains largely unknown. Methods: In three patients with chronic pain (2 facial pain/1 post-stroke pain), we compared pain intensity using a visual analog scale (VAS 1–10) and parameters of autonomic cardiovascular modulation at supine rest, during parasympathetic challenge with six cycles per minute of metronomic deep breathing, and during sympathetic challenge (active standing) at baseline and after 4 months of burstMCS compared to age-/gender-matched healthy controls. Results: While two out of three patients were responsive after 4 months of adjunctive burstMCS (defined as pain reduction of > 30%), no differences were found in any of the three patients regarding the R-R intervals of adjacent QRS complexes (RRI, 642 vs. 676 ms) and blood pressure (BP, 139/88 vs. 141/90 mmHg). Under resting conditions, parameters of parasympathetic tone [normalized units of high-frequency oscillations of RRI (RRI-HFnu power) 0.24 vs. 0.38, root-mean-square differences of successive RRI (RRI-RMSSD) 7.7 vs. 14.7 ms], total autonomic cardiac modulation [RRI total power 129.3 vs. 406.2 ms2, standard deviation of RRI (RRI-SD) 11.6 vs. 18.5 ms, coefficient of variation of RRI (RRI-CV) 1.9 vs. 3.7%], and baroreceptor reflex sensitivity (BRS, 1.9 vs. 2.3 ms/mmHg) increased, and parameters of sympathetic tone [normalized units of low-frequency oscillations of RRI (RRI-LFnu power) 0.76 vs. 0.62] and sympatho-vagal balance [ratio of RR-LF to RRI-HF power (RRI-LF/HF ratio) 3.4 vs. 1.9] decreased after 4 months of burstMCS. Low-frequency oscillations of systolic blood pressure (SBP-LF power), a parameter of sympathetic cardiovascular modulation, increased slightly (17.6 vs. 20.4 mmHg2). During parasympathetic stimulation, the expiratory–inspiratory ratio (E/I ratio) increased slightly, while upon sympathetic stimulation, the ratio between the shortest RRI around the 15th heartbeat and the longest RRI around the 30th heartbeat after standing up (RRI 30/15 ratio) remained unchanged. Conclusion: Four months of adjunctive burstMCS was associated with an increase in parameters reflecting both total and parasympathetic autonomic modulation and baroreceptor reflex sensitivity. In contrast, sympathetic tone declined in our three patients, suggesting stimulation-associated improvement not only in subjectively perceived VAS pain scores, but also in objectifiable parameters of autonomic cardiovascular modulation.
CRIS-Team Scopus Importer:2023-08-11
Keywords: Autonomic cardiovascular modulation; Burst motor cortex stimulation; Chronic post stroke pain; Objective outcome measures

The impact of the DWI-FLAIR-mismatch in the ECASS-4 trial – A post hoc analysis - Pfaff, Johannes A. R.; Bendszus, Martin; Donnan, Geoffrey; Molina, Carlos; Leys, Didier; Schellinger, Peter D.; Schwab, Stefan; Toni, Danilo; Wahlgren, Nils; Hacke, Werner; Ringleb, Peter Arthur (European Stroke Journal, 2020)
Introduction: To investigate the impact of a mismatch between diffusion-weighted imaging (DWI) and fluid attenuated inversion recovery (FLAIR) on functional outcome in patients with acute stroke in a prolonged time window or unknown time of symptom onset randomized to intravenous thrombolysis or placebo. Patients and Methods: We performed a post-hoc analysis of the European Cooperative Acute Stroke Study-4 (ECASS-4) trial. ECASS-4 was an investigator driven, phase 3, multi-center, double-blind, placebo-controlled study which randomized ischemic stroke patients presenting within 4.5 and 9h of stroke onset or unknown time-window to either rt-PA or placebo after MR-imaging. Two subgroups “no mismatch” (nMM) and “any mismatch” (aMM) were created by applying a DWI-FLAIR-mismatch criterion. We calculated frequency of nMM and aMM and performed a univariate analysis (Fisher's Test) for excellent clinical outcome (mRS 0-1) and mortality (mRS=6). Results: MR-Imaging of n=111/119 (93.2%) patients was suitable for this analysis. DWI-FLAIR mismatch was found in 49 patients (44.1%). Proportions of mismatch nMM and aMM were comparable in treatment-groups (aMM: Placebo 46.3%, Alteplase 42.1%; p=0.70). Patients with nMM showed no benefit of rt-PA-treatment (OR (95%CI) mRS 0-1: 0.95 (0.29-3.17)). Patients with aMM showed a point estimate of the odds ratio in favour of a treatment benefit of rt-PA (mRS 0-1: OR (95%CI) 2.62 (0.68-11.1)). Mortality within 90 days was not different in patients treated with rt-PA if nMM (15.2%) or aMM (12.5%) was present. Discussion: In this analysis no significant evidence, but subtle indication towards patients treated with rt-PA in a prolonged time window reaching an excellent clinical outcome if a DWI-FLAIR-mismatch is present on initial stroke MR-imaging. Conclusion: A DWI-FLAIR mismatch in the region of ischemia as imaging based surrogate parameter for patient selection for i.v. rt-PA should be strongly pursued.
CRIS-Team Scopus Importer:2020-05-08
Keywords: acute ischemic stroke; diffusion-weighted imaging; DWI-FLAIR-mismatch; European Cooperative Acute Stroke Study-4; fluid-attenuated inversion recovery; magnetic resonance imaging; Thrombolysis

Therapeutic hypothermia for acute ischaemic stroke. Results of a European multicentre, randomised, phase III clinical trial - Van Der Worp, H. Bart; Macleod, Malcolm R.; Bath, Philip M. W.; Bathula, Raj; Christensen, Hanne; Colam, Bridget; Cordonnier, Charlotte; Demotes-Mainard, Jacques; Durand-Zaleski, Isabelle; Gluud, Christian; Jakobsen, Janus Christian; Kallmünzer, Bernd; et al. (European Stroke Journal, 2019)
Introduction We assessed whether modest systemic cooling started within 6 hours of symptom onset improves functional outcome at three months in awake patients with acute ischaemic stroke. Patients and methods In this European randomised open-label clinical trial with blinded outcome assessment, adult patients with acute ischaemic stroke were randomised to cooling to a target body temperature of 34.0-35.0 degrees C, started within 6 h after stroke onset and maintained for 12 or 24 h , versus standard treatment. The primary outcome was the score on the modified Rankin Scale at 91 days, as analysed with ordinal logistic regression. Results The trial was stopped after inclusion of 98 of the originally intended 1500 patients because of slow recruitment and cessation of funding. Forty-nine patients were randomised to hypothermia versus 49 to standard treatment. Four patients were lost to follow-up. Of patients randomised to hypothermia, 15 (31%) achieved the predefined cooling targets. The primary outcome did not differ between the groups (odds ratio for good outcome, 1.01; 95% confidence interval, 0.48-2.13; p = 0.97). The number of patients with one or more serious adverse events did not differ between groups (relative risk, 1.22; 95% confidence interval, 0.65-1.94; p = 0.52). Discussion In this trial, cooling to a target of 34.0-35.0 degrees C and maintaining this for 12 or 24 h was not feasible in the majority of patients. The final sample was underpowered to detect clinically relevant differences in outcomes. Conclusion Before new trials are launched, the feasibility of cooling needs to be improved.
CRIS-Team WoS Importer:2019-10-01

Time-dependent risk factors for epileptic seizures in glioblastoma patients: A retrospective analysis of 520 cases - Stritzelberger, Jenny; Gesmann, Anna; Fuhrmann, Imke; Brandner, Sebastian; Welte, Tamara; Balk, Stefanie; Eisenhut, Felix; Dörfler, Arnd; Coras, Roland; Adler, Werner; Schwab, Stefan; Putz, Florian; et al. (Epilepsia, 2023)
Objective: Epilepsy is a common comorbidity of glioblastoma. Seizures may occur in various phases of the disease. We aimed to assess potential risk factors for seizures in accordance with the point in time at which they occurred. Methods: We retrospectively analyzed medical files of adult patients with de novo glioblastoma treated at our institution between January 2006 and January 2020. We categorized seizures as preoperative seizures (POS), early postoperative seizures (EPS; before initiation of radio[chemo]therapy [RCT]), seizures during radiotherapy (SDR; during or <30 days after RCT), and posttherapeutic seizures (PTS; ≥30 days after completion of RCT). We addressed associations between patients' characteristics and their seizures. Results: In the final cohort (N = 520), 292 patients experienced seizures. POS, EPS, SDR, and/or PTS occurred in 29.6% (154/520), 6.0% (31/520), 13.8% (70/509), and 36.1% (152/421) of patients, respectively. POS occurred more frequently in patients with higher Karnofsky Performance Scale scores (odds ratio [OR] = 3.27, p =.001) and tumor location in the temporal lobe (OR = 1.51, p =.034). None of the parameters we analyzed was related to the occurrence of EPS. SDR were independently associated with tumor location (parietal lobe, OR = 1.86, p =.027) and POS, but not EPS, and were independent of RCT. PTS were independently associated with tumor progression (OR = 2.32, p <.001) and with occurrence of SDR (OR = 3.36, p <.001), and negatively correlated with temporal lobe location (OR =.58, p <.014). In patients with tumors exclusively located in the temporal lobe, complete tumor resection was associated with a decreased risk of postoperative seizures. Significance: Seizures in glioblastoma patients have various, time-dependent risk factors. Temporal lobe localization was a risk factor for preoperative seizures; surgery may have had a protective effect in these patients. RCT did not have dose-dependent pro- or anticonvulsive effects. PTS were associated with tumor progression.
CRIS-Team Scopus Importer:2023-07-07
Keywords: glioblastoma; radiochemotherapy; seizures; surgery

Time trends in incidence of pathological and etiological stroke subtypes during 16 years: the Erlangen Stroke Project - Kolominsky-Rabas, Peter; Wiedmann, Silke; Weingärtner, Michael; Liman, Thomas G.; Endres, Matthias; Schwab, Stefan; Buchfelder, Michael; Heuschmann, Peter U. (Neuroepidemiology, 2015)
Population-based data, which continuously monitors time trends in stroke epidemiology are limited. We investigated the incidence of pathological and etiological stroke subtypes over a 16 year time period.Data were collected within the Erlangen Stroke Project (ESPro), a prospective, population-based stroke register in Germany covering a total study population of 105,164 inhabitants (2010). Etiology of ischemic stroke was classified according to the Trial of Org 10172 in Acute Stroke Treatment (TOAST) criteria.Between January 1995 and December 2010, 3,243 patients with first-ever stroke were documented. The median age was 75 and 55% were females. The total stroke incidence decreased over the 16 year study period in men (Incidence Rate Ratio 1995-1996 vs. 2009-2010 (IRR) 0.78; 95% CI 0.58-0.90) but not in women. Among stroke subtypes, a decrease in ischemic stroke incidence (IRR 0.73; 95% CI 0.57-0.93) and of large artery atherosclerotic stroke (IRR 0.27; 95% CI 0.12-0.59) was found in men and an increase of stroke due to small artery occlusion in women (IRR 2.33; 95% CI 1.39-3.90).Variations in time trends of pathological and etiological stroke subtypes were found between men and women that might be linked to gender differences in the development of major vascular risk factors in the study population.
EVALuna2:22434

Tracking cell turnover in human brain using 15N-thymidine imaging mass spectrometry - Röder, Sebastian; Bonnin, Elisa A.; Wu, Ting Di; Guerquin-Kern, Jean Luc; Jabari, Samir; Brandner, Sebastian; Eyüpoglu, Ilker Yasin; Gollwitzer, Stephanie; Hamer, Hajo; Gerner, Stefan; Döppner, Thorsten R.; Rummel, Christoph; et al. (Frontiers in Neuroscience, 2023)
Microcephaly is often caused by an impairment of the generation of neurons in the brain, a process referred to as neurogenesis. While most neurogenesis in mammals occurs during brain development, it thought to continue to take place through adulthood in selected regions of the mammalian brain, notably the hippocampus. However, the generality of neurogenesis in the adult brain has been controversial. While studies in mice and rats have provided compelling evidence for neurogenesis occurring in the adult rodent hippocampus, the lack of applicability in humans of key methods to demonstrate neurogenesis has led to an intense debate about the existence and, in particular, the magnitude of neurogenesis in the adult human brain. Here, we demonstrate the applicability of a powerful method to address this debate, that is, the in vivo labeling of adult human patients with 15N-thymidine, a non-hazardous form of thymidine, an approach without any clinical harm or ethical concerns. 15N-thymidine incorporation into newly synthesized DNA of specific cells was quantified at the single-cell level with subcellular resolution by Multiple-isotype imaging mass spectrometry (MIMS) of brain tissue resected for medical reasons. Two adult human patients, a glioblastoma patient and a patient with drug-refractory right temporal lobe epilepsy, were infused for 24 h with 15N-thymidine. Detection of 15N-positive leukocyte nuclei in blood samples from these patients confirmed previous findings by others and demonstrated the appropriateness of this approach to search for the generation of new cells in the adult human brain. 15N-positive neural cells were easily identified in the glioblastoma tissue sample, and the range of the 15N signal suggested that cells that underwent S-phase fully or partially during the 24 h in vivo labeling period, as well as cells generated therefrom, were detected. In contrast, within the hippocampus tissue resected from the epilepsy patient, none of the 2,000 dentate gyrus neurons analyzed was positive for 15N-thymidine uptake, consistent with the notion that the rate of neurogenesis in the adult human hippocampus is rather low. Of note, the likelihood of detecting neurogenesis was reduced because of (i) the low number of cells analyzed, (ii) the fact that hippocampal tissue was explored that may have had reduced neurogenesis due to epilepsy, and (iii) the labeling period of 24 h which may have been too short to capture quiescent neural stem cells. Yet, overall, our approach to enrich NeuN-labeled neuronal nuclei by FACS prior to MIMS analysis provides a promising strategy to quantify even low rates of neurogenesis in the adult human hippocampus after in vivo15N-thymidine infusion. From a general point of view and regarding future perspectives, the in vivo labeling of humans with 15N-thymidine followed by MIMS analysis of brain tissue constitutes a novel approach to study mitotically active cells and their progeny in the brain, and thus allows a broad spectrum of studies of brain physiology and pathology, including microcephaly.
CRIS-Team Scopus Importer:2023-11-03
Keywords: adult; cell turnover; DNA-labeling; glioblastoma; hippocampus; Nano-SIMS; neurogenesis

Transient decrease in circulating dendritic cell precursors after acute stroke: Potential recruitment into the brain - Yilmaz, Atilla; Fuchs, Tanja; Dietel, Barbara; Altendorf, Regina; Cicha, Iwona; Stumpf, Christian; Schellinger, Peter D.; Blümcke, Ingmar; Schwab, Stefan; Daniel, Werner; Garlichs, Christoph; Kollmar, Rainer (Clinical Science, 2010)
The role of DCs (dendritic cells) as potent mediators of inflammation has not been sufficiently investigated in stroke. Therefore, in the present study, circulating mDCPs (myeloid DC precursors), pDCPs (plasmacytoid DCPs) and tDCPs (total DCPs) were analysed by flow cytometry in (i) healthy controls (n = 29), (ii) patients with ACI-S (asymptomatic cerebral infarction stenosis; n = 46), (iii) patients with TIA (transient ischaemic attack; n = 39), (iv) patients with AIS (acute ischaemic stroke; n = 73), and (v) patients with AHS (acute haemorrhagic stroke; n = 31). The NIHSS (National Institutes of Health Stroke Scale) and infarction size on a CT (computer tomography) scan were evaluated after stroke. In a patient subgroup, post-mortem immunohistochemical brain analyses were performed to detect mDCs (CD209), pDCs (CD123), T-cells (CD3) and HLA-DR. In AIS and AHS, the numbers of circulating mDCPs (P < 0.005), pDCPs (P < 0.005) and tDCPs (P < 0.001) were significantly reduced. A significant inverse correlation was found between the NIHSS and circulating DCPs (P < 0.02), as well as between hsCRP (high-sensitivity C-reactive protein) and circulating DCPs (P < 0.001). Patients with large stroke sizes on a CT scan had significantly lower numbers of mDCPs (P = 0.007), pDCPs (P = 0.05) and tDCPs (P = 0.01) than those with smaller stroke sizes. Follow-up analysis showed a significant recovery of circulating DCPs in the first few days after stroke. In the infarcted brain, a dense infiltration of mDCs co-localized with T-cells, single pDCs and high HLA-DR expression were observed. In conclusion, acute stroke leads to a decrease in circulating DCPs. Potentially, circulating DCPs are recruited from the blood into the infarcted brain and probably trigger cerebral immune reactions there. © The Authors Journal compilation © 2010 Biochemical Society.
CRIS-Team Scopus Importer:2024-12-04
Keywords: Dendritic cell; Inflammation; Ischaemic brain injury; Leucocyte infiltration; Stroke; T-cell activation

Transient naming deficits associated with insular lesions in a patient with encephalitis - Marxreiter, Franz; Utz, Kathrin; Schlachetzki, Johannes; Seifert, Frank; Schmidt, Manuel; Dörfler, Arnd; Schwab, Stefan; Schenk, Thomas (Neurocase, 2019)
We describe a patient with acute herpes simplex encephalitis with left-hemispheric hippocampal, parahippocampal and insular lesions. Although prototypic language areas were unaffected, the patient suffered from an inability to name objects or animals displayed on pictures. This deficit was transient and gradually disappeared 8 weeks after the initial diagnosis. Our findings are in line with a previous report showing similar deficits in a patient with a comparable lesion pattern and support the hypothesis that left insular lesions can produce severe naming deficits. Using FDG-PET we ruled out that functional deactivation in classical language areas account for the observed naming deficits.
EVALuna2:204482

Trends in the neurological emergency room, focusing on persons with seizures - Welte, Tamara; Ernst, Sebastian; Stritzelberger, Jenny; Gollwitzer, Stephanie; Lang, Johannes; Reindl, Caroline; Sprügel, Maximilian; Olmes, David; Schwab, Stefan; Blinzler, Christian; Hamer, Hajo (European Journal of Neurology, 2023)
Background and purpose: Previous studies in neurological emergency rooms (nERs) have reported many non-acute, self-presenting patients, patients with delayed presentation of stroke, and frequent visits of persons with seizures (PWS). The aim of this study was to evaluate trends during the last decade, with special focus on PWS. Methods: We retrospectively analyzed patients who presented to our specialized nER during the course of 5 months in 2017 and 2019, and included information on admission/referral, hospitalization, discharge diagnosis, and diagnostic tests/treatment in the nER. Results: A total of 2791 patients (46.6% male, mean age 57 ± 21 years) were included. The most common diagnoses were cerebrovascular events (26.3%), headache (14.1%), and seizures (10.5%). Most patients presented with symptoms lasting >48 h (41.3%). The PWS group included the largest proportion of patients presenting within 4.5 h of symptom onset (171/293, 58.4%), whereas only 37.1% of stroke patients presented within this time frame (273/735). Self-presentation was the most common admission pathway (31.1%), followed by emergency service referral (30.4%, including the majority of PWS: 197/293, 67.2%). Despite known diagnosis of epilepsy in 49.2%, PWS more often underwent accessory diagnostic testing including cerebral imaging, compared to the overall cohort (accessory diagnostics 93.9% vs. 85.4%; cerebral imaging 70.1% vs. 64.1%). Electroencephalography in the nER was only performed in 20/111 patients (18.0%) with a first seizure. Nearly half of the patients (46.7%) were discharged home after nER work-up, including most self-presenters (632/869, 72.7%) and headache patients (377/393, 88.3%), as well as 37.2% (109/293) of PWS. Conclusion: After 10 years, nER overuse remains a problem. Stroke patients still do not present early enough, whereas PWS, even those with known epilepsy, often seek acute and extensive assessment, indicating gaps in pre-hospital management and possible over-assessment.
CRIS-Team Scopus Importer:2023-09-15
Keywords: epilepsy; headache; neurological emergency room; seizures; stroke

Twenty-Year Time Trends in Long-Term Case-Fatality and Recurrence Rates After Ischemic Stroke Stratified by Etiology - Rücker, Viktoria; Heuschmann, Peter U.; O'Flaherty, Martin; Weingärtner, Michael; Hess, Manuela; Sedlak, Claudia; Schwab, Stefan; Kolominsky-Rabas, Peter (Stroke, 2020)
BACKGROUND AND PURPOSE: Data on long-term survival and recurrence after stroke are lacking. We investigated time trends in ischemic stroke case-fatality and recurrence rates over 20-years stratified by etiological subtype according to the Trial of ORG 10172 in Acute Stroke Treatment classification within a population-based stroke register in Germany. METHODS: Data was collected within the Erlangen Stroke Project, a prospective, population-based stroke register covering a source population of 105 164 inhabitants (2010). Case fatality and recurrence rates for 3 months, 1 year, and 5 years were estimated with Kaplan-Meier estimates. Sex-specific time trends for case-fatality and recurrence rates were estimated with Cox regression. We adjusted for age, sex, and year of event and stratified for etiological subtypes. A sensitivity analysis with competing risk analysis for time trends in recurrence were performed. RESULTS: Between 1996 and 2015, 3346 patients with first ischemic stroke were included; age-standardized incidence per 100 000 was 75.8 in women and 131.6 in men (2015). Overall, 5-year survival probabilities were 50.4% (95% CI, 47.9-53.1) in women and 59.2% (95% CI, 56.4-62.0) in men; 5-year survival was highest in patients with first stroke due to small-artery occlusion (women, 71.8% [95% CI, 67.1-76.9]; men, 75.9% [95% CI, 71.3-80.9]) and lowest in cardioembolic stroke (women, 35.7% [95% CI, 31.0-41.1]; men, 47.8% [95% CI, 42.2-54.3]). Five-year recurrence rates were 20.1% (95% CI, 17.5-22.6) in women and 20.1% (95% CI, 17.5-22.7) in men; 5-year recurrence rate was lowest in women in stroke due to small artery occlusion 16.0% (95% CI, 11.7-20.1) and in men in large-artery atherosclerosis 16.6% (95% CI, 8.7-23.9); highest risk of recurrence was observed in undefined strokes (women, 22.3% [95% CI, 17.8-26.6]; men, 21.4% [95% CI, 16.7-25.9]). Cox regression revealed improvements in case-fatality rates over time with differences in stroke causes. No time trends in recurrence rates were observed. CONCLUSIONS: Long-term survival and recurrence varied substantially by first stroke cause. Survival probabilities improved over the past 2 decades; no major trends in stroke recurrence rates were observed.
CRIS-Team Scopus Importer:2020-09-04
Keywords: arteries; atherosclerosis; incidence; mortality; recurrence

Ultrasound in dual nerve impairment after proximal radial nerve lesion - Laemmer, Alexandra B.; Schwab, Stefan; Schramm, Axel (PLoS ONE, 2015)
Sonography in classical nerve entrapment syndromes is an established and validated method. In contrast, few publications highlight lesions of the radial nerve, particularly of the posterior interosseus nerve (PIN).Five patients with a radial nerve lesion were investigated by electromyography, nerve conduction velocity and ultrasound. Further normative values of 26 healthy subjects were evaluated.Four patients presented a clinical and electrophysiological proximal axonal radial nerve lesion and one patient showed a typical posterior interosseous nerve syndrome (PINS). The patient with PINS presented an enlargement of the PIN anterior to the supinator muscle. However four patients with proximal lesions showed an unexpected significant enlargement of the PIN within the supinator muscle.High-resolution sonography is a feasible method to demonstrate the radial nerve including its distal branches. At least in axonal radial nerve lesions, sonography might reveal abnormalities far distant from a primary proximal lesion site clearly distinct from the appearance in classical PINS.
EVALuna2:22367

Uncertainty-aware deep learning for trustworthy prediction of long-term outcome after endovascular thrombectomy - Martín Vicario, Celia; Rodriguez Salas, Dalia; Maier, Andreas; Hock, Stefan; Kuramatsu, Joji; Kallmünzer, Bernd; Thamm, Florian; Taubmann, Oliver; Ditt, Hendrik; Schwab, Stefan; Dörfler, Arnd; Mühlen, Iris (Scientific Reports, 2024)
Acute ischemic stroke (AIS) is a leading global cause of mortality and morbidity. Improving long-term outcome predictions after thrombectomy can enhance treatment quality by supporting clinical decision-making. With the advent of interpretable deep learning methods in recent years, it is now possible to develop trustworthy, high-performing prediction models. This study introduces an uncertainty-aware, graph deep learning model that predicts endovascular thrombectomy outcomes using clinical features and imaging biomarkers. The model targets long-term functional outcomes, defined by the three-month modified Rankin Score (mRS), and mortality rates. A sample of 220 AIS patients in the anterior circulation who underwent endovascular thrombectomy (EVT) was included, with 81 (37%) demonstrating good outcomes (mRS≤2). The performance of the different algorithms evaluated was comparable, with the maximum validation under the curve (AUC) reaching 0.87 using graph convolutional networks (GCN) for mRS prediction and 0.86 using fully connected networks (FCN) for mortality prediction. Moderate performance was obtained at admission (AUC of 0.76 using GCN), which improved to 0.84 post-thrombectomy and to 0.89 a day after stroke. Reliable uncertainty prediction of the model could be demonstrated.
CRIS-Team Scopus Importer:2024-05-17

Use of a telestroke service for evaluation of non-stroke neurological cases - Handschu, Rene; Wacker, Angela; Scibor, Mateusz; Sancu, Camelia; Schwab, Stefan; Erbguth, Frank; Oschmann, Patrick; Stark, David Rianto; Marquardt, Lars (Journal of Neurology, 2015)
Telemedicine is a growing field in many medical specialties. Within clinical neurosciences one of its largest applications is in acute stroke care. However, little is known about its value and effect in general neurology, despite stroke. In a retrospective survey of 1500 teleconsultations over a time period of 12 months from October 2008 to September 2009, from a large telestroke network in Germany, we evaluated 352 cases with a non-stroke diagnosis. Duration and methods of teleconsultation as well as neurological consultations at bedside and discharge diagnosis were analyzed and compared to stroke cases. Discharge diagnosis was not identical to teleconsultation diagnosis in 48.9% of all non-stroke cases compared to 12.5% of all stroke cases. Duration of teleconsultation was 26.5 min in non-stroke cases compared to 14.3 min for stroke cases. In non-stroke cases other parts of the neurological examination were added to the pure administration of a stroke scale. There were no significant differences between non-stroke cases with correct and incorrect consultation diagnoses concerning in-hospital mortality (4.6 vs. 5.0%) and length of hospital stay (8.3 vs. 7.6 days). We conclude that diagnostic accuracy and protocol routine is not as exact in non-stroke cases compared to acute stroke cases. Other neurologic conditions may need different algorithms for a telemedicine service. Thus experience from a telestroke service cannot be transferred to other neurologic conditions on a routine basis.
EVALuna2:22364

Vasospasm in intracerebral hemorrhage with ventricular involvement: a prospective pilot transcranial Doppler sonography study - Kiphuth, Ines C.; Huttner, Hagen; Breuer, Lorenz; Engelhorn, Tobias; Schwab, Stefan; Köhrmann, Martin (Cerebrovascular Diseases, 2011)
Cerebral vasospasm (VSP) is a common complication after subarachnoid hemorrhage (SAH), but has rarely been reported after intracerebral hemorrhage (ICH) without subarachnoidal bleeding. The underlying pathophysiological mechanism is mainly mediated by circulating heme products within the cerebrospinal fluid, and thus patients with ICH and ventricular involvement (IVH) may also be in danger of developing VSP. The incidence and role of VSP in IVH, however, have not been systematically studied.We prospectively enrolled 115 patients with ICH with or without IVH into the study between April 2009 and April 2010. All patients received serial extracranial and transcranial Doppler sonography (TCD) at baseline, on days 3-5 and 7-9 to detect and monitor VSP. In addition, CT scans taken on admission, after 24 h and before discharge were evaluated for the occurrence of delayed cerebral ischemia.Three out of 53 patients (5.7%) with IVH showed a significant elevation of flow velocities over the examined timeframe. One of these patients developed severe VSP resulting in secondary ischemic infarction. None of the ICH patients without IVH showed significantly elevated flow velocities or secondary infarction.Cerebral VSP with secondary infarction may occur in patients with spontaneous IVH, though far less frequently than in SAH; thus, systematic screening of all patients with IVH may not be warranted. However, serial TCD should be considered in patients with secondary clinical worsening or extensive IVH.
EVALuna2:21961

Why Does It Shine?-A Prognostic Analysis about Predisposing Factors for Blood-Brain Barrier Damage after Revascularisation of Cerebral Large-Vessel Occlusion. - Knott, Michael; Hock, Stefan; Soder, Liam; Mühlen, Iris; Kremer, Svenja; Sprügel, Maximilian; Sembill, Jochen; Kuramatsu, Joji; Schwab, Stefan; Engelhorn, Tobias; Dörfler, Arnd (Journal of Cardiovascular Development and Disease, 2023)
BACKGROUND: Hyperdense lesions in CT after EVT of LVO are common. These lesions are predictors for haemorrhages and an equivalent of the final infarct. The aim of this study based on FDCT was the evaluation of predisposing factors for these lesions. METHODS: Using a local database, 474 patients with mTICI ≥ 2B after EVT were recruited retrospectively. A postinterventional FDCT after recanalisation was analysed regarding such hyperdense lesions. This was correlated with a variety of items (demographics, past medical history, stroke assessment/treatment and short-/long-term follow-up). RESULTS: Significant differences were present in NHISS at admission, regarding time window, ASPECTS in initial NECT, location of the LVO, CT-perfusion (penumbra, mismatch ratio), haemostatic parameters (INR, aPTT), duration of EVT, number of EVT attempts, TICI, affected brain region, volume of demarcation and FDCT-ASPECTS. The ICH-rate, the volume of demarcation in follow-up NECT and the mRS at 90 days differed in association with these hyperdensities. INR, the location of demarcation, the volume of demarcation and the FDCT-ASPECTS could be demonstrated as independent factors for the development of such lesions. CONCLUSION: Our results support the prognostic value of hyperdense lesions after EVT. We identified the volume of the lesion, the affection of grey matter and the plasmatic coagulation system as independent factors for the development of such lesions.
EVALuna2:536989